Mining and floods: a systematic review of empirical studies on community resilience strategies and interventions - Mariam Bouzid; William J. Guerrero; Luz Elba Torres-Guevara; Dairo Steven Muñoz Pinzón; Carlos Daniel Montes Rodriguez; Lady Giovanna Rojas Pineda; Juan José Díaz Castro; Erika Cardona Patiño; Karol Elkjaer Mondragon Sanchez (The Extractive Industries and Society, 2026)

Liver fibrosis and type 2 diabetes modulate postprandial incretin and glucagon responses in fatty liver disease - Brenno Astiarraga; Adrià Rodriguez-Castellano; Victoria Ceperuelo-Mallafré; Anna Marsal-Beltran; Francisco J. Osuna-Prieto; Nerea Vilanova; Jordi Gracia-Sancho; Joan Carles Quer; Ana Megía; Albert Pardo Balteiro; Joan Vendrell; Sonia Fernández-Veledo (Journal of Physiology and Biochemistry, 2026)
The study aims to characterize the secretion dynamics of glucagon-related peptides, including GLP-1, GIP, and GLP-2, across different stages of metabolic-associated steatotic liver disease (MASLD), while evaluating the impact of type 2 diabetes (T2D) on these hormonal responses. Thirty-four MASLD subjects were stratified according with the liver transient elastography (TE ≥ 9 kPa) and T2D in NF (no fibrosis, without T2D; n = 12), NFD (no fibrosis, with T2D; n = 8), F (fibrosis, without T2D; n = 5), and FD (fibrosis, with T2D; n = 9) and completed a standardized 3-h meal tolerance test (MTT). The presence of liver fibrosis, regardless of diabetes status, was associated with hyperglycemia, hyperinsulinemia, and greater insulin resistance compared to the non-fibrosis (NF) group. Significant differences in glucagon and GLP-1 response curves were observed across groups. People with T2D showed an elevated peak of glucagon and increased glucagon exposure, as indicated by both the 60-min area under the curve (AUC60’) and total AUC during the MTT. In the FD group, fasting and peak GLP-1 levels, as well as AUC60’ and total AUC GLP-1, were 1.9-, 1.8-, and 1.9-fold higher, respectively, compared to the NF group. GIP responses were similar across groups, except for elevated fasting levels in NFD ( p = 0.002). GLP-2 mirrored GLP-1, with FD showing the highest fasting and postprandial levels. Stepwise regression identified fibrosis and FPG as the main predictors of GLP-1, while glucagon was linked to FPG, HbA1c, and BMI. Liver fibrosis and T2D impact glucagon-related peptides responses in MASLD, revealing important metabolic alterations that may guide therapeutic approaches.

An event-related potentials account of brain predictive coding - Carlos M. Gómez; Antonio Arjona; Francisco J. Ruíz-Martínez; Manuel Muñoz-Caracuel; Vanesa Muñoz; Elena I. Rodriguez-Martinez (Cognitive Neurodynamics, 2026)
Predictive coding is a theory that tries to account for how the brain processes in an anticipatory manner the expected stimuli, and reorganizes the underlying neural networks as a consequence of the outcome of predictions: Correct or incorrect. EEG has the advantage of making a continuous and almost instantaneous record of brain activity. The present report summarizes work on Event-Related Potentials (ERPs) and reviews the neural validity of Predictive processing as a mechanism to predict future events, assess the validity of predictions, and then update the probabilities associated with future events. Using two experimental models: predictive tone sequences and central cue Posner paradigms and Bayesian modelling, the report suggests that Contingent Negative Variation (CNV) would be related to prior expectation, Mismatch negativity (MMN) and P300 to Bayesian surprise and/or prediction error, and Post Imperative Negative Variation (PINV) to the assessment of trial outcome in uncertainty situations. The review tends to support predictive coding as a theory consistent with brain operations indexed by ERPs.

Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Patient-specific 3D-printed ALBA osteotomy guides for oblique tibial tuberosity osteotomy in dogs: An ex vivo study - P. Agüera-Espejo; J.L. Fontalba-Navas; H. Fominaya-Garcia; C. Cano-Lopez; R. Mendaza-DeCal; A. Garau-Camacho; T. Guerrero; J. Rodriguez-Quiros (Research in Veterinary Science, 2026)

Lake sediment records of deglaciation and post-glacial paleoenvironmental conditions, northeast Pennsylvania, USA - Matthew S. Finkenbinder; Timothy P. Lane; Kathryn R. Adamson; Bruce P. Finney; Mark B. Abbott; Alistair J. Monteath; Adam Ianno; Cassandra N. Papp; Angus F. Fortune; Michael J. Delpais; Megan E. Novak; Angelica Y. Delgado Rodriguez; et al. (Quaternary Science Reviews, 2026)

A hybrid physics-machine learning framework for improving simulations of urban air-conditioning electricity consumption - Xiangwen Deng; Jed J. Cohen; Justin Rodriguez; Bohumil M. Svoma; Chris Gonzales; Matei Georgescu (Energy and Buildings, 2026)

Identifying unique biomass burning marker fingerprints for Australian hardwoods, softwoods, and grasses using controlled combustion and chemometrics - Harrison Stevens; Snezhana Astrakhantseva; Andrew R. Bowie; Bernadette C. Proemse; Paul R. Haddad; Gregory J. Jordan; Brett Paull; Estrella Sanz Rodriguez (Atmospheric Environment, 2026)

Moraxella species isolated from blood cultures in Europe (MORAXEu): a multicentre study of epidemiology and antimicrobial susceptibility with complementary phylogenomic analysis of publicly available genomes - Tone Tønjum; Vinicius da Silva Franklin-Duarte; Johan Christian Berild; Konstantina Gartzonika; Eirini Christaki; Viktoria Eirini Mavromanolaki; Sofia Maraki; Anastasia Spiliopoulou; Nikolaos Giormezis; Gergana Lengerova; Yordan Kalchev; Ana Budimir; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Using fracture scarp intersection lineations as kinematic indicators on active normal fault scarps - Billy J. Andrews; Zoë K. Mildon; Manuel L. Diercks; Sam Mitchell; Gerald P. Roberts; Constanza Rodriguez Piceda; Jenni Robertson (Journal of Structural Geology, 2026)

P134 Effects of post-thawing transport and donor mare age on pregnancy outcomes of vitrified IVP equine embryos produced in a commercial ICSI laboratory - P. Arrondo Navarrete; S.A. Stampfli; J. Sieber; A. Ferrante; A. Ballester; M.B. Rodriguez (Journal of Equine Veterinary Science, 2026)

136 Effect of transvaginal follicular aspiration on pregnancy rates and corpus luteum development in noncyclic recipient mares - J.S. Rodriguez; J. Frati; N.J.B.N. Rivas; L. Segabinazzi; A. Tibary (Journal of Equine Veterinary Science, 2026)

Shrimp (sub-)national traceability and retail fraud detection using stable isotopes and multi-element profiling - V. Deklerck; R.P. Davis; A. Rodriguez-Zunino; S. Khongtanakrittakorn; S. Hofem; J. Jungkeit; A. Leyton; M. Osorto-Nuñez; C. Podmore; L. Prior; C.C. Smith; B. Soule; et al. (Food Control, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Hypertrophic cardiomyopathy-linked Tnnc1 variants are associated with distinct myopathic changes in slow skeletal muscle of mice - Sonu Patel; Gabriel Leite da Silva Santos; Jaelynn Florence; Aida Rahimi Kahmini; Yun Shi; Michelle Rodriguez Garcia; Bradley S. Gordon; P. Bryant Chase; Christopher Solís; Orlando Laitano; J. Renato Pinto; Michelle S. Parvatiyar (Journal of Muscle Research and Cell Motility, 2026)

Which soil health indicators best track diversification benefits in tropical agroecosystems? - Anna M. Visscher; Simon Fonteyne; Mirjam Pulleman; Anna Alekseeva; Martin Hartmann; Jose M. Rodriguez-Castellanos; Pankaj Trivedi; Rodolfo Vilchis-Ramos; Sergio Zapata-Martínez; Bruce G. Ferguson; Helda Morales; Steven Vanek; et al. (Applied Soil Ecology, 2026)

High protein diets early in life improve survival, reduce cannibalism, and increase growth and yield in farmed yellow mealworms - N. Dobrowolski; C.D. Perl; J. Brumfield; J. Christie; R. Rodriguez-Guevara; S.O. Durosaro; M. Barrett (Applied Animal Behaviour Science, 2026)

A human PBMC-based new approach method reveals PFAS-driven T-cell proliferation and immune dysregulation - Allison Loan; Lauren M. Bradford; Andrée Nunnikhoven; Gong Zhang; Emily Dupuis; Eunnara Cho; Matthew J. Meier; Rocio Aranda-Rodriguez; Azam Tayabali; Kristin M. Eccles; David Prescott (Archives of Toxicology, 2026)
Immunotoxicity has emerged as a key health concern for per- and polyfluoroalkyl substances (PFAS), with animal studies showing reduced T-dependent antibody responses (TDAR) and epidemiological studies reporting decreased vaccine antibody titres. Notably, immunotoxicity is considered one of the most sensitive endpoints for PFAS exposure and has been used to inform regulatory guidance and health-based values. Given that more than 14,000 PFAS exist and are highly environmentally persistent, evaluating the immunotoxicity of individual compounds is critical but impractical, highlighting the need for efficient, human-relevant test systems that provide mechanistically informative, immune-relevant endpoints. Here, we assessed immunomodulatory effects of six PFAS analogues using an in vitro human peripheral blood mononuclear cell (PBMC) model. Two immune stimuli were applied, including lipopolysaccharide (LPS) to trigger innate responses and phytohemagglutinin (PHA) to simulate T-cell-mediated adaptive immune activation. Critically, several PFAS analogues enhanced T-cell proliferation following PHA activation, while a non-inclusive but overlapping subset of analogues suppressed cytokine secretion in response to PHA and LPS. Transcriptomic analyses indicate reduced B-cell identity and immunoglobulin gene expression alongside increased expression of genes associated with T-cell activation and proliferation. These findings implicate a dysregulated coordination between T- and B-cell responses as a potential mechanism underlying PFAS-associated immunotoxicity. Overall, the human PBMC model demonstrated that it is a cost-effective and ethical method for identifying and characterizing key events (KEs) in the adverse outcome pathway (AOP) for PFAS-induced immunotoxicity and has the potential to be refined and incorporated into a robust new approach method (NAM) to assess the next generation of commercial PFAS.

Nanoscale silician defects in magnetite record protolith inheritance and control chain silicate growth during skarn formation - Jing Xu; Yuri Tatiana Campo-Rodriguez; Cristiana L. Ciobanu; Nigel J. Cook; Ashley Slattery; Benjamin P. Wade; Jiaxing Hu; Taiping Zhao (Lithos, 2026)

Low-dose inorganic arsenic exposure reprograms macrophages differentiation and function toward tumor-promoting phenotypes - Emily J. Illingworth; Sylvia S. Sanchez; Kristal A. Rychlik; Andre Kleensang; Jason Laird; Gabriel A. Lopez-Cecetaite; M. Carolina Rodriguez Steube; Aakriti Mathur; Pritam Sadhukhan; Daniel A. Medina-Cleghorn; Daniel Nomura; Martyn T. Smith; et al. (Environmental Research, 2026)

On the Possibility of Ionospheric Memory Over the Low-Latitude Mexican Region - M. A. Sergeeva; I. D. Orrala-Legorreta; E. Rodriguez-Orozco; J. H. Castro-Chacon; O. A. Maltseva; J. A. Gonzalez-Esparza; P. Corona-Romero; V. J. Gatica-Acevedo; M. Pazos; M. E. Gonzalez-Alvarez; R. Bonifaz; A. Melgarejo-Morales; et al. (Pure and Applied Geophysics, 2026)
Features of possible regional ionospheric memory manifested themselves at low-latitudes under solar eclipse conditions.

Reliability of M-wave amplitude measurement from paired stimulations across different muscle groups before and after submaximal contraction to failure - C. Lanfranchi; D. Neyroud; J. Rodriguez-Falces; N. Place (European Journal of Applied Physiology, 2026)

Soil refrigeration and air-drying preserve sensitivity of aminopeptidase activities to long-term nitrogen fertilization - Chammi P. Attanayake; Sara Eldessouky; Katie Indorante; Ivanellis Rodriguez-Torres; Ekundayo Adeleke; Maria B. Villamil; Andrew J. Margenot (Biology and Fertility of Soils, 2026)
Evaluating soil storage impacts on aminopeptidase activity can inform the use of aminopeptidase activity in soil N cycling assessments. We evaluated the impact of soil refrigeration (4 °C) and air-drying relative to field-fresh (4 °C for ≤ 3 d) on the activities and sensitivity of eight amino acid-specific aminopeptidase activities across a 42 y N fertilization gradient (0–269 kg N ha − 1 ) over 1.5, 6, 12 and 24 mo storage. Soil storage generally decreased (7–95%) or did not impact aminopeptidase activities, but in some cases increased activity (7–18%). Activity decreases were greatest for glutamic acid, arginine, and lysine aminopeptidases. Proline and leucine aminopeptidase activities were least impacted by soil storage. In field-fresh soils, only arginine and lysine aminopeptidase activities differed across the N fertilization gradient: ≈50% lower at the second highest (202 kg N ha − 1 ) relative to the lowest (67 kg N ha − 1 ) positive fertilization rate, a trend preserved for up to 12 mo in refrigerated soils and up to 24 mo in air-dried soils. Aminopeptidase activities that were similar across the N fertilization gradient in field-fresh soils also remained similar in stored soils, or responded similarly to N fertilization as arginine and lysine aminopeptidase activities. Most aminopeptidase activities were similar between refrigerated and air-dried soils for at least 6 mo or up to 24 mo. Though soil storage impacts on activities were aminopeptidase-specific, both storage methods preserved the sensitivity of aminopeptidase activities to long-term field N fertilization treatments.

Confirmed Outbreaks of Streptococcosis Caused by Streptococcus agalactiae Serotype Ia in Nile Tilapia Culture From Campeche, Mexico - R. A. Avila‐Castillo; R. E. del Rio‐Rodriguez; S. A. Soto‐Rodriguez; J. Navarro‐Flores; A. D. Cu‐Escamilla; F. I. Marrujo‐Lopez; K. G. Aguilar‐Rendon; M. I. Gomez‐Solano (Journal of Fish Diseases, 2026)
Streptococcus agalactiae was confirmed as the etiologic agent of streptococcosis in Nile tilapia ( Oreochromis niloticus ) from Campeche, Mexico, during a cross‐sectional investigation of eight semi‐intensive farms (2021–2022) that yielded virulent strains in a challenge assay. Standard bacteriology, histopathology, API‐20 Strep phenotyping, one‐step PCR, and real‐time PCR confirmed S. agalactiae in five farms (62.5%). Gross and histological lesions were characterised by mid‐axial and peduncular muscle abscesses, extensive myonecrosis, granuloma formation, polyserositis, and occasional suppurative meningitis. Experimental infections fulfilled Koch's postulates. Juveniles of O. niloticus (20 g) infected with strain ASG‐2290 at 10 6 CFU/mL produced 53% mortality at 96 h. Whole‐genome sequencing of the strains ASG‐2290 and ASG‐2292 identified them as S. agalactiae Ia, marking the first report of this serotype isolated from farmed tilapia in Mexico. Frequent interstate fry movements are likely to be a risk factor for pathogen dissemination. These findings document the geographic expansion of pathogenic S. agalactiae into the Yucatan Peninsula, underscoring the need for strengthened surveillance, biosecurity, and diagnostic capacity to mitigate economic losses in Mexican tilapia aquaculture. Considering that tilapia aquaculture is carried out all year‐round in the Yucatan Peninsula, the implications of these findings are of major concern.

Coupling generative and predictive machine learning algorithms to enhance haloacetonitriles prediction in small water systems - Chengfeng Cao; Yixiang Zhou; Guangji Hu; Manuel J. Rodriguez; Kasun Hewage; Rehan Sadiq (Journal of Hazardous Materials, 2026)

Lessons learned from applying eDNA surveying to diadromous fish detection across the Northeast Atlantic region - Cristina Claver; Mukesh Bhendarkar; Iñaki Mendibil; Natalia Fraija‐Fernández; David J. Nachón; Phil I. Davison; Tea Bašić; Ciara O'Leary; William K. Roche; Iker Azpiroz; Marie‐Laure Acolas; Aitor Lekuona; et al. (Journal of Fish Biology, 2026)
Regular monitoring of diadromous fishes is critical to inform their management and conservation. Yet, the in situ data collection for these species is challenging due to their complex life cycle and low abundance. Focusing on the sea lamprey ( Petromyzon marinus , Petromyzontidae) and the European shads (allis shad Alosa alosa and twaite shad Alosa fallax , Clupeidae), emblematic diadromous fishes in the Northeast Atlantic region, this study leverages the use of aquatic environmental DNA (eDNA) samples to monitor their distribution range. For that aim, we developed quantitative PCR (qPCR) and digital PCR (dPCR) assays and applied them to detect sea lamprey and European shad DNA in a network of 44 river basins across Spain, France, Ireland and the UK. We found that qPCR efficiently detected presence/absence of European shads, whereas the higher sensitivity of dPCR was essential for detecting sea lamprey, which is likely to occur at lower abundance. Moreover, sea lamprey showed significantly lower eDNA copies per litre of water compared to European shads, probably due to their larvae spending several years burrowed within soft sediments, reducing eDNA shedding into the water column. The integration of previously recorded data as reference datasets with this wide‐ranging snapshot study enhances our understanding of the distribution of sea lamprey and European shads in Northeast Atlantic rivers. Importantly, the lessons learned within this international collaboration are critical towards achieving a prevailing framework for conservation of migratory fishes, highlighting the need of well‐designed sampling strategies coupled with species‐specific assays applied to eDNA samples to boost long‐term monitoring efforts of diadromous species.

Space explorer: floral evolution and lineage diversification of the Neotropical Sapranthinae clade (Annonaceae) - María Fernanda Martínez- Velarde; Francis J. Nge; Carlos Rodrigues-Vaz; Vincent Soulé; Santiago Ramírez-Barahona; Thomas L.P. Couvreur; Andrés Ernesto Ortiz-Rodriguez (Molecular Phylogenetics and Evolution, 2026)

Effect of graphene quantum dot size on the capacitance of rGO-based supercapacitors fabricated with a sustainable electrolyte (seawater) - R.A. Mendoza-Jiménez; J. Oliva; T.A. Esquivel-Castro; C. Rodriguez-Gonzalez; P. Salas (Chemical Engineering Journal, 2026)

Genetic diversity among three Mexican local goat populations assessed by microsatellite DNA markers - Irlanda J. Siliceo-Cantero; Glafiro Torres-Hernández; Ricardo Lobato-Ortíz; Samuel Vargas-López; Omar Hernández-Mendo; Javier Suárez-Espinoza; Martha Hernández-Rodriguez; Jorge A. Maldonado-Jáquez (Tropical Animal Health and Production, 2026)

Plant domestication influences the distribution and host-location behavior of entomopathogenic nematodes - Monique J. Rivera; Albrecht M. Koppenhöfer; Cesar Rodriguez-Saona; Rubén Blanco-Pérez (Applied Soil Ecology, 2026)

Optimism predicts future economic mobility among hurricane maria migrants - Maria Duque; Yara Acaf; Christopher P. Salas-Wright; Mildred M. Maldonado-Molina; Pablo Montero-Zamora; Evelyn Gualdron; Mia Cisco; Sumeyra Sahbaz; Carolina Scaramutti-Gladfelter; Lawrence G. Watkins; Duyen H. Vo; Seo Woo Lee; et al. (Climate and Development, 2026)

Transcriptomic response of Acropora cervicornis following transplantation to a marginal, nearshore environment - Allyson DeMerlis; Colin Foord; Dalton J. Hesley; Richard F. Karp; Lys M. Isma; Natalia Andrade-Rodriguez; Kevin H. Wong; Michael S. Studivan; Mike Jankulak; Andrew C. Baker; Diego Lirman; Nikki Traylor-Knowles; et al. (Frontiers in Marine Science, 2026)
As reef-building coral cover has declined worldwide, coral restoration has become a widespread response towards repopulating degraded reefs. In-situ nurseries have provided refugia for the regrowth of several coral species, yet long-term success following outplanting remains highly variable, particularly when corals are introduced into novel or marginal environments. Additionally, while growth and survivorship are commonly used to evaluate restoration success, molecular responses may also provide critical insights into the capacity of corals to acclimatize following transplantation. Here, we examined host and algal symbiont gene expression in the critically endangered reef-building coral Acropora cervicornis following transplantation from an offshore nursery in Key Biscayne, Florida to a nearshore, urbanized habitat in the Port of Miami, Florida. Three nursery-propagated genotypes were outplanted in June 2021 and sampled after four months at both sites for transcriptomic analysis ( n =12 after quality filtering). Transplanted corals exhibited significant shifts in host gene expression relative to nursery controls, with 961 host and symbiont genes significantly upregulated and 165 significantly downregulated. Upregulated host genes were predominantly associated with the environmental stress response, including heat shock proteins, unfolded protein binding, apoptotic processes, detoxification pathways, and innate immune signaling. Weighted gene co-expression network analysis identified two host modules positively associated with the nearshore outplant site and were enriched for pathways related to protein folding, immune activity, and cellular reorganization. These results demonstrate that A. cervicornis outplanted to a nearshore, urbanized environment exhibits sustained activation of stress- and immune-related molecular pathways months after transplantation, which is consistent with a stress-response profile that may reflect ongoing acclimatization. Integrating molecular diagnostics with environmental monitoring may refine genotype and site selection to enhance restoration outcomes.

Pheromone trail following is not modulated by previous visit to food location, distance travelled, or travel direction in the ant Lasius niger - L.-A. Poissonnier; D. Winter; F.‑J. Olivera‑Rodriguez; C. Werneke; T. J. Czaczkes (Insectes Sociaux, 2026)
Ant foraging and recruitment often relies heavily on pheromone trails, and ants modulate pheromone trail deposition strategically. Ants are also known to modulate trail following depending on their own private information, such as the known location of the nest and their knowledge of food sources in the environment. Here we ask how a series of important context variables—distance from the nest, direction of travel, and prior food discovery—affects the fidelity of pheromone trail following in the black garden ant Lasius niger . Using both an open arena assay and a binary Y-maze design, we evaluated whether ants adjust their trail-following behaviour. Ants exhibited robust and consistent trail-following behaviour across all conditions. Surprisingly, we found no significant modulation by distance, travel direction, or recent experience. However, we observed that distance travelled before finding a pheromone trail significantly influenced subsequent walking patterns such as straightness, speed, and total distance travelled. These findings suggest that while L. niger trail-following behaviour is remarkably stable across contexts, locomotory traits remain plastic and context-sensitive. The decoupling of pheromone response from internal or external conditions highlights the need for further investigation into the mechanisms regulating individual foraging decisions in social insects.

Modelling primary production: multitude of theories, or multitude of languages? - Jozef Skákala; Shubha Sathyendranath; Yuri Artioli; Deep S. Banerjee; Heather Bouman; Robert J. W. Brewin; Momme Butenschön; Stefano Ciavatta; Stephanie Dutkiewicz; Yanna Fidai; David Ford; Grinson George; et al. (Ocean Science, 2026)
Marine primary production, converting approximately 50 Gt of inorganic carbon into organic carbon per year, is an important component of the global carbon cycle, and a major determinant of past, present and future climate. Large-scale, long-term estimates of marine primary production rely primarily on two types of models: satellite-based models that make extensive use of remote-sensing data, and ecosystem models providing numerical simulation of ecological processes embedded in general ocean circulation models. Intercomparison exercises of model outputs (both within and across the two model types) have consistently revealed high discrepancies between estimated global ocean primary production, including divergent magnitudes and even opposite trends. Model-observation comparisons are also complex, because paucity of data, differences in measurement techniques, and evolving methodologies could all lead to difficulties with the interpretation of results. These uncertainties limit the applications of primary production models (both satellite-based and ecosystem), especially in the climate context, where an important question is whether climate change will drive significant future changes in regional or global primary production. Both satellite-based and ecosystem models rely on a range of fixed model parameters, whose values need to be carefully estimated and tested. In this paper, we suggest that such model parameters represent an underappreciated but important source of inter-model differences. With the proliferation of both satellite and in situ observations of relevant variables at global scales, and the availability of powerful statistical tools such as data assimilation and machine learning, we argue that time is right to systematically examine model parameters, gaining both better insights into parameter values and how those values might vary in space and time. We argue that such spatio-temporal parameter variability can be theoretically justified for ecosystem models with complexity similar to those commonly used within Earth System Models (ESMs) in climate studies. The spatially and temporally varying parameter values could serve to unify models that are structurally different. An important aspect of this unification could be the ability to infer the spatio-temporal variability of parameters in the less complex models from the emergent behaviour of the more complex ones. This could include ecosystem model simulations of nutrients, temperature, phytoplankton classes, or vertical distributions informing satellite-based models. We conclude that better understanding of model parameter roles and integration (or inter-calibration) of different types of models could reduce discrepancies among the primary production models and improve the reliability of marine primary production projections.

Corrigendum to: “The effects of parental occupational exposures on autism spectrum disorder severity and skills in cognitive and adaptive domains in children with autism spectrum disorder” [Int. J. Hyg Environ. Health 268 (2025) 25 114613] - Erin C. McCanlies; Ja Kook Gu; Claudia C. Ma; Wayne T. Sanderson; Yunin J. Ludeña-Rodriguez; Irva Hertz-Picciotto (International Journal of Hygiene and Environmental Health, 2026)

MFC 5.0: An exascale many-physics flow solver - Benjamin Wilfong; Henry A. Le Berre; Anand Radhakrishnan; Ansh Gupta; Daniel J. Vickers; Diego Vaca-Revelo; Dimitrios Adam; Haocheng Yu; Hyeoksu Lee; Jose Rodolfo Chreim; Mirelys Carcana Barbosa; Yanjun Zhang; et al. (Computer Physics Communications, 2026)

Morphology and particle size distribution in the indoor dust: A hidden threat to human health? - D. Meza-Figueroa; E. Vega; J. Entwistle; A. Angulo-Molina; A. Valencia-Meza; B. Schiavo; V. Rodriguez; B. González-Grijalva; F. Berrellez-Reyes; C. Ortega-Rosas; A. Wellens; A. Namdeo (Environmental Geochemistry and Health, 2026)

Mechanical Performance of Thoracic Aortic Stent-Grafts: An In Vitro and In Silico Study - Anna Ramella; Sara Barati; Giulia De Campo; Giulia Luraghi; Jose Felix Rodriguez Matas; Frederic Heim; Nabil Chakfé; Tim J. Mandigers; Irene Fulgheri; Maurizio Domanin; Santi Trimarchi; Francesco Migliavacca (Annals of Biomedical Engineering, 2026)
Thoracic endovascular aortic repair (TEVAR) is the standard of care for thoracic aortic pathologies, and its clinical success is related to the choice of stent-grafts (SGs). In this study, we conducted a comprehensive assessment of four commercial SGs (Valiant Captivia (VC), Terumo RelayPro Bare Stent (TBS), Cook Zenith Alpha (CZA), and Gore CTAG (CTAG)) to evaluate their mechanical performance in idealised and patient-specific conditions. High-fidelity finite element models were developed and validated against experimental tests and in vitro TEVAR procedures in 3D-printed rigid phantoms. The validation showed strong agreement between simulations and experiments (average error Then, the SGs were virtually deployed in two aortic models to investigate device-wall interaction through geometrical and mechanical parameters. A greater metal density led to increased graft apposition (up to 94%) and increased radial forces (up to 354 N vs 116N). Conversely, sparser metal structures produced lower but more localised stress regions: maximum values of 0.25 MPa versus 0.49 MPa with denser metal. Higher stresses may contribute to improved device fixation and, when associated with greater apposition, may reduce the risk of endoleak. Nevertheless, high stresses could potentially induce long-term vascular remodelling. These results underscore the influence of SG’s design on TEVAR outcomes and support the integration of validated computational simulations into pre-operative planning. The SG performance varied across patient anatomies: this study highlights the importance of personalized device selection and establishes a foundation for using in silico methods to optimize TEVAR strategies and mitigate procedural risks.

Deacetylation and Mechanical Refining Pathway for the Bioconversion of Sugarcane Bagasse - Fernando Roberto Paz Cedeno; Gustavo R. Gomes; Jessica J. Silva; Fabricia F. Menezes; Viviane M. Nascimento; George J. M. Rocha; Renata P. Rodriguez; Xiaowen Chen; Antonio Bonomi; Carlos Driemeier (BioEnergy Research, 2026)
Advancing lignocellulose biorefining is imperative for the deployment of cellulosic (2G) biofuels. This work investigates the tailoring of the alkaline deacetylation and mechanical refining (DMR) pathway for the bioconversion of sugarcane bagasse. Experiments are conducted at laboratory and pilot scales, varying the pretreatment conditions (70–92 °C; 48–100 g NaOH /kg) and the mechanical refining technologies (PFI and disk refining). The pretreatments selectively solubilize acetyl groups (> 86%) and lignin (10–63%) while mostly preserving structural carbohydrates in the solid phase. Enzymatic hydrolysis generates hydrolysates of clean sugars (glucose and xylose), with sugar yields increasing up to 81% for glucose and 89% for xylose in response to delignification and mechanical refining. Biochemical methane potential assays reveal specific methane productions of up to 568 NmL CH₄ gVS⁻¹ for alkaline liquor monodigestion and 344 NmL CH₄ gVS⁻¹ for co-digestion with sugarcane vinasse from the conventional (1G) sugarcane ethanol, indicating a strong potential for bioenergy recovery from this process stream. Synergies are identified in integrating 1G ethanol, 2G DMR processing of bagasse, and anaerobic co-digestion of 1G vinasse and 2G DMR alkaline liquor. This technology enables sugarcane biorefineries to enhance the co-production of ethanol, methane, and concentrated streams of CO 2 .

Fish welfare in a changing world: New developments and current challenges - Sonia Rey Planellas; João L. Saraiva; Eliane Gonçalves‐de‐Freitas; Pablo Arechavala‐Lopez; Bernice Bovenkerk; Michael Breen; Steven J. Cooke; Martin Føre; Lene Northwood; Lars Helge Stien; Sunil Kadri; Chris Noble; et al. (Journal of Fish Biology, 2026)
The welfare of non‐human animals is central to ethical discussions on animal use, with increasing attention to fish welfare across research, aquaria, aquaculture, and fisheries. This paper reviews current theoretical approaches to animal welfare and recent advances in defining and assessing fish welfare since the seminal paper by Huntingford et al. (2006; J Fish Biol 68 : 332–372), highlighting the growing role of cognitive and affective processes. It also includes the concept of positive welfare and some of the current research advances in this field. Methods for measuring, monitoring and assessing welfare via the utilisation of outcome‐ and input‐based indicators are outlined, ranging from practical operational tools to laboratory‐based measures. Welfare concerns in wild‐capture fisheries are examined in relation to stress, flesh quality and sustainability, including the welfare of released fish. Recent advances in fish neurobiology, cognition and pain perception are summarised, together with technological innovations that enhance welfare monitoring and management. The paper also explores the relationship between fish welfare, sustainability, public concerns and consumer demand, and legal and moral recognition across contexts, situating fish welfare within the ‘One Health’ and ‘One Welfare’ frameworks that link animal welfare, environmental stewardship and human well‐being. Ongoing challenges include climate change, cultural factors and the interpretation of fish sentience and cognition among others.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Full Model Optimisation of the Processing Pipeline in Functional Near-Infrared Spectroscopy - Robert J. Ward; Gustavo Rodriguez-Gomez; Felipe Orihuela-Espina (Neuroinformatics, 2026)

Activation of Toll-like receptor 2 reveals microbial contamination beyond endotoxins on micro- and nanoplastics - Øyvind P. Haugen; Itziar Polanco-Garriz; Victor Alcolea-Rodriguez; Raquel Portela; Rita Bæra; Hamed Sadeghiankaffash; Jana Hildebrandt; Dmitri Ciornii; Korinna Altmann; Francesco Barbero; Ivana Fenoglio; Julián J. Reinosa; et al. (Toxicology in Vitro, 2026)

Exposure to low-dose ionizing radiation and dementia mortality in Canadian nuclear power plant workers - Brianna Frangione; Laura A. Rodriguez Villamizar; Ian Colman; Franco Momoli; Estelle Davesne; Lydia Zablotska; Cheryl E. Peters; Paul Demers; Minh Do; Tim Prendergast; Philippe Prince; Paul J. Villeneuve (Environmental Research, 2026)

Retraction notice to ‘A comprehensive study on the application of FeNi3@SiO2@ZnO magnetic nanocomposites as a novel photo-catalyst for degradation of tamoxifen in the presence of simulated sunlight’ [Environ. Pollut. 261 (2020) 114127] - Negin Nasseh; Tariq J. Al-Musawi; Mohammad Reza Miri; Susana Rodriguez-Couto; Ayat Hossein Panahi (Environmental Pollution, 2026)

Cytotoxic Edema and Intra-parenchymal Hemorrhage: A Mediated Pathway to Mortality and Functional Outcome in Cerebral Venous Sinus Thrombosis- A sub-analysis of the CLOT-VENUS Registry - Nashwa Abdelhakim; Milagros Galecio-Castillo; Piyush Kalakoti; Leonardo Cruz-Criollo; Aaron Rodriguez-Calienes; Anderson Brito; Jorge Cespedes; Amir Shaban; Anish Venkatesan; Vanessa Cano Nigenda; Andres Alberto Mercado Pompa; Nicholas M. Mohr; et al. (Translational Stroke Research, 2026)
Cytotoxic edema (CE) is a radiographic marker of early tissue injury in cerebral venous thrombosis (CVT) associated with poor outcomes, yet its mechanistic pathway remains unclear. We investigated whether intraparenchymal hemorrhage (IPH) mediates the association between CE and outcomes. We conducted a retrospective cohort study using the multicenter CLOT-VENUS registry, including acute CVT patients treated at two Comprehensive Stroke Centers in the USA and Mexico (2004–2024). CE was defined as hyperintensities around IPH or venous infarct with DWI restricted diffusion and corresponding low ADC, confirming true restricted diffusion. IPH was defined as hemorrhagic transformation of venous infarction or intracerebral hemorrhage on GRE MRI and/or NCCT. Mediation analyses assessed whether IPH mediated CE associations with in-hospital mortality and functional outcomes. Among 394 patients (mean age 42.7 years; 65.5% female), 128 (32.5%) demonstrated CE and 111(30.2%) IPH. CE was associated with in-hospital mortality (aOR 2.63, 95% CI 1.01–7.12) and poor 6-month mRS (aOR 1.71, 95% CI 1.06–2.74). CE was associated with IPH, which in turn was associated with mortality (aOR 8.73, 95% CI 2.93–30.45) and poor mRS (aOR 1.96, 95% CI 1.18–3.25). Adjustment for IPH rendered the CE-outcome associations non-significant. IPH accounted for 76.8% of CE’s effect on mortality and 83.8% on 6-month mRS. Our findings suggest that IPH likely mediates the effect of CE on outcomes in CVT. Although the temporal sequence could not be confirmed, the results underscore the value of early CE detection for timely intervention.

Petiole Nitrate Analysis: A Diagnostic Method for Optimizing Nitrogen Management in Potato - C. M. Giletto; W. Carciochi; S. E. Silva; M. N. Cassino; S. Rodriguez; J. C. Laborde Amador; E. C. Zamuner; N. I. Reussi Calvo (Potato Research, 2026)

Using genomic tools to evaluate assumptions in a conservation breeding program for endangered red siskins (Spinus cucullatus) - Karen M. Holm; Kathryn M. Rodriguez-Clark; Brian J. Coyle; Rebecca M. Gooley; Erica Royer; Emperatriz Gamero García; Haw Chuan Lim (Conservation Genetics, 2026)
Ex situ conservation breeding programs can provide essential support for recovering endangered species. However, breeding recommendations and strategies may be suboptimal due to untested or incorrect assumptions about conservation units, hybrid ancestry, inbreeding history and family relationships. While genomic approaches have been used to address specific questions in ex situ programs, they are not yet routinely used to test and adjust assumptions, often due to limitations in sample availability and quality particularly at the start of a new program. Using a new conservation breeding program for the endangered red siskin ( Spinus cucullatus ) as an example, we demonstrate how genomic data from a relatively small number of samples, of uneven quality, may be employed to critically examine fundamental assumptions. Using genetic data from 72 individuals, we confirmed strong differentiation between birds from Venezuela and Guyana, supporting an assumption that they should not be mixed in a conservation breeding program. Molecular estimates of genetic diversity and inbreeding also aligned with assumptions that widespread historical illegal trade had introduced the species’ Venezuelan wild diversity into U.S. avicultural flocks. We found no evidence of hybrid ancestry with canaries, which would have resulted from intentional crosses to produce red-colored canaries. Finally, while observational pedigree data were generally reliable, molecular relationship assignments and kinship estimates had high accuracy only for first-degree relatives, limiting our ability to evaluate assumptions about relatedness. Our results highlight the utility of constrained but informative datasets for developing conservation breeding programs, supporting effective management for the long-term survival of endangered species.

Enhancing Community Pharmacists’ Professional Competencies and Sun-Safe Behaviors Through the FarmaSoludable Educational Program - Guillermo J. Pozuelo-Sánchez; Magdalena de Troya-Martín; Francisco Rivas Ruiz; Alba Rodriguez-Martinez; Andras Subert; Maria Alvarez de Sotomayor (Journal of Cancer Education, 2026)
This study examined the impact of a structured educational intervention on professional competencies in individualized photoprotection counselling and on personal sun-safe behaviors. A quasi-experimental pre–post study was conducted among community pharmacists in Seville, Spain, in 2024. The intervention consisted of a blended educational program comprising an online training course delivered by a multidisciplinary faculty and a one-day practical session. Professional counselling practices were assessed using the Counselling Habits in Individualized Photoprotection questionnaire, while personal habits, attitudes, and knowledge related to photoprotection were evaluated using the Habits, Attitudes, and Knowledge in Photoprotection questionnaire. Data were collected at baseline and after completion of the intervention, and analyses included descriptive and comparative pre–post statistics, with statistical significance set at p < 0.05. A total of 116 pharmacists completed the baseline professional assessment and 80 the post-intervention, while 125 and 85 pharmacists completed the personal behavior questionnaire, respectively. Professional competencies improved significantly, including identification of skin cancer risk factors (45.2% to 72.2%), promotion of skin self-examination (31.6% to 65.8%), and adaptation of counselling to occupational sun exposure ( p < 0.001). Knowledge scores increased from 6.03 to 7.07 ( p < 0.001). Personal sun-safe behaviors also improved, including sunscreen use, regular reapplication, and reduced sunburn frequency. Knowledge of early skin cancer detection criteria increased markedly (ABCDE rule: 61.5% to 100%; ugly duckling sign: 27.9% to 98.8%; p < 0.001). The FarmaSoludable educational program improved professional competencies and personal preventive behaviors, supporting pharmacists’ roles as behavioral role models and educators for community knowledge transfer.

Standardising research on marine biological carbon pathways required to estimate sequestration at Polar and sub-Polar latitudes - Simon A. Morley; David K.A. Barnes; Camila Neder; Ricardo Sahade; Chester J. Sands; Carla M. de Aranzamendi; Kaja Balazy; Piotr Balazy; Facundo Barrera; Narissa Bax; Sofia Becerra; Lucia Bergagna; et al. (Earth-Science Reviews, 2026)

Hydraulic Fracture Propagation in Pre-structured Media: Stress Field and Fracture Network Topology - Adrian V. Garcia; Rached M. Rached; Carlos D. Rodriguez-Hernandez; J. Carlos Santamarina (Rock Mechanics and Rock Engineering, 2026)

Contributions to the knowledge of DNA barcodes and diversity of intertidal and shallow-water mollusks in the Beagle Channel - L. D. Chiberry; J. Sánchez; V. M. Núñez; S. Rodriguez; M. Pellegrino; S. Poljak (Polar Biology, 2026)

Evidence of deep-sea trophic resource partitioning between the glowbellies Acropoma hanedai and A. japonicum near Southwestern Taiwan - Michael J. Ghedotti; Kurt L. Riggin; Milo A. Marsh; Sarah A. Bramlett; Hayden D. Pearson; Gabriel J. Rodriguez; Josephine N. Gruber; Joshua P. Egan; Kristofor A. Voss (Environmental Biology of Fishes, 2026)

Plumeria ampelovirus 1, a novel ampelovirus subgroup II member infecting Plumeria spp. - Olufemi J. Alabi; Ashrafou Ouro-Djobo; Audrey A. Rodriguez; John O. Oladokun; Minsook Hwang; Cecilia Villegas; Kristian Stevens; Maher Al Rwahnih; Kevin Ong (Archives of Virology, 2026)

‘Building the (Im)perfect Beast’: Strategies for Identifying Appropriate Spatial Stock Assessment Model Complexity From an International, Blinded High‐Resolution Simulation Experiment - Aaron M. Berger; Daniel R. Goethel; Simon D. Hoyle; Patrick Lynch; Caren Barceló; Alistar Dunn; Brian J. Langseth; Carolina Minte‐Vera; Jemery Day; Haikun Xu; Francisco Izquierdo; Dan Fu; et al. (Fish and Fisheries, 2026)
Despite their potential to inform sustainable regional harvest and climate‐resilient fisheries management, spatial stock assessment models remain underused for management advice. To identify barriers that inhibit broader use of these methods, we conducted a blinded international simulation experiment mimicking real‐world stock assessment development when confronting spatial complexity. Seven analyst teams built spatially aggregated and spatially explicit assessment models using data simulated from high‐resolution operating models based on Indian Ocean yellowfin tuna and Ross Sea Antarctic toothfish dynamics. Each team documented how assessment software platform, data analyses, model building approach, and diagnostics influenced model complexity and realism. A consensus emerged on key assessment building approaches: (1) conduct high‐resolution data analyses to identify appropriate spatial structure; (2) start with simplified models and incrementally add complexity; (3) iteratively evaluate diagnostics to determine necessary spatial complexity; and (4) maintain models with different spatial structures to aid interpretation. The experiment also revealed several valuable insights for parameterising assessments, including consideration of data pre‐processing with spatiotemporal models to better inform data‐sparse regions; regression trees to identify fleet and spatial structure; trade‐offs in complexity between productivity and movement dynamics to achieve tractable and stable model structures; and ensemble modelling approaches to address structural uncertainty. Our findings demonstrate that international collaborations and simulation experiments are crucial for addressing challenges in implementing spatial stock assessments and for evaluating whether their added complexity is justified given management objectives. Broader collaborations are encouraged to foster innovation in fisheries management and to help recognise the practical trade‐offs between model parsimony and complexity.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Continental Contrasts in Climate Extremes That Control Tree Fecundity - James S. Clark; Robert Andrus; Margarita Arianoutsou; Davide Ascoli; Yves Bergeron; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; J. Julio Camarero; et al. (Global Change Biology, 2026)
In 2023, more than half of olive harvests ( Olea europaea ) across Spain, Greece, and Türkiye were lost to drought. The same year late freeze destroyed 90% of the peach crop ( Prunus persica ) on the Georgia Piedmont and the apple crop ( Malus domestica ) in central New York, Vermont, and southern Quebec. Climate extremes now rank with the costliest threats to agriculture, but their role in forest recovery from diebacks that are happening globally is unknown for lack of tree fecundity estimates in forests. Tolerance of climate extremes could depend on past exposure but constrained by phylogenetic conservatism. We report a continental scale analysis of climate extremes and forest fecundity across North America and Europe showing that responses to late freeze and drought are happening now. Species differences are not explained by the traits typically included in ecological studies and they are weakly associated with phylogeny. Late freeze, that is, freezing temperatures that follow the onset of flower development in spring, is shown to be “normal” in North America, but not Europe, potentially explaining failed seed production due to delayed onset and the resultant shorter growing period by North American transplants dating back at least to the 18th century. Drought has thus far had the greatest impacts in dry forested regions, but here too, species differences are not explained by traditional trait values. If responses have been buffered from drought and late freeze by past exposure, acclimation and local adaptation prove inadequate as extremes intensify.

Changes in Key Biodiversity Area networks following national comprehensive assessments - Andrew J. Plumptre; Zoltan Waliczky; Daniele Baisero; Olivia Crowe; Jeannot Kivono; Cecilia Tobar; Maria Gabriela Toscano; Natalia Boulad; Hugo Costa; Camila Davila; Sophie Dirou; Eleuterio Duarte; et al. (Conservation Biology, 2026)
Key Biodiversity Areas (KBAs) are sites of significance for the global persistence of biodiversity. Based on the Global Standard for the Identification of Key Biodiversity Areas (KBA Standard), published in 2016, sites are currently being assessed for KBA designation in a growing number of countries across the world. For these assessments, the KBA criteria are applied to all species and ecosystems with available data. We reviewed the first comprehensive assessments of 11 countries and compared the KBA network before and after assessments. The mean (SD) number of KBAs per country increased by 69.6% (102.1), and the mean total extent of KBAs per country increased by 164.2% (150.7). More than half of the KBAs in 2024 had >50% of their area outside the 2019 KBAs, indicating a substantial increase in KBA extent (54.0% [18.8] of KBAs). The mean proportion of each KBA covered by protected or conserved areas decreased from 56.2% (20.2) to 44.5% (15.5), owing to the incorporation of unprotected sites in the KBA network. On average, 41.1% (14.0) of sites in each country (mean 44.5 [46.4] sites per country) and 47.2% (20.5) of new KBA area after the assessment were completely unprotected, indicating that many of the new sites were not recognized in national protected area networks as significant for biodiversity before the assessment. Making a comprehensive assessment of KBAs increased the combined coverage of protected and conserved area networks from 25.4% (10.6) to 32.0% (13.1) in each country and thus contributed to reducing biodiversity loss. Therefore, comprehensive assessments of KBAs led to a substantially increased number and extent of recognized sites of importance for biodiversity published in the World Database of KBAs. Where such assessments have not been made, many important areas for biodiversity may be overlooked. We therefore encourage other nations to update their KBA networks to inform efforts to meet the goals and targets of the Kunming–Montreal Global Biodiversity Framework.

Correction: Gut microbial communities of Rocky Mountain Sculpin (Cottus bondi) and suckerfish (Catostomus spp.) in the East Gallatin River - Maria L Rodriguez; Andrew J Maritan; Christine E Verhille; Frank J Stewart; Deborah E Keil; Augustus Armijo; Zoe A Pratte (Frontiers in Marine Science, 2026)

Modulatory Role of Oral GHRP-6 in the Immune Response and Digestive Enzyme Function in Juvenile Tilapia (Oreochromis sp.) Challenged with Pseudomonas aeruginosa - Liz Mariam de Armas; Adrian Rodríguez-Gabilondo; Liz Hernández; Ernesto A. Quintana; Alejandro J. Campos; Noelia N. Pérez; Danielle Reyes; Antonio Morales; Osmany Rodrigo; Yaima González; Leandro Rodriguez-Viera; Mario Pablo Estrada; et al. (Fishes, 2026)
Aquaculture has been established as a sustainable alternative to traditional fisheries, which face challenges such as overexploitation and environmental degradation. However, disease outbreaks, often caused by poor farming conditions, pollution, and environmental stress, remain a major concern, leading to economic losses and increasing the risk of antibiotic resistance due to the overuse of antibiotics. Therefore, it is crucial to seek new strategies that improve fish health and well-being, preventing drug resistance and promoting sustainable practices. GHRP-6, a synthetic growth hormone-releasing peptide that mimics ghrelin, has shown potential immunostimulatory properties and feed efficiency in fish. In this study, we evaluated the effects of orally administered GHRP-6 in an oil-based formulation on juvenile tilapia (Oreochromis sp.) challenged or unchallenged with Pseudomonas aeruginosa. We assessed its influence on immune gene expression and digestive enzyme activity. The results demonstrated that GHRP-6 treatment significantly enhanced growth performance (weight and length), reduced in vivo bacterial load after infection, and modulated key genes related to innate and adaptive immunity in the gills, intestine and head kidney. In addition, our results demonstrated, for the first time, a direct link between a growth hormone secretagogue in fish and the modulation of specific enzyme activity in the gut following a bacterial challenge. These findings highlight the potential of GHRP-6 as a dietary immunomodulator and growth promoter in fish farming, offering a promising strategy to reduce antibiotic usage and promote more sustainable aquaculture practices.

Impacts of Diverse Stakeholder Participation on Fisheries Management - Sangeeta Mangubhai; S. L. Smith; Z. Davis; N. Koedyker; J. Augustyn; D. Durholtz; S. Fulton; Harlisa; M. T. Hidayat; L. Hiriart-Bertrand; M. Khazali; E. Litsinger; et al. (Coastal Management, 2026)

Toxicological assessment of hawksbill sea turtle eggs from the Arabian Gulf - Fatin Samara; Fadi Yaghmour; Ishraq Osman; Waqas Ahmad; Areej Mohammed; Clara Jimena Rodriguez-Zarate; Brendan J. Godley (Marine Pollution Bulletin, 2026)

Identifying and quantifying greenhouse gas emissions with the AVIRIS-3 airborne imaging spectrometer - Red Willow Coleman; Andrew K. Thorpe; Philip G. Brodrick; Adam Chlus; Jay E. Fahlen; Brian Bue; John Chapman; Regina F. Eckert; Daniel J. Jensen; Michael L. Eastwood; David R. Thompson; Clayton D. Elder; et al. (Remote Sensing of Environment, 2026)

The rhythms of environmental conditions, particles dynamics, and barnacle activity captured by underwater imaging in sub-Antarctic kelp forests of the Beagle Channel - E. Trudnowska; P. Balazy; M. Bagur; P. Kuklinski; J. Kaminsky; K. Balazy; M. Rodriguez; Z. Derwich; G. Lovrich (Progress in Oceanography, 2026)

Use of shotgun immunoproteomics for the development of protein vaccines against Edwardsiella piscicida - Kim L. Jacobsen; Matt J. Griffin; Brett S. Phinney; Michelle Salemi; Zeinab Yazdi; Sujita Balami; Caitlin E. Older; Cynthia C. Ware; Fernando Y. Yamamoto; Noor-ul Huda; Tania Rodriguez-Ramos; Brian Dixon; et al. (Fish & Shellfish Immunology, 2026)

Associations between exposure to metals, chlorinated pesticides, and PCBs and differential leukocyte profiles in Flemish adolescents - Fen Zhang; Lützen Portengen; Hamid Y. Hassen; Laura Rodriguez Martin; Madeline Carsique; Amélie Crépet; Jasper Engel; Jacob Van Klaveren; Nicolas Van Larebeke; Willy Baeyens; Stefaan De Henauw; Tim S. Nawrot; et al. (Environmental Research, 2026)

An open, reproducible benchmark of daily CO2 forecasting models with applications to GHG monitoring - Pablo Catret-Ruber; David Garcia-Rodriguez; Domingo J. Iglesias Fuente; Ernesto López-Baeza; J. Javier Samper-Zapater; Juan José Martínez Durá (Environmental Modelling & Software, 2026)

Evaluating the NASA MPLNET Rain Masking Algorithm at Goddard Space Flight Center and Barcelona sites: Relevance to EarthCARE Cloud Profiling Radar Validation - Simone Lolli; Jasper R. Lewis; Ali Tokay; Gemine Vivone; James R. Campbell; Erica K. Dolinar; Michael Sïcard; Adolfo Comerón; Alejandro Rodriguez-Gomez; Constantino Muñoz-Porcar; Albert García-Benadí; Mireia Udina; et al. (Atmospheric Research, 2026)

Biochar enhances nitrogen use efficiency in lettuce by promoting its metabolic assimilation - Alvaro F. Garcia-Rodriguez; Francisco J. Moreno-Racero; Rosario Álvarez; José M. Colmenero-Flores; Heike Knicker; Miguel A. Rosales (Plant and Soil, 2026)
Background and aims Peat replacement with biochar (BC) offers a sustainable strategy in horticultural substrates but its effects on plant nitrogen (N) metabolism and N use efficiency (NUE) remain unclear. This study tested whether vineyard-pruning-derived BC can boost NUE and metabolic activity in lettuce, providing a pathway toward more productive and sustainable horticulture. Methods Plant substrates (BC, peat and vermiculite) were prepared in the following proportions (v:v:v): B0 (0:70:30), B15 (15:55:30) and B30 (30:40:30) for growing lettuce (Lactuca sativa L. var. Batavia) under greenhouse conditions for 31 days. We assessed plant growth and physiological traits, quantified N species and calculated NUE parameters and the activities of key N assimilation enzymes. Results B30 plants produced 44.2% more biomass and 23.2% larger leaf area than B0, resulting in lower specific leaf area and greater succulence. BC addition decreased available NO₃⁻ and NH₄⁺ in substrate and roots without causing any plant stress symptoms, as chlorophyll content and PSII efficiency remained stable. B30 increased N uptake flux, N utilization efficiency, partial N balance, and N productivity by 31.8%, 34.8%, 27.8%, and 13.8%, respectively, relative to B0, coinciding with enhanced N-assimilation enzymatic activity. Despite lower total N in roots and shoots, protein accumulation increased, indicating more efficient N conversion into organic compounds. Conclusion These findings demonstrate the potential of BC-based substrates (especially 30% BC) to enhance lettuce productivity by improving NUE through the stimulation of N assimilation pathway, offering a promising strategy to optimize N-fertilizer needs to support more sustainable agriculture and soil management practices.

Phytochemicals as promising agents against pathogenic free-living amoebas - Erick P. Gutiérrez-Grijalva; Laura A. Contreras-Angulo; Marilyn Shomara Criollo-Mendoza; J. Basilio Heredia; Jaime López-Cervantes; Dalia Isabel Sánchez-Machado; Jose Reyes Gonzalez-Galaviz; Libia Zulema Rodriguez-Anaya (Phytochemistry Reviews, 2026)

Citral impairs intestinal changes caused by ulcerative colitis through modulation of antioxidant, anti-inflammatory and healing activities - Maycon T. Emílio-Silva; Vinícius P. Rodrigues; Antonio J. Ruiz-Malagon; Isabela G. Guidolin; Felipe L. Dario; Mariana M. Fioravanti; Alba Rodriguez-Nogales; Julio Gálvez; Clelia A. Hiruma-Lima (Inflammopharmacology, 2026)

Gut microbial communities of Rocky Mountain Sculpin (Cottus bondi) and suckerfish (Catostomus spp.) in the East Gallatin River - Maria L Rodriguez; Andrew J Maritan; Christine E Verhille; Frank J Stewart; Deborah E Keil; Augustus Armijo; Zoe A Pratte (Frontiers in Marine Science, 2025)
The gastrointestinal (GI) microbiome plays a critical role in animal health and fitness, yet it remains understudied in many species—particularly those inhabiting freshwater environments affected by anthropogenic activity. This study investigates the gut microbiomes of two benthic fish species, Rocky Mountain Sculpin ( Cottus bondi ) and suckerfish ( Catostomus spp.), collected upstream and downstream of a wastewater treatment plant (WWTP) effluent outflow into the East Gallatin River in southwestern Montana. Prokaryotic and eukaryotic microbiome diversity in the fish GI tract was assessed using 16S and 18S rRNA gene sequencing, respectively, from samples collected in the summer and fall of 2022 and 2023. While alpha diversity only had insignificant and small shifts across samples, beta diversity (taxonomic composition) differed significantly across sites and collection dates. Notably, the composition of eukaryotic sequences shifted markedly from upstream to downstream locations, suggesting that WWTP effluents may influence both prokaryotic and eukaryotic microbial communities. By establishing baseline GI microbiome characteristics for these species, this study provides important insights into the potential ecological effects of wastewater discharge on freshwater systems and supports conservation efforts aimed at mitigating pollutant impacts.

The Guajira contourite depositional system along the northern Colombian Caribbean convergent margin - J. Naranjo-Vesga; O. Mantilla; D. Rincón-Martínez; E. Rodriguez-Rubio; A. Ortiz-Karpf; C. Winter; Y. Rojas-Agramonte (Marine and Petroleum Geology, 2025)

Environmental identities of college students reveal potential conflicts and common ground for wildlife conservation - Richard Von Furstenberg; Lincoln R. Larson; M. Nils Peterson; Kangjae Jerry Lee; Victoria R. Vayer; kathryn stevenson; Stacy A.C. Nelson; Jeremy Bruskotter; Adam A. Ahlers; Christine Anhalt-Depies; Taniya Bethke; Chris Chizinski; et al. (Biological Conservation, 2025)

A Simple Model to Estimate the Economic Optimum Nitrogen Rate in Potato Using Vegetation Indices - Claudia M. Giletto; W. D. Carciochi; F. M. Inchauspe; S. E. Silva; M. N. Cassino; V. Ortega; S. Rodriguez; J. C. Laborde Amador; N. Reussi Calvo (Potato Research, 2025)

Cause-effect relationship between volcanism and travertine-tufa deposition: the case study of Barranco de Azuaje, Gran Canaria, revisited - F. J. Perez-Torrado; M. C. Cabrera; A. Rodriguez-Gonzalez; Á. Marrero-Rodríguez; C. Ravazzi; P. Vidal-Matutano; J. L. Fernandez-Turiel (Journal of Iberian Geology, 2025)

Linking genomic and proteomic signatures to brain amyloid burden: insights from GR@ACE/DEGESCO - Raquel Puerta; Itziar de Rojas; Pablo García-González; Clàudia Olivé; Oscar Sotolongo-Grau; Ainhoa García-Sánchez; Fernando García-Gutiérrez; Laura Montrreal; Juan Pablo Tartari; Ángela Sanabria; Vanesa Pytel; Carmen Lage; et al. (Functional & Integrative Genomics, 2025)

“Resilience-based framework for enhancing NaTech risk management in industrial critical infrastructures” - David J. Castro Rodriguez; Antonello A. Barresi; Micaela Demichela (Environment Systems and Decisions, 2025)
Industrial facilities, once considered isolated entities, are now approached as complex socio-technical systems that involve intricate networks operating within the confines of the surrounding environment. The increasing frequency of extreme natural events due to climate change has highlighted the vulnerability of industrial plants to NaTech (natural hazards triggering technological scenarios). Current methodologies for NaTech risk assessment focus predominantly on immediate consequences, overlooking the long-term complexities that both industrial systems and their surrounding territories may face. This research proposes a resilience-based framework for NaTech risk management, considering three main stages —awareness, preparedness, recovery—and a loop for continuous learning to address the evolving NaTech challenges. Awareness emphasizes proactive vulnerability characterization under the function-location perspective. It addresses the interactions between industrial plants and multi-hazard contexts by implementing innovative methodological procedures based on qualitative, quantitative, and spatial techniques. Preparedness is supported by an innovative multi-risk tool considering the dynamic vulnerability of equipment categories to individual and overlapped interacting hazards, able to deploy the vulnerability into hierarchical safety layers to design robust and context-specific safer systems. The recovery stage is described through a retrospective case of hydrocarbon pollution caused by rainfall, integrating countermeasures and sustainable technological solutions. Overall, this research highlights the need for multidimensional approaches to tackle the evolving challenges posed by NaTech events. The outcomes present a comprehensive resilience-based framework, and operational procedures guiding the practical implementation of resilience principles and advancing the understanding of complex industrial systems while supporting their long-term sustainability facing natural factors.

Combining wood traits as a promising timber origin verification and its application in the Brazilian trade chain - Bruna Hornink; Daigard Ricardo Ortega-Rodriguez; Deoclecio J. Amorim; Peter Groenendijk; Kathelyn Paredes-Villanueva; José Guilherme Roquette; Ana Carolina M.C. Barbosa; Edson Vidal; Alexandre Bahia Gontijo; Monique S. Costa; Norma Rodrigues Nunes de Senna; Davi Neves de Lemos; et al. (Science of The Total Environment, 2025)

Assessment of microplastic retention efficiency using pilot-scale filtration systems applied to drinking water - K. Herrera; A. Egea-Corbacho; D. Coello; J. Quiroga; E. Marin; V. Monsalvo; E. Lucero; R. Rodriguez (Journal of Hazardous Materials, 2025)

“Effects of mercury exposure in three Amazonian agricultural plant species and the impact on bacterial population in soil” - Maria J. Rodriguez-Pascual; Claudia Vega; Natasha Andrade; Luis E. Fernández; Shih-Huai Cheng; Birthe Kjellerup; Alba Torrents (Environmental Research, 2025)

Evaluating the combined methods of live planting and seed dispersal in restoration of Zostera marina (eelgrass) in Barnegat Bay, New Jersey by genetic diversity and pedigree analysis of restored populations - Nicole Rodriguez Ortiz; Nathan Cruz; Tiffany V. Santos; Paul A.X. Bologna; James J. Campanella (Aquatic Botany, 2025)

Discovery of Latissimia ningalooensis: a new invasive soft coral species in Puerto Rico - Daniel A. Toledo-Rodriguez; Catherine S. McFadden; Nilda M. Jimenez Marrero; J. David Muñoz-Maravilla; Alex J. Veglia; Ernesto Weil; Nikolaos V. Schizas (Biological Invasions, 2025)

The key mechanisms associated with the survival of Gulf toadfish, Opsanus beta , when in severe hypoxia - Anastasiya Plotnikova; Isabelle R. Nelson; Shara Y. Sookhoo; Jacob M. Belkin; Vanessa P. Lima; Ross D. Bronfman Bunch; Athena M. Santomero; Sophia A. Santomero; Emily C. Rodriguez; Jayda K. Rodriguez; Kathleen M. Davis; Amanda J. Kaplan; et al. (Journal of Fish Biology, 2025)
Florida's shallow seagrass beds experience daily diurnal fluctuations in environmental oxygen, leading to hypoxic episodes (PO 2 −1 , ~6 kPa) that have increased in frequency and intensity in recent decades. The native Gulf toadfish ( Opsanus beta ) have been shown to employ a suite of adaptive cardiovascular, ventilatory and metabolic adjustments to survive moderate hypoxia, but little is known of the mechanisms used to survive severe hypoxia. The objective of this study was to characterize the acute response of Gulf toadfish to severe hypoxia ( 2 ~0.4 kPa for 3 h followed by 1 h recovery). Heart rate, pulse pressure, caudal arterial blood pressure, ventilation frequency and ventilation amplitude were monitored and blood samples were taken from both groups and analysed for pH, glucose, lactate and other endpoints. Hypoxia‐exposed fish experienced a statistically significant 70% decrease in heart rate and a 32% decrease in ventilation frequency during hypoxia exposure. Moreover, plasma glucose concentrations increased 5‐fold and plasma lactate concentrations increased 6‐fold, with a minimal reduction in pH. Our findings support our hypothesis that Gulf toadfish are highly hypoxia tolerant and survive severe hypoxia by reducing energy expenditure and switching to anaerobic metabolism. It is important to understand how the Gulf toadfish deal with severe hypoxia due to the increasing prevalence of severe hypoxia in its natural environment.

Soft Range Limits Shape Sensitivity to Forest Cover More Strongly Than Hard Range Limits - Natasha R. Granville; Alex L. Pigot; Benjamin Howes; Luiz dos Anjos; Victor Arroyo‐Rodriguez; Luc Barbaro; Jos Barlow; Matthew G. Betts; Alexis Cerezo; Pedro F. Develey; Jack H. Hatfield; Hervé Jactel; et al. (Global Ecology and Biogeography, 2025)
Aim Land‐use change is a major threat to biodiversity, yet there remains considerable unexplained variation in how it affects different populations of the same species. Here, we examine how sensitivity to forest cover changes depending on proximity to different limits of a species' range. By comparing responses as species approach their coastal (‘hard’) and inland (‘soft’) range limits, we aim to provide insight into the relative influence of mass effects, as compared to abiotic and biotic environmental suitability in shaping population sensitivity. Location Global. Time Period 1996–2019. Major Taxa Studied Birds. Methods We combined data from several large databases to obtain a dataset of 2543 bird species surveyed across 116 studies, spanning six continents. Using expert‐verified range maps, we calculated the position of populations relative to their species' nearest inland (‘soft’) and coastal (‘hard’) range limits and categorised the inland limits as equatorward‐ or poleward‐ facing. We investigated how distance to range limits and forest cover, derived from a 30 m‐resolution global dataset, affect the probability of species' incidence. Results We found that bird populations are more sensitive to forest cover when located closer to their species' inland (‘soft’) range limits, whereas this was not the case at coastal (‘hard’) range limits. The heightened sensitivity to forest cover at soft range limits was similar regardless of whether the range limit faced equatorward or poleward. Main Conclusions These results highlight how populations close to the soft limits of their species' ranges are at higher risk of extirpation resulting from loss of forest cover. This suggests that environmental conditions (e.g., climate), which become more challenging away from the core of the species' range, drive variability in sensitivity to forest cover.

Sulforaphane improves exercise-induced NRF2 signaling in older adults: an in vivo-ex vivo approach - Dominick J. Rodriguez; Ethan L. Ostrom; Connor Chassman; Jay Robertson; Vincent Pan; Robert Buscaglia; Aimee L. Eggler; Tinna Traustadóttir (GeroScience, 2025)

Managing fisheries and ecosystems: current good practices and the EcoScope project experience - Georgi M. Daskalov; Santiago de la Puente; Marco Scotti; Stefania Klayn; Marie Briguglio; Gianpaolo Coro; Gideon Gal; Johanna J. Heymans; Ana Rodriguez-Perez; Jeroen Gerhard Steenbeek; Georgios Sylaios; Athanassios C. Tsikliras (Frontiers in Marine Science, 2025)
Ecosystem Based Management (EBM) is a comprehensive way of managing fisheries and marine resources. As such, it needs a large and complex suite of concepts and tools to address a variety of problems ranging from climate change, through various forms of water pollution, to trophic interactions and social-economic sustainability. Industry, scientists, managers, and policy makers involved in the fisheries sector are the main actors in EBM. EBM objectives based on policy needs, legal requirements, and ecosystem considerations may target specific fish stocks, or encompass several ecosystem components aiming for balanced fisheries, but they need to address the trade-offs between maximizing economic gains versus sustainable fisheries and healthy ecosystems. Fishing at Maximum Sustainable Yield (MSY), setting ecosystem reference points, discards ban, avoiding bycatch of protected species, habitat protection, accounting for the effects of climate change, achieving good environmental status, setting effective marine protected areas, and considering ecosystem effects from marine spatial planning, are all examples of EBM objectives. The EcoScope project aimed to address ecosystem degradation, anthropogenic impacts, and unsustainable fisheries by developing an efficient, holistic, ecosystem-based approach to sustainable fisheries management that can easily be used by policy makers and advisory bodies. The EcoScope consortium reflects an interdisciplinary advisory team of biologists, modelers, economists, and social scientists. It performed comprehensive reviews of data, data gaps, and various tools (models, indicators, management evaluation procedures). An online platform, toolbox, academy, and a mobile application are end products delivered and maintained by EcoScope to facilitate knowledge sharing, communication, and education. The EcoScope project has built modules ready to be used in the implementation of EBM, but a more direct approach by the responsible organizations, such as ICES, FAO, GFCM and the EC, is needed to set explicit and formal research and managerial frameworks for implementing and coordinating the EBM activities.

Determination of flowering stage based on artificial intelligence and the daily weight of bee hives - Andrés Gersnoviez; Francisco J. Rodriguez-Lozano; María Brox; José Moreno-Carbonell; Manuel Ortiz-Lopez; José M. Flores (Computers and Electronics in Agriculture, 2025)

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

A comparison of the life history and distribution of vermilion rockfish (Sebastes miniatus) and its cryptic pair, sunset rockfish (S. crocotulus) along the Pacific Coast - John H. Harms; Anita Wray; John R. Hyde; Gary C. Longo; Jennifer A. Hempelmann; Anna E. Elz; R. Matthew Barnhart; James A. Benante; Aaron C. Chappell; Peter H. Frey; Colin L. Jones; Betty Kamikawa; et al. (Fisheries Research, 2025)

Disease prevalence in confiscated exotic and indiginous birds and reptiles housed in a cites-authorized rescue center in Spain - M. Jimenez Martinez; A. Martin; A. Rabanal Soto; V. Hidalgo Martinez; A. Rodriguez Luis; M. Aranda Vazquez; J. De Andres Gamazo (Journal of Comparative Pathology, 2025)

Development of a biotechnological process for the production of recombinant canine interferon-alpha using the baculovirus-insect cell and larvae system - Maria S. Rodriguez; Ignacio Smith; Marcela S. Villaverde; Joaquin M. Birenbaum; Joaquin Poodts; Federico J. Wolman; Alexandra M. Targovnik; Maria V. Miranda (Biotechnology Letters, 2025)

Multi-wavelength internal standardization using inductively coupled plasma optical emission spectrometry - Reagan Elia; Thomas J. Johnston; Alberto D. Figueroa; Emily M. Curbow; Mayra S. Gonzalez Guzman; Leah C. Rodriguez Cabrera; Marisa M. Morcom; Willis B. Jones (Analytica Chimica Acta, 2025)

Infection by the Marine Cestode Hepatoxylon trichiuri in Returning Chinook Salmon ( Oncorhynchus tshawytscha ) Spawners in Patagonia: Implications for a Novel Fishery - Guillermo Figueroa‐Muñoz; Patricio Torres; J. Marcos Rodriguez; Christina A. Murphy (Fisheries Management and Ecology, 2025)
Parasitological information may be useful for managing economically important fisheries by providing insights into population dynamics and health effects. The Chinook salmon ( Oncorhynchus tshawytscha ), an invasive species with high socio‐ecological importance in South America, supports recreational and incipient artisanal fisheries. In Southern Chile, the recent approval of coastal fisheries for returning Chinook salmon in some regions highlights the importance of understanding salmon foraging, habitat use, and commercial value. However, such information is lacking. Parasites have been extensively used as cost‐effective biological tags to identify fish stocks. We conducted the first parasitological examination of the marine tapeworm Hepatoxylon trichiuri larvae in returning adult Chinook salmon from the Cisnes River to assess its potential as a biological tag for returning Chinook salmon in Patagonia. Of 61 Chinook salmon from the Cisnes River, 52.46% were infected by H. trichiuri , with 1.65 ± 1.26 parasites per infected salmon (mean ± SD). Infection prevalence and intensity did not differ significantly between males and females. Infection intensity was higher in larger salmon but decreased with increasing salmon condition. Infection intensity was not significantly related to length, mass, or body condition. Infection prevalence and intensity of H. trichiuri varied spatially among Patagonian river‐basin populations of Chinook salmon, thereby supporting the use of H. trichiuri as a biological tag. Our findings provide important parasitological metrics that may enhance future management practices by informing geographic variability in foraging locations of adult salmon and their commercial value for human consumption.

A methodology for coagulant virtual testing to improve dissolved organic matter removal in surface water treatment - Christian Ortiz-Lopez; Christian Bouchard; Manuel J. Rodriguez (Science of The Total Environment, 2025)

Soil salinity effects on inter-plant signalling in wild cotton are contingent on herbivore load and differentially shape direct and indirect defences - Jonathan Interian-Aguiñaga; Uriel Solís-Rodriguez; Yeyson Briones-May; Patricia Guadarrama-Chávez; Marine Mamin; Mary V. Clancy; Ted C. J. Turlings; Xoaquín Moreira; Luis Abdala-Roberts (Planta, 2025)

A machine learning approach for type 2 diabetes diagnosis and prognosis using tailored heterogeneous feature subsets - J. Ramón Navarro-Cerdán; Pedro Pons-Suñer; Laura Arnal; Joaquim Arlandis; Rafael Llobet; Juan-Carlos Perez-Cortes; Francisco Lara-Hernández; Celeste Moya-Valera; Maria Elena Quiroz-Rodriguez; Gemma Rojo-Martinez; Sergio Valdés; Eduard Montanya; et al. (Medical & Biological Engineering & Computing, 2025)
Type 2 diabetes (T2D) is becoming one of the leading health problems in Western societies, diminishing quality of life and consuming a significant share of healthcare resources. This study presents machine learning models for T2D diagnosis and prognosis, developed using heterogeneous data from a Spanish population dataset (Di@bet.es study). The models were trained exclusively on individuals classified as controls and undiagnosed diabetics, ensuring that the results are not influenced by treatment effects or behavioral changes due to disease awareness. Two data domains are considered: environmental (patient lifestyle questionnaires and measurements) and clinical (biochemical and anthropometric measurements). The preprocessing pipeline consists of four key steps: geospatial data extraction, feature engineering, missing data imputation, and quasi-constancy filtering. Two working scenarios (Environmental and Healthcare) are defined based on the features used, and applied to two targets (diagnosis and prognosis), resulting in four distinct models. The feature subsets that best predict the target have been identified based on permutation importance and sequential backward selection, reducing the number of features and, consequently, the cost of predictions. In the Environmental scenario, models achieved an AUROC of 0.86 for diagnosis and 0.82 for prognosis. The Healthcare scenario performed better, with an AUROC of 0.96 for diagnosis and 0.88 for prognosis. A partial dependence analysis of the most relevant features is also presented. An online demo page showcasing the Environmental and Healthcare T2D prognosis models is available upon request. Graphic abstract

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Host‐Microbiome Associations in Livebearing Fishes Adapted to Toxic Environments Rich in Hydrogen Sulfide - Elizabeth J. Wilson; Sonny T. M. Lee; Lydia H. Zeglin; Lenin Arias Rodriguez; Michael Tobler (Molecular Ecology, 2025)
Organisms inhabiting extreme environments must tolerate a variety of physiochemical stressors. In some cases, host‐associated microbial communities facilitate the survival of their hosts in extreme environments, but extremophile symbioses have not been identified in vertebrates. We used 16S rRNA amplicon sequencing to investigate commonalities and differences in the gut bacterial communities of livebearing fishes ( Poecilia mexicana species complex, Poeciliidae) that have repeatedly colonised toxic sulfide streams in southern Mexico. We found shared gut microbial taxa across habitat types and drainages but also differences in the microbiomes between sulfidic and nonsulfidic populations, both in terms of patterns of diversity and community composition. Most importantly, we documented convergent changes in microbiome composition across evolutionarily independent sulfide spring lineages. These patterns were consistent when we analysed the gut microbiomes as well as primarily host‐associated microbiomes that excluded taxa that are commonly found in the environment. Our analyses also revealed several microbial taxa associated with sulfide spring coloniation that have previously been implicated in symbioses and may influence the host's tolerance to the extreme environmental conditions. Our study sheds light on how shared environmental pressures can give rise to convergent host‐microbiome associations in fishes, and it provides a foundation for investigating the role of host‐microbiome interactions in vertebrate adaptation to extreme environments.

Removal of PFAS and pharmaceuticals from municipal wastewater using a novel β-cyclodextrin adsorbent over distinct contact times - Emma F. Shapiro; Zhi-Wei Lin; Edwin Saavedra Cifuentes; Francisco J. Barajas-Rodriguez; Rosa Gwinn; William R. Dichtel; Aaron I. Packman (Water Research, 2025)

Optical and particulate properties of dust aerosols in El Paso, Texas - German Rodriguez Ortiz; Manisha Mehra; Mackenzie Ramirez; Sujan Shrestha; Sascha Usenko; James Flynn; Rebecca J. Sheesley; Thomas E. Gill (Atmospheric Research, 2025)

Characterization of agr-like Loci in Lactiplantibacillus plantarum and L. paraplantarum and Their Role in Quorum Sensing and Virulence Inhibition of Staphylococcus aureus - Weizhe Wang; Ifigeneia Kyrkou; Martin S. Bojer; Dina Kalloubi; Abdul Jabbar Kali; Miguel Alena-Rodriguez; Jørgen J. Leisner; Stephanie Fulaz; Hanne Ingmer (Probiotics and Antimicrobial Proteins, 2025)
The pathogenicity of Staphylococcus aureus is largely regulated by the agr quorum sensing (QS) system encoded by agrBDCA , which coordinates virulence factor production through secretion and sensing of auto-inducing peptides (AIPs). agr -like systems are also present in coagulase-negative staphylococci, and several of these encode AIPs that inhibit S. aureus QS. In lactic acid bacteria, a similar locus was previously identified in Lactiplantibacillus plantarum WCSF1 termed lamBDCA . Here, we characterized the lamBDCA locus in L. plantarum LMG 13556 and L. paraplantarum CIRM-BIA 1870, and explored the effects on S. aureus QS. Notably, we found that co-cultivation with L. paraplantarum significantly inhibits S. aureus QS and hemolysin production, while less so for L. plantarum . The inhibition by L. paraplantarum was lost upon disruption of its lamBDCA locus, suggesting that the L. paraplantarum AIP mediates cross-species interference with S. aureus agr activation. Transcriptomic analysis revealed that lamBDCA in L. paraplantarum controls the expression of genes belonging to various functional categories, including stress response and metabolism. The latter includes genes encoding riboflavin (B2 vitamin) biosynthesis, which enabled the growth of the L. paraplantarum lamB mutant in the presence of roseoflavin, a toxic riboflavin analogue. Collectively, our results show that L. paraplantarum CIRM-BIA 1870 interferes with S. aureus virulence gene expression through QS suppression, and they implicate QS in the probiotic properties of L. paraplantarum .

Trace element distributions among Cu-(Fe)-sulfides from the Olympic Dam Cu-U-Au-Ag deposit, South Australia - Samuel A. King; Nigel J. Cook; Cristiana L. Ciobanu; Kathy Ehrig; Sarah Gilbert; Benjamin Wade; Yuri T. Campo Rodriguez (Mineralium Deposita, 2025)

Active and passive pathways of nutrient transfer in coral reef ecosystems - Ruth E. Dunn; Nicholas A. J. Graham; Laura-Li Jeannot; Rucha Karkarey; F. Javier Gonzalez-Barrios; Ines D. Lange; Julia Rodriguez Fillol; Ronan Roche; Marleen Stuhr; Cassandra E. Benkwitt (Coral Reefs, 2025)
Coral reefs receive both passive and active nutrient subsidies, supplied via oceanographic processes and animal-mediated transfer, which can bolster reef productivity and resilience to disturbance. We examined the relative importance of these two pathways across lagoonal and seaward reefs, reefs of different depths, and those around islands either with or without breeding seabird colonies using carbon and nitrogen stable isotopes (ð 13 C and ð 15 N) and nutrient metrics (per cent N, %N and carbon-to-nitrogen ratios, C:N). We found increased passive oceanic nutrient inputs in reefs that were both deep and seaward facing, indicated by lower ð 13 C values. Enriched ð 15 N values and lower carbon-to-nitrogen ratios within reefs adjacent to islands with seabird colonies provided evidence of the role of seabirds as active vectors of nutrients to coral reef food webs, particularly within shallow, lagoonal reefs. Though %N values did not seem to provide a good indicator through which to disentangle active vs passive nutrient transport within this context, variation in ð 13 C and ð 15 N values and C:N ratios highlighted the interplay between passive oceanic processes and active seabird contributions to coral reefs. We emphasise the importance of both preserving and restoring natural nutrient pathways, particularly at a time when coral reef ecosystems are under increasing pressure from anthropogenic threats.

Shadows over Caribbean reefs: occurrence of a new invasive soft coral species, Xenia umbellata, in southwest Puerto Rico - Daniel A. Toledo-Rodriguez; Alex J. Veglia; Nilda M. Jimenez Marrero; Joyce M. Gomez-Samot; Catherine S. McFadden; Ernesto Weil; Nikolaos V. Schizas (Coral Reefs, 2025)

Leveraging Remote Sensing and Theory to Predict Tree Size Abundance Distributions Across Space - Adam J. Eichenwald; John M. Grady; Jonathan A. Knott; J. Marcos Rodriguez; Ben Weinstein; David A. Orwig; Sydne Record (Global Ecology and Biogeography, 2025)
Background Remote sensing (RS) technologies provide unprecedented opportunities to assess forest structure at broad spatial scales. Light detection and ranging (LiDAR) is a powerful tool that offers detailed vertical information, but its consistent high‐resolution coverage can be limited across vast areas and quantifying understory vegetation remains challenging due to occlusion. Conversely, while high‐resolution RGB imagery is more accessible and valuable for large‐scale analyses, it comes with higher uncertainty and only captures canopy‐level information. Integrating RGB data with ecological theory and existing LiDAR‐derived products (e.g., canopy height models, CHM) allows us to enhance predictions and broaden the applicability of forest size structure mapping from the understory to the canopy, particularly through tree size–abundance relationships. Theory Tree size and abundance generally follow known distributions, where smaller trees are exponentially more common than larger trees. This pattern emerges from fundamental ecological constraints, including volume packing, metabolic scaling and light competition, which collectively govern forest self‐organisation across spatial scales. Proposed Approach We present a workflow that integrates size‐abundance scaling theory with RGB data and CHMs to improve predictions of forest structure. By estimating tree size distributions from RGB imagery, we extend the applicability of ecological scaling models to broader spatial scales and offer an approach that complements traditional methods. Assessment We apply this approach to forest monitoring networks, including NEON and ForestGEO, to assess its accuracy and generalisability across a range of forests (e.g., subtropical pine, boreal, low and dry, tall and dense) in North America. Our results show that RGB‐based estimates can successfully recover size‐abundance distributions from the understory to the canopy. Future Directions Further refinement of our approach could enhance predictions by incorporating species classifications from hyperspectral data and using more spatially or taxonomically specific allometric equations. These additions would enable more precise scaling of tree diameter from remote sensing data.

The Impact of Disturbance on Tree Size Distributions in the United States - Adam J. Eichenwald; John M. Grady; Jonathan A. Knott; Quentin D. Read; J. Marcos Rodriguez; Sydne Record (Global Ecology and Biogeography, 2025)
Aim Tree size distributions are an emergent feature of forest dynamics across space and time. Theory suggests that undisturbed forests exhibit a size‐abundance distribution captured by a power‐law relationship with a near‐2 slope. We aimed to quantify how disturbances systematically and predictably cause deviations from this expected pattern. Location Contiguous United States. Time Period 2001–2023. Major Taxa Studied Diverse tree communities. Methods We analysed size‐abundance distributions in over 160,000 FIA plots for both disturbed and undisturbed forests, examining changes in slope associated with disturbances, stand age, and maximum tree height. We used a Structural Equation Model (SEM) to evaluate whether disturbance effects on size‐abundance slopes were indirectly mediated by changes in stand age or maximum height. Results We found that the predominant disturbances across the dataset (e.g., ground fires, animal damage) result in predictable flattening of size‐abundance slopes, reflecting the selective removal of smaller trees. In contrast, many disturbances (e.g., wind, disease) did not shift the slopes predictably, indicating that they did not selectively impact any specific size class. Maximum tree height and stand age were also reliable predictors of size‐abundance distributions, but a structural equation model demonstrated that the impact of disturbance on size‐abundance slopes was not mediated through its indirect effects on stand age or maximum tree height, suggesting a direct pathway of influence. Main Conclusions Disturbances result in predictable changes to forest size‐abundance slopes. As climate change and increased disturbance frequencies produce younger and shorter forests, future size‐abundance slopes are expected to be steeper than those in undisturbed forests. Our findings suggest a temporary flattening in the size‐abundance relationship immediately after the predominant disturbances across the dataset (ground fires, animal damage). These findings underscore the importance of understanding disturbance impacts on forest size structure to improve predictions of forests across broad spatial and temporal scales.

The nature-based solution implementation gap: A review of nature-based solution governance barriers and enablers - Juliette G.C. Martin; Anna Scolobig; JoAnne Linnerooth-Bayer; Jenan Irshaid; Julia J. Aguilera Rodriguez; Alberto Fresolone-Caparrós; Amy Oen (Journal of Environmental Management, 2025)

The effects of parental occupational exposures on autism spectrum disorder severity and skills in cognitive and adaptive domains in children with autism spectrum disorder - Erin C. McCanlies; Ja Kook Gu; Claudia C. Ma; Wayne T. Sanderson; Yunin J. Ludeña-Rodriguez; Irva Hertz-Picciotto (International Journal of Hygiene and Environmental Health, 2025)

Correction: Parasite diversity in sea turtles of the temperate SW Atlantic: a bridge between systematics and ecology - E. O. Palumbo; C. K. Álvarez; S. Rodriguez-Heredia; A. Rosenthal; M. Vassallo; I. M. Bruno; J. Loureiro; L. Diaz; A. Faiella; M. R. Werneck; J. I. Diaz; V. González Carman (Marine Biology, 2025)

Application of a high-density microelectrode array assay using a 3D human iPSC-derived brain microphysiological system model for in vitro neurotoxicity screening of environmental compounds - Kelly E. Carstens; Elena Gronskaya; David Jäckel; Jessica Bertoli; Kelvin Ramirez Cuevas; Julien Dorier; Shan Wang; David Lopez-Rodriguez; Timothy J. Shafer; Marie-Gabrielle Zurich; David Pamies (Archives of Toxicology, 2025)
Unraveling the associations between human exposure to environmental chemicals and potential neurotoxicity presents significant challenges. Evaluation of neurotoxicity potential using animal testing is resource-intensive (financial, labor, and animal use) and faces uncertainties regarding biological relevance to human health outcomes. Therefore, there is a need to develop efficient and human-relevant in vitro new approach methodologies (NAMs) to screen and evaluate chemicals for neurotoxicity potential. Recording of neural network activity using microelectrode array (MEA) technology has been identified as a reliable and reproducible method for evaluating neurotoxicity. Much of this research has been performed in 2D rodent-derived cell models. The ‘BrainSpheres MEA assay’ described in this study offers a promising functional human induced pluripotent stem cell (iPSC)-derived 3D brain model comprising neurons, astrocytes, and oligodendrocytes. We demonstrate consistent spontaneous neuronal firing and network bursting parameters from 7-week-old BrainSpheres using a high-density MEA technology. The performance of this model as a human-relevant NAM was evaluated by conducting a multi-concentration, 13 day exposure study with a set of ten chemicals. Neural activity metrics were assessed and compared to results from a 2D-MEA assay using rodent cells. Loperamide and domoic acid (two assay positive controls) demonstrated similar bioactivity profiles in the BrainSphere MEA assay to the 2D-MEA assay, while acetaminophen (assay negative control) was inactive in both assays. The 2D-MEA model demonstrated more potent bioactivity for 4/7 chemicals that were active in both assays. In the future, reducing replicate variability and testing a larger set of chemicals will likely improve the accuracy and reliability of the assay. These preliminary findings suggest that the BrainSphere assay could be used alongside the rat network formation assay (rNFA) as part of a tiered strategy, where hits in the rNFA are confirmed and further characterized in the BrainSphere model, helping move toward animal-free toxicological testing.

Exploring Nutritional Condition of Merluccius hubbsi During Early Life Stages: Environmental Drivers and Possible Implications on Subsequent Recruitment - Julieta Rodriguez; Nadia M. Alves; Harold Fenco Chavesta; Gustavo J. Macchi; Agustin Schiariti; Rosana Di Mauro; Marina V. Diaz (Fisheries Oceanography, 2025)
The early life stages of fish represent a period of high energy requirements due to profound changes that characterize the passage to adulthood, crucial for fisheries recruitment. This study focuses on the North Patagonian Frontal System (NPFS) that guarantees successful larval development and fulfills the three postulates of Bakun's “fundamental triad” in regards to nutrients, concentration of food, and retention of eggs and larvae inside the favorable area. The objective was to evaluate the nutritional condition of Merluccius hubbsi larvae and juveniles, from the Patagonian stock in January during austral summer (2010–2021). The standardized RNA/DNA index (RDs) was used. Interannual variation in the larval condition was observed in relation to NPFS features. RDs were positively linked to the stratification of the water column in the stratified zone. An opposite trend was observed between larval condition and potential egg production that might indicate the existence of density‐dependent mechanisms. On the other hand, the positive relation between larval condition and egg production of older females (≥7 years) supports the idea of a maternal effect on larval survival. There was also a positive relationship between juveniles condition, body size, and recruitment, but no relationship was observed with the stratification of the water column. The high sensitivity of the RDs index links physiological state with survival probability, informing on factors affecting eggs, larvae, and juveniles until their posterior recruitment. This study identified the stratified area of the NPFS as a favorable nursery zone, providing crucial information for managing populations under high fishing pressure.

The fingerprint of pesticides in agricultural used polyethylene - Gabriela Castro; Victoria Fernández-Fernández; Miguel Cobo-Golpe; María Ramil; Enrique Blázquez-Blázquez; María L. Cerrada; I. Bernabé; J. Martínez Urreaga; M.U. de la Orden; Isaac Rodriguez (Waste Management, 2025)

Coupled Lu-Hf and U-Pb apatite geochronology of Jatobá orebody supports ∼ 2.5 Ga metamorphism in deep shear zones from southern Copper Belt, Carajás Domain, Brazil - Yuri Tatiana Campo-Rodriguez; Cristiana L. Ciobanu; Sarah Gilbert; Benjamin Wade; Nigel J. Cook; Maria Emilia Schutesky; Kathy Ehrig (Precambrian Research, 2025)

Lignin hydrotreatment to aromatics products on metallic phosphides carbon-based catalysts produced from lignin - M. García-Rollán; S. Bertran-Llorens; M.A. Palazzolo; P.J. Deuss; H.J. Heeres; R. Ruiz-Rosas; J.M. Rosas; J. Rodriguez-Mirasol; T. Cordero (Fuel, 2025)

Understanding osmoregulation, cryoprotectant toxicity, and cold tolerance in sea urchin eggs: Implications for cryopreservation - S. Campos; Uxía Rodriguez; J. Troncoso; E. Paredes (Cryobiology, 2025)

Monazite, lanthanide-rich glasses, and other trace elements in copper smelter slags: constraints on critical metal behaviour in Si-Fe-rich melts - Hassan Gezzaz; Cristiana L. Ciobanu; Nigel J. Cook; Kathy Ehrig; Ashley Slattery; Benjamin Wade; Sarah Gilbert; Yuri T. Campo Rodriguez (Mineralogy and Petrology, 2025)
Furnace slags are potential new sources of critical metals. We undertook a micron- to nanoscale study that addresses speciation, distribution and associations of phases in air-cooled flash furnace (FF, oxidised) and electric furnace (EF, reduced) slags from the Olympic Dam mining-smelting-refinery operation. Results enable understanding of the behaviour and partitioning of critical metals between melt and cooling crystalline phases in a controlled smelter environment that mimics Fe-Si-rich systems in Nature. Melts at ~ 1300 °C result in slags that differ in the relative proportions of component phases. Both FF and EF slags comprise major magnetite and two, compositionally distinct Si-Fe-rich glasses (glass-1 and -2); fayalite is a main component of EF slag. Glass-1 is rich in REE + Y (4.5–5.4 wt%, Ce 2 O 3 + La 2 O 3 ) and contains dendritic monazite-(Ce). Glass-2 (~ 70 wt% SiO 2 ) contains < 1 wt% Ce 2 O 3 + La 2 O 3 . The EF slag reaction sequence is: magnetite $$→$$ → fayalite + glass-1 $$→$$ → monazite $$→$$ → glass-2. Immiscibility of REE-rich liquid from Si-Fe-rich melt is inferred from amorphous ‘monazite-like’ droplets. Chondrite-normalised fractionation patterns are defined by downwards-sloping LREE segments in both glasses. Partition coefficients are calculated for magnetite and fayalite relative to glasses. D REY for HREE exceeds those for LREE in all phases and fayalite has an order of magnetite higher D HREE than co-existing EF magnetite. Applying lattice strain models to experimental values show excellent fits for D HREE-model trends, even if lattice strain is not the sole factor controlling partitioning. Melt polymerisation, variable/unpredictable oxidation states, and constraints from specific crystallographic sites, also impact on observed trends. This study provides clues to element behaviour in metallurgical plants that can assist potential utilization of copper smelter slags to meet the demand for REE and other contained critical metals.

Lemongrass (Cymbopogon citratus) peroxidase-modified screen-printed graphene electrodes for electrochemical sensing of hydrogen peroxide - Ella Rodriguez; Stefania Correa; Herminsul Cano; John J. Castillo (Journal of Plant Biochemistry and Biotechnology, 2025)

Biomechanical and Compositional Changes in the Murine Uterus with Age - Mari J. E. Domingo; Triniti N. Vanoven; Raffaella De Vita; Maria E. Florian Rodriguez; Kristin S. Miller; Isaac J. Pence (Annals of Biomedical Engineering, 2025)

Anthocyanin supplementation in adults at risk for dementia: a randomized controlled trial on its cardiometabolic and anti-inflammatory biomarker effects - Miguel German Borda; Robinson Ramírez-Vélez; Felipe Botero-Rodriguez; Jonathan Patricio-Baldera; Chiara de Lucia; Ilaria Pola; George E. Barreto; Khadija Khalifa; Anne Katrine Bergland; Miia Kivipelto; Tommy Cederholm; Henrik Zetterberg; et al. (GeroScience, 2025)
Anthocyanins are dietary flavonoids shown to have a therapeutic capacity to mitigate inflammation and oxidative stress. The present secondary analyses from the “Anthocyanins in People at Risk for Dementia Study” were aimed at (I) determining the intervention’s effect on blood-based markers of cardiovascular disease and inflammation and (II) evaluating whether baseline factors such as age, sex, inflammation, or cardiometabolic score may moderate the intervention’s effect on inflammatory status. This study was an ancillary, 24-week randomized, double-blind, placebo-controlled Phase II trial. Sub-sample participants ( n = 99), aged 60–80 years with mild cognitive impairment or cardiometabolic disorders, were randomized to receive either 320 mg/day of anthocyanins or placebo. The biomarkers analyzed included inflammatory biomarker assessment (IL − 6, IL − 8, IL − 10, IL − 1b, TNF − α, IFN − γ), and C-reactive protein (CRP), as well as albumin, thrombocytes, cholesterol, LDL, HDL, and triglycerides, which were longitudinally compared between both groups. Baseline characteristics were balanced between the groups. ANCOVA analyses reveal 24-week differences favoring the anthocyanin treatment in LDL cholesterol levels (ƞp 2 = 0.078; p = 0.015), cardiometabolic score (ƞp 2 = 0.073; p = 0.021), CRP levels (ƞp 2 = 0.417; p = 0.0001), IL − 6 (ƞp2 = 0.085; p = 0.015), IL − 1b (ƞp 2 = 0.058; p = 0.037), and Inflam z-score 5 (ƞp 2 = 0.059, p = 0.004). Moderation analysis demonstrated that the inflammatory score at baseline was a significant predictor of the effect of the intervention on the CRP levels. Anthocyanin supplementation reduces CRP and cardiovascular disease biomarkers in individuals at risk of dementia, especially when there is increased inflammation at baseline. ClinicalTrials.gov study identifier: NCT03419039.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Genome mining to elucidate antimicrobial and plant growth promoting potentials in Lactic acid bacteria - Christian Vargas; Lina Botero; Edwin Rodriguez; Lorena Dávila; Camilo Racedo; Claudia Barrera; Adriana J. Bernal; Hugo Jiménez; Paola Zuluaga; Carolina González (European Journal of Plant Pathology, 2025)
The pangenome of lactic acid bacteria (LAB) was constructed with five bacterial strains isolated from oat silage produced by smallholder farmers from a region in the highlands of the Colombian Andes. The goal of this work was to use genome mining to elucidate some potential mechanisms of action associated with plant growth promotion and biocontrol in LAB. Multiple genes were uncovered, including those associated with antibiosis and antimicrobial compound production, genes that induce plant defense and phytohormone activation. Additionally, genome sequencing suggested mechanisms for LAB to protect against abiotic and biotic stress. Furthermore, genes that may improve phosphorus availability and those that might stimulate root growth were present. We then tested some of these findings in vitro . For instance, the biocontrol activity of these strains was evaluated against the fungal pathogens Fusarium oxsyporum f. sp. cubense ( Foc R1 and Foc TR4) and the bacterial pathogen Ralstonia solanacearum ( Rs ). All tested strains showed the ability to significantly inhibit pathogen growth in vitro . The capability of LAB to grow at high concentrations of fusaric acid was demonstrated, suggesting that LAB might have detoxification mechanisms to compete with other microorganisms. Also, the ability of LAB to solubilize phosphate and produce IAA was demonstrated. These two properties might be involved in plant-growth promotion. Here we show that genomic sequencing can be an efficient tool to identify putative biocontrol or plant-growth promoting related sequences for genome mining.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Earth's most needed uncultivated aquatic prokaryotes - Sophie A. Simon; Vera Aschmann; Annika Behrendt; Michael Hügler; Lisa M. Engl; Marion Pohlner; Sönke Rolfes; Thorsten Brinkhoff; Bert Engelen; Martin Könneke; Luis M. Rodriguez-R; Till L.V. Bornemann; et al. (Water Research, 2025)

Venom variation and ontogenetic changes in the Crotalus molossus complex: Insights into composition, activities, and antivenom neutralization - Miguel Borja; Gamaliel Castañeda-Gaytán; Alejandro Alagón; Jason L. Strickland; Christopher L. Parkinson; Areli Gutiérrez-Martínez; Bruno Rodriguez-López; Vanessa Zarzosa; Bruno Lomonte; Anthony J. Saviola; Julián Fernández; Cara F. Smith; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Development of a generalized pseudo-continuous model for fluid dynamics in packed bed reactors with a low d t / d p - Alberto Hernandez-Aguirre; Roel Hernandez-Rodriguez; J. Alberto Ochoa-Tapia; Carlos O. Castillo-Araiza (Chemical Engineering Journal, 2025)

Safety Outcomes of Antiplatelet Therapy During Endovascular Treatment of Tandem Lesions in Acute Ischemic Stroke Patients - Mudassir Farooqui; Afshin A. Divani; Milagros Galecio-Castillo; Ameer E. Hassan; Mouhammad A. Jumaa; Marc Ribo; Michael Abraham; Nils Petersen; Johanna Fifi; Waldo R. Guerrero; Amer M. Malik; James E. Siegler; et al. (Translational Stroke Research, 2025)

Parasite diversity in sea turtles of the temperate SW Atlantic: a bridge between systematics and ecology - E. O. Palumbo; C. K. Álvarez; S. Rodriguez-Heredia; A. Rosenthal; M. Vassallo; I. M. Bruno; J. Loureiro; L. Diaz; A. Faiella; M. R. Werneck; J. I. Diaz; V. González Carman (Marine Biology, 2025)

Social and knowledge diversity in forest education: Vital for the world’s forests - Mika Rekola; Andrew B. Taber; Terry L. Sharik; John A. Parrotta; Michael J. Dockry; Folaranmi D. Babalola; Tara L. Bal; David Ganz; Marta Gruca; Manuel R. Guariguata; James Kungu; Pipiet Larasatie; et al. (Ambio, 2025)
A global assessment of the status of tertiary, vocational, and technical forest education and training found deficits in inclusion of knowledge and student diversity. Coverage of forest services and cultural and social issues was characterized as weak in the curricula of many programs. The inclusion of traditional and Indigenous knowledge was frequently poor or absent. Gaps were found in enrollment at tertiary education levels with respect to diversity by gender, race/ethnicity, and other societal groups. If unaddressed, forest researchers, professionals, and workers will continue to lack familiarity with different knowledge systems and the importance of inclusive representation. Improvements in forest education related curricula, research, monitoring, policy, recruitment, and promotion are recommended. Without remedial action to build a representative, skilled, and knowledgeable workforce, prospects for forests to meet local, national, and global goals are at risk. Improved social and knowledge diversity in forest education is paramount for the future of forests.

Temperature Drives Seagrass Recovery Across the Western North Atlantic - Fee O. H. Smulders; Justin E. Campbell; Andrew H. Altieri; Anna R. Armitage; Elisabeth S. Bakker; Savanna C. Barry; S. Tatiana Becker; Enrique Bethel; James G. Douglass; Hannah J. van Duijnhoven; Jimmy de Fouw; Thomas K. Frazer; et al. (Global Change Biology, 2025)
Climate‐driven shifts in herbivores, temperature, and nutrient runoff threaten coastal ecosystem resilience. However, ecological resilience, particularly for foundation species, remains poorly understood due to the scarcity of field experiments conducted across appropriate spatial and temporal scales that investigate multiple stressors. This study evaluates the resilience of a widespread tropical marine plant (turtlegrass) to disturbances across its geographic range and examines how environmental gradients in (a)biotic factors influence recovery. We assessed turtlegrass resilience by following recovery rates for a year after a simulated pulse disturbance (complete above‐ and belowground biomass removal). Contrary to studies in temperate areas, higher temperature generally enhanced seagrass recovery. While nutrients had minimal individual effects, they reduced aboveground recovery when combined with high levels of herbivore grazing (meso and megaherbivore). Belowground recovery was also affected by combined high levels of nutrients and grazing (megaherbivores only). Light availability had minimal effects. Our results suggest that the resilience of some tropical species, particularly in cooler subtropical waters, may initially benefit from warming. However, continuing shifts in nutrient supply and changes in grazing pressure may ultimately serve to compromise seagrass recovery.

Fosfomycin in bacteraemic urinary tract infection due to multidrug-resistant Escherichia coli : insights of post hoc DOOR analysis of the FOREST trial - Jesús Sojo-Dorado; Inmaculada López-Hernández; Belén Gutiérrez-Gutiérrez; Sandra De la Rosa-Riestra; Fernando Docobo-Pérez; Alicia Hernánez-Torres; Álvaro Pascual; Jesús Rodriguez-Baño; Esperanza Merino de Lucas; Laura Escolà-Vergé; Elena Bereciartua; Elisa García-Vázquez; et al. (Infectious Diseases, 2025)

Developmental exposure to an environmentally relevant dose of Bisphenol S impairs postnatal growth and disrupts placental transcriptional profile in female rat - J. Fudvoye; D. Lopez-Rodriguez; C. Glachet; D. Franssen; Q. Terwagne; A. Lavergne; A.F. Donneau; C. Munaut; P. Dehan; A. Lomniczi; A.S. Parent (Reproductive Toxicology, 2025)

Balancing supply security and decarbonization: Optimizing Germany’s LNG port infrastructure under the European Green Deal - Per J. Agrell; Henri Dehaybe; Manuel Herrera Rodriguez (Energy Policy, 2025)

Feed intake, preferences, in vivo digestibility, and nutritional value of tedera (B. bituminosa var. bituminosa) and maralfalfa (Pennisetum purpureum) in Canary sheep - M. Barbera; V. Mendoza-Grimón; J. Espinosa; E. Rodriguez-Ponce; A. Gracia; E. SanJuán; M. R. Ventura (Tropical Animal Health and Production, 2025)
This study evaluated the nutritional value and energy content of tedera ( B. bituminosa var. bituminosa ) and maralfalfa ( Pennisetum purpureum ) through analyses of chemical composition, digestibility, intake, and preference trials. Tedera was compared with maralfalfa and alfalfa hay ( Medicago sativa ). Tedera showed higher crude protein (193 g CP/kg DM) and estimated energy (10.5 MJ DE/kg DM) but lower dry matter (286.3 g DM/kg) and neutral detergent fiber (373 g NDF/kg DM) than both maralfalfa and alfalfa hay. The in vitro organic matter digestibility (IVOMD) of tedera was 61.7%, compared to 51.0% for alfalfa hay and 66.3% for maralfalfa. Digestible organic matter (DOM) ranged from 467 g/kg DM in alfalfa hay to 566.4 g/kg DM in tedera. Four Canary sheep with a mean body weight (BW) of 42.2 ± 5.0 kg were used for digestibility and preference trials. The live weights of the sheep were recorded at the start and end of the 12-day trial. Feed offered and refusals were weighed and recorded daily for eight days, while feces were collected for four days to calculate apparent in vivo digestibility. For tedera, the apparent in vivo OM digestibility, estimated digestible energy, and digestible organic matter were 69.4%, 11.8 MJ/kg DM, and 637.7 g/kg DM, respectively. Preference and feed intake were compared between tedera, maralfalfa and alfalfa hay. Total DM consumption was 1091.3 g/day (tedera + maralfalfa + alfalfa hay), with alfalfa hay intake representing 40.8%, maralfalfa 37.3%, and tedera 21.9% of the total DM consumed. However, no significant differences were observed in the ratio of forages consumed/offered (44.8% for tedera and 51.8% for maralfalfa) or in the total grams of DM, CP, and MJ/kg of DE consumed by the sheep with both forages. The sheep adopted different feeding strategies in response to the chemical composition and nutritive value of the forages. Preferences and intake in this trial were associated with high NDF content in maralfalfa and alfalfa hay and with the high CP content in tedera rather than digestibility results. This may be due to the complementarity of the three forages and the higher CP content in tedera affecting intake. Nevertheless, tedera and marafalfa could be a good forage considering its nutritive value, digestibility, and proven growth performance in herbivores.

Leaf Gene Expression in Response to Boron Toxicity in Native Maize (Zea mays L.) Cultivars - Mirko J. Ortiz; José Delatorre-Herrera; Juan Pablo Rodriguez Calle; Gerzon Moreno; Javier Palacios; Camila Molina; Víctor Espinoza; Cristopher Low-Pfeng; José Delatorre-Castillo; Isabel Sepúlveda-Soto (Journal of Soil Science and Plant Nutrition, 2025)

Perceptions and Attitudes of Drinking Water Supply Systems Staff Towards Climate Change Adaptation for Drinking Water Quality Management - S. M. Cynthia Compaoré; Ianis Delpla; Sonja Behmel; Manuel J. Rodriguez (Environmental Processes, 2025)

18S rRNA Metagenomic Analysis of Nodular Gill Disease in Swiss Rainbow Trout ( Oncorhynchus mykiss ) - James W. Wynne; Chloe J. English; Stefania M. Vannetti; Megan Rigby; Petra R. Quezada‐Rodriguez; Ralph Knüsel; Christine Huynh; Heike Schmidt‐Posthaus (Journal of Fish Diseases, 2025)
Nodular gill disease (NGD) is a serious proliferative gill condition that affects farmed salmonids, particularly in Europe. While the cause of NGD remains unknown (and maybe multifactorial), various amoebae are often isolated from the gills of affected fish and can in some cases be seen associated with lesions by histopathology. The present study aimed to quantify the abundance of different amoeba species directly from the gills of rainbow trout affected by NGD and healthy controls. An 18S rRNA amplicon metagenomic approach was employed to profile the diversity and abundance of micro‐eukaryotes (including amoebae) while suppressing the amplification of host DNA using a salmonid‐specific C3 spacer blocking primer. The 18S rRNA metagenomics approach identified a diversity of micro‐eukaryotes on the gills of rainbow trout, including the phylum's Amoebozoa , Diatomea , Platyhelminthes and Ciliophora . Rainbow trout clinically affected by NGD had a significantly higher abundance of a specific sequence (zOTU2) classified as Vannella sp. compared to healthy controls. A quantitative PCR assay was then developed and validated which accurately quantified the abundance of this Vannella sp. sequence from a NGD outbreak in a Swiss rainbow trout farm. Additional PCR and Sanger sequencing analysis of the zOTU2 sequence demonstrated that this sequence is most likely derived from Vannella mustalahtiana . Our study highlights the potential role of Vannella mustalahtiana in NGD in Switzerland and further describes a specific and validated diagnostic PCR assay for accurate detection of this Vannella species.

Exploring the potential of hydrolytic enzymes combined with antibacterial agents to disrupt pathogenic biofilms and disinfect released cells - Patricia Palafox-Rivera; Melvin R. Tapia-Rodriguez; Julio Cesar Lopez-Romero; Marco A. Lugo-Flores; Karen P. Quintero-Cabello; Brenda A. Silva-Espinoza; M. Reynaldo Cruz-Valenzuela; Filomena Nazzaro; J. Fernando Ayala-Zavala (Biofouling, 2025)

Toward an integrated pantropical ocean observing system - Gregory R. Foltz; Yassir A. Eddebbar; Janet Sprintall; Antonietta Capotondi; Sophie Cravatte; Peter Brandt; Adrienne J. Sutton; Tamaryn Morris; Juliet Hermes; Clive R. McMahon; Michael J. McPhaden; Lev B. Looney; et al. (Frontiers in Marine Science, 2025)
Global climate is regulated by the ocean, which stores, releases, and transports large amounts of mass, heat, carbon, and oxygen. Understanding, monitoring, and predicting the exchanges of these quantities across the ocean’s surface, their interactions with the atmosphere, and their horizontal and vertical pathways through the global oceans, are key for advancing fundamental knowledge and improving forecasts and longer-term projections of climate, weather, and ocean ecosystems. The existing global observing system provides immense value for science and society in this regard by supplying the data essential for these advancements. The tropical ocean observing system in particular has been developed over decades, motivated in large part by the far-reaching and complex global impacts of tropical climate variability and change. However, changes in observing needs and priorities, new challenges associated with climate change, and advances in observing technologies demand periodic evaluations to ensure that stakeholders’ needs are met. Previous reviews and assessments of the tropical observing system have focused separately on individual basins and their associated observing needs. Here we provide a broader perspective covering the tropical observing system as a whole. Common gaps, needs, and recommendations are identified, and interbasin differences driven by socioeconomic disparities are discussed, building on the concept of an integrated pantropical observing system. Finally, recommendations for improved observations of tropical basin interactions, through oceanic and atmospheric pathways, are presented, emphasizing the benefits that can be achieved through closer interbasin coordination and international partnerships.

Optimizing activated carbon production from chontaduro seeds via physical activation with steam for ibuprofen removal: A factorial design and multi-attribute utility theory approach - L. Angel; A. Villot; M. Rodriguez Susa; J. Plazas-Tuttle; Y. Andres; C. Gerente (Journal of Water Process Engineering, 2025)

The use of lichens and mosses as sentinel organisms for the determination of the airborne organic pollution in Western Pyrenees: The case of the Irati forest - J. Bustamante; A. Gredilla; O. Liñero; D. Amouroux; D. Elustondo; J.M. Santamaría; A. Rodriguez-Iruretagoiena; S. Fdez-Ortiz de Vallejuelo; G. Arana; A. de Diego (Atmospheric Pollution Research, 2025)

Evaluation of intra- and inter-rater agreement on ultrasound measurements of dairy cow teats by operators with different experience levels - I. Nocera; G. Sala; C. Orsetti; J. M. Rodriguez-Lopez; M. Sgorbini; F. Bonelli (Veterinary Research Communications, 2025)

Advancing Patient Advocacy in Mycology: Cultivating Collaboration in Education, Research, and Policy - Rob Purdie; Rasha Kuran; Ana Alastruey-Izquierdo; Hatim Sati; Juan Luis Rodriguez-Tudela; Martin Hoenigl; John Perfect; Rita Oladele; Thomas J. Walsh; Tom Chiller (Mycopathologia, 2025)
In the healthcare landscape, diseases such as cancer and HIV/AIDS have benefited from the patient's perspective. For fungal diseases, the patient voice remains absent in critical areas such as policy formulation, funding decisions, and research priorities. Patients affected by fungal disease, along with their caregivers and advocacy groups, possess invaluable insights into the challenges and unmet needs they face. By elevating their voices and experiences, policymakers, funding agencies, and researchers can gain a more comprehensive understanding of the multifaceted nature of fungal disease and the urgency of addressing them. This paper addresses the pressing need for a coordinated effort to elevate the patient voice in advocating for improved policies, increased funding, and enhanced research initiatives regarding fungal disease.

Analysis of high-molecular-weight proteins using MALDI-TOF MS and machine learning for the differentiation of clinically relevant Clostridioides difficile ribotypes - Ana Candela; David Rodriguez-Temporal; Mario Blázquez-Sánchez; Manuel J. Arroyo; Mercedes Marín; Luis Alcalá; Germán Bou; Belén Rodríguez-Sánchez; Marina Oviaño (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Promoting Workplace Health, Safety, and Well-Being Among Essential Agricultural Workers Through Vaccine-Preventable Infectious Diseases Training in the Rio Grande Valley - Anabel Rodriguez; David I Douphrate; Ana L Pineda Reyes; Susana Zavala; Andrea V. Cabrera Cruz; Maria D Alegria; Brian Ukaegbu; Annie J Keeney; Brenda Berumen-Flucker; Eva M Shipp; Shannon P Guillot-Wright; Maria E Fernandez-Esquer; et al. (Journal of Agromedicine, 2025)

Modeling MBR fouling: A critical review analysis towards establishing a framework for good modeling practices - V. Sandoval-García; M.V. Ruano; M. Alliet; C. Brepols; J. Comas; J. Harmand; M. Heran; G. Mannina; I. Rodriguez-Roda; I. Smets; A. Robles (Water Research, 2025)

Enhancing road performance and sustainability: A study on recycled porous warm mix asphalt - B. De Pascale; P. Tataranni; I. Indacoechea-Vega; J. Rodriguez-Hernandez; C. Lantieri; A. Bonoli (Science of The Total Environment, 2025)

Photodegradation of acetaminophen on titania fibers prepared by electrospinning - M. García-Rollán; F.J. Garcia-Mateos; J.M. Rosas; J. Rodriguez-Mirasol; T. Cordero; C. Belver; J. Bedia (Chemical Engineering Journal, 2025)

Exploring the effects of cellulose sources on silver reduction and the bacterial removal of nanocellulose-based hydrogel beads - Diego Gomez-Maldonado; Brieanne R. Dickson; Gabriel Au; Michael J. Bortner; Mi Li; Eduardo Espinosa; Alejandro Rodriguez; Brendan Higgins; Maria S. Peresin (Carbohydrate Polymers, 2025)

Age, growth, and reproductive biology of Achilles tang (Acanthurus achilles) around Hawai'i Island, USA - Timothy B. Grabowski; Richard Masse; Dawn McSwain; Annie Larson; Lillian J. Tuttle Raz; Eva Schemmel; Danielle E. Bartz; Nikola Rodriguez (Environmental Biology of Fishes, 2025)

A review of the venom microbiome and its utility in ecology and evolution including future directions for emerging research - Marina E. De León; Eduardo G. P. Fox; Sara Dunaj; Ronald A. Jenner; Carl N. Keiser; Jason Macrander; Samantha A. Nixon; Clarissa J. Nobile; Daniel Petras; Eduardo Rodriguez-Roman; Anthony J. Saviola; Steven A. Trim; et al. (Symbiosis, 2025)

Between and within-city variations of PM2.5 oxidative potential in five cities in Colombia - Néstor Y. Rojas; Dayana M. Agudelo-Castañeda; Daniela Bustos; Krystal J. Godri Pollitt; Dong Gao; Laura A. Rodriguez-Villamizar (Air Quality, Atmosphere & Health, 2025)
Fine particulate matter (PM 2.5 ) has been shown to cause oxidative stress, which has negative health consequences. The oxidative potential (OP) of PM 2.5 , a promising health exposure metric, was assessed in five Colombian cities using the synthetic respiratory tract lining fluid assay that tracks the depletions of glutathione and ascorbate. For this, a set of 91 integrated 2-week ambient PM 2.5 samples were collected using Ultrasonic Personal Aerosol Samplers (UPAS) at background (5), traffic (37), industrial (12) and residential (37) sites. Across all site types, mean PM 2.5 mass concentration was 20.20 ± 9.36 µg m − 3 . The oxidative potential (OP AA for ascorbate and OP GSH for glutathione) varied widely across cities with an average of 2.67 ± 1.27 for AA and 2.93 ± 1.22 % depletion m − 3 for GSH. OP metrics among cities were not correlated with PM 2.5 mass concentrations. Overall, industrial sites showed higher PM 2.5 mass concentrations and OP AA . In contrast, OP GSH was not found to differ among industrial, traffic, or residential sites, but was lower for background sites. Our findings provide substantial evidence of variations in PM 2.5 OP between cities and within the cities. Further research is needed to assess the association between OP and adverse health effects, as well as to attribute the sources that cause such variations.

Capped honey segmentation in honey combs based on deep learning approach - Francisco J. Rodriguez-Lozano; Sergio R. Geninatti; José M. Flores; Francisco J. Quiles-Latorre; Manuel Ortiz-Lopez (Computers and Electronics in Agriculture, 2024)

Fate of fluoroquinolones associated with antimicrobial resistance in circular periurban agriculture - Barbara Prack McCormick; Camila A. Knecht; Ana Clara Sokolowski; Pablo Martín Palladino; Dante Emanuel Rojas; Diego Sebastián Cristos; Hernan J. Rivera; Carola Gonçalves Vila Cova; Javier De Grazia; Hernán A. Rodriguez; Pablo Tittonell; Daniela Centrón; et al. (Science of The Total Environment, 2024)

Legacy persistent organic pollutants among multiple cetacean species in the Northwest Atlantic - Anaïs Remili; Melissa A. McKinney; Ambar Maldonado-Rodriguez; Steven H. Ferguson; Michelle Caputo; Jeremy J. Kiszka (Science of The Total Environment, 2024)

Deployment-invariant probability of detection characterization for aerial LiDAR methane detection - Michael J. Thorpe; Aaron Kreitinger; Dominic T. Altamura; Cameron D. Dudiak; Bradley M. Conrad; David R. Tyner; Matthew R. Johnson; Jason K. Brasseur; Peter A. Roos; William M. Kunkel; Asa Carre-Burritt; Jerry Abate; et al. (Remote Sensing of Environment, 2024)

Optimization of the stowage of fishing discards: Innovations in trawlers in the Gulf of Cadiz (SW Iberian Peninsula) - Daniel J. Coronil-Huertas; Carlos Rodriguez-García; Santiago Pavón-Quintana; Juan M. Vidal-Pérez; Jésica Sarmiento-Carbajal; Remedios Cabrera-Castro (Regional Studies in Marine Science, 2024)

Recycling pulverized concrete as cementitious precursor in alkaline one-part cements, with a waste glass-based sodium silicate - Juliana Rodriguez-Morales; J Ivan Escalante-Garcia (Journal of Cleaner Production, 2024)

Environmental fluoxetine promotes skin cell proliferation and wound healing - Quentin Rodriguez-Barucg; Angel A. Garcia; Belen Garcia-Merino; Tomilayo Akinmola; Temisanren Okotie-Eboh; Thomas Francis; Eugenio Bringas; Inmaculada Ortiz; Mark A. Wade; Adam Dowle; Domino A. Joyce; Matthew J. Hardman; et al. (Environmental Pollution, 2024)

Digital holography interferometry for in-situ thermodynamic analysis during cryopreservation cooling and rewarming - Crysthal Alvarez; Balaji Baskar; Carla Berrrospe-Rodriguez; Soheil Kavian; Ron Sellers; Matthew J. Powell-Palm; Guillermo Aguilar (Cryobiology, 2024)

On the role of glass transition temperature in thermal stress cracking during vitrification - Soheil Kavian; Ronald Sellers; Crysthal Alvarez; Carla Berrrospe-Rodriguez; Matthew J. Powell-Palm (Cryobiology, 2024)

Taxonomy, systematics and conservation of the highly threatened and endemic Mexican genus Tridimeris (Annonaceae) - Andrés Ernesto Ortiz-Rodriguez; Francis J. Nge; Carlos Rodrigues-Vaz; Vincent Soulé; George E. Schatz; María Fernanda Martínez-Velarde; Leopoldo Hurtado-Reveles; Moises Rangel-Olguin; Thomas L. P. Couvreur (Plant Systematics and Evolution, 2024)
Tridimeris is the only genus of Annonaceae endemic to Mexico, and since its description more than 150 years ago, the genus has been largely ignored. Here, based on herbarium specimens and a comprehensive phylogenomic study involving hundreds of nuclear markers, the first taxonomic revision of the genus Tridimeris (Annonaceae, Malmeioideae, subtribe Sapranthinae) is presented. Ten species are recognized, six of which are newly described here. All the species are exclusively found in Mexico's most humid forests, particularly in the montane cloud forest and the tropical rainforest. The genus Tridimeris is morphologically distinguished from other neotropical genera of the Annonaceae by its leaves with pocket domatia present in the axils of the secondary veins, by its dimerous flowers (two sepals and four petals), basally fused sepals with ciliated margins, by a reduced number of carpels per flower (1–5) and by its large and fleshy fruits (monocarps) with numerous seeds. A highly resolved phylogenetic hypothesis provides strong support for the relationships among Tridimeris species, forming two well-supported clades. Consequently, two new sections are proposed, namely Tridimeris sect. Tridimeris and Tridimeris sect. Zoque . A detailed description of the morphology of the genus is presented, including the description of the pollen, domatia and its phylogenetic relationships. Taxonomic treatments of the species include synonyms, geographic and ecological notes, comparisons with similar species and a preliminary assessment of their conservation status. All species of the genus are potentially threatened with extinction and eight are assessed as Critically Endangered, which makes it the most threatened lineage of Mexican trees. This study emphasizes the importance of scientific collections as invaluable sources of data for current taxonomic revisions and conservation. It is a formal invitation to preserve and support the basic scientific research.

Correction: Long-term antigen-specific immune response by an oncolytic adenovirus encoding SP-SA-E7-4-1BBL in HPV-16 cancer model - Alejandra G. Martinez-Perez; Rodolfo Garza-Morales; Maria J. de Loera-Arias; Sheila A. Villa-Cedillo; Aracely Garcia-Garcia; Humberto Rodriguez-Rocha; Orlando E. Flores-Maldonado; Jesus Valdes; Jose J. Perez-Trujillo; Odila Saucedo-Cardenas (Molecular Biology Reports, 2024)

Long-term antigen-specific immune response by an oncolytic adenovirus encoding SP-SA-E7-4-1BBL in HPV-16 cancer model - Alejandra G. Martinez-Perez; Rodolfo Garza-Morales; Maria de J. Loera-Arias; Sheila A. Villa-Cedillo; Aracely Garcia-Garcia; Humberto Rodriguez-Rocha; Orlando E. Flores-Maldonado; Jesus Valdes; Jose J. Perez-Trujillo; Odila Saucedo-Cardenas (Molecular Biology Reports, 2024)

The role of traditional NSAIDs and selective COX-2 inhibitors on COVID-19 outcomes: a real-world data study - Narmeen Mallah; Irene Visos-Varela; Bahi Takkouche; Rosendo Bugarín-González; María Piñeiro-Lamas; Teresa Herdeiro; Maruxa Zapata-Cachafeiro; Almudena Rodríguez-Fernández; Angel Salgado-Barreira; Adolfo Figueiras; Eduardo Carracedo-Martínez; Rosa M. García-Álvarez; et al. (Inflammopharmacology, 2024)

Nucleic acid-loaded poly(beta-aminoester) nanoparticles for cancer nano-immuno therapeutics: the good, the bad, and the future - J. Rodrigo Magaña Rodriguez; Marta Guerra-Rebollo; Salvador Borrós; Cristina Fornaguera (Drug Delivery and Translational Research, 2024)
Immunotherapy has emerged as a promising approach to cancer treatment, offering improved survival rates and enhanced patients’ quality of life. However, realizing the full potential of immunotherapy in clinical practice remains a challenge, as there is still plenty of room for modulating the complexity of the human immune system in favor of an antitumor immunogenicity. Nanotechnology, with its unique properties, holds promise in augmenting the efficacy of cancer immunotherapies in biotherapeutic protection and site- and time-controlled delivery of the immune modulator biologicals. Polymeric nanoparticles are promising biomaterials among different nanocarriers thanks to their robustness, versatility, and cost-efficient design and production. This perspective paper overviews critical concepts in nanometric advanced delivery systems applied to cancer immunotherapy. We focus on a detailed exploration of the current state of the art and trends in using poly(beta-aminoester) (pBAE) polymers for nucleic acid-based antitumor immunotherapies. Through different examples of the use of pBAE polymers reported in the literature, we revise the main advantages these polymers offer and some challenges to overcome. Finally, the paper provides insights and predictions on the path toward the clinical implementation of cancer nano-immunotherapies, highlighting the potential of pBAE polymers for advancements in this field. Graphical abstract

Measuring interspecific admixture in endangered Houston toads (Bufo [= Anaxyrus] houstonensis) at a main recovery site in the Lost Pines ecosystem of Texas, USA - Ferris Eric-Hisham Zughaiyir; Shashwat Sirsi; David Rodriguez; Diana J. McHenry; Michael R. J. Forstner (Conservation Genetics, 2024)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Ants (Lasius niger) deposit more pheromone close to food sources and further from the nest but do not attempt to update erroneous pheromone trails - Tomer J. Czaczkes; Federico-Javier Olivera-Rodriguez; Laure-Anne Poissonnier (Insectes Sociaux, 2024)
Many social insects use pheromone trails to recruit workers to resources. Pheromone trails have some limitations, however. Two major limitations are that they evaporate over time, meaning that more distant locations may be more difficult to recruit precisely to, and that they cannot be removed if laid erroneously, or if they become outdated. Here, we ask whether Lasius niger ants can adaptively modulate pheromone deposition to overcome these limitations. Specifically, we first ask whether ants which have followed a pheromone trail to a wrong (unrewarded) location upregulate pheromone deposition to the correct food location to compete with the erroneous trail. They do not. Then, we examine how food distance and proximity to food influence pheromone deposition. We find that ants deposit up to 22 times more pheromone within 10 cm of a food source compared to when they are about to reach the nest. Moreover, they deposit up to four times more pheromone next to a food source placed 100 cm away from the nest as compared to one placed 20 cm away from the nest. Lasius niger ants thus do not display a mechanism for overcoming outdated or erroneously-laid trails by strengthening correct alternatives in our experiment, but do strongly upregulate recruitment to more distant food sources, which are more difficult to locate and recruit to.

Urban novel ecosystems as affective landscapes - Clair Cooper; Marcus J. Collier; Melissa Pineda-Pinto; Natalia Rodriguez Castañeda; Mairéad O’Donnell; Fiona Nulty (Sustainability Science, 2024)

Predation on Live and Artificial Insect Prey Shows Different Global Latitudinal Patterns - Elena L. Zvereva; Benjamin Adroit; Tommi Andersson; Craig R. A. Barnett; Sofia Branco; Bastien Castagneyrol; Giancarlo Maria Chiarenza; Wesley Dáttilo; Ek del‐Val; Jan Filip; Jory Griffith; Anna L. Hargreaves; et al. (Global Ecology and Biogeography, 2024)
Aim Long‐standing theory predicts that the intensity of biotic interactions increases from high to low latitudes. Studies addressing geographic variation in predation on insect prey have often relied on prey models, which lack many characteristics of live prey. Our goals were to explore global latitudinal patterns of predator attack rates on standardised live insect prey and to compare the patterns in predation on live insects with those on plasticine prey models. Location Global forested areas. Time Period 2021–2023. Major Taxa Arthropods, birds. Methods We measured predation rates in 43 forested locations distributed across five continents from 34.1° S to 69.5° N latitude. At each location, we exposed 20 sets of three bait types, one set per tree. Each set included three live fly larvae (maggots), three live fly puparia and three plasticine models of the puparia. We used glue rings to isolate half of the sets from non‐flying predators. Results Arthropod attack rates on plasticine prey decreased linearly from low to high latitudes, whereas attack rates on maggots had a U shaped distribution, with the lowest predation rates at temperate latitudes and the highest rates at tropical and boreal latitudes. This difference emerged from intensive predator attacks on live maggots, but not on plasticine models, in boreal sites. Site‐specific attack rates of arthropod predators on live and plasticine prey were not correlated. In contrast, bird attack rates on live maggots and plasticine models were positively correlated, but did not show significant latitudinal changes. Main Conclusions Latitudinal patterns in predation differ between major groups of predators and between types of prey. Poleward decreases in both arthropod and combined arthropod and bird predation on plasticine models do not mirror patterns of predation on our live prey, the latter likely reflecting real patterns of predation risk better than do patterns of attack on artificial prey.

Challenges and Security Risks in the Red Sea: Impact of Houthi Attacks on Maritime Traffic - Emilio Rodriguez-Diaz; J. I. Alcaide; R. Garcia-Llave (Journal of Marine Science and Engineering, 2024)
This study examines the significant impact of Houthi insurgent activities on maritime traffic within the strategic Red Sea and Suez Canal routes, essential conduits for global trade. It explores the correlation between regional instability, exemplified by Houthi actions from 19 November 2023 to 5 February 2024, and changes in maritime traffic patterns and operational efficiency. This study seeks to answer a critical question in transport geography: how does regional instability, exemplified by Houthi insurgent activities, affect the maritime traffic patterns and operational efficiency of the Red Sea and Suez Canal? Using descriptive statistics, qualitative analysis, and geospatial methods, this research highlights recent trends in maritime traffic and incidents, revealing spatial and geopolitical challenges in this crucial trade route. The findings indicate a notable decline in maritime activity in the Gulf of Aden and Suez Canal due to security concerns from Houthi attacks, prompting a significant shift to alternative routes, particularly around the Cape of Good Hope. This shift underscores the broader implications of regional instability on global trade and the importance of maintaining an uninterrupted maritime flow. This study also emphasizes the economic ramifications, such as increased operational costs and freight rates due to longer transit times and enhanced security measures. This research concludes with a call for improved maritime security protocols and international cooperation to protect these strategic maritime pathways. It contributes to the discourse on transport geography by quantifying the direct impacts of regional conflicts on maritime logistics and proposing strategies for future resilience, highlighting the interconnected nature of global trade and security and the need for collective action against evolving geopolitical challenges.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Changing How We Talk About DSMES: Creating a Playbook for Programs and Providers - B. Rodriguez; A. Williams; K. Pellechia; J. Bromberg; E. Hanlon (Journal of the Academy of Nutrition and Dietetics, 2024)

A Multicriteria Model for the Assessment of Source Water Contamination by Anthropogenic Activities to Support Land Use Management - Ariane E. Marais; Irène Abi-Zeid; Manuel J. Rodriguez; Roxane Lavoie (Environmental Modeling & Assessment, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

P02-07 Using microfluidic hepatic spheroid cultures for assessing effects of T2 mycotoxin - M. Taroncher; J.-M. de Hoyos-Vega; A.-M. Gonzalez-Suarez; Y. Rodriguez-Carrasco; M.-J. Ruiz; A. Revzin (Toxicology Letters, 2024)

S13-04 Towards interoperable modelling tools for integrative risk assessment – the PARC model network approach - J. Kruisselbrink; W. de Boer; M. van Lenthe; T. van Voorthuijsen; P. Palmont; L. Rodriguez Martin; D. Devriendt; E. Govarts; M. Carsique; A. Crépet; J. van Klaveren; J. Engel (Toxicology Letters, 2024)

Sperm melatonin receptors, seminal plasma melatonin and semen freezability in goats - Alberto J. Cardenas-Padilla; Francisco Jimenez-Trejo; Marco Cerbon; Araceli Chavez-Garcia; Norma B. Cruz-Cano; Martin Martinez-Torres; Alicia Alcantar-Rodriguez; Alfredo Medrano (Theriogenology, 2024)

The effect of fluvial avulsion on the Holocene chronostratigraphic record and the agricultural signal of the world's largest coastal lagoonal system - A.S.P. Avila; S.R. Bottezini; D. Diniz; C. Bueno; L. Perez; G. Martínez de la Escalera; C. Piccini; A. Leonhardt; F. Garcia-Rodriguez; J. Weschenfelder (Science of The Total Environment, 2024)

Mapping a sustainable water future: Private sector opportunities for global water security and resilience - Pamela A. Green; Charles J. Vörösmarty; Dinah A. Koehler; Casey Brown; William Rex; Vanesa Rodriguez Osuna; Zachary Tessler (Global Environmental Change, 2024)

Evaluating the impact of protected areas in lowering extinction risks in a biodiversity hotspot - Manuel Esperon-Rodriguez; Alex Correa-Metrio; Linda J. Beaumont; John B. Baumgartner; Jonathan Lenoir (Biological Conservation, 2024)

A direct geolocation method for aerial imaging surveys of invasive plants - R. Rodriguez; D. M. Jenkins; J. Leary; R. Perroy (International Journal of Environmental Science and Technology, 2024)

A multi-technique approach to unveil the composition and fabrication of a pre-Roman glass masterpiece: a double-faced human-head shape polychrome glass pendant (2nd -1st c. BC) - S. Barroso-Solares; E. Estalayo; J. Aramendia; E. Rodriguez-Gutierrez; C. Sanz-Minguez; A. C. Prieto; J. M. Madariaga; J. Pinto (Archaeological and Anthropological Sciences, 2024)
Pre-Roman glass craftsmanship reached its summit with the development of complex polychrome glass beads, being the Phoenician glass pendants the most exquisite and elaborate example. The uniqueness and complexity of such findings could reveal key information for the understanding of the production and trade of glass pieces at that age. However, these findings have practically never been studied from a physic-chemical perspective. In this work, a remarkable polychrome glass pendant (2nd -1st c. BC) found at the archaeological site of Pintia (Padilla de Duero, Valladolid, Spain) is studied by a multi-analytical non-destructive approach, employing X-ray tomography to understand its fabrication procedure, as well as X-ray fluorescence (XRF) and Raman spectroscopy, both employed in microscopic mode, to determine the composition of each glass employed in its fabrication. The outstanding preservation state and well-defined archaeological context of this glass pendant offered a unique opportunity to expand the understanding of pre-Roman glass pieces, while the combination of the experimental techniques employed provided the first complete and detailed study of a Phoenician glass pendant. The fabrication procedure of the pendant has been identified step-by-step, showing evidence of the use of pre-made pieces for the eyes, as well as hints of its fabrication in a secondary workshop. Moreover, the microchemical analysis of the vividly colored glasses by XRF and Raman spectroscopy revealed a composition compatible with the use of natron as fluxing agent, typical of Phoenician glass, the presence of surface alterations corresponding to carbonatation processes, as well as the nature of the employed chromophores or pigments: Mn, Cu, and Co for the blue, Fe-S for the black, CaSb 2 O 7 and CaSb 2 O 7 + TiO 2 for two diverse white glasses, and a pyrochloric triple oxide (Pb 2 Sb 2 − x Sn x O 7−x/2 ) and lead oxides for the yellow. Remarkably, the use of pyrochloric triple oxides as yellow pigments has scarcely been previously reported at that age. Finally, the identification by Raman spectroscopy of CaSb 2 O 7 and the β-phase of CaSiO 3 , as well as the Raman spectra features of the glass matrix corresponding to the blue glass, indicated maximum firing temperatures below 1100 °C.

“Hg distribution and accumulation in soil and vegetation in areas impacted by artisanal gold mining in the Southern Amazonian region of Madre de Dios, Peru.” - Maria J. Rodriguez-Pascual; Claudia M. Vega; Natasha Andrade; Luis E. Fernández; Miles R. Silman; Alba Torrents (Chemosphere, 2024)

No Effect of Breakfast Consumption Observed for Afternoon Resistance Training Performance in Habitual Breakfast Consumers and Nonconsumers: A Randomized Crossover Trial - Matthew T. Stratton; Madelin R. Siedler; Christian Rodriguez; Patrick S. Harty; Jake R. Boykin; Dale S. Keith; Jacob J. Green; Sarah J. White; Ethan Tinoco; Brielle DeHaven; Trisha A. VanDusseldorp; Grant M. Tinsley (Journal of the Academy of Nutrition and Dietetics, 2024)

Optimizing sampling location for water quality degradation monitoring in distribution systems: Assessing global representativeness and potential health risk - Andres Ardila; Manuel J. Rodriguez; Genevieve Pelletier (Journal of Environmental Management, 2024)

Optimization of LiF dissolution with Al2(SO4)3 and its application to lithium extraction by fluorination of α-spodumene - Gustavo D. Rosales; Alexander C. Resentera; Gretel J. Fino; Eliana G. Pinna; Mario H. Rodriguez (Hydrometallurgy, 2024)

Impact of a water restriction on the summer climatic benefits of trees inside an outdoor street canyon scale model - J. Thierry; S. Herpin; R. Levi; D. Canonne; S. Demotes-Mainard; P. Cannavo; D. Lemesle; L. Brialix; F. Rodriguez; P.E. Bournet (Building and Environment, 2024)

Outpatient glucocorticoid use and COVID-19 outcomes: a population-based study - Almudena Rodríguez-Fernández; Irene Visos-Varela; Maruxa Zapata-Cachafeiro; Samuel Pintos-Rodríguez; Rosa M. García-Álvarez; Teresa M. Herdeiro; María Piñeiro-Lamas; Adolfo Figueiras; Ángel Salgado-Barreira; Rosendo Bugarín-González; Eduardo Carracedo-Martínez; Rosa M García-Álvarez; et al. (Inflammopharmacology, 2024)
Introduction Owing to controversy information surrounds effect of glucocorticoids on the evolution of COVID-19, we evaluate the effects of outpatient glucocorticoid use on the severity and progression of COVID-19 and risk of infection and analyse the effect of window of exposure and dose. Methods We conducted a population-based case − control study, involving 4 substudies: (i) Hospitalisation; (ii) Mortality, using subjects hospitalised with a PCR + as cases and subjects without a PCR + as controls; (iii) Progression, including subjects with a PCR + (hospitalised versus non-hospitalised); and (iv) Susceptibility, with all subjects with a PCR + and subjects without a PCR + . Adjusted odds ratios (ORa) and their 95% confidence intervals (95% CI) were calculated. Results The outpatient glucocorticoid use was associated with an increased risk of hospitalisation (aOR 1.79; 95% CI 1.56–2.05), mortality (aOR 2.30; 95% CI 1.68–3.15), progression (aOR 1.69; 95% CI 1.43–2.00) and susceptibility (aOR 1.29, 95% CI 1.19–1.41). Furthermore, the effects was observed to be greater at higher doses and the closer that drug use approached the outcome date, with an almost fourfold increase in mortality among users in the previous month (aOR 3.85; 95% CI 2.63–5.62). Conclusions According to the results of this real-world data study, outpatient glucocorticoid use should be considered in making decisions about intrahospital treatment.

Ataxia-telangiectasia in Latin America: clinical features, immunodeficiency, and mortality in a multicenter study - Renan A. Pereira; Ellen O. Dantas; Jessica Loekmanwidjaja; Juliana T. L. Mazzucchelli; Carolina S. Aranda; Maria E. G. Serrano; Elisabeth A. De La Cruz Córdoba; Liliana Bezrodnik; Ileana Moreira; Janaira F. S. Ferreira; Vera M. Dantas; Valéria S. F. Sales; et al. (Immunologic Research, 2024)

Environmental performance analysis of coated austenitic steels for their use in supercritical steam turbines - M. Baranda; C. Mayo; R. Diaz; R. Rodriguez; F. J. Pérez (Clean Technologies and Environmental Policy, 2024)

Screening mammography frequency following dense breast notification among a predominantly Hispanic/Latina screening cohort - Erica J. Lee Argov; Carmen B. Rodriguez; Mariangela Agovino; Karen M. Schmitt; Elise Desperito; Anita G. Karr; Ying Wei; Mary Beth Terry; Parisa Tehranifar (Cancer Causes & Control, 2024)

The history and processes of Titan's equator from the geospatial-topology of spectrally distinct units - N. Kutsop; A.G. Hayes; C. Sotin; J.I. Lunine; S.P.D. Birch; P.M. Corlies; K. Lawrence; S. Le Mouélic; J. Madden; M.J. Malaska; S. Rodriguez; J.M. Soderblom; et al. (Icarus, 2024)

Sunflower yield gaps and their causes in Argentina - Ignacio M. Rodriguez; Antonio J. Hall; Juan P. Monzon; Jorge L. Mercau; Sofia Gayo; Monica Lopez Pereira; Anibal Cerrudo; Hernán A. Urcola; Carolina B. Troglia; Sebastián Zuil; María Paolini; Gustavo Martini; et al. (Field Crops Research, 2024)

Integrated organismal responses induced by projected levels of CO 2 and temperature exposures in the early life stages of lake sturgeon - Luke D. Belding; Matt J. Thorstensen; Alex R. Quijada‐Rodriguez; William S. Bugg; Gwangseok R. Yoon; Alison R. Loeppky; Garrett J. P. Allen; Alexandra N. Schoen; Madison L. Earhart; Catherine Brandt; Jennifer L. Ali; Dirk Weihrauch; et al. (Molecular Ecology, 2024)
Atmospheric CO 2 and temperature are rising concurrently, and may have profound impacts on the transcriptional, physiological and behavioural responses of aquatic organisms. Further, spring snowmelt may cause transient increases of p CO 2 in many freshwater systems. We examined the behavioural, physiological and transcriptomic responses of an ancient fish, the lake sturgeon ( Acipenser fulvescens ) to projected levels of warming and p CO 2 during its most vulnerable period of life, the first year. Specifically, larval fish were raised in either low (16°C) or high (22°C) temperature, and/or low (1000 μatm) or high (2500 μatm) p CO 2 in a crossed experimental design over approximately 8 months. Following overwintering, lake sturgeon were exposed to a transient increase in p CO 2 of 10,000 μatm, simulating a spring melt based on data in freshwater systems. Transcriptional analyses revealed potential connections to otolith formation and reduced growth in fish exposed to high p CO 2 and temperature in combination. Network analyses of differential gene expression revealed different biological processes among the different treatments on the edges of transcriptional networks. Na + /K + ‐ATPase activity increased in fish not exposed to elevated p CO 2 during development, and mRNA abundance of the β subunit was most strongly predictive of enzyme activity. Behavioural assays revealed a decrease in total activity following an acute CO 2 exposure. These results demonstrate compensatory and compounding mechanisms of p CO 2 and warming dependent on developmental conditions in lake sturgeon. Conserved elements of the cellular stress response across all organisms provide key information for how other freshwater organisms may respond to future climate change.

Multinational evaluation of genetic diversity indicators for the Kunming‐Montreal Global Biodiversity Framework - Alicia Mastretta‐Yanes; Jessica M. da Silva; Catherine E. Grueber; Luis Castillo‐Reina; Viktoria Köppä; Brenna R. Forester; W. Chris Funk; Myriam Heuertz; Fumiko Ishihama; Rebecca Jordan; Joachim Mergeay; Ivan Paz‐Vinas; et al. (Ecology Letters, 2024)
Under the recently adopted Kunming‐Montreal Global Biodiversity Framework, 196 Parties committed to reporting the status of genetic diversity for all species. To facilitate reporting, three genetic diversity indicators were developed, two of which focus on processes contributing to genetic diversity conservation: maintaining genetically distinct populations and ensuring populations are large enough to maintain genetic diversity. The major advantage of these indicators is that they can be estimated with or without DNA‐based data. However, demonstrating their feasibility requires addressing the methodological challenges of using data gathered from diverse sources, across diverse taxonomic groups, and for countries of varying socio‐economic status and biodiversity levels. Here, we assess the genetic indicators for 919 taxa, representing 5271 populations across nine countries, including megadiverse countries and developing economies. Eighty‐three percent of the taxa assessed had data available to calculate at least one indicator. Our results show that although the majority of species maintain most populations, 58% of species have populations too small to maintain genetic diversity. Moreover, genetic indicator values suggest that IUCN Red List status and other initiatives fail to assess genetic status, highlighting the critical importance of genetic indicators.

Spatially heterogeneous discharge of glacial meltwater to drainages surrounding the ablating Coropuna ice cap, Peruvian Andes - Elizabeth J. Olson; Lisa R. Welp; Marty D. Frisbee; Sebastián A. Zúñiga Medina; Odiney Alvarez-Campos; Wendy R. Roque Quispe; Carol I. Salazar Mamani; Midhuar R. Arenas Carrión; José Diaz Rodriguez; Juan Manuel Jara Gonzalez; Alexander Ccanccapa-Cartagena; Chad T. Jafvert (Hydrological Sciences Journal, 2024)

Total CO2 budget estimate and degassing dynamics for an active stratovolcano: Turrialba Volcano, Costa Rica - Kate M. Nelson; Christofer Jiménez; Chad D. Deering; Maarten J. de Moor; Joshua M. Blackstock; Stephen P. Broccardo; Florian M. Schwandner; Joshua B. Fisher; Snehamoy Chatterjee; Guillermo Alvarado Induni; Alejandro Rodriguez; Doménicca Guillén Pachacama; et al. (Journal of Volcanology and Geothermal Research, 2024)

Ensemble machine learning using hydrometeorological information to improve modeling of quality parameter of raw water supplying treatment plants - Christian Ortiz-Lopez; Christian Bouchard; Manuel J. Rodriguez (Journal of Environmental Management, 2024)

Predicting milk-derived hydrogel-forming peptides with TANGO - Muhammed Aslam Khan; Yacine Hemar; Ka-Wing Cheng; Florian J. Stadler; Luis M. De Leon-Rodriguez (International Dairy Journal, 2024)

Carotid-femoral pulse wave velocity score, an estimator of cognitive performance in the elderly: results from the Toledo Study for Healthy Aging - Fabio A. Quiñónez Bareiro; José A. Carnicero; Ana Alfaro Acha; Cristina Rosado Artalejo; María C. Grau Jimenez; Leocadio Rodriguez Mañas; Francisco J. García García (GeroScience, 2024)

Transforming construction and demolition waste concrete as a precursor in sustainable cementitious materials: An innovative recycling approach - Juliana Rodriguez-Morales; Oswaldo Burciaga-Diaz; Lauren Y. Gomez-Zamorano; J. Ivan Escalante-Garcia (Resources, Conservation and Recycling, 2024)

Residential surrounding greenness and the incidence of childhood asthma: Findings from a population-based cohort in Ontario, Canada - Razieh Mansouri; Eric Lavigne; Robert Talarico; Audrey Smargiassi; Laura A. Rodriguez-Villamizar; Paul J. Villeneuve (Environmental Research, 2024)

Engineered separator of cellulose/ionic-liquid for the fabrication of a novel device with H-type architecture and dual function: Supercapacitor and NO2 gas sensor - L. Ojeda; A. Molina; K.P. Padmasree; A.I. Mtz-Enriquez; A. Zakhidov; V. Rodriguez-Gonzalez; J. Oliva (Chemical Engineering Journal, 2024)

Increases in regional brain volume across two native South American male populations - Nikhil N. Chaudhari; Phoebe E. Imms; Nahian F. Chowdhury; Margaret Gatz; Benjamin C. Trumble; Wendy J. Mack; E. Meng Law; M. Linda Sutherland; James D. Sutherland; Christopher J. Rowan; L. Samuel Wann; Adel H. Allam; et al. (GeroScience, 2024)
Industrialized environments, despite benefits such as higher levels of formal education and lower rates of infections, can also have pernicious impacts upon brain atrophy. Partly for this reason, comparing age-related brain volume trajectories between industrialized and non-industrialized populations can help to suggest lifestyle correlates of brain health. The Tsimane, indigenous to the Bolivian Amazon, derive their subsistence from foraging and horticulture and are physically active. The Moseten, a mixed-ethnicity farming population, are physically active but less than the Tsimane. Within both populations ( N = 1024; age range = 46–83), we calculated regional brain volumes from computed tomography and compared their cross-sectional trends with age to those of UK Biobank (UKBB) participants ( N = 19,973; same age range). Surprisingly among Tsimane and Moseten (T/M) males, some parietal and occipital structures mediating visuospatial abilities exhibit small but significant increases in regional volume with age. UKBB males exhibit a steeper negative trend of regional volume with age in frontal and temporal structures compared to T/M males. However, T/M females exhibit significantly steeper rates of brain volume decrease with age compared to UKBB females, particularly for some cerebro-cortical structures (e.g., left subparietal cortex). Across the three populations, observed trends exhibit no interhemispheric asymmetry. In conclusion, the age-related rate of regional brain volume change may differ by lifestyle and sex. The lack of brain volume reduction with age is not known to exist in other human population, highlighting the putative role of lifestyle in constraining regional brain atrophy and promoting elements of non-industrialized lifestyle like higher physical activity.

How microbial communities shape peatland carbon dynamics: New insights and implications - Etienne Richy; Pedro J. Cabello-Yeves; Felipe Hernandes-Coutinho; Francisco Rodriguez-Valera; Iván González-Álvarez; Laure Gandois; François Rigal; Béatrice Lauga (Soil Biology and Biochemistry, 2024)

Pathological and transcript analysis of protection induced by MTBVAC and BCG against Mycobacterium tuberculosis infection in rhesus macaques - F.J. Salguero; J. Medley; L. Hunter; I. Ruedas-Torres; A. Bird; E. Puentes; E. Rodriguez; S.J. Waddell; C. Martin; S. Sharpe (Journal of Comparative Pathology, 2024)

MaPPeRTrac: A Massively Parallel, Portable, and Reproducible Tractography Pipeline - Lanya T. Cai; Joseph Moon; Paul B. Camacho; Aaron T. Anderson; Won Jong Chwa; Bradley P. Sutton; Amy J. Markowitz; Eva M. Palacios; Alexis Rodriguez; Geoffrey T. Manley; Shivsundaram Shankar; Peer-Timo Bremer; et al. (Neuroinformatics, 2024)

Considerations for the development of guidance on dose level selection for developmental and reproductive toxicity studies - R.W. Lewis; A.K. Andrus; J. Arroyo; S. Brescia; P.A. Botham; M. Corvaro; G.P. Daston; T. Hofmann; C. Rodriguez; F. Sewell; B. van Ravenzwaay; K. Wiench; et al. (Regulatory Toxicology and Pharmacology, 2024)

Holocene organic matter composition in relation to relative sea level stands and associated morphometric changes of a lagoonal system - V. Carvalho; L. Gonzalez; C. Bueno; C. Segura; S.R. Bottezini; A. Leonhardt; D. Diniz; P. Dentzien-Dias; L. Perez; H. Evangelista; M.V. Licínio; H. Inda; et al. (Marine Geology, 2024)

A trajectory of Zostera marina (eelgrass) ecosystem recovery: pre- and post-Hurricane Sandy degradation in Barnegat Bay, New Jersey - Edgar A. Medina; Abdullah J. Alhaddad; Adi Ackerman; Julia Kopell; Nicole Rodriguez Ortiz; Mya-Hali T. Theodore; Paul A.X. Bologna; James J. Campanella (Aquatic Botany, 2024)

A solar evaporator fabricated from corncob waste for the desalination of seawater and removal of oil/herbicides from contaminated water - E. Valadez-Renteria; J. Oliva; A.I. Oliva; M.A. Ruiz-Gomez; A. Encinas; V. Rodriguez-Gonzalez (Chemosphere, 2024)

Welfare of rainbow trout at slaughter: Integrating behavioural, physiological, proteomic and quality indicators and testing a novel fast-chill stunning method - João L. Saraiva; Filippo Faccenda; María J. Cabrera-Álvarez; Michele Povinelli; Peter C. Hubbard; Marco Cerqueira; Ana Paula Farinha; Giulia Secci; Maria Vittoria Tignani; Lina F. Pulido Rodriguez; Giuliana Parisi (Aquaculture, 2024)

Practice Is Evolving—a Briefing of the Revised 2024 Scopes and Standards of Practice - Susan Adams; Patricia Davidson; Erica Howes; Kimi McAdam; Christopher M. Messenger; Christopher Mills; Egondu M. Onuoha; Anna Marie Rodriguez; Christina Rollins; Dana Buelsing Sowards; Karen Hui; Carol J. Gilmore; et al. (Journal of the Academy of Nutrition and Dietetics, 2024)

Neighborhood greenness and participation in specific types of recreational physical activities in the Sister Study - Laura A. Rodriguez-Villamizar; Kim Hellemans; Michael Jerrett; Jason Su; Dale P. Sandler; Paul J. Villeneuve (Environmental Research, 2024)

Effect of biosolid compost amended on Pb availability in soils cultivated with lettuce - M. E. Gómez; G. V. Ferreyroa; M. J. Salazar; M. L. Pignata; J. H. Rodriguez (International Journal of Environmental Science and Technology, 2024)

Exploring the potential of microbial fuel cell-assisted biodegradation of nonylphenol - E. De la Peña; C. Castillo-Zacarías; R. G. Araújo; M. Rostro-Alanis; R. Parra-Saldivar; J. Rodriguez-Rodriguez (International Journal of Environmental Science and Technology, 2024)

Nativity differences in socioeconomic barriers and healthcare delays among cancer survivors in the All of Us cohort - Angel Arizpe; Stephanie Navarro; Carol Y. Ochoa-Dominguez; Claudia Rodriguez; Sue E. Kim; Albert J. Farias (Cancer Causes & Control, 2024)
Purpose We aimed to assess whether nativity differences in socioeconomic (SES) barriers and health literacy were associated with healthcare delays among US cancer survivors. Methods “All of Us” survey data were analyzed among adult participants ever diagnosed with cancer. A binary measure of healthcare delay (1+ delays versus no delays) was created. Health literacy was assessed using the Brief Health Literacy Screen. A composite measure of SES barriers (education, employment, housing, income, and insurance statuses) was created as 0, 1, 2, or 3+. Multivariable logistic regression model tested the associations of (1) SES barriers and health literacy with healthcare delays, and (2) whether nativity modified this relationship. Results Median participant age was 64 years ( n = 10,020), with 8% foreign-born and 18% ethnic minorities. Compared to survivors with no SES barriers, those with 3+ had higher likelihood of experiencing healthcare delays (OR 2.18, 95% CI 1.84, 2.58). For every additional barrier, the odds of healthcare delays were greater among foreign-born (1.72, 1.43, 2.08) than US-born (1.27, 1.21, 1.34). For every 1-unit increase in health literacy among US-born, the odds of healthcare delay decreased by 9% (0.91, 0.89, 0.94). Conclusion We found that SES barriers to healthcare delays have a greater impact among foreign-born than US-born cancer survivors. Higher health literacy may mitigate healthcare delays among US cancer survivors. Healthcare providers, systems and policymakers should assess and address social determinants of health and promote health literacy as a way to minimize healthcare delays among both foreign- and US-born cancer survivors.

Patterns of Polydrug Use Classes Among a Subset of Latino Male Seasonal Workers in South Florida: A Latent Class Analysis - Ariana L. Johnson; Kyle J. Self; Cho-Hee Shrader; Edda Rodriguez; Mariano Kanamori (Journal of Agromedicine, 2024)

Flathead grey mullet (Mugil cephalus) juveniles exhibit consistent proactive and reactive stress coping styles - Joel Fitzgerald Linares-Cordova; Sonia Rey-Planellas; Anaïs Boglino; Jessica A. Jimenez-Rivera; Neil J. Duncan; Gustavo Alejandro Rodriguez-Montes de Oca; Zohar Ibarra-Zatarain (Aquaculture, 2024)

Embryo-maternal communication mediated by extracellular vesicles in the early stages of embryonic development is modified by in vitro conditions - C. Aguilera; Y.S. Wong; M.A. Gutierrez-Reinoso; A.E. Velásquez; B. Melo-Báez; J. Cabezas; D. Caamaño; F. Navarrete; F.O. Castro; L.l. Rodriguez-Alvarez (Theriogenology, 2024)

Understanding the differences between car and motorcycle ownership. The case of Bogotá, Colombia - Alvaro Rodriguez-Valencia; J. de D. Ortúzar; Santiago Mesa-Garcia (Journal of Transport Geography, 2024)

A user's guide to the bioinformatic analysis of shotgun metagenomic sequence data for bacterial pathogen detection - Blake G. Lindner; Kenji Gerhardt; Dorian J. Feistel; Luis M. Rodriguez-R; Janet K. Hatt; Konstantinos T. Konstantinidis (International Journal of Food Microbiology, 2024)

Dietary intakes of dioxins and polychlorobiphenyls (PCBs) and mortality: EPIC cohort study in 9 European countries - Thibault Fiolet; Geneviève Nicolas; Corinne Casagrande; Zsuzsanna Horvath; Pauline Frenoy; Elisabete Weiderpass; Marc J. Gunter; Jonas Manjer; Emily Sonestedt; Domenico Palli; Vittorio Simeon; Rosario Tumino; et al. (International Journal of Hygiene and Environmental Health, 2024)

Intra-urban variability of long-term exposure to PM2.5 and NO2 in five cities in Colombia - Laura A. Rodriguez-Villamizar; Yurley Rojas; Sara Grisales; Sonia C. Mangones; Jhon J. Cáceres; Dayana M. Agudelo-Castañeda; Víctor Herrera; Diana Marín; Juan G. Piñeros Jiménez; Luis C. Belalcázar-Ceron; Oscar Alberto Rojas-Sánchez; Jonathan Ochoa Villegas; et al. (Environmental Science and Pollution Research, 2023)
Rapidly urbanizing cities in Latin America experience high levels of air pollution which are known risk factors for population health. However, the estimates of long-term exposure to air pollution are scarce in the region. We developed intraurban land use regression (LUR) models to map long-term exposure to fine particulate matter (PM 2.5 ) and nitrogen dioxide (NO 2 ) in the five largest cities in Colombia. We conducted air pollution measurement campaigns using gravimetric PM 2.5 and passive NO 2 sensors for 2 weeks during both the dry and rainy seasons in 2021 in the cities of Barranquilla, Bucaramanga, Bogotá, Cali, and Medellín, and combined these data with geospatial and meteorological variables. Annual models were developed using multivariable spatial regression models. The city annual PM 2.5 mean concentrations measured ranged between 12.32 and 15.99 µg/m 3 while NO 2 concentrations ranged between 24.92 and 49.15 µg/m 3 . The PM 2.5 annual models explained 82% of the variance ( R 2 ) in Medellín, 77% in Bucaramanga, 73% in Barranquilla, 70% in Cali, and 44% in Bogotá. The NO 2 models explained 65% of the variance in Bucaramanga, 57% in Medellín, 44% in Cali, 40% in Bogotá, and 30% in Barranquilla. Most of the predictor variables included in the models were a combination of specific land use characteristics and roadway variables. Cross-validation suggests that PM 2.5 outperformed NO 2 models. The developed models can be used as exposure estimate in epidemiological studies, as input in hybrid models to improve personal exposure assessment, and for policy evaluation.

Correction to: Role of Toll-like receptor 2 and 4 signaling pathways on the inflammatory response to resistance training in elderly subjects - Paula Rodriguez-Miguelez; Rodrigo Fernandez-Gonzalo; Mar Almar; Yubisay Mejías; Ana Rivas; José A. de Paz; María J. Cuevas; Javier González-Gallego (GeroScience, 2023)

Current deformation along the northern Caribbean plate boundary from GNSS measurements in Cuba - E. Calais; O.F. Gonzalez; E.D. Arango-Arias; B. Moreno; R. Palau; M. Cutie; E. Diez; C. Montenegro; E. Rodriguez Roche; J. Garcia; E. Castellanos; S. Symithe (Tectonophysics, 2023)

Nanoscale CuO charge and morphology control Fusarium suppression and nutrient biofortification in field-grown tomato and watermelon - Chaoyi Deng; Connor R. Protter; Yi Wang; Jaya Borgatta; Jingyi Zhou; Peiying Wang; Vinod Goyal; Hannah J. Brown; Kevin Rodriguez-Otero; Christian O. Dimkpa; Rigoberto Hernandez; Robert J. Hamers; et al. (Science of The Total Environment, 2023)

Monitoring long-term vegetation condition dynamics in persistent semi-arid wetland communities using time series of Landsat data - Li Wen; Tanya J. Mason; Shawn Ryan; Joanne E. Ling; Neil Saintilan; Jose Rodriguez (Science of The Total Environment, 2023)

Unraveling the in vivo fate of inhaled micro- and nanoplastics with PET imaging - Samantha Delaney; Cindy Rodriguez; Samantha M. Sarrett; Eric J. Dayts; Brian M. Zeglis; Outi Keinänen (Science of The Total Environment, 2023)

Modulation of the lipolysis and subsequent antibacterial activity of the fat from black soldier fly (Hermetia illucens) by the combined selection of slaughtering, drying and defatting methods of the larvae - Raúl Hurtado-Ribeira; Jose Manuel Silvan; Tiziana Fornari; Luis Vázquez; Adolfo J. Martinez-Rodriguez; Diana Martin (Innovative Food Science & Emerging Technologies, 2023)

Digital holography: a tool to measure temperature and characterize phase changes during vitrification and rewarming - Crysthal Alvarez; Balaji Baskar; Aditya Pandya; Soheil Kavian; Carla Berrrospe-Rodriguez; Matthew J. Powell-Palm; Guillermo Aguilar (Cryobiology, 2023)

Metformin and Trehalose-Modulated Autophagy Exerts a Neurotherapeutic Effect on Parkinsonʼs Disease - Yareth Gopar-Cuevas; Odila Saucedo-Cardenas; Maria J. Loera-Arias; Roberto Montes-de-Oca-Luna; Humberto Rodriguez-Rocha; Aracely Garcia-Garcia (Molecular Neurobiology, 2023)

Geological context and human exposures to element mixtures in mining and agricultural settings in Colombia - Oscar Florez-Vargas; Eugenio Vilanova; Carolina Alcaide; José A. Henao; Carlos A. Villarreal-Jaimes; Olga M. Medina-Pérez; Laura A. Rodriguez-Villamizar; Alvaro J. Idrovo; Luz H. Sánchez-Rodríguez (Science of The Total Environment, 2023)

Assessment of plastic waste generated by the aquaculture industry: The case study of pearl farming in French Polynesia - M. Crusot; J.-C. Gaertner; T. Rodriguez; C. Lo; N. Gaertner-Mazouni (Journal of Cleaner Production, 2023)

Improvement of genetic health and diversity of Zostera marina (eelgrass) in Barnegat Bay, New Jersey ten years after Hurricane Sandy: Support for the “storm stimulus” hypothesis - James J. Campanella; Paul A.X. Bologna; Abdullah J. Alhaddad; Edgar A. Medina; Adi Ackerman; Julia Kopell; Nicole Rodriguez Ortiz; Mya-Hali T. Theodore (Aquatic Botany, 2023)

Vertical niche occupation and potential metabolic interplay of microbial consortia in a deeply stratified meromictic model lake - Pedro J. Cabello‐Yeves; Antonio Picazo; Juan J. Roda‐Garcia; Francisco Rodriguez‐Valera; Antonio Camacho (Limnology and Oceanography, 2023)
The microbial ecology of meromictic lakes assessed with “omics” is still poorly studied compared to other aquatic systems. Here, a combination of metagenomics, high resolution sampling and detailed physical–chemical data gathering allowed to study the planktonic prokaryotic assemblages and metabolic capabilities in the crenogenic meromictic Lake El Tobar (Spain), a model lake for such purposes. This system presents a specific stratification comprising a freshwater layer and a halocline linked to the oxycline, driving to the euxinic hypersaline waters of the deep monimolimnion. The different strata showed a highly diverse and vertically distributed microbiome with their metabolic capacities fitting/influencing the physical–chemical environment. Overall, up to 338 novel genomes were found from metagenome assembled genomes. Picocyanobacteria and methanotrophs were abundant in the upper part of the oxycline. Anoxygenic phototrophs ( Chlorobium , Thiohalocapsa , Chromatiaceae, Rhodospirillum, and Rhodobacteraceae spp.) dominated the 12.5–14 m anoxic waters with dim light availability. Sulfate reducers (Desulfobacterota and Firmicutes) inhabited low redox horizons from 13.5 to the bottom (18 m). The potential microbial synergistic performance increases toward the monimolimnion. Among these, a microbial assemblage mostly composed of Spirochaetota, Cloacimonadota, Omitrophota, Firmicutes, Marinisomatota, Nanoarchaeota, and Patescibacteria in hypersaline waters of 14–18 m (conductivities of 118–213 mS cm −1 ), is potentially capable of performing mixed‐acid fermentations, even including hydrogen and butanol biosynthesis of biotechnological interest. This metagenomics study shows how microbial lifestyles may be determinant in the interplay of environmental gradients, and exemplifies the potential interactions between the microbial guilds thereby.

Integrity of the nucleus basalis of meynert and self-reported cognitive dysfunction during wearing-off periods in parkinson’s disease - Daniel H. Lench; Travis H. Turner; Emma Wetmore; Federico J. Rodriguez-Porcel; Gonzalo J. Revuelta (Brain Imaging and Behavior, 2023)

How cognitive performance changes according to the ankle-brachial index score in an elderly cohort? Results from the Toledo Study of Healthy Ageing - Fabio A. Quiñónez Bareiro; José A. Carnicero; Ana Alfaro Acha; Cristina Rosado Artalejo; María C. Grau Jimenez; Leocadio Rodriguez Mañas; Francisco J. García García (GeroScience, 2023)

Human milk: From complex tailored nutrition to bioactive impact on child cognition and behavior - Carolina de Weerth; Anna-Katariina Aatsinki; Meghan B. Azad; Frank F. Bartol; Lars Bode; Maria Carmen Collado; Amanda M. Dettmer; Catherine J. Field; Meagan Guilfoyle; Katie Hinde; Aniko Korosi; Hellen Lustermans; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Using ecosystem models to inform ecosystem-based fisheries management in Europe: a review of the policy landscape and related stakeholder needs - Ana Rodriguez-Perez; Athanassios C. Tsikliras; Gideon Gal; Jeroen Steenbeek; Jannike Falk-Andersson; Johanna J. Heymans (Frontiers in Marine Science, 2023)
The need to implement an ecosystem-based fisheries management (EBFM) is enshrined in numerous regulations and strategies, at both global and European level. In practice, it is challenging to implement EBFM because it requires a complex evaluation of interlinked management effects and environmental and climate forcing on multi-species interactions, habitat status and human activities. Ecosystem models are one of the most critical research tools to inform EBFM, because they can integrate a wide variety of data, examine multiple and complex ecosystem interactions, and can make forecasts based on specific management scenarios. However, despite clear progress in marine ecosystem modelling, many models do not address policy goals and targets, which hinders uptake in policy. In this paper, we review the global and European policies and implementing bodies which directly or indirectly have a repercussion on the implementation of EBFM. Moreover, we highlight specific stakeholder needs related to the implementation of EBFM in European waters, which ecosystem models could help address. We review the policy commitments that drive these needs and the concerns raised by stakeholders during a survey and dedicated workshop. Key topics of concern were effects of climate change; bycatch; protected areas/fisheries restricted areas; and reducing the impacts of trawling. Stakeholders also provided specific questions related to these topics which ecosystem models could help address. Scenario and data results visualizations, as well as specific barriers in using the results of ecosystem models for decision-making are also discussed. A close involvement of stakeholders in scenario development and in designing graphical outputs is important, and can help overcome some of the main barriers that can hinder uptake of models and scenarios, including a lack of understanding of the benefits and limits of ecosystem models; insufficient involvement and interaction with stakeholders; and inadequate characterization of uncertainties.

Financial and Operational Feasibility Pilot of a Medically Tailored Meal Program - W. Phillips; S. Geneva; M. Yepes-Rios; M. Alejandro-Rodriguez; J. Evans; R. Miles (Journal of the Academy of Nutrition and Dietetics, 2023)

Identifying pollution dynamics using discrete Fourier transform: From an urban-rural river, Central Mexico - P.F. Rodriguez-Espinosa; Jorge Fonseca-Campos; K.M. Ochoa-Guerrero; A.G. Hernandez-Ramirez; J. Tabla-Hernandez; E. Martínez-Tavera; E. Lopez-Martínez; M.P. Jonathan (Journal of Environmental Management, 2023)

Matrix changes driven by cultivar diversity, inulin addition and drying techniques - shaping the antioxidant, antimicrobial and anti-inflammatory properties of blueberry powders - Jessica Brzezowska; Adolfo J. Martinez-Rodriguez; Jose Manuel Silvan; Grzegorz P. Łysiak; Aneta Wojdyło; Krzysztof Lech; Anna Michalska-Ciechanowska (Innovative Food Science & Emerging Technologies, 2023)

Willing or complying? The delicate interplay between voluntary and mandatory interventions to promote farmers' environmental behavior - Jesus Barreiro-Hurle; Francois J. Dessart; Jens Rommel; Mikołaj Czajkowski; Maria Espinosa-Goded; Macario Rodriguez-Entrena; Fabian Thomas; Katarzyna Zagorska (Food Policy, 2023)

Boron isotopes in Central American volcanics indicate a key role for the subducting oceanic crust - Stephen J. Turner; Mattison H. Barickman; Julian Rodriguez; David A. Fike; Clive M. Jones; Kun Wang; Ivan P. Savov; Samuele Agostini; Michael J. Krawczynski; Rita Parai (Earth and Planetary Science Letters, 2023)

Fruit juice and childhood obesity: a review of epidemiologic studies - Junichi R. Sakaki; Nancy R. Rodriguez; Maria-Luz Fernandez; Michael J. Puglisi; Ming-Hui Chen; Ock K. Chun (Critical Reviews in Food Science and Nutrition, 2023)

LP-51: Determining of a broad range of organic chemicals in seminal plasma through an innovative LC-HRMS-based methodology suitable for target and non-target analysis - E. Sánchez-Resino; M. Marquès; D. Gutiérrez-Martín; E. Restrepo-Montes; M. Á. Martínez-Rodriguez; A. Salas-Huetos; N. Babio; J. Salas-Salvadó; J.L. Domingo; R. Gil-Solsona; P. Gago-Ferrero (Toxicology Letters, 2023)

P21-14: Neurodevelopmental toxicity of T-2 mycotoxin in human-based primary and induced pluripotent stem cell-derived neural progenitor cells in 3D and 2D - M. Taroncher Ruiz; J. Kapr; K. Bartmann; J. Tigges; Y. Rodriguez-Carrasco; M.J. Ruiz; E. Fritsche (Toxicology Letters, 2023)

Fine-tuning the CROPGRO-Sunflower model and its application to the quantification of crop responses to environmental and management variables - Ignacio M. Rodriguez; Jorge L. Mercau; Pablo A. Cipriotti; Antonio J. Hall; Juan P. Monzon (Field Crops Research, 2023)

Effect of Supranutritional Dosage Selenium in Neonatal Goat Kids on Productive Performance, Physicochemical Profiles in Meat, Selenium Levels in Tissues, and Histopathological Findings - Oscar Ortiz-Morales; J. Efrén Ramírez-Bribiesca; Jorge Hernández-Bautista; David Hernández-Sánchez; José Ricardo Bárcena-Gama; Elein Hernández-Trujillo; Victor M. Díaz-Sánchez; German Garrido-Fariña; José C. López-Ojeda; Martha Hernández-Rodriguez (Biological Trace Element Research, 2023)

A byproduct from the Valles Calchaquíes vineyards (Argentina) rich in phenolic compounds: a tool against endemic Leishmania dissemination - Paula B. Salazar; Martín Fanzone; Brenda A. Zabala; María J. Rodriguez Vaquero; Eduardo Cilli; Paola A. Barroso; Carlos Minahk; Leonardo Acuña (Environmental Science and Pollution Research, 2023)

Computer-supported probabilistic engineering tools assisting fill optimization and the waste reduction of low/intermediate moisture foods supporting vulnerable populations - Reynaldo de la Cruz Quiroz; Veronica Rodriguez-Martinez; J. Antonio Torres (Innovative Food Science & Emerging Technologies, 2023)

Correction to: Neuromuscular electrical stimulation in garments optimized for compliance - R. Juthberg; J. Flodin; L. Guo; S. Rodriguez; N. K. Persson; P. W. Ackermann (European Journal of Applied Physiology, 2023)

Neuromuscular electrical stimulation in garments optimized for compliance - R. Juthberg; J. Flodin; L. Guo; S. Rodriguez; N. K. Persson; P. W. Ackermann (European Journal of Applied Physiology, 2023)
Purpose Physical inactivity is associated with muscle atrophy and venous thromboembolism, which may be prevented by neuromuscular electrical stimulation (NMES). This study aimed to investigate the effect on discomfort, current amplitude and energy consumption when varying the frequency and phase duration of low-intensity NMES (LI-NMES) via a sock with knitting-integrated transverse textile electrodes (TTE). Methods On eleven healthy participants (four females), calf-NMES via a TTE sock was applied with increasing intensity (mA) until ankle-plantar flexion at which point outcomes were compared when testing frequencies 1, 3, 10 and 36 Hz and phase durations 75, 150, 200, 300 and 400 µs. Discomfort was assessed with a numerical rating scale (NRS, 0–10) and energy consumption was calculated and expressed in milli-Joule (mJ). Significance set to p ﻿≤ 0.05. Results 1 Hz yielded a median (inter-quartile range) NRS of 2.4 (1.0–3.4), significantly lower than both 3 Hz with NRS 2.8 (1.8–4.2), and 10 Hz with NRS 3.4 (1.4–5.4) (both p ≤ .014). Each increase in tested frequency resulted in significantly higher energy consumption, e.g. 0.6 mJ (0.5–0.8) for 1 Hz vs 14.9 mJ (12.3–21.2) for 36 Hz ( p = .003). Longer phase durations had no significant effect on discomfort despite generally requiring significantly lower current amplitudes. Phase durations 150, 200 and 400 µs required significantly lower energy consumption compared to 75 µs (all p ≤ .037). Conclusion LI-NMES applied via a TTE sock produces a relevant plantar flexion of the ankle with the best comfort and lowest energy consumption using 1 Hz and phase durations 150, 200 or 400 µs.

Radio- and stable carbon isotope analysis reveals minimal assimilation of petrogenic carbon into an oligotrophic freshwater food web after experimental spills of diluted bitumen - Stephanie D. Graves; Johanna J. Mason; Jose Luis Rodriguez-Gil; Jonathan Y. Séguin; Jules M. Blais; Mark L. Hanson; Bruce P. Hollebone; Vince P. Palace; Ian Clark; Leah Cundall; Daniel Layton-Matthews; Matthew I. Leybourne; et al. (Chemosphere, 2023)

Spatiotemporal optimization of water quality degradation monitoring in water distribution systems supplied by surface sources: A chronological and critical review - Andres Ardila; Manuel J. Rodriguez; Geneviève Pelletier (Journal of Environmental Management, 2023)

Comprehensive review on carotenoid composition: Transformations during processing and storage of foods - Antonio J. Meléndez-Martínez; Patricia Esquivel; Delia B. Rodriguez-Amaya (Food Research International, 2023)

Parental occupational exposure to solvents and autism spectrum disorder: An exploratory look at gene-environment interactions - Erin C. McCanlies; Ja Kook Gu; Michael Kashon; Berran Yucesoy; Claudia C. Ma; Wayne T. Sanderson; Kyoungmi Kim; Yunin J. Ludeña-Rodriguez; Irva Hertz-Picciotto (Environmental Research, 2023)

The interaction between liver cirrhosis, infection by Streptococcus bovis, and colon cancer - Juan Corredoira; Enrique Miguez; Lara María Mateo; Ricardo Fernández-Rodríguez; José Francisco García-Rodríguez; Alexandre Pérez-González; Ana Sanjurjo; María Victoria Pulian; Blanca Ayuso-García; M. Serrano; M. J. Jove; P. Alonso; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Seagrass Abundance Predicts Surficial Soil Organic Carbon Stocks Across the Range of Thalassia testudinum in the Western North Atlantic - James W. Fourqurean; Justin E. Campbell; O. Kennedy Rhoades; Calvin J. Munson; Johannes R. Krause; Andrew H. Altieri; James G. Douglass; Kenneth L. Heck; Valerie J. Paul; Anna R. Armitage; Savanna C. Barry; Enrique Bethel; et al. (Estuaries and Coasts, 2023)

Enhancement of biogas production rate from bioplastics by alkaline pretreatment - Octavio García-Depraect; Raquel Lebrero; Leonardo J. Martínez-Mendoza; Sara Rodriguez-Vega; Rosa Aragão Börner; Tim Börner; Raúl Muñoz (Waste Management, 2023)

Highly efficient adsorption of furosemide drug by using a Ce0.8Sm0.15Nd0.05O2-δ compound immobilized on massively wasted single use packets - E. Valadez-Renteria; J. Oliva; K.P. Padmasree; A.I. Oliva; V. Rodriguez-Gonzalez (Journal of Environmental Chemical Engineering, 2023)

Metronidazole photodegradation under solar light with UiO-66-NH2 photocatalyst: Mechanisms, pathway, and toxicity assessment - Y.-L. Wang; A. Gómez-Avilés; S. Zhang; J.J. Rodriguez; J. Bedia; C. Belver (Journal of Environmental Chemical Engineering, 2023)

Observation of large scale precursor correlations between cosmic rays and earthquakes with a periodicity similar to the solar cycle - P. Homola; V. Marchenko; A. Napolitano; R. Damian; R. Guzik; D. Alvarez-Castillo; S. Stuglik; O. Ruimi; O. Skorenok; J. Zamora-Saa; J.M. Vaquero; T. Wibig; et al. (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

Environmental controls on the hydrogen isotopic composition of volcanic glass from the Southern Afar rift, eastern Ethiopia - Sebastian Jimenez-Rodriguez; Jay Quade; Naomi E. Levin; Christopher J. Campisano; Gary E. Stinchcomb; Diana C. Roman; Zelalem Bedaso (Chemical Geology, 2023)

Contrasting reproductive strategies between stress-tolerant and competitive coral taxa - K. G. Bonilla; J. R. Guest; M. V. Baria-Rodriguez (Coral Reefs, 2023)

Single‐amplified genomes reveal most streamlined free‐living marine bacteria - Juan J. Roda‐Garcia; Jose M. Haro‐Moreno; Francisco Rodriguez‐Valera; Salvador Almagro‐Moreno; Mario López‐Pérez (Environmental Microbiology, 2023)
Evolutionary adaptations of prokaryotes to the environment sometimes result in genome reduction. Our knowledge of this phenomenon among free‐living bacteria remains scarce. We address the dynamics and limits of genome reduction by examining one of the most abundant bacteria in the ocean, the SAR86 clade. Despite its abundance, comparative genomics has been limited by the absence of pure cultures and the poor representation in metagenome‐assembled genomes. We co‐assembled multiple previously available single‐amplified genomes to obtain the first complete genomes from members of the four families. All families showed a convergent evolutionary trajectory with characteristic features of streamlined genomes, most pronounced in the TMED112 family. This family has a genome size of ca. 1 Mb and only 1 bp as median intergenic distance, exceeding values found in other abundant microbes such as SAR11, OM43 and Prochlorococcus . This genomic simplification led to a reduction in the biosynthesis of essential molecules, DNA repair‐related genes, and the ability to sense and respond to environmental factors, which could suggest an evolutionary dependence on other co‐occurring microbes for survival (Black Queen hypothesis). Therefore, these reconstructed genomes within the SAR86 clade provide new insights into the limits of genome reduction in free‐living marine bacteria.

Establishing initial urban bioclimatic planning recommendations for Ankara to address existing and future urban thermophysiological risk factors - A. Santos Nouri; J. Rodriguez-Algecíras; A. Matzarakis (Urban Climate, 2023)

PlantACT! – how to tackle the climate crisis - Heribert Hirt; Salim Al-Babili; Marilia Almeida-Trapp; Antoine Martin; Manuel Aranda; Dorothea Bartels; Malcolm Bennett; Ikram Blilou; Damian Boer; Alix Boulouis; Chris Bowler; Sophie Brunel-Muguet; et al. (Trends in Plant Science, 2023)

Carrot genotypes differentially alter soil bacterial communities and decomposition of plant residue in soil - Narda J. Triviño; Alejandro Rodriguez-Sanchez; Timothy Filley; James J. Camberato; Micaela Colley; Phillip Simon; Lori Hoagland (Plant and Soil, 2023)
Purpose Farmers need alternative approaches to manage nitrogen (N) that meet crop needs while reducing loss to the environment. Identifying crop genotypes that promote decomposition of organic materials and understanding the potential mechanisms responsible could help address this challenge. Consequently, we aimed to 1) determine whether carrot genotypes differ in their potential to facilitate organic matter decomposition in soil, and 2) identify bacterial taxa that are stimulated by carrot roots, and thus could play a role in these processes. Methods We grew five genotypes expected to differ in N use efficiency in a nutrient-poor soil amended with 15 N-enriched corn residue, tracked changes in carbon (C) and N pools, quantified microbial activity and bacterial community composition, and predicted the potential expression of microbial genes involved in soil C and N cycles. Results Experimental genotype 8503 had the greatest capacity to promote decomposition of corn residues. This genotype had the highest % of N from the corn residue in its taproots and on average, promoted higher b-glucosidase activity in soils. Distinct bacterial communities from the families Micromonosporaceae , Chromatiaceae , and Rhodospirillaceae were also enriched in the soils of genotypes like 8503 that were most effective in obtaining N from the corn residue, and this was correlated with greater potential expression of genes responsible for β-glucosidase and nitrification activity. Conclusions Carrot genotypes do differ in their potential to alter soil bacterial communities and stimulate microbially-mediated decomposition of organic materials indicating that it may be possible to begin selecting for this important trait.

The HL-60 human promyelocytic cell line constitutes an effective in vitro model for evaluating toxicity, oxidative stress and necrosis/apoptosis after exposure to black carbon particles and 2.45 GHz radio frequency - Rosa Ana Sueiro Benavides; José Manuel Leiro-Vidal; J. Antonio Rodriguez-Gonzalez; Francisco J. Ares-Pena; Elena López-Martín (Science of The Total Environment, 2023)

A case-based reasoning tool to recommend drinking water source protection actions - Jérôme Cerutti; Irène Abi-Zeid; Luc Lamontagne; Roxane Lavoie; Manuel J. Rodriguez-Pinzon (Journal of Environmental Management, 2023)

Harmonized human biomonitoring in European children, teenagers and adults: EU-wide exposure data of 11 chemical substance groups from the HBM4EU Aligned Studies (2014–2021) - Eva Govarts; Liese Gilles; Laura Rodriguez Martin; Tiina Santonen; Petra Apel; Paula Alvito; Elena Anastasi; Helle Raun Andersen; Anna-Maria Andersson; Lenka Andryskova; Jean-Philippe Antignac; Brice Appenzeller; et al. (International Journal of Hygiene and Environmental Health, 2023)

Management proposal of a naturally occurring wetland modeled as a constructed wetland - J. Tabla-Hernandez; P.F. Rodriguez-Espinosa; A.V. Dellepere; J. Marrugo-Negrete (Ecological Engineering, 2023)

Assessment of rain event effects on source water quality degradation and subsequent water treatment operations - Ianis Delpla; Christian Bouchard; Caetano Dorea; Manuel J. Rodriguez (Science of The Total Environment, 2023)

Appraisal of machine learning techniques for predicting emerging disinfection byproducts in small water distribution networks - Guangji Hu; Haroon R. Mian; Saeed Mohammadiun; Manuel J. Rodriguez; Kasun Hewage; Rehan Sadiq (Journal of Hazardous Materials, 2023)

Detecting mass sediment transport and movement tainted by decades of mining activities in river Quito, Western Colombia - José Marrugo-Negrete; P.F. Rodriguez-Espinosa; P. Godwyn-Paulson; Roberth J. Paternina-Uribe; Mareley Y. Ibarguen Amud; Mauricio Rosso-Pinto; German Enamorado-Montes; Ivan Urango-Cardenas; Harry Gutierrez-Mosquera; Manuel Haminton Salas-Moreno; Carlos Salazar-Camacho; Leonomir Córdoba-Tovar; et al. (Journal of Cleaner Production, 2023)

The impacts of social determinants of health and cardiometabolic factors on cognitive and functional aging in Colombian underserved populations - Hernando Santamaria-Garcia; Sebastian Moguilner; Odir Antonio Rodriguez-Villagra; Felipe Botero-Rodriguez; Stefanie Danielle Pina-Escudero; Gary O’Donovan; Cecilia Albala; Diana Matallana; Michael Schulte; Andrea Slachevsky; Jennifer S. Yokoyama; Katherine Possin; et al. (GeroScience, 2023)
Global initiatives call for further understanding of the impact of inequity on aging across underserved populations. Previous research in low- and middle-income countries (LMICs) presents limitations in assessing combined sources of inequity and outcomes (i.e., cognition and functionality). In this study, we assessed how social determinants of health (SDH), cardiometabolic factors (CMFs), and other medical/social factors predict cognition and functionality in an aging Colombian population. We ran a cross-sectional study that combined theory- (structural equation models) and data-driven (machine learning) approaches in a population-based study ( N = 23,694; M = 69.8 years) to assess the best predictors of cognition and functionality. We found that a combination of SDH and CMF accurately predicted cognition and functionality, although SDH was the stronger predictor. Cognition was predicted with the highest accuracy by SDH, followed by demographics, CMF, and other factors. A combination of SDH, age, CMF, and additional physical/psychological factors were the best predictors of functional status. Results highlight the role of inequity in predicting brain health and advancing solutions to reduce the cognitive and functional decline in LMICs.

Evidence of sea level rise at the Peruvian coast (1942–2019) - Bismarck Jigena-Antelo; Carol Estrada-Ludeña; Stephan Howden; Wilmer Rey; Jorge Paz-Acosta; Patricia Lopez-García; Eric Salazar-Rodriguez; Nieves Endrina; Juan J. Muñoz-Pérez (Science of The Total Environment, 2023)

Water, environment, and socioeconomic justice in California: A multi-benefit cropland repurposing framework - Angel Santiago Fernandez-Bou; José M. Rodríguez-Flores; Alexander Guzman; J. Pablo Ortiz-Partida; Leticia M. Classen-Rodriguez; Pedro A. Sánchez-Pérez; Jorge Valero-Fandiño; Chantelise Pells; Humberto Flores-Landeros; Samuel Sandoval-Solís; Gregory W. Characklis; Thomas C. Harmon; et al. (Science of The Total Environment, 2023)

Corrigendum to “Forest Hydrology in Chile; paste, present, and future” [J. Hydrol. 616 (2023)] - Francisco Balocchi; Mauricio Galleguillos; Diego Rivera; Alejandra Stehr; Jose Luis Arumi; Roberto Pizarro; Pablo Garcia-Chevesich; Andrés Iroumé; Juan J. Armesto; Pedro Hervé-Fernández; Carlos Oyarzún; Pilar Barria; et al. (Journal of Hydrology, 2023)

Adapting to climate change on desert rangelands: A multi-site comparison of grazing behavior plasticity of heritage and improved beef cattle - Andres F. Cibils; Rick E. Estell; Sheri Spiegal; Shelemia Nyamuryekung'e; Matthew M. McIntosh; Danielle M. Duni; Oscar A. Herrera Conegliano; Felipe A. Rodriguez Almeida; Octavio Roacho Estrada; Lisandro J. Blanco; Michael C. Duniway; Santiago A. Utsumi; et al. (Journal of Arid Environments, 2023)

Measurement of airborne nicotine, as a marker of secondhand smoke exposure, in homes with residents who smoke in 9 European countries - Elisabet Henderson; Luis A. Rodriguez Guerrero; Xavier Continente; Esteve Fernández; Olena Tigova; Nuria Cortés-Francisco; Sean Semple; Ruaraidh Dobson; Anna Tzortzi; Vergina K. Vyzikidou; Giuseppe Gorini; Gergana Geshanova; et al. (Environmental Research, 2023)

The Challenges of Characterizing the Zooplankton Community Response Following Simulated Spills of Diluted Bitumen into Boreal Lake Limnocorrals - T. A. Black; M. J. Paterson; L. Timlick; J. Cederwall; J. M. Blais; B. Hollebone; D. M. Orihel; V. P. Palace; J. L. Rodriguez-Gil; M. L. Hanson (Bulletin of Environmental Contamination and Toxicology, 2023)

Correction to: Current regular aspirin use and mammographic breast density: a cross-sectional analysis considering concurrent statin and metformin use - Teoflia Acheampong; Erica J. Lee Argov; Mary Beth Terry; Carmen B. Rodriguez; Mariangela Agovino; Ying Wei; Shweta Athilat; Parisa Tehranifar (Cancer Causes & Control, 2023)

RecruitNet : A global database of plant recruitment networks - Miguel Verdú; Jose L. Garrido; Julio M. Alcántara; Alicia Montesinos‐Navarro; Salomón Aguilar; Marcelo A. Aizen; Ali A. Al‐Namazi; Mohamed Alifriqui; David Allen; Kristina J. Anderson‐Teixeira; Cristina Armas; Jesús M. Bastida; et al. (Ecology, 2023)
Plant recruitment interactions (i.e., what recruits under what) shape the composition, diversity, and structure of plant communities. Despite the huge body of knowledge on the mechanisms underlying recruitment interactions among species, we still know little about the structure of the recruitment networks emerging in ecological communities. Modeling and analyzing the community‐level structure of plant recruitment interactions as a complex network can provide relevant information on ecological and evolutionary processes acting both at the species and ecosystem levels. We report a data set containing 143 plant recruitment networks in 23 countries across five continents, including temperate and tropical ecosystems. Each network identifies the species under which another species recruits. All networks report the number of recruits (i.e., individuals) per species. The data set includes >850,000 recruiting individuals involved in 118,411 paired interactions among 3318 vascular plant species across the globe. The cover of canopy species and open ground is also provided. Three sampling protocols were used: (1) The Recruitment Network (RN) protocol (106 networks) focuses on interactions among established plants (“canopy species”) and plants in their early stages of recruitment (“recruit species”). A series of plots was delimited within a locality, and all the individuals recruiting and their canopy species were identified; (2) The paired Canopy‐Open (pCO) protocol (26 networks) consists in locating a potential canopy plant and identifying recruiting individuals under the canopy and in a nearby open space of the same area; (3) The Georeferenced plot (GP) protocol (11 networks) consists in using information from georeferenced individual plants in large plots to infer canopy‐recruit interactions. Some networks incorporate data for both herbs and woody species, whereas others focus exclusively on woody species. The location of each study site, geographical coordinates, country, locality, responsible author, sampling dates, sampling method, and life habits of both canopy and recruit species are provided. This database will allow researchers to test ecological, biogeographical, and evolutionary hypotheses related to plant recruitment interactions. There are no copyright restrictions on the data set; please cite this data paper when using these data in publications.

Detecting volunteer cotton plants in a corn field with deep learning on UAV remote-sensing imagery - Pappu Kumar Yadav; J. Alex Thomasson; Robert Hardin; Stephen W. Searcy; Ulisses Braga-Neto; Sorin C. Popescu; Daniel E Martin; Roberto Rodriguez; Karem Meza; Juan Enciso; Jorge Solorzano Diaz; Tianyi Wang (Computers and Electronics in Agriculture, 2023)

Forest hydrology in Chile: Past, present, and future - Francisco Balocchi; Mauricio Galleguillos; Diego Rivera; Alejandra Stehr; Jose Luis Arumi; Roberto Pizarro; Pablo Garcia-Chevesich; Andrés Iroumé; Juan J. Armesto; Pedro Hervé-Fernández; Carlos Oyarzún; Pilar Barría; et al. (Journal of Hydrology, 2023)

Drinking water management strategies for distribution networks: An integrated performance assessment framework - Haroon R. Mian; Guangji Hu; Kasun Hewage; Manuel J. Rodriguez; Rehan Sadiq (Journal of Environmental Management, 2023)

Domestic water security in the Arctic: A scoping review - Alexandra Cassivi; Anna Covey; Manuel J. Rodriguez; Stéphanie Guilherme (International Journal of Hygiene and Environmental Health, 2023)

PFAS levels and determinants of variability in exposure in European teenagers – Results from the HBM4EU aligned studies (2014–2021) - D. Richterová; E. Govarts; L. Fábelová; K. Rausová; L. Rodriguez Martin; L. Gilles; S. Remy; A. Colles; L. Rambaud; M. Riou; C. Gabriel; D. Sarigiannis; et al. (International Journal of Hygiene and Environmental Health, 2023)

Ground-motion prediction models for induced earthquakes in the Groningen gas field, the Netherlands - Julian J. Bommer; Peter J. Stafford; Elmer Ruigrok; Adrian Rodriguez-Marek; Michail Ntinalexis; Pauline P. Kruiver; Benjamin Edwards; Bernard Dost; Jan van Elk (Journal of Seismology, 2022)
Small-magnitude earthquakes induced by gas production in the Groningen field in the Netherlands have prompted the development of seismic risk models that serve both to estimate the impact of these events and to explore the efficacy of different risk mitigation strategies. A core element of the risk modelling is ground-motion prediction models (GMPM) derived from an extensive database of recordings obtained from a dense network of accelerographs installed in the field. For the verification of damage claims, an empirical GMPM for peak ground velocity (PGV) has been developed, which predicts horizontal PGV as a function of local magnitude, M L ; hypocentral distance, R hyp ; and the time-averaged shear-wave velocity over the upper 30 m, V S30 . For modelling the risk due to potential induced and triggered earthquakes of larger magnitude, a GMPM for response spectral accelerations has been developed from regressions on the outputs from finite-rupture simulations of motions at a deeply buried rock horizon. The GMPM for rock motions is coupled with a zonation map defining frequency-dependent non-linear amplification factors to obtain estimates of surface motions in the region of thick deposits of soft soils. The GMPM for spectral accelerations is formulated within a logic-tree framework to capture the epistemic uncertainty associated with extrapolation from recordings of events of M L ≤ 3.6 to much larger magnitudes.

Determination of the natural potential groundwater recharge in the Valle Alto basin, Bolivia, through a soil water balance - Cristian J. Apaza-Coria; Inti E. Rodriguez-Levy; Mirko Delfín Soruco; Marijke Huysmans (Hydrogeology Journal, 2022)

Validation and Verification of High-Fidelity Simulations of Thoracic Stent-Graft Implantation - Anna Ramella; Francesco Migliavacca; Jose Felix Rodriguez Matas; Frederic Heim; Francesca Dedola; Stefania Marconi; Michele Conti; Sara Allievi; Tim J. Mandigers; Daniele Bissacco; Maurizio Domanin; Santi Trimarchi; et al. (Annals of Biomedical Engineering, 2022)
Thoracic Endovascular Aortic Repair (TEVAR) is the preferred treatment option for thoracic aortic pathologies and consists of inserting a self-expandable stent-graft into the pathological region to restore the lumen. Computational models play a significant role in procedural planning and must be reliable. For this reason, in this work, high-fidelity Finite Element (FE) simulations are developed to model thoracic stent-grafts. Experimental crimp/release tests are performed to calibrate stent-grafts material parameters. Stent pre-stress is included in the stent-graft model. A new methodology for replicating device insertion and deployment with explicit FE simulations is proposed. To validate this simulation, the stent-graft is experimentally released into a 3D rigid aortic phantom with physiological anatomy and inspected in a computed tomography (CT) scan at different time points during deployment with an ad-hoc set-up. A verification analysis of the adopted modeling features compared to the literature is performed. With the proposed methodology the error with respect to the CT is on average 0.92 ± 0.64%, while it is higher when literature models are adopted (on average 4.77 ± 1.83%). The presented FE tool is versatile and customizable for different commercial devices and applicable to patient-specific analyses.

FishShapes v1: Functionally relevant measurements of teleost shape and size on three dimensions - Samantha A. Price; Sarah T. Friedman; Katherine A. Corn; Olivier Larouche; Kasey Brockelsby; Anna J. Lee; Maya Nagaraj; Nick G. Bertrand; Mailee Danao; Megan C. Coyne; John R. Estrada; Rachel Friedman; et al. (Ecology, 2022)
Teleost fishes account for 96% of all fish species and exhibit a spectacular variety of body forms. Teleost lineages range from deep bodied to elongate (e.g., eels, needlefish), laterally compressed (e.g., ribbonfish) to globular (e.g., pufferfish), and include uniquely shaped lineages such as seahorses, flatfishes, and ocean sunfishes. Adaptive body shape convergence within fishes has long been hypothesized but the nature of the relationships between fish form and ecological and environmental variables remain largely unknown at the macroevolutionary scale. To facilitate the investigation of the interacting factors influencing teleost body shape evolution we measured eight functionally relevant linear traits on adult‐sized specimens along with specimen mass. Linear measurements of standard length, maximum body depth, maximum fish width, lower jaw length, mouth width, head depth, minimum caudal peduncle depth, and minimum caudal peduncle width were taken in millimeters with calipers, or tape measures for oversized specimens. We measured these traits on a total of 16,523 specimens (1–3 specimens per species) at the Smithsonian National Museum of Natural History and took approximately 7000 person hours of data collection to complete. The data went through a three‐step error‐checking process to clean and validate the data and then species averages were calculated. We present the complete specimen data set, which encompasses approximately one‐fifth of extant teleost species diversity, spanning ~90% of teleost families and ~96% of orders. The species and family names are compatible with the taxonomy used by FishBase and the order information with the phylogenetically informed taxonomy of Betancur‐R and colleagues published in 2014. This dataset is licensed under Creative Commons CC0 1.0 Universal (CC0 1.0) but please cite this paper when using the data or a subset of it.

A novel equation that incorporates the linear and hyperbolic nature of the force–velocity relationship in lower and upper limb exercises - Julian Alcazar; Fernando Pareja-Blanco; Carlos Rodriguez-Lopez; Hector Gutierrez-Reguero; Juan Sanchez-Valdepeñas; Pedro J. Cornejo-Daza; Ignacio Ara; Luis M. Alegre (European Journal of Applied Physiology, 2022)

Achieving effective outreach for invasive species: firewood case studies from 2005 to 2016 - Angelica Solano; Shari L. Rodriguez; Leigh Greenwood; Patrick J. Rosopa; David R. Coyle (Biological Invasions, 2022)

Correction: Amphibian phylogenetic diversity in the face of future climate change: not so good news for the Chilean biodiversity hotspot - Leonardo J. Rodriguez; Olga A. Barbosa; Claudio Azat; Mario Alvarado-Rybak; Claudio Correa; Marco A. Méndez; Felipe N. Moreno-Gómez; Felipe E. Rabanal; Marcela A. Vidal; Nelson A. Velásquez; Leonardo D. Bacigalupe (Biodiversity and Conservation, 2022)

Amphibian phylogenetic diversity in the face of future climate change: not so good news for the chilean biodiversity hotspot - Leonardo J. Rodriguez; Olga A. Barbosa; Claudio Azat; Mario Alvarado-Rybak; Claudio Correa; Marco A. Méndez; Felipe N. Moreno-Gómez; Felipe E. Rabanal; Marcela A. Vidal; Nelson A. Velásquez; Leonardo D. Bacigalupe (Biodiversity and Conservation, 2022)

An overview of ionic liquid degradation by advanced oxidation processes - Ismael F. Mena; Elena Diaz; Juan J. Rodriguez; Angel F. Mohedano (Critical Reviews in Environmental Science and Technology, 2022)

Editorial: Small cetacean conservation: Current challenges and opportunities - Jeremy J. Kiszka; Lars Bejder; Randall Davis; Rob Harcourt; Mark Meekan; Diego H. Rodriguez; Karen A. Stockin (Frontiers in Marine Science, 2022)

Using Multi-decadal Satellite Records to Identify Environmental Drivers of Fire Severity Across Vegetation Types - Dario Rodriguez-Cubillo; Gregory J. Jordan; Grant J. Williamson (Remote Sensing in Earth Systems Sciences, 2022)
To date, most studies of fire severity, which is the ecological damage produced by a fire across all vegetation layers in an ecosystem, using remote sensing have focused on wildfires and forests, with less attention given to prescribed burns and treeless vegetation. Our research analyses a multi-decadal satellite record of fire severity in wildfires and prescribed burns, across forested and treeless vegetation, in western Tasmania, a wet region of frequent clouds. We used Landsat satellite images, fire history mapping and environmental predictor variables to understand what drives fire severity. Remotely-sensed fire severity was estimated by the Delta Normalised Burn Ratio (ΔNBR) for 57 wildfires and 70 prescribed burns spanning 25 years. Then, we used Random Forests to identify important predictors of fire severity, followed by generalised additive mixed models to test the statistical association between the predictors and fire severity. In the Random Forests analyses, mean summer precipitation, mean minimum monthly soil moisture and time since previous fire were important predictors in both forested and treeless vegetation, whereas mean annual precipitation was important in forests and temperature seasonality was important in treeless vegetation. Modelled ΔNBR (predicted ΔNBRs from the best-performing generalised additive mixed model) of wildfire forests was higher than modelled ΔNBR of prescribed burns. This study confirms that western Tasmania is a valuable pyrogeographical model for studying fire severity of wet ecosystems under climate change, and provides a framework to better understand the interactions between climate, fire severity and prescribed burning.

Soil macroinvertebrate communities: A world‐wide assessment - Patrick Lavelle; Jérôme Mathieu; Alister Spain; George Brown; Carlos Fragoso; Emmanuel Lapied; Adriana De Aquino; Isabelle Barois; Edmundo Barrios; Maria Eleusa Barros; Jose Camilo Bedano; Eric Blanchart; et al. (Global Ecology and Biogeography, 2022)
Aim Macroinvertebrates comprise a highly diverse set of taxa with great potential as indicators of soil quality. Communities were sampled at 3,694 sites distributed world‐wide. We aimed to analyse the patterns of abundance, composition and network characteristics and their relationships to latitude, mean annual temperature and rainfall, land cover, soil texture and agricultural practices. Location Sites are distributed in 41 countries, ranging from 55° S to 57° N latitude, from 0 to 4,000 m in elevation, with annual rainfall ranging from 500 to >3,000 mm and mean temperatures of 5–32°C. Time period 1980–2018. Major taxa studied All soil macroinvertebrates: Haplotaxida; Coleoptera; Formicidae; Arachnida; Chilopoda; Diplopoda; Diptera; Isoptera; Isopoda; Homoptera; Hemiptera; Gastropoda; Blattaria; Orthoptera; Lepidoptera; Dermaptera; and “others”. Methods Standard ISO 23611‐5 sampling protocol was applied at all sites. Data treatment used a set of multivariate analyses, principal components analysis (PCA) on macrofauna data transformed by Hellinger’s method, multiple correspondence analysis for environmental data (latitude, elevation, temperature and average annual rainfall, type of vegetation cover) transformed into discrete classes, coinertia analysis to compare these two data sets, and bias‐corrected and accelerated bootstrap tests to evaluate the part of the variance of the macrofauna data attributable to each of the environmental factors. Network analysis was performed. Each pairwise association of taxonomic units was tested against a null model considering local and regional scales, in order to avoid spurious correlations. Results Communities were separated into five clusters reflecting their densities and taxonomic richness. They were significantly influenced by climatic conditions, soil texture and vegetation cover. Abundance and diversity, highest in tropical forests (1,895 ± 234 individuals/m 2 ) and savannahs (1,796 ± 72 individuals/m 2 ), progressively decreased in tropical cropping systems (tree‐associated crops, 1,358 ± 120 individuals/m 2 ; pastures, 1,178 ± 154 individuals/m 2 ; and annual crops, 867 ± 62 individuals/m 2 ), temperate grasslands (529 ± 60 individuals/m 2 ), forests (232 ± 20 individuals/m 2 ) and annual crops (231 ± 24 individuals/m 2 ) and temperate dry forests and shrubs (195 ± 11 individuals/m 2 ). Agricultural management decreased overall abundance by ≤54% in tropical areas and 64% in temperate areas. Connectivity varied with taxa, with dominant positive connections in litter transformers and negative connections with ecosystem engineers and Arachnida. Connectivity and modularity were higher in communities with low abundance and taxonomic richness. Main conclusions Soil macroinvertebrate communities respond to climatic, soil and land‐cover conditions. All taxa, except termites, are found everywhere, and communities from the five clusters cover a wide range of geographical and environmental conditions. Agricultural practices significantly decrease abundance, although the presence of tree components alleviates this effect.

Coral‐bleaching responses to climate change across biological scales - Robert van Woesik; Tom Shlesinger; Andréa G. Grottoli; Rob J. Toonen; Rebecca Vega Thurber; Mark E. Warner; Ann Marie Hulver; Leila Chapron; Rowan H. McLachlan; Rebecca Albright; Eric Crandall; Thomas M. DeCarlo; et al. (Global Change Biology, 2022)
The global impacts of climate change are evident in every marine ecosystem. On coral reefs, mass coral bleaching and mortality have emerged as ubiquitous responses to ocean warming, yet one of the greatest challenges of this epiphenomenon is linking information across scientific disciplines and spatial and temporal scales. Here we review some of the seminal and recent coral‐bleaching discoveries from an ecological, physiological, and molecular perspective. We also evaluate which data and processes can improve predictive models and provide a conceptual framework that integrates measurements across biological scales. Taking an integrative approach across biological and spatial scales, using for example hierarchical models to estimate major coral‐reef processes, will not only rapidly advance coral‐reef science but will also provide necessary information to guide decision‐making and conservation efforts. To conserve reefs, we encourage implementing mesoscale sanctuaries (thousands of km 2 ) that transcend national boundaries. Such networks of protected reefs will provide reef connectivity, through larval dispersal that transverse thermal environments, and genotypic repositories that may become essential units of selection for environmentally diverse locations. Together, multinational networks may be the best chance corals have to persist through climate change, while humanity struggles to reduce emissions of greenhouse gases to net zero.

Novel Fusarium wilt resistance genes uncovered in natural and cultivated strawberry populations are found on three non-homoeologous chromosomes - Dominique D. A. Pincot; Mitchell J. Feldmann; Michael A. Hardigan; Mishi V. Vachev; Peter M. Henry; Thomas R. Gordon; Marta Bjornson; Alan Rodriguez; Nicolas Cobo; Randi A. Famula; Glenn S. Cole; Gitta L. Coaker; et al. (Theoretical and Applied Genetics, 2022)
Key Message Several Fusarium wilt resistance genes were discovered, genetically and physically mapped, and rapidly deployed via marker-assisted selection to develop cultivars resistant to Fusarium oxysporum f. sp. fragariae , a devastating soil-borne pathogen of strawberry . Abstract Fusarium wilt, a soilborne disease caused by Fusarium oxysporum f. sp. fragariae , poses a significant threat to strawberry ( Fragaria $$×$$ × ananassa ) production in many parts of the world. This pathogen causes wilting, collapse, and death in susceptible genotypes. We previously identified a dominant gene ( FW1 ) on chromosome 2B that confers resistance to race 1 of the pathogen, and hypothesized that gene-for-gene resistance to Fusarium wilt was widespread in strawberry. To explore this, a genetically diverse collection of heirloom and modern cultivars and octoploid ecotypes were screened for resistance to Fusarium wilt races 1 and 2. Here, we show that resistance to both races is widespread in natural and domesticated populations and that resistance to race 1 is conferred by partially to completely dominant alleles among loci ( FW1 , FW2 , FW3 , FW4 , and FW5 ) found on three non-homoeologous chromosomes (1A, 2B, and 6B). The underlying genes have not yet been cloned and functionally characterized; however, plausible candidates were identified that encode pattern recognition receptors or other proteins known to confer gene-for-gene resistance in plants. High-throughput genotyping assays for SNPs in linkage disequilibrium with FW1 - FW5 were developed to facilitate marker-assisted selection and accelerate the development of race 1 resistant cultivars. This study laid the foundation for identifying the genes encoded by FW1-FW5 , in addition to exploring the genetics of resistance to race 2 and other races of the pathogen, as a precaution to averting a Fusarium wilt pandemic.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Increasing Vascular Response to Injury Improves Tendon Early Healing Outcome in Aged Rats - Corinne N. Riggin; Stephanie N. Weiss; Ashley B. Rodriguez; Harina Raja; Mengcun Chen; Susan M. Schultz; Chandra M. Sehgal; Louis J. Soslowsky (Annals of Biomedical Engineering, 2022)

Toad invasion of Malagasy forests triggers severe mortality of a predatory snake - Fulvio Licata; Rodino Fetraharijaona Harison; Gentile Francesco Ficetola; Karen Freeman; Benjamin J. Muller; Virginia Rodriguez Ponga; Franco Andreone; Angelica Crottini (Biological Invasions, 2022)

Trends in the use of oral anticoagulants, antiplatelets and statins in four European countries: a population-based study - Luis A. García Rodríguez; Lucía Cea Soriano; Francisco J. de Abajo; Francesca Valent; Jesper Hallas; Miguel Gil; Chiara Cattaruzzi; Sara Rodriguez-Martin; Pareen Vora; Montse Soriano-Gabarró; David Gaist (European Journal of Clinical Pharmacology, 2022)
Purpose To evaluate time trends in the prevalence of antithrombotic and statin use in four European countries. Methods Using population-based data from the United Kingdom, Denmark, Spain and Italy between 2010 and 2018, we calculated standardized annual prevalence proportions of antithrombotics and statin use, and changes in prevalence proportions (2018 vs. 2010). Results Prevalence proportion of statins increased from 24.8% to 24.6% (UK), 21.0% to 22.3% (Region of Southern Denmark [RSD]), 12.9% to 14.3% (Udine, Italy), and 20.3% to 23.2% (Spain). Prevalence proportions of antithrombotics declined in all four countries: 18.7% to 15.9% (UK; − 2.8% points), 18.9% to 18.1% (RSD; − 0.8% points), 17.7% to 16.6% (Udine; − 1.1% points) and 15.0% to 13.6% (Spain; − 1.4% points). These declines were driven by reductions in low-dose aspirin use: 15.3% to 8.9% (UK; − 6.4% points), 16.3% to 9.5% (RSD; − 6.8% points), 13.5% to 11.6% (Udine; − 1.9% points), and 10.2% to 8.8% (Spain; − 1.4% points). In the UK, low-dose aspirin use declined from 9.1% to 4.3% (− 4.8% points) for primary CVD prevention, and from 49.6% to 36.9% (− 12.7% points) for secondary prevention. Oral anticoagulant use gradually increased but did not fully account for the decrease in low-dose aspirin use. Conclusions Antithrombotic use in the UK, RSD, Udine and Spain declined between 2010 and 2018, driven by a reduction in use of low-dose aspirin that is not completely explained by a gradual increase in OAC use. Use of statins remained constant in the UK, and increased gradually in the RSD, Udine and Spain.

Phenotypic responses in fish behaviour narrow as climate ramps up - Almendra Rodriguez-Dominguez; Sean D. Connell; Ericka O. C. Coni; Minami Sasaki; David J. Booth; Ivan Nagelkerken (Climatic Change, 2022)
Natural selection alters the distribution of phenotypes as animals adjust their behaviour and physiology to environmental change. We have little understanding of the magnitude and direction of environmental filtering of phenotypes, and therefore how species might adapt to future climate, as trait selection under future conditions is challenging to study. Here, we test whether climate stressors drive shifts in the frequency distribution of behavioural and physiological phenotypic traits (17 fish species) at natural analogues of climate change (CO 2 vents and warming hotspots) and controlled laboratory analogues (mesocosms and aquaria). We discovered that fish from natural populations (4 out of 6 species) narrowed their phenotypic distribution towards behaviourally bolder individuals as oceans acidify, representing loss of shyer phenotypes. In contrast, ocean warming drove both a loss (2/11 species) and gain (2/11 species) of bolder phenotypes in natural and laboratory conditions. The phenotypic variance within populations was reduced at CO 2 vents and warming hotspots compared to control conditions, but this pattern was absent from laboratory systems. Fishes that experienced bolder behaviour generally showed increased densities in the wild. Yet, phenotypic alterations did not affect body condition, as all 17 species generally maintained their physiological homeostasis (measured across 5 different traits). Boldness is a highly heritable trait that is related to both loss (increased mortality risk) and gain (increased growth, reproduction) of fitness. Hence, climate conditions that mediate the relative occurrence of shy and bold phenotypes may reshape the strength of species interactions and consequently alter fish population and community dynamics in a future ocean.

Current regular aspirin use and mammographic breast density: a cross-sectional analysis considering concurrent statin and metformin use - Teofilia Acheampong; Erica J. Lee Argov; Mary Beth Terry; Carmen B. Rodriguez; Mariangela Agovino; Ying Wei; Shweta Athilat; Parisa Tehranifar (Cancer Causes & Control, 2022)

“Right diet for the right person”: a focus group study of nutritionist-dietitians’ perspectives on nutritional genomics and gene-based nutrition advice - Jacus S. Nacis; Marilou R. Galang; Jason Paolo H. Labrador; Milflor S. Gonzales; Aurora Maria Francesca D. Dablo; Diana Glades A. Domalanta-Ronquillo; Victor Franco J. Alfonso; Idelia G. Glorioso; Marietta P. Rodriguez (Journal of Community Genetics, 2022)
Advances in nutritional genomics are intended to revolutionize nutrition practice. A basic understanding of nutritional genomics among nutritionist-dietitians is critical for such advancements to occur. As a precedent to the development and integration of gene-based nutrition advice, this study aimed to assess hospital-based nutritionist-dietitians’ perceptions of nutritional genomics. A total of ten focus group discussions (FGDs) with sixty-one registered nutritionist-dietitians (RNDs) from hospitals in the National Capital Region (NCR), Philippines, were conducted from October to November 2019. Data were collected using a pretested semistructured discussion guide, and thematic analysis was subsequently performed. Diverging perceptions about nutritional genomics were noted among the FGD participants. Five themes emerged relating to the enablers and barriers of gene-based nutrition advice: training and capacity building, the extent of information to be disclosed, cost, ethical considerations, and government support. Themes related to the desired features of the gene-based nutrition advice included being consent-driven, cost-effective, technology-oriented, and guided by standards. The results of this study suggest that training and continued learning will equip RNDs to provide nutrition advice based on genetic information. However, other factors, such as cost and ethical considerations, are critical dimensions that need to be acknowledged and addressed before integrating gene-based advice into nutrition practice.

Parallel shifts of visual sensitivity and body coloration in replicate populations of extremophile fish - Gregory L. Owens; Thor Veen; Dylan R. Moxley; Lenin Arias‐Rodriguez; Michael Tobler; Diana J. Rennison (Molecular Ecology, 2022)
Visual sensitivity and body pigmentation are often shaped by both natural selection from the environment and sexual selection from mate choice. One way of quantifying the impact of the environment is by measuring how traits have changed after colonization of a novel habitat. To do this, we studied Poecilia mexicana populations that have repeatedly adapted to extreme sulphidic (H 2 S‐containing) environments. We measured visual sensitivity using opsin gene expression, as well as body pigmentation, for populations in four independent drainages. Both visual sensitivity and body pigmentation showed significant parallel shifts towards greater medium‐wavelength sensitivity and reflectance in sulphidic populations. Altogether we found that sulphidic habitats select for differences in visual sensitivity and pigmentation. Shifts between habitats may be due to both differences in the water's spectral properties and correlated ecological changes.

A Comprehensive, FAIR File Format for Neuroanatomical Structure Modeling - A. E. Sullivan; S. J. Tappan; P. J. Angstman; A. Rodriguez; G. C. Thomas; D. M. Hoppes; M. A. Abdul-Karim; M. L. Heal; Jack R. Glaser (Neuroinformatics, 2022)
With advances in microscopy and computer science, the technique of digitally reconstructing, modeling, and quantifying microscopic anatomies has become central to many fields of biological research. MBF Bioscience has chosen to openly document their digital reconstruction file format, the Neuromorphological File Specification, available at www.mbfbioscience.com/filespecification (Angstman et al., 2020). The format, created and maintained by MBF Bioscience, is broadly utilized by the neuroscience community. The data format’s structure and capabilities have evolved since its inception, with modifications made to keep pace with advancements in microscopy and the scientific questions raised by worldwide experts in the field. More recent modifications to the neuromorphological file format ensure it abides by the Findable, Accessible, Interoperable, and Reusable (FAIR) data principles promoted by the International Neuroinformatics Coordinating Facility (INCF; Wilkinson et al., Scientific Data, 3 , 160018,, 2016). The incorporated metadata make it easy to identify and repurpose these data types for downstream applications and investigation. This publication describes key elements of the file format and details their relevant structural advantages in an effort to encourage the reuse of these rich data files for alternative analysis or reproduction of derived conclusions.

Genome-wide analysis of mitochondrial DNA copy number reveals loci implicated in nucleotide metabolism, platelet activation, and megakaryocyte proliferation - R. J. Longchamps; S. Y. Yang; C. A. Castellani; W. Shi; J. Lane; M. L. Grove; T. M. Bartz; C. Sarnowski; C. Liu; K. Burrows; A. L. Guyatt; T. R. Gaunt; et al. (Human Genetics, 2022)
Mitochondrial DNA copy number (mtDNA-CN) measured from blood specimens is a minimally invasive marker of mitochondrial function that exhibits both inter-individual and intercellular variation. To identify genes involved in regulating mitochondrial function, we performed a genome-wide association study (GWAS) in 465,809 White individuals from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank (UKB). We identified 133 SNPs with statistically significant, independent effects associated with mtDNA-CN across 100 loci. A combination of fine-mapping, variant annotation, and co-localization analyses was used to prioritize genes within each of the 133 independent sites. Putative causal genes were enriched for known mitochondrial DNA depletion syndromes ( p = 3.09 × 10 –15 ) and the gene ontology (GO) terms for mtDNA metabolism ( p = 1.43 × 10 –8 ) and mtDNA replication ( p = 1.2 × 10 –7 ). A clustering approach leveraged pleiotropy between mtDNA-CN associated SNPs and 41 mtDNA-CN associated phenotypes to identify functional domains, revealing three distinct groups, including platelet activation, megakaryocyte proliferation, and mtDNA metabolism. Finally, using mitochondrial SNPs, we establish causal relationships between mitochondrial function and a variety of blood cell-related traits, kidney function, liver function and overall ( p = 0.044) and non-cancer mortality ( p = 6.56 × 10 –4 ).

Incorporating dwelling mounds into induced seismic risk analysis for the Groningen gas field in the Netherlands - Pauline P. Kruiver; Manos Pefkos; Erik Meijles; Gerard Aalbersberg; Xander Campman; Wim van der Veen; Antony Martin; Kira Ooms-Asshoff; Julian J. Bommer; Adrian Rodriguez-Marek; Rui Pinho; Helen Crowley; et al. (Bulletin of Earthquake Engineering, 2022)
In order to inform decision-making regarding measures to mitigate the impact of induced seismicity in the Groningen gas field in the Netherlands, a comprehensive seismic risk model has been developed. Starting with gas production scenarios and the consequent reservoir compaction, the model generates synthetic earthquake catalogues which are deployed in Monte Carlo analyses, predicting ground motions at a buried reference rock horizon that are combined with nonlinear amplification factors to estimate response spectral accelerations at the surface. These motions are combined with fragility functions defined for the exposed buildings throughout the region to estimate damage levels, which in turn are transformed to risk in terms of injury through consequence functions. Several older and potentially vulnerable buildings are located on dwelling mounds that were constructed from soils and organic material as a flood defence. These anthropogenic structures are not included in the soil profile models used to develop the amplification factors and hence their influence has not been included in the risk analyses to date. To address this gap in the model, concerted studies have been identified to characterize the dwelling mounds. These include new shear-wave velocity measurements that have enabled dynamic site response analyses to determine the modification of ground shaking due to the presence of the mound. A scheme has then been developed to incorporate the dwelling mounds into the risk calculations, which included an assessment of whether the soil-structure interaction effects for buildings founded on the mounds required modification of the seismic fragility functions.

Recognizing Indigenous peoples’ and local communities’ rights and agency in the post-2020 Biodiversity Agenda - Victoria Reyes-García; Álvaro Fernández-Llamazares; Yildiz Aumeeruddy-Thomas; Petra Benyei; Rainer W. Bussmann; Sara K. Diamond; David García-del-Amo; Sara Guadilla-Sáez; Natalia Hanazaki; Nicolas Kosoy; Margarita Lavides; Ana C. Luz; et al. (Ambio, 2022)
The Convention on Biological Diversity is defining the goals that will frame future global biodiversity policy in a context of rapid biodiversity decline and under pressure to make transformative change. Drawing on the work of Indigenous and non-Indigenous scholars, we argue that transformative change requires the foregrounding of Indigenous peoples’ and local communities’ rights and agency in biodiversity policy. We support this argument with four key points. First, Indigenous peoples and local communities hold knowledge essential for setting realistic and effective biodiversity targets that simultaneously improve local livelihoods. Second, Indigenous peoples’ conceptualizations of nature sustain and manifest CBD’s 2050 vision of “Living in harmony with nature.” Third, Indigenous peoples’ and local communities’ participation in biodiversity policy contributes to the recognition of human and Indigenous peoples’ rights. And fourth, engagement in biodiversity policy is essential for Indigenous peoples and local communities to be able to exercise their recognized rights to territories and resources.

NGS and phenotypic ontology-based approaches increase the diagnostic yield in syndromic retinal diseases - I. Perea-Romero; F. Blanco-Kelly; I. Sanchez-Navarro; I. Lorda-Sanchez; S. Tahsin-Swafiri; A. Avila-Fernandez; I. Martin-Merida; M. J. Trujillo-Tiebas; R. Lopez-Rodriguez; M. Rodriguez de Alba; I. F. Iancu; R. Romero; et al. (Human Genetics, 2021)
Syndromic retinal diseases (SRDs) are a group of complex inherited systemic disorders, with challenging molecular underpinnings and clinical management. Our main goal is to improve clinical and molecular SRDs diagnosis, by applying a structured phenotypic ontology and next-generation sequencing (NGS)-based pipelines. A prospective and retrospective cohort study was performed on 100 probands with an a priori diagnosis of non-Usher SRDs, using available clinical data, including Human Phenotype Ontology annotation, and further classification into seven clinical categories (ciliopathies, specific syndromes and five others). Retrospective molecular diagnosis was assessed using different molecular and bioinformatic methods depending on availability. Subsequently, uncharacterized probands were prospectively screened using other NGS approaches to extend the number of analyzed genes. After phenotypic classification, ciliopathies were the most common SRD (35%). A global characterization rate of 52% was obtained, with six cases incompletely characterized for a gene that partially explained the phenotype. An improved characterization rate was achieved addressing prospective cases (83%) and well-recognizable syndrome (62%) subgroups. The 27% of the fully characterized cases were reclassified into a different clinical category after identification of the disease-causing gene. Clinical-exome sequencing is the most appropriate first-tier approach for prospective cases, whereas whole-exome sequencing and bioinformatic reanalysis increases the diagnosis of uncharacterized retrospective cases to 45%, mostly those with unspecific symptoms. Our study describes a comprehensive approach to SRDs in daily clinical practice and the importance of thorough clinical assessment and selection of the most appropriate molecular test to be used to solve these complex cases and elucidate novel associations.

The human hepatocyte TXG-MAPr: gene co-expression network modules to support mechanism-based risk assessment - Giulia Callegaro; Steven J. Kunnen; Panuwat Trairatphisan; Solène Grosdidier; Marije Niemeijer; Wouter den Hollander; Emre Guney; Janet Piñero Gonzalez; Laura Furlong; Yue W. Webster; Julio Saez-Rodriguez; Jeffrey J. Sutherland; et al. (Archives of Toxicology, 2021)
Mechanism-based risk assessment is urged to advance and fully permeate into current safety assessment practices, possibly at early phases of drug safety testing. Toxicogenomics is a promising source of mechanisms-revealing data, but interpretative analysis tools specific for the testing systems (e.g. hepatocytes) are lacking. In this study, we present the TXG-MAPr webtool (available at https://txg-mapr.eu/WGCNA_PHH/TGGATEs_PHH/ ), an R-Shiny-based implementation of weighted gene co-expression network analysis (WGCNA) obtained from the Primary Human Hepatocytes (PHH) TG-GATEs dataset. The 398 gene co-expression networks (modules) were annotated with functional information (pathway enrichment, transcription factor) to reveal their mechanistic interpretation. Several well-known stress response pathways were captured in the modules, were perturbed by specific stressors and showed preservation in rat systems (rat primary hepatocytes and rat in vivo liver), with the exception of DNA damage and oxidative stress responses. A subset of 87 well-annotated and preserved modules was used to evaluate mechanisms of toxicity of endoplasmic reticulum (ER) stress and oxidative stress inducers, including cyclosporine A, tunicamycin and acetaminophen. In addition, module responses can be calculated from external datasets obtained with different hepatocyte cells and platforms, including targeted RNA-seq data, therefore, imputing biological responses from a limited gene set. As another application, donors’ sensitivity towards tunicamycin was investigated with the TXG-MAPr, identifying higher basal level of intrinsic immune response in donors with pre-existing liver pathology. In conclusion, we demonstrated that gene co-expression analysis coupled to an interactive visualization environment, the TXG-MAPr, is a promising approach to achieve mechanistic relevant, cross-species and cross-platform evaluation of toxicogenomic data.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Pursuing Multiple Biomarkers for Early Idiopathic Parkinson’s Disease Diagnosis - Yareth Gopar-Cuevas; Ana P. Duarte-Jurado; Rosa N. Diaz-Perez; Odila Saucedo-Cardenas; Maria J. Loera-Arias; Roberto Montes-de-Oca-Luna; Humberto Rodriguez-Rocha; Aracely Garcia-Garcia (Molecular Neurobiology, 2021)

Practical evaluation of single-frequency dGNSS for monitoring slow-moving landslides - Rodriguez J; Deane E; Hendry M. T; Macciotta R; Evans T; Gräpel C; Skirrow R (Landslides, 2021)

Spontaneously fermented traditional beverages as a source of bioactive compounds: an overview - R. B. Cuvas-Limon; Clarisse Nobre; Mario Cruz; Rosa M. Rodriguez-Jasso; Héctor A. Ruíz; Araceli Loredo-Treviño; J. A. Texeira; Ruth Belmares (Critical Reviews in Food Science and Nutrition, 2021)

Trade‐offs between reducing complex terminology and producing accurate interpretations from environmental DNA: Comment on “Environmental DNA: What's behind the term?” by Pawlowski et al., (2020) - Naiara Rodriguez‐Ezpeleta; Olivier Morissette; Colin W. Bean; Shivakumara Manu; Pritam Banerjee; Anaïs Lacoursière‐Roussel; Kingsly C. Beng; S. Elizabeth Alter; Fabian Roger; Luke E. Holman; Kathryn A. Stewart; Michael T. Monaghan; et al. (Molecular Ecology, 2021)
In a recent paper, “Environmental DNA: What's behind the term? Clarifying the terminology and recommendations for its future use in biomonitoring,” Pawlowski et al . argue that the term eDNA should be used to refer to the pool of DNA isolated from environmental samples, as opposed to only extra‐organismal DNA from macro‐organisms. We agree with this view. However, we are concerned that their proposed two‐level terminology specifying sampling environment and targeted taxa is overly simplistic and might hinder rather than improve clear communication about environmental DNA and its use in biomonitoring. This terminology is based on categories that are often difficult to assign and uninformative, and it overlooks a fundamental distinction within eDNA: the type of DNA (organismal or extra‐organismal) from which ecological interpretations are derived.

Sulfur isotope fractionations constrain the biological cycling of dimethylsulfoniopropionate in the upper ocean - Daniela Osorio‐Rodriguez; Manuel Razo‐Mejia; Nathan F. Dalleska; Alex L. Sessions; Victoria J. Orphan; Jess F. Adkins (Limnology and Oceanography, 2021)
The rapid turnover of dimethylsulfoniopropionate (DMSP), likely the most relevant dissolved organic sulfur compound in the surface ocean, makes it pivotal to understand the cycling of organic sulfur. Dimethylsulfoniopropionate is mainly synthesized by phytoplankton, and it can be utilized as carbon and sulfur sources by marine bacteria or cleaved by bacteria or algae to produce the volatile compound dimethylsulfide (DMS), involved in the formation of sulfate aerosols. The fluxes between the consumption (i.e., demethylation) and cleavage pathways are thought to depend on community interactions and their sulfur demand. However, a quantitative assessment of the sulfur partitioning between each of these pathways is still missing. Here, we report for the first time the sulfur isotope fractionations by enzymes involved in DMSP degradation with different catalytic mechanisms, expressed heterologously in Escherichia coli . We show that the residual DMSP from the demethylation pathway is 2.7‰ enriched in δ 34 S relative to the initial DMSP, and that the fractionation factor ( 34 ε ) of the cleavage pathways varies between −1 and −9‰. The incorporation of these fractionation factors into mass balance calculations constrains the biological fates of DMSP in seawater, supports the notion that demethylation dominates over cleavage in marine environments, and could be used as a proxy for the dominant pathways of degradation of DMSP by marine microbial communities.

Multi-Tissue Methylation Clocks for Age and Sex Estimation in the Common Bottlenose Dolphin - Todd R. Robeck; Zhe Fei; Amin Haghani; Joseph A. Zoller; Caesar Z. Li; Karen J. Steinman; Stacy Dirocco; Lydia Staggs; Todd Schmitt; Steve Osborn; Gisele Montano; Magdalena Rodriguez; et al. (Frontiers in Marine Science, 2021)
Accurate identification of individual ages within wild bottlenose dolphins ( Tursiops truncatus ) is critical for determining population health and the development of population management strategies. As such, we analyzed DNA methylation (DNAm) patterns by applying a custom methylation array (HorvathMammalMethyl40) to both blood ( n = 140) and skin samples ( n = 87) from known age or approximate age (0–57 years) bottlenose dolphins. We present three bottlenose dolphin specific age estimation clocks using combined blood and skin [48 CpGs, R = 0.93, median absolute error (MAE) = 2.13 years], blood only (64 CpGs, R = 0.97, error = 1.46 years) and skin only (39 CpGs, R = 0.95, error = 2.53). We characterized individual cytosines that correlate with sex and age in dolphins and developed a sex estimator based on 71 CpGs that predicts the sex of any odontocete species with 99.5% accuracy. The presented epigenetic clocks are expected to be useful for conservation efforts and for determining if anthropogenic events affect aging rates in wild populations.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Host genetic polymorphisms associated with beta human papillomavirus seropositivity - Annika Antonsson; Astrid J. Rodriguez-Acevedo; Upekha E. Liyanage; Maria Celia B. Hughes; Jolieke C. van der Pols; Adele C. Green (Archives of Virology, 2021)

Molecular systematics of the Awaous banana complex (River gobies; Teleostei: Oxudercidae ) - Caleb D. McMahan; Diego J. Elías; Yue Li; Omár Domínguez‐Domínguez; Sheila Rodriguez‐Machado; Alejandra Morales‐Cabrera; Diana Velásquez‐Ramírez; Kyle R. Piller; Prosanta Chakrabarty; Wilfredo A. Matamoros (Journal of Fish Biology, 2021)
Diadromous fishes can exhibit interesting evolutionary and population‐level patterns given their use of freshwater and marine environments as part of their life histories. The River goby genus Awaous are prominent members of riverine ichthyofaunas and occur throughout Atlantic and Pacific slopes of the Americas from the southern United States to Ecuador and Brazil. Here we study the widespread and polymorphic Awaous banana complex to assess phylogeographic patterns and test previous hypotheses that all populations of this species in the Americas belong to the same species. Analysis of sequence data based on the mitochondrial cytochrome oxidase I gene shows multiple clades within the Atlantic and Pacific basins, which correspond to previously described species. Additionally, haplotype analysis demonstrates unique and unconnected networks between these species. Within these clades we document biogeographic patterns that are congruent with results of other co‐occurring diadromous species, as well as a novel biogeographic pattern for the region. Our results support the recognition of distinct species of Awaous in the Atlantic ( A. banana and A. tajasica ) and Pacific ( A. transandeanus ) basins. These results are concordant with previously established morphological characters permitting the separation of these species.

Nutritional and ecotoxicological aspects of the acidotolerant alga Keratococcus rhaphidioides (Chlorophyta): a potential candidate for algal mediated bioremediation of extremely acidic waters - J. M. Cabrera; S. S. Schultz; G. D. Baffico; M. C. Rodriguez; F. L. Pedrozo; M. M. Diaz (Journal of Applied Phycology, 2021)

The role of 5-lipoxygenase in the pathophysiology of COVID-19 and its therapeutic implications - Nohora Cristina Ayola-Serrano; Namrata Roy; Zareena Fathah; Mohammed Moustapha Anwar; Bivek Singh; Nour Ammar; Ranjit Sah; Areej Elba; Rawan Sobhi Utt; Samuel Pecho-Silva; Alfonso J. Rodriguez-Morales; Kuldeep Dhama; et al. (Inflammation Research, 2021)

New insights into the mechanisms underlying 5-fluorouracil-induced intestinal toxicity based on transcriptomic and metabolomic responses in human intestinal organoids - Daniela Rodrigues; Terezinha de Souza; Luke Coyle; Matteo Di Piazza; Bram Herpers; Sofia Ferreira; Mian Zhang; Johanna Vappiani; Daniel C. Sévin; Attila Gabor; Anthony Lynch; Seung-Wook Chung; et al. (Archives of Toxicology, 2021)
5-Fluorouracil (5-FU) is a widely used chemotherapeutical that induces acute toxicity in the small and large intestine of patients. Symptoms can be severe and lead to the interruption of cancer treatments. However, there is limited understanding of the molecular mechanisms underlying 5-FU-induced intestinal toxicity. In this study, well-established 3D organoid models of human colon and small intestine (SI) were used to characterize 5-FU transcriptomic and metabolomic responses. Clinically relevant 5-FU concentrations for in vitro testing in organoids were established using physiologically based pharmacokinetic simulation of dosing regimens recommended for cancer patients, resulting in exposures to 10, 100 and 1000 µM. After treatment, different measurements were performed: cell viability and apoptosis; image analysis of cell morphological changes; RNA sequencing; and metabolome analysis of supernatant from organoids cultures. Based on analysis of the differentially expressed genes, the most prominent molecular pathways affected by 5-FU included cell cycle, p53 signalling, mitochondrial ATP synthesis and apoptosis. Short time-series expression miner demonstrated tissue-specific mechanisms affected by 5-FU, namely biosynthesis and transport of small molecules, and mRNA translation for colon; cell signalling mediated by Rho GTPases and fork-head box transcription factors for SI. Metabolomic analysis showed that in addition to the effects on TCA cycle and oxidative stress in both organoids, tissue-specific metabolic alterations were also induced by 5-FU. Multi-omics integration identified transcription factor E2F1, a regulator of cell cycle and apoptosis, as the best key node across all samples. These results provide new insights into 5-FU toxicity mechanisms and underline the relevance of human organoid models in the safety assessment in drug development.

First evidence of fish nocardiosis in Mexico caused by Nocardia seriolae in farmed red drum ( Sciaenops ocellatus , Linnaeus) - Rodolfo Enrique del Rio‐Rodriguez; Jose Gustavo Ramirez‐Paredes; Sonia Araceli Soto‐Rodriguez; Yechiam Shapira; Mariana del Jesus Huchin‐Cortes; Judith Ruiz‐Hernandez; Monica Isela Gomez‐Solano; David J. Haydon (Journal of Fish Diseases, 2021)
Between August and December 2013, the offshore cages of a commercial marine farm culturing red drum Sciaenops ocellatus in Campeche Bay Mexico were affected by an outbreak of an ulcerative granulomatous disease with up to 70% cumulative mortality. Thirty‐one adults displaying open ulcers on the skin were submitted for diagnosis. At necropsy, multiple white‐yellowish nodules (0.1–0.5 cm in diameter) were present in all internal organs, where the kidney and the spleen were the most severely affected. Histopathology evinced typical systemic granulomatous formations. Gram and Ziehl–Neelsen stains on tissue imprints, bacterial swabs and tissue sections revealed Gram‐positive, acid‐fast, branching beaded long rod filamentous bacteria. Tissue samples resulted positive for nocardiosis with a Nocardia genus‐specific nested PCR. Definite identification at the species level and taxonomic positioning of the fastidious pathogen were achieved through a specific Nocardia seriolae PCR and by sequencing the gyrB gene of pure isolates. After administration of antibiotics during fry production, a posterior follow‐up monitoring (from 2014 to 2017) detected mild but recurrent outbreaks of the bacteria with no seasonality pattern. To the extent of our knowledge, this is the first report of piscine nocardiosis in Mexico and the first time this disease is detected in red drum.

Roundup negatively impacts the behavior and nerve function of the Madagascar hissing cockroach (Gromphadorhina portentosa) - Megha Kanabar; Samuel Bauer; Zimuzo M. Ezedum; Ian P. Dwyer; William S. Moore; Gabriella Rodriguez; Aditya Mall; Anne T. Littleton; Michael Yudell; Jenil Kanabar; Wade J. Tucker; Emily R. Daniels; et al. (Environmental Science and Pollution Research, 2021)

Gene Expression Response to Stony Coral Tissue Loss Disease Transmission in M. cavernosa and O. faveolata From Florida - Nikki Traylor-Knowles; Michael T. Connelly; Benjamin D. Young; Katherine Eaton; Erinn M. Muller; Valerie J. Paul; Blake Ushijima; Allyson DeMerlis; Melissa K. Drown; Ashley Goncalves; Nicholas Kron; Grace A. Snyder; et al. (Frontiers in Marine Science, 2021)
Since 2014, corals within Florida’s Coral Reef have been dying at an unprecedented rate due to stony coral tissue loss disease (SCTLD). Here we describe the transcriptomic outcomes of three different SCTLD transmission experiments performed at the Smithsonian Marine Station and Mote Marine Laboratory between 2019 and 2020 on the corals Orbicella faveolata and Montastraea cavernosa. Overall, diseased O. faveolata had 2194 differentially expressed genes (DEGs) compared with healthy colonies, whereas diseased M. cavernosa had 582 DEGs compared with healthy colonies. Many significant DEGs were implicated in immunity, extracellular matrix rearrangement, and apoptosis. These included, but not limited to, peroxidases, collagens, Bax-like, fibrinogen-like, protein tyrosine kinase, and transforming growth factor beta. A gene module was identified that was significantly correlated to disease transmission. This module possessed many apoptosis and immune genes with high module membership indicating that a complex apoptosis and immune response is occurring in corals during SCTLD transmission. Overall, we found that O. faveolata and M. cavernosa exhibit an immune, apoptosis, and tissue rearrangement response to SCTLD. We propose that future studies should focus on examining early time points of infection, before the presence of lesions, to understand the activating mechanisms involved in SCTLD.

Comparison of real and simulated lava flows in the Holocene volcanism of Gran Canaria (Canary Islands, Spain) with Q-LavHA: contribution to volcanic hazard management - A. Rodriguez-Gonzalez; M. Aulinas; S. Mossoux; F. J. Perez-Torrado; J. L. Fernandez-Turiel; M. Cabrera; C. Prieto-Torrell (Natural Hazards, 2021)

A robust machine learning framework to identify signatures for frailty: a nested case-control study in four aging European cohorts - David Gomez-Cabrero; Stefan Walter; Imad Abugessaisa; Rebeca Miñambres-Herraiz; Lucia Bernad Palomares; Lee Butcher; Jorge D. Erusalimsky; Francisco Jose Garcia-Garcia; José Carnicero; Timothy C. Hardman; Harald Mischak; Petra Zürbig; et al. (GeroScience, 2021)

Correction to: Impact of acute high‑intensity interval exercise on plasma pentraxin 3 and endothelial function in obese individuals—a pilot study - Aaron L. Slusher; Brandon G. Fico; Katelyn M. Dodge; Ryan S. Garten; Peter J. Ferrandi; Alexandra A. Rodriguez; Gabriel Pena; Chun-Jung Huang (European Journal of Applied Physiology, 2021)

Impact of acute high-intensity interval exercise on plasma pentraxin 3 and endothelial function in obese individuals—a pilot study - Aaron L. Slusher; Brandon G. Fico; Katelyn M. Dodge; Ryan S. Garten; Peter J. Ferrandi; Alexandra A. Rodriguez; Gabriel Pena; Chun-Jung Huang (European Journal of Applied Physiology, 2021)

Managing groundwater supplies subject to drought: perspectives on current status and future priorities from England (UK) - M. J. Ascott; J. P. Bloomfield; I. Karapanos; C. R. Jackson; R. S. Ward; A. B. McBride; B. Dobson; N. Kieboom; I. P. Holman; A. F. Van Loon; E. J. Crane; B. Brauns; et al. (Hydrogeology Journal, 2021)
Effective management of groundwater resources during drought is essential. How is groundwater currently managed during droughts, and in the face of environmental change, what should be the future priorities? Four themes are explored, from the perspective of groundwater management in England (UK): (1) integration of drought definitions; (2) enhanced fundamental monitoring; (3) integrated modelling of groundwater in the water cycle; and (4) better information sharing. Whilst these themes are considered in the context of England, globally, they are relevant wherever groundwater is affected by drought.

Analysis of urinary metabolites of polycyclic aromatic hydrocarbons in precarious workers of highly exposed occupational scenarios in Mexico - Lorena Díaz de León-Martínez; Rogelio Flores-Ramírez; Maribel Rodriguez-Aguilar; Alejandra Berumen-Rodríguez; Francisco J. Pérez-Vázquez; Fernando Díaz-Barriga (Environmental Science and Pollution Research, 2021)

Lead uptake and translocation pathways in soybean seedlings: the role of ion competition and transpiration rates - Andrés Blanco; María L. Pignata; Hernán R. Lascano; María J. Salazar; Judith H. Rodriguez (Environmental Science and Pollution Research, 2021)

Comparison of Hydrological Model-Based and Geographical-Based Approaches for Estimating Water Travel Times for Source Water Protection - Flavie St-Pierre; Françoise Tardif; Manuel J. Rodriguez; Geneviève Pelletier (Environmental Processes, 2021)

Optimization of training sets for genomic prediction of early-stage single crosses in maize - Dnyaneshwar C. Kadam; Oscar R. Rodriguez; Aaron J. Lorenz (Theoretical and Applied Genetics, 2021)

Mechanical ventilation-induced alterations of intracellular surfactant pool and blood–gas barrier in healthy and pre-injured lungs - Jeanne-Marie Krischer; Karolin Albert; Alexander Pfaffenroth; Elena Lopez-Rodriguez; Clemens Ruppert; Bradford J. Smith; Lars Knudsen (Histochemistry and Cell Biology, 2021)
Mechanical ventilation triggers the manifestation of lung injury and pre-injured lungs are more susceptible. Ventilation-induced abnormalities of alveolar surfactant are involved in injury progression. The effects of mechanical ventilation on the surfactant system might be different in healthy compared to pre-injured lungs. In the present study, we investigated the effects of different positive end-expiratory pressure (PEEP) ventilations on the structure of the blood–gas barrier, the ultrastructure of alveolar epithelial type II (AE2) cells and the intracellular surfactant pool (= lamellar bodies, LB). Rats were randomized into bleomycin-pre-injured or healthy control groups. One day later, rats were either not ventilated, or ventilated with PEEP = 1 or 5 cmH 2 O and a tidal volume of 10 ml/kg bodyweight for 3 h. Left lungs were subjected to design-based stereology, right lungs to measurements of surfactant proteins (SP−) B and C expression. In pre-injured lungs without ventilation, the expression of SP-C was reduced by bleomycin; while, there were fewer and larger LB compared to healthy lungs. PEEP = 1 cmH 2 O ventilation of bleomycin-injured lungs was linked with the thickest blood–gas barrier due to increased septal interstitial volumes. In healthy lungs, increasing PEEP levels reduced mean AE2 cell size and volume of LB per AE2 cell; while in pre-injured lungs, volumes of AE2 cells and LB per cell remained stable across PEEPs. Instead, in pre-injured lungs, increasing PEEP levels increased the number and decreased the mean size of LB. In conclusion, mechanical ventilation-induced alterations in LB ultrastructure differ between healthy and pre-injured lungs. PEEP = 1 cmH 2 O but not PEEP = 5 cmH 2 O ventilation aggravated septal interstitial abnormalities after bleomycin challenge.

Tryptophan depletion predicts lower positive affect in sexual minority men living with HIV who use methamphetamine - Ji-Young Lee; Tiffany R. Glynn; Judith T. Moskowitz; Dietmar Fuchs; Torsten B. Neilands; Samantha E. Dilworth; Daniel J. Feaster; Allan Rodriguez; Adam W. Carrico (Journal of NeuroVirology, 2021)

The influence of natural fire and cultural practices on island ecosystems: Insights from a 4,800 year record from Gran Canaria, Canary Islands - Cesare Ravazzi; Michela Mariani; Constantino Criado; Lorena Garozzo; Agustín Naranjo‐Cigala; Francisco J. Perez‐Torrado; Roberta Pini; Alejandro Rodriguez‐Gonzalez; Sandra Nogué; Robert J. Whittaker; José María Fernández‐Palacios; Lea de Nascimento (Journal of Biogeography, 2021)
Aim Long‐term ecological data provide a stepped frame of island ecosystem transformation after successive waves of human colonization, essential to determine conservation and management baselines. However, the timing and ecological impact of initial human settlement on many islands is still poorly known. Here, we report analyses from a 4800‐year sedimentary sequence from Gran Canaria (Canary Islands), with the goal of disentangling forest responses to natural fire from early human pressure on the island. Location La Calderilla, a volcanic maar caldera at 1,770 m a.s.l. on Gran Canaria. Taxon Plants and fungi. Methods A core from the caldera infill was analysed for sediment properties, pollen, micro‐ and macrocharcoal, with radiocarbon and biochronology dating. Fossil data were statistically zoned and interpreted with the help of cross‐correlation and ordination analyses. Surface samples and a pollen–vegetation training set were used as modern analogues for vegetation reconstruction. Results Before human settlement (4,800–2,000 cal. yr bp ), pine ( Pinus canariensis ) pollen dominated. Extensive dry pine forests characterized the highlands, although with temporary declining phases, followed by prompt (sub‐centennial scale) recovery. Towards 2,280 cal. yr bp there was a shift to open vegetation, marked by an increase in coprophilous spores. Coincidental with independent evidence of human settlement in the pine belt (2,000–470 cal. yr bp ) there was a decline of pine and a peak in charcoal. Following historic settlement (470–0 cal. yr bp ), pollen producers from anthropogenic habitats, secondary vegetation and coprophilous fungi increased in abundance, reflecting higher pressure of animal husbandry and farming. Modern moss polsters reflect extensive reforestation since 1950 ce (Common Era). Main conclusions From 4,800 cal. yr bp, the pristine vegetation covering the Gran Canaria highlands was a mosaic of dry pine forests and open vegetation. The pine forests sustained intense fires, which may well have promoted habitat diversity. Human interference was initiated around 2,280 cal. yr bp probably by recurrent cultural firing and animal husbandry, triggering a steady trend of forest withdrawal and expansion of grasses and scrubs, until the final disappearance of the pine forest locally in the 20th century. Grasslands were found to be of ancient cultural origin in the summit areas of Gran Canaria, although they underwent an expansion after the Castilian Conquest.

The current situation and future perspectives of Quercus ilex and Pinus halepensis afforestation on agricultural land in Spain under climate change scenarios - L. Quinto; Rafael M. Navarro-Cerrillo; Guillermo Palacios-Rodriguez; F. Ruiz-Gómez; J. Duque-Lazo (New Forests, 2021)

Using a biophysical model to investigate connectivity between spawning grounds and nursery areas of King George whiting ( Sillaginodes punctatus : Perciformes) in South Australia’s gulfs - Troy A. Rogers; Ana Redondo Rodriguez; Anthony J. Fowler; Mark J. Doubell; Michael J. Drew; Michael A. Steer; Damian Matthews; Charles James; Bronwyn M. Gillanders (Fisheries Oceanography, 2021)
Many demersal marine fish species depend on a dispersive larval stage that connects geographically discrete sub‐populations. Understanding connectivity between these sub‐populations is necessary to determine stock structure, which identifies the appropriate spatial scale for fishery management. Such connectivity is poorly understood for King George whiting ( Sillaginodes punctatus ; Perciformes) in South Australia's gulf system, even though spawning grounds and nursery areas are adequately defined. In response to declines in commercial catches and estimated biomass, this study aimed to determine the most important spawning grounds and nursery areas to recruitment, and the connectivity between them. A biophysical model was seeded with particles according to the distribution and density of eggs throughout the spawning area in 2017 and 2018. Despite inter‐annual differences in the origins of particles, dispersal pathways and predicted settlement areas remained consistent between years. Predicted settlement was generally highest to nursery areas only short distances from regional spawning grounds, consistent with previous hydrodynamic models. However, the model also predicted that spawning in one region could contribute to recruitment in an adjacent region later in the spawning season, which aligned with the breakdown of thermohaline fronts at the entrance of each gulf. The connectivity between spawning grounds and nursery areas predicted by the model is supported by spatio‐temporal patterns in the otolith chemistry of pre‐flexion larvae and settled juveniles. Consequently, the most parsimonious explanation is that the populations of King George whiting in South Australia's gulf system constitute a single, panmictic stock, which has implications for fishery management.

Superoxide-mediated oxidative stress accelerates skeletal muscle atrophy by synchronous activation of proteolytic systems - Young C. Jang; Karl Rodriguez; Michael S. Lustgarten; Florian L. Muller; Arunabh Bhattacharya; Anson Pierce; Jeongmoon J. Choi; Nan Hee Lee; Asish Chaudhuri; Arlan G. Richardson; Holly Van Remmen (GeroScience, 2020)

Removal of emerging pollutants in aqueous phase by heterogeneous Fenton and photo-Fenton with Fe2O3-TiO2-clay heterostructures - Carmen B. Molina; Eva Sanz-Santos; Ali Boukhemkhem; Jorge Bedia; Carolina Belver; Juan J. Rodriguez (Environmental Science and Pollution Research, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Dynamics of volatilomes emitted during cross-talking of plant-growth-promoting bacteria and the phytopathogen, Fusarium solani - A. Gutiérrez-Santa Ana; H. A. Carrillo-Cerda; J. Rodriguez-Campos; J. B. Velázquez-Fernández; O. A. Patrón-Soberano; S. M. Contreras-Ramos (World Journal of Microbiology and Biotechnology, 2020)

Ageusia and anosmia, a common sign of COVID-19? A case series from four countries - Jair Vargas-Gandica; Daniel Winter; Rainer Schnippe; Andrea G. Rodriguez-Morales; Johana Mondragon; Juan Pablo Escalera-Antezana; María del Pilar Trelles-Thorne; D. Katterine Bonilla-Aldana; Alfonso J. Rodriguez-Morales; Alberto Paniz-Mondolfi (Journal of NeuroVirology, 2020)

The pervasive and multifaceted influence of biocrusts on water in the world's drylands - David J. Eldridge; Sasha Reed; Samantha K. Travers; Matthew A. Bowker; Fernando T. Maestre; Jingyi Ding; Caroline Havrilla; Emilio Rodriguez‐Caballero; Nichole Barger; Bettina Weber; Anita Antoninka; Jayne Belnap; et al. (Global Change Biology, 2020)
The capture and use of water are critically important in drylands, which collectively constitute Earth's largest biome. Drylands will likely experience lower and more unreliable rainfall as climatic conditions change over the next century. Dryland soils support a rich community of microphytic organisms (biocrusts), which are critically important because they regulate the delivery and retention of water. Yet despite their hydrological significance, a global synthesis of their effects on hydrology is lacking. We synthesized 2,997 observations from 109 publications to explore how biocrusts affected five hydrological processes (times to ponding and runoff, early [sorptivity] and final [infiltration] stages of water flow into soil, and the rate or volume of runoff) and two hydrological outcomes (moisture storage, sediment production). We found that increasing biocrust cover reduced the time for water to pond on the surface (−40%) and commence runoff (−33%), and reduced infiltration (−34%) and sediment production (−68%). Greater biocrust cover had no significant effect on sorptivity or runoff rate/amount, but increased moisture storage (+14%). Infiltration declined most (−56%) at fine scales, and moisture storage was greatest (+36%) at large scales. Effects of biocrust type (cyanobacteria, lichen, moss, mixed), soil texture (sand, loam, clay), and climatic zone (arid, semiarid, dry subhumid) were nuanced. Our synthesis provides novel insights into the magnitude, processes, and contexts of biocrust effects in drylands. This information is critical to improve our capacity to manage dwindling dryland water supplies as Earth becomes hotter and drier.

Amphetamine-induced striatal dopamine release in schizotypal personality disorder - Judy L. Thompson; Daniel R. Rosell; Mark Slifstein; Xiaoyan Xu; Ethan G. Rothstein; Yosefa A. Modiano; Lawrence S. Kegeles; Harold W. Koenigsberg; Antonia S. New; Erin A. Hazlett; Margaret M. McClure; M. Mercedes Perez-Rodriguez; et al. (Psychopharmacology, 2020)

UAVs for monitoring, investigation, and mitigation design of a rock slope with multiple failure mechanisms—a case study - J. Rodriguez; R. Macciotta; M. T. Hendry; M. Roustaei; C. Gräpel; R. Skirrow (Landslides, 2020)

Human carnosinase 1 overexpression aggravates diabetes and renal impairment in BTBROb/Ob mice - Jiedong Qiu; Thomas Albrecht; Shiqi Zhang; Sibylle J. Hauske; Angelica Rodriguez-Niño; Xinmiao Zhang; Darya Nosan; Diego O. Pastene; Carsten Sticht; Carolina Delatorre; Harry van Goor; Stefan Porubsky; et al. (Journal of Molecular Medicine, 2020)
Objective To assess the influence of serum carnosinase (CN1) on the course of diabetic kidney disease (DKD). Methods hCN1 transgenic (TG) mice were generated in a BTBR Ob/Ob genetic background to allow the spontaneous development of DKD in the presence of serum carnosinase. The influence of serum CN1 expression on obesity, hyperglycemia, and renal impairment was assessed. We also studied if aggravation of renal impairment in hCN1 TG BTBR Ob/Ob mice leads to changes in the renal transcriptome as compared with wild-type BTBR Ob/Ob mice. Results hCN1 was detected in the serum and urine of mice from two different hCN1 TG lines. The transgene was expressed in the liver but not in the kidney. High CN1 expression was associated with low plasma and renal carnosine concentrations, even after oral carnosine supplementation. Obese hCN1 transgenic BTBR Ob/Ob mice displayed significantly higher levels of glycated hemoglobin, glycosuria, proteinuria, and increased albumin-creatinine ratios (1104 ± 696 vs 492.1 ± 282.2 μg/mg) accompanied by an increased glomerular tuft area and renal corpuscle size. Gene-expression profiling of renal tissue disclosed hierarchical clustering between BTBR Ob/Wt , BTBR Ob/Ob, and hCN1 BTBR Ob/Ob mice. Along with aggravation of the DKD phenotype, 26 altered genes have been found in obese hCN1 transgenic mice; among them claudin-1, thrombospondin-1, nephronectin, and peroxisome proliferator–activated receptor-alpha have been reported to play essential roles in DKD. Conclusions Our data support a role for serum carnosinase 1 in the progression of DKD. Whether this is mainly attributed to the changes in renal carnosine concentrations warrants further studies. Key messages Increased carnosinase 1 (CN1) is associated with diabetic kidney disease (DKD). BTBR Ob/Ob mice with human CN1 develop a more aggravated DKD phenotype. Microarray revealed alterations by CN1 which are not altered by hyperglycemia. These genes have been described to play essential roles in DKD. Inhibiting CN1 could be beneficial in DKD.

Mislocalization of SMN from the I-band and M-band in human skeletal myofibers in spinal muscular atrophy associates with primary structural alterations of the sarcomere - María T. Berciano; María S. Castillo-Iglesias; J. Fernando Val-Bernal; Vanesa Lafarga; José C. Rodriguez-Rey; Miguel Lafarga; Olga Tapia (Cell and Tissue Research, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Compound-specific δ2H analysis highlights the relationship between direct assimilation and de novo synthesis of amino acids from food and water in a terrestrial mammalian omnivore - Seth D. Newsome; Bobby J. Nakamoto; Mauriel Rodriguez Curras; Marilyn L. Fogel (Oecologia, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Development of a drinking water quality index based on a participatory procedure using mixed multicriteria methods - Anna Scheili; Ianis Delpla; Manuel J. Rodriguez (Environmental Monitoring and Assessment, 2020)

Predicting unregulated disinfection by-products in small water distribution networks: an empirical modelling framework - Haroon R. Mian; Gyan Chhipi-Shrestha; Kasun Hewage; Manuel J. Rodriguez; Rehan Sadiq (Environmental Monitoring and Assessment, 2020)

Microbiome of the deep Lake Baikal, a unique oxic bathypelagic habitat - Pedro J. Cabello‐Yeves; Tamara I. Zemskaya; Alexandra S. Zakharenko; Mariya V. Sakirko; Vyacheslav G. Ivanov; Rohit Ghai; Francisco Rodriguez‐Valera (Limnology and Oceanography, 2020)
Lake Baikal is the deepest lake in the world. Its depth provides the only bathypelagic (> 1000 m deep) freshwater habitat on Earth and its oxic, ultra‐oligotrophic features make it a freshwater counterpart of the deep ocean. Here we have analyzed metagenomes from 1250 and 1350 m deep samples and built 231 metagenome‐assembled genomes (MAGs). We detected high fractions of Thaumarchaeota (ca. 20% of 16S rRNA reads) and members of the candidate phyla radiation (CPR) (3–4.5%). Among the MAGs, we obtained ammonia‐oxidizing archaea (AOA, Nitrosopumilaceae) and bacteria (AOB, Nitrosomonadaceae), and nitrite‐oxidizers (Nitrospirae) indicating very active nitrification. A new clade of freshwater SAR202 Chloroflexi and methanotrophs ( Methyloglobulus ) were also remarkably abundant, the latter reflecting a possible role of methane oxidation as well. Novel species of streamlined and cosmopolitan bacteria such as Ca. Fonsibacter or acI Actinobacteria were more abundant at the surface but also present in deep waters. Conversely, CPRs, Myxococcales, Chloroflexi, DPANN (Diapherotrites, Parvarchaeota, Aenigmarchaeota, Nanoarchaeota and Nanohaloarchaeota) archaea, or Gammaproteobacteria were found only in bathypelagic samples. We noted various important taxonomic and metabolic differences between deep aphotic region of Lake Baikal and marine waters of similar depth: Betaproteobacteriales, CPR, and DPANN superphylum were only found in bathypelagic Baikal, while Deltaproteobacteria, Gammaproteobacteria, or Alphaproteobacteria prevailed in oceanic samples. The genes mediating ammonia and methane oxidation, aromatic compound degradation, or alkane/methanesulfonate monooxygenases were detected in higher numbers in deep Baikal compared to their oceanic counterparts or its own surface. Overall, depth seems to be less relevant than salinity in configuring the microbial community.

Three-dimensional regional bi-ventricular shape remodeling is associated with exercise capacity in endurance athletes - G. Bernardino; M. Sanz de la Garza; B. Domenech-Ximenos; S. Prat-Gonzàlez; R. J. Perea; I. Blanco; F. Burgos; A. Sepulveda-Martinez; M. Rodriguez-Lopez; F. Crispi; C. Butakoff; M. A. González Ballester; et al. (European Journal of Applied Physiology, 2020)

A Metabolic Intravascular Platform to Study FDG Uptake in Vascular Injury - F. Franchi; M. Olthoff; J. Krier; C. Noble; M. Al-Hijji; V. Ramaswamy; T. Witt; M. Burke; M. Benscoter; A. Lerman; G. S. Sandhu; M. Rodriguez-Porcel (Cardiovascular Engineering and Technology, 2020)

Genetic Ablation of Hematopoietic Cell Kinase Accelerates Alzheimer’s Disease–Like Neuropathology in Tg2576 Mice - Siok Lam Lim; Diana Nguyen Tran; Zanett Kieu; Christine Chen; Emmanuel Villanueva; Sagar Ghiaar; Victoria Gallup; Joannee Zumkehr; David H. Cribbs; Carlos J. Rodriguez-Ortiz; Masashi Kitazawa (Molecular Neurobiology, 2020)

Diabetes and cardiovascular disease mortality among a population-based cohort of women with and without breast cancer - Luis A. Rodriguez; Patrick T. Bradshaw; Humberto Parada; Nikhil K. Khankari; Tengteng Wang; Rebecca J. Cleveland; Susan L. Teitelbaum; Alfred I. Neugut; Marilie D. Gammon (Cancer Causes & Control, 2020)

Ecogenomics of the SAR11 clade - Jose M. Haro‐Moreno; Francisco Rodriguez‐Valera; Riccardo Rosselli; Francisco Martinez‐Hernandez; Juan J. Roda‐Garcia; Monica Lluesma Gomez; Oscar Fornas; Manuel Martinez‐Garcia; Mario López‐Pérez (Environmental Microbiology, 2020)
Summary Members of the SAR11 clade, despite their high abundance, are often poorly represented by metagenome‐assembled genomes. This fact has hampered our knowledge about their ecology and genetic diversity. Here we examined 175 SAR11 genomes, including 47 new single‐amplified genomes. The presence of the first genomes associated with subclade IV suggests that, in the same way as subclade V, they might be outside the proposed Pelagibacterales order. An expanded phylogenomic classification together with patterns of metagenomic recruitment at a global scale have allowed us to define new ecogenomic units of classification (genomospecies), appearing at different, and sometimes restricted, metagenomic data sets. We detected greater microdiversity across the water column at a single location than in samples collected from similar depth across the global ocean, suggesting little influence of biogeography. In addition, pangenome analysis revealed that the flexible genome was essential to shape genomospecies distribution. In one genomospecies preferentially found within the Mediterranean, a set of genes involved in phosphonate utilization was detected. While another, with a more cosmopolitan distribution, was unique in having an aerobic purine degradation pathway. Together, these results provide a glimpse of the enormous genomic diversity within this clade at a finer resolution than the currently defined clades.

Sub-Arctic Field Degradation of Metsulfuron-Methyl in Two Alaskan Soils and Microbial Community Composition Effects - Patrick L. Tomco; Steven S. Seefeldt; Katinna Rodriguez-Baisi; Jasmine J. Hatton; Khrystyne N. Duddleston (Water, Air, & Soil Pollution, 2020)

Sexual recombination within the “Kranich” race of the yellow rust fungus Puccinia striiformis f.sp. tritici on Berberis vulgaris - J. Rodriguez-Algaba; M. S. Hovmøller; A. F. Justesen (European Journal of Plant Pathology, 2020)

Evaluating the performance of freshwater macroalgae in the bioremediation of nutrient-enriched water in temperate environments - J. M. Valero-Rodriguez; S. E. Swearer; T. Dempster; R. de Nys; A. J. Cole (Journal of Applied Phycology, 2020)

SPEXOR passive spinal exoskeleton decreases metabolic cost during symmetric repetitive lifting - S. J. Baltrusch; J. H. van Dieën; A. S. Koopman; M. B. Näf; C. Rodriguez-Guerrero; J. Babič; H. Houdijk (European Journal of Applied Physiology, 2020)

Synergistic effects of quenching agents and pH on the stability of regulated and unregulated disinfection by-products for drinking water quality monitoring - Jianan Gao; Francois Proulx; Manuel J. Rodriguez (Environmental Monitoring and Assessment, 2020)

Development of a Co2+/PMS process involving target contaminant degradation and PMS decomposition - O. M. Rodriguez-Narvaez; M. O. A. Pacheco-Alvarez; K. Wróbel; J. Páramo-Vargas; E. R. Bandala; E. Brillas; J. M. Peralta-Hernandez (International Journal of Environmental Science and Technology, 2020)

Annual bacterial community cycle in a seasonally ice‐covered river reflects environmental and climatic conditions - Perrine Cruaud; Adrien Vigneron; Marie‐Stéphanie Fradette; Caetano C. Dorea; Alexander I. Culley; Manuel J. Rodriguez; Steve J. Charette (Limnology and Oceanography, 2020)
Bacteria are key players in biogeochemical cycles and control water quality in freshwater ecosystems. Nevertheless, little is known about the identity and ecology of riverine bacteria, especially during ice‐covered periods that are often mistakenly perceived as periods with negligible biological activities. Here, we analyzed in detail the effects of environmental and climatic conditions on freshwater bacterial community structure and diversity over a 2‐yr sampling campaign, targeting a seasonally ice‐covered river of the Quebec City (Canada) area, the Saint‐Charles River. Quantitative polymerase chain reaction and 16S ribosomal RNA gene high‐throughput sequencing demonstrated a strong seasonal cycle of the bacterial community composition with rapid successions of bacterial lineages, reflecting the harsh climatic condition of the region. During the summer, the bacterial community was dominated by typical freshwater microorganisms such as Limnohabitans , Sporichthyaceae hgcI/acI clade, and Pseudarcicella . In contrast, the results suggest that during the cold season, the low water temperatures, combined with other prevailing conditions such as reduced light availability and minimal particulate inputs from the catchment, created various environmental niches for potential methanotrophic Gammaproteobacteria , such as Crenothrix and Methylobacter , other Betaproteobacteria , such as Candidatus Methylopumilus, Candidatus Nitrotoga, and Rhodoferax, as well as Verrucomicrobia and Parcubacteria . The presence of these taxa in the winter suggests active carbon, iron, and nitrogen cycling under ice, whereas summer lineages are dormant or in a phase of reduced activity. These results increase our understanding of bacterial dynamic and potential metabolic processes occurring in seasonally ice‐covered inland waters, providing evidence that winter can be an especially important period for freshwater ecological processes.

Design of an Adaptive Sliding Mode Control for a Micro-AUV Subject to Water Currents and Parametric Uncertainties - Jonathan Rodriguez; Herman Castañeda; J. L. Gordillo (Journal of Marine Science and Engineering, 2019)
This paper addresses the design of an adaptive sliding mode control for an autonomous underwater vehicle with the objective to reject bounded internal and external perturbations. The proposed control is used to achieve velocity regulation and autonomous path-following using waypoints. Each task is successfully performed in the presence of parametric uncertainties and irrotational water currents. Due to complex dynamics and random external perturbations, underwater vehicles need robust control. The closed-loop stability and finite-time convergence of the system are demonstrated using the Lyapunov direct method. To provide a detailed and realistic testing environment for the proposed adaptive controller, a dynamic model of the vehicle using the Lagrange method is derived where all underwater effects are included. On that basis, the proposed adaptive sliding mode controller is compared to its non-adaptive equivalent and PD (Proportional Derivative) computed torque control. The simulation results demonstrate that the proposed adaptive control has better robustness and precision for this particular type of vehicle.

A comparison of regional brain volumes and white matter connectivity in subjects with stimulant induced psychosis versus schizophrenia - Peter D. Alexander; Kristina M. Gicas; Alex Cheng; Donna J. Lang; Ric M. Procyshyn; Alexandra T. Vertinsky; William J. Panenka; Allen E. Thornton; Alexander Rauscher; Jamie Y. X. Wong; Tasha Chan; Andrea A. Jones; et al. (Psychopharmacology, 2019)

Autophagy Stimulation Decreases Dopaminergic Neuronal Death Mediated by Oxidative Stress - Marcela J. Ramirez-Moreno; Ana P. Duarte-Jurado; Yareth Gopar-Cuevas; Alfredo Gonzalez-Alcocer; Maria J. Loera-Arias; Odila Saucedo-Cardenas; Roberto Montes de Oca-Luna; Humberto Rodriguez-Rocha; Aracely Garcia-Garcia (Molecular Neurobiology, 2019)

Free‐living and symbiotic lifestyles of a thermotolerant coral endosymbiont display profoundly distinct transcriptomes under both stable and heat stress conditions - Anthony J. Bellantuono; Katherine E. Dougan; Camila Granados‐Cifuentes; Mauricio Rodriguez‐Lanetty (Molecular Ecology, 2019)
Reef‐building corals depend upon a nutritional endosymbiosis with photosynthetic dinoflagellates of the family Symbiodiniaceae for the majority of their energetic needs. While this mutualistic relationship is impacted by numerous stressors, warming oceans are a predominant threat to coral reefs, placing the future of the world's reefs in peril. Some Symbiodiniaceae species exhibit tolerance to thermal stress, but the in hospite symbiont response to thermal stress is underexplored. To describe the underpinnings of symbiosis and heat stress response, we compared in hospite and free‐living transcriptomes of Durusdinium trenchii , a pan‐tropical heat‐tolerant Symbiodiniaceae species, under stable temperature conditions and acute hyperthermal stress. We discovered that symbiotic state was a larger driver of the transcriptional landscape than heat stress. The majority of differentially expressed transcripts between in hospite and free‐living cells were downregulated, suggesting the in hospite condition is associated with the shutdown of numerous processes uniquely required for a free‐living lifestyle. In the free‐living state, we identified enrichment for numerous cell signalling pathways and other functions related to detecting and responding to a changing environment, as well as transcripts relating to mitosis, meiosis, and motility. In contrast, in hospite cells exhibited enhanced transcriptional activity for photosynthesis and carbohydrate transport as well as chromatin modifications and a disrupted circadian clock. Hyperthermal stress induced drastic alteration of transcriptional activity in hospite, suggesting symbiotic engagement with the host elicited an exacerbated stress response when compared to free‐living D. trenchii . Altogether, the dramatic differences in gene expression between in hospite and free‐living D. trenchii indicate the importance of considering symbiotic state in investigations of symbiosis and hyperthermal stress in Symbiodiniaceae.

Metabolomic profile of cacao cell suspensions growing in blue light/dark conditions with potential in food biotechnology - Adriana M. Gallego; Luisa F. Rojas; Héctor A. Rodriguez; Conrado Mora; Lucía Atehortúa; Aura I. Urrea; Mark J. Guiltinan; Siela N. Maximova; Emmanuel Gaquerel; Martha Zuluaga; Natalia Pabón-Mora (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Australia-Asian monsoon in two versions of the UK Met Office Unified Model and their impacts on tropical–extratropical teleconnections - L. Jin; H. Zhang; A. Moise; G. Martin; S. Milton; J. Rodriguez (Climate Dynamics, 2019)

Energy balance related lifestyle factors and risk of endometrial and colorectal cancer among individuals with lynch syndrome: a systematic review - Adriana M. Coletta; Susan K. Peterson; Leticia A. Gatus; Kate J. Krause; Susan M. Schembre; Susan C. Gilchrist; Mala Pande; Eduardo Vilar; Y. Nancy You; Miguel A. Rodriguez-Bigas; Larkin L. Strong; Patrick M. Lynch; et al. (Familial Cancer, 2019)

Non-native ungulates indirectly impact foliar arthropods but not soil function - Mariano A. Rodriguez-Cabal; M. Noelia Barrios-Garcia; Christopher J. Greyson-Gaito; Heather L. Slinn; M. Paz Tapella; Agustín Vitali; Gregory M. Crutsinger (Biological Invasions, 2019)

Defining the indigenous ranges of species to account for geographic and taxonomic variation in the history of human impacts: reply to Sanderson 2019 - P. J. Stephenson; Molly K. Grace; H. Resit Akçakaya; Ana S. L. Rodrigues; Barney Long; David P. Mallon; Erik Meijaard; Jon Paul Rodriguez; Richard P. Young; Thomas M. Brooks; Craig Hilton‐Taylor (Conservation Biology, 2019)

Reorganization of the nuclear compartments involved in transcription and RNA processing in myonuclei of type I spinal muscular atrophy - María S. Castillo-Iglesias; María T. Berciano; J. Oriol Narcis; J. Fernando Val-Bernal; José C. Rodriguez-Rey; Olga Tapia; Miguel Lafarga (Histochemistry and Cell Biology, 2019)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Halogenated acetaldehydes in water: A review of their occurrence, formation, precursors and control strategies - Jianan Gao; Francois Proulx; Manuel J. Rodriguez (Critical Reviews in Environmental Science and Technology, 2019)

NIR-based Sudan I to IV and Para-Red food adulterants screening - Gimena J. Trentanni Hansen; Johnatan Almonacid; Liliana Albertengo; María Susana Rodriguez; Carolina Di Anibal; Claudio Delrieux (Food Additives & Contaminants: Part A, 2019)

Addressing limitations in existing ‘simplified’ liquefaction triggering evaluation procedures: application to induced seismicity in the Groningen gas field - R. A. Green; J. J. Bommer; A. Rodriguez-Marek; B. W. Maurer; P. J. Stafford; B. Edwards; P. P. Kruiver; G. de Lange; J. van Elk (Bulletin of Earthquake Engineering, 2019)

Phylogenomics of Enterococcus faecalis from wild birds: new insights into host‐associated differences in core and accessory genomes of the species - Ricardo León‐Sampedro; Rosa del Campo; Mercedes Rodriguez‐Baños; Val F. Lanza; María José Pozuelo; Carlos Francés‐Cuesta; Ana P. Tedim; Ana R. Freitas; Carla Novais; Luísa Peixe; Rob J. L. Willems; Jukka Corander; et al. (Environmental Microbiology, 2019)
Summary Wild birds have been suggested to be reservoirs of antimicrobial resistant and/or pathogenic Enterococcus faecalis ( Efs ) strains, but the scarcity of studies and available sequences limit our understanding of the population structure of the species in these hosts. Here, we analysed the clonal and plasmid diversity of 97 Efs isolates from wild migratory birds. We found a high diversity, with most sequence types (STs) being firstly described here, while others were found in other hosts including some predominant in poultry. We found that pheromone‐responsive plasmids predominate in wild bird Efs while 35% of the isolates entirely lack plasmids. Then, to better understand the ecology of the species, the whole genome of fivestrains with known STs (ST82, ST170, ST16 and ST55) were sequenced and compared with all the Efs genomes available in public databases. Using several methods to analyse core and accessory genomes (AccNET, PLACNET, hierBAPS and PANINI), we detected differences in the accessory genome of some lineages (e.g. ST82) demonstrating specific associations with birds. Conversely, the genomes of other Efs lineages exhibited divergence in core and accessory genomes, reflecting different adaptive trajectories in various hosts. This pangenome divergence, horizontal gene transfer events and occasional epidemic peaks could explain the population structure of the species.

Integrated Observations of Global Surface Winds, Currents, and Waves: Requirements and Challenges for the Next Decade - Ana B. Villas Bôas; Fabrice Ardhuin; Alex Ayet; Mark A. Bourassa; Peter Brandt; Betrand Chapron; Bruce D. Cornuelle; J. T. Farrar; Melanie R. Fewings; Baylor Fox-Kemper; Sarah T. Gille; Christine Gommenginger; et al. (Frontiers in Marine Science, 2019)

Genotype-by-environment interactions and the dynamic relationship between tree vitality and height in northern Pinus sylvestris - Ainhoa Calleja-Rodriguez; Bengt Andersson Gull; Harry X. Wu; Tim J. Mullin; Torgny Persson (Tree Genetics & Genomes, 2019)

Bioethanol Production From Sugarcane Bagasse Hemicellulose Hydrolysate by Immobilized S. shehatae in a Fluidized Bed Fermenter Under Magnetic Field - Kelly J. Dussán; Oselys Rodriguez Justo; Victor Haber Perez; Geraldo F. David; Euripedes Garcia Silveira Junior; Silvio S. da Silva (BioEnergy Research, 2019)

Nutritional evaluation and productivity of supplemented sheep grazing in semiarid rangeland of northeastern Brazil - A. R. Araújo; N. M. Rodriguez; Marcos Cláudio Pinheiro Rogério; I. Borges; E. O. S. Saliba; S. A. Santos; R. C. F. F. Pompeu; F. E. P. Fernandes; J. P. Monteiro; J. P. Muir (Tropical Animal Health and Production, 2019)

Simulating rewetting events in intermittent rivers and ephemeral streams: A global analysis of leached nutrients and organic matter - Oleksandra Shumilova; Dominik Zak; Thibault Datry; Daniel von Schiller; Roland Corti; Arnaud Foulquier; Biel Obrador; Klement Tockner; Daniel C. Allan; Florian Altermatt; María Isabel Arce; Shai Arnon; et al. (Global Change Biology, 2019)
Climate change and human pressures are changing the global distribution and the extent of intermittent rivers and ephemeral streams (IRES), which comprise half of the global river network area. IRES are characterized by periods of flow cessation, during which channel substrates accumulate and undergo physico‐chemical changes (preconditioning), and periods of flow resumption, when these substrates are rewetted and release pulses of dissolved nutrients and organic matter (OM). However, there are no estimates of the amounts and quality of leached substances, nor is there information on the underlying environmental constraints operating at the global scale. We experimentally simulated, under standard laboratory conditions, rewetting of leaves, riverbed sediments, and epilithic biofilms collected during the dry phase across 205 IRES from five major climate zones. We determined the amounts and qualitative characteristics of the leached nutrients and OM, and estimated their areal fluxes from riverbeds. In addition, we evaluated the variance in leachate characteristics in relation to selected environmental variables and substrate characteristics. We found that sediments, due to their large quantities within riverbeds, contribute most to the overall flux of dissolved substances during rewetting events (56%–98%), and that flux rates distinctly differ among climate zones. Dissolved organic carbon, phenolics, and nitrate contributed most to the areal fluxes. The largest amounts of leached substances were found in the continental climate zone, coinciding with the lowest potential bioavailability of the leached OM. The opposite pattern was found in the arid zone. Environmental variables expected to be modified under climate change (i.e. potential evapotranspiration, aridity, dry period duration, land use) were correlated with the amount of leached substances, with the strongest relationship found for sediments. These results show that the role of IRES should be accounted for in global biogeochemical cycles, especially because prevalence of IRES will increase due to increasing severity of drying events.

Bottom boundary layer cooling and wind‐driven upwelling enhance the catchability of spanner crab ( Ranina ranina ) in South‐East Queensland, Australia - David M. Spencer; Ian W. Brown; Mark J. Doubell; Christopher J. Brown; Ana Redondo Rodriguez; Shing Yip Lee; Hong Zhang; Charles J. Lemckert (Fisheries Oceanography, 2019)
Species catchability is an important parameter used to help optimise stock assessment modelling and the economic efficiency of commercial fishing operations. Previous studies have shown several physical oceanographic parameters, including ambient temperature, waves and currents, affect the catchability of spanner crabs ( Ranina ranina ) throughout the Indo‐Pacific. Most notably in the Australian fishery, where oceanographic processes vary over space and time, a positive relationship between bottom boundary layer temperature ( BBLT ) and catch rates was observed. Here, we aimed to better understand how localised oceanographic processes affected this relationship in the southernmost South‐East Queensland ( SEQ ) sector of the Australian fishery at seasonal and short temporal scales. Our results show cooler BBLT , upwelling‐favourable alongshore wind stress and increased catch rates occurred during mating season in austral spring. At the end of austral summer, BBLT began warming, downwelling‐favourable winds were dominant, and catch rates declined around the post‐moult period. Outputs from the generalised linear models ( GLM s) that separated these effects in each season show that, at shorter temporal scales, daily catch rates also increased with episodic BBLT cooling and upwelling‐favourable alongshore wind stress, but only during austral autumn and winter. These new findings suggest that region‐specific, short‐term and seasonal variability of oceanographic processes responsible for changes in BBLT play an important role in influencing the catchability of spanner crabs. We suggest that the effects of region‐specific physical oceanographic processes must be considered in future work when investigating the catchability of commercially important fisheries species fished over large spatial domains.

Long-term improvement in renal, bone, lipid parameters, and CD4/CD8 ratio in HIV-infected patients switching to a dual therapy with lamivudine plus boosted darunavir - María Fontecha; Marta Monsalvo; Miguel A. Rodriguez-Sagrado; María J. Vivancos; Ana Moreno; José L. Casado (Infectious Diseases, 2019)

Source relationships between streambank soils and streambed sediments in a mercury-contaminated stream - Johnbull O. Dickson; Melanie A. Mayes; Scott C. Brooks; Tonia L. Mehlhorn; Kenneth A. Lowe; Jennifer K. Earles; Leroy Goñez-Rodriguez; David B. Watson; Mark J. Peterson (Journal of Soils and Sediments, 2019)

Doubting dung: eDNA reveals high rates of misidentification in diverse European ungulate communities - Robert Spitzer; Marcin Churski; Annika Felton; Marco Heurich; Dries P. J. Kuijper; Marietjie Landman; Esther Rodriguez; Navinder J. Singh; Pierre Taberlet; Suzanne T. S. van Beeck Calkoen; Fredrik Widemo; Joris P. G. M. Cromsigt (European Journal of Wildlife Research, 2019)

Drinking Water Source Monitoring Using Early Warning Systems Based on Data Mining Techniques - Ianis Delpla; Mihai Florea; Manuel J. Rodriguez (Water Resources Management, 2019)

Lichen species assemblage gradient in South Shetlands Islands, Antarctica: relationship to deglaciation and microsite conditions - J. M. Rodriguez; A. Passo; J. O. Chiapella (Polar Biology, 2018)

Serum P-glycoprotein level: a potential biomarker of DMARD failure in patients with rheumatoid arthritis - E. E. Perez-Guerrero; L. Gonzalez-Lopez; J. F. Muñoz-Valle; J. C. Vasquez-Jimenez; M. Ramirez-Villafaña; E. N. Sanchez-Rodriguez; S. R. Gutierrez-Ureña; S. Cerpa-Cruz; E. A. Aguilar-Chavez; E. G. Cardona-Muñoz; M. L. Vazquez-Villegas; A. M. Saldaña-Cruz; et al. (Inflammopharmacology, 2018)

Removal of imidazolium- and pyridinium-based ionic liquids by Fenton oxidation - Esther Gomez-Herrero; Montserrat Tobajas; Alicia Polo; Juan J. Rodriguez; Angel F. Mohedano (Environmental Science and Pollution Research, 2018)

Genetic diversity and cultivar variants in the NCGR cranberry (Vaccinium macrocarpon Aiton) collection - B. Schlautman; G. Covarrubias-Pazaran; L. Rodriguez-Bonilla; K. Hummer; N. Bassil; T. Smith; J. Zalapa (Journal of Genetics, 2018)

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Relationships between variability in precipitation, river levels, and beef cattle production in the Brazilian Pantanal - Ana Gabriela de J. Araujo; Guillermo O. Obregón; Gilvan Sampaio; Antonio Miguel V. Monteiro; Luiz Tadeu da Silva; Balbina Soriano; Carlos Padovani; Daniel Andres Rodriguez; Jelena Maksic; José Felipe Silva Farias (Wetlands Ecology and Management, 2018)

Invasive Rhinosinusitis Caused by Lasiodiplodia theobromae in an Allogeneic Hematopoietic Cell Transplant Recipient Case Report and Review of Literature - Anamaria Rodriguez; Shweta Anjan; Octavio V. Martinez; Lazaros J. Lekakis; Amer Beitinjaneh; Jose F. Camargo; Connie F. C. Gibas; Carmita J. Sanders; Nathan P. Wiederhold; Lilian M. Abbo (Mycopathologia, 2018)

Comparing the impact of a grazing regime with European bison versus one with free-ranging cattle on coastal dune vegetation in the Netherlands - E. Valdés-Correcher; Esther Rodriguez; Yvonne J. M. Kemp; Martin J. Wassen; Joris P. G. M. Cromsigt (Mammal Research, 2018)

Activated carbon as catalyst for microwave-assisted wet peroxide oxidation of aromatic hydrocarbons - Alicia L. Garcia-Costa; Lucia Lopez-Perela; Xiyan Xu; Juan A. Zazo; Juan J. Rodriguez; Jose A. Casas (Environmental Science and Pollution Research, 2018)

Ecological and genomic features of two widespread freshwater picocyanobacteria - Pedro J. Cabello‐Yeves; Antonio Picazo; Antonio Camacho; Cristiana Callieri; Riccardo Rosselli; Juan J. Roda‐Garcia; Felipe H. Coutinho; Francisco Rodriguez‐Valera (Environmental Microbiology, 2018)
Summary We present two genomes of widespread freshwater picocyanobacteria isolated by extinction dilution from a Spanish oligotrophic reservoir. Based on microscopy and genomic properties, both picocyanobacteria were tentatively designated Synechococcus lacustris Tous, formerly described as a metagenome assembled genome (MAG) from the same habitat, and Cyanobium usitatum Tous, described here for the first time. Both strains were purified in unicyanobacterial cultures, and their genomes were sequenced. They are broadly distributed in freshwater systems; the first seems to be a specialist on temperate reservoirs (Tous, Amadorio, Dexter, Lake Lanier, Sparkling), and the second appears to also be abundant in cold environments including ice‐covered lakes such as Lake Baikal, Lake Erie or the brackish Baltic Sea. Having complete genomes provided access to the flexible genome that does not assemble in MAGs. We found several genomic islands in both genomes, within which there were genes for nitrogen acquisition, transporters for a wide set of compounds and biosynthesis of phycobilisomes in both strains. Some of these regions of low coverage in metagenomes also included antimicrobial compounds, transposases and phage defence systems, including a novel type III CRISPR‐Cas phage defence system that was only detected in Synechococcus lacustris Tous.

Bidirectional Neural Interaction Between Central Dopaminergic and Gut Lesions in Parkinson’s Disease Models - Pablo Garrido-Gil; Ana I. Rodriguez-Perez; Antonio Dominguez-Meijide; Maria J. Guerra; Jose L. Labandeira-Garcia (Molecular Neurobiology, 2018)

Invasive pulmonary aspergillosis is associated with adverse clinical outcomes in critically ill patients receiving veno-venous extracorporeal membrane oxygenation - I. Rodriguez-Goncer; S. Thomas; P. Foden; M. D. Richardson; A. Ashworth; J. Barker; C. G. Geraghty; E. G. Muldoon; T. W. Felton (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

The impact of depuration on mussel hepatopancreas bacteriome composition and predicted metagenome - J. A. Rubiolo; A. Lozano-Leon; R. Rodriguez-Souto; N. Fol Rodríguez; M. R. Vieytes; L. M. Botana (Antonie van Leeuwenhoek, 2018)

Computational Investigation of a Self-Powered Fontan Circulation - Marcus W. Ni; Ray O. Prather; Giovanna Rodriguez; Rachel Quinn; Eduardo Divo; Mark Fogel; Alain J. Kassab; William M. DeCampli (Cardiovascular Engineering and Technology, 2018)

Controlling the mechanoelasticity of model biomembranes with room-temperature ionic liquids - Chiara Rotella; Pallavi Kumari; Brian J. Rodriguez; Suzanne P. Jarvis; Antonio Benedetto (Biophysical Reviews, 2018)

Characterisation of ground motion recording stations in the Groningen gas field - Rik Noorlandt; Pauline P. Kruiver; Marco P. E. de Kleine; Marios Karaoulis; Ger de Lange; Antonio Di Matteo; Julius von Ketelhodt; Elmer Ruigrok; Benjamin Edwards; Adrian Rodriguez-Marek; Julian J. Bommer; Jan van Elk; et al. (Journal of Seismology, 2018)

How can leadership processes in European bison be used to improve the management of free-roaming herds - Amandine Ramos; Lola Manizan; Esther Rodriguez; Yvonne J. M. Kemp; Cédric Sueur (European Journal of Wildlife Research, 2018)

Adapting clonally propagated crops to climatic changes: a global approach for taro (Colocasia esculenta (L.) Schott) - V. Lebot; V. Tuia; A. Ivancic; G. V. H. Jackson; F. Saborio; G. Reyes; S. Rodriguez; G. Robin; R. Traoré; L. Aboagye; J. Onyeka; W. van Rensburg; et al. (Genetic Resources and Crop Evolution, 2018)

Brain-specific HIV Nef identified in multiple patients with neurological disease - Susanna L. Lamers; Gary B. Fogel; Enoch S. Liu; Andrew E. Barbier; Christopher W. Rodriguez; Elyse J. Singer; David J. Nolan; Rebecca Rose; Michael S. McGrath (Journal of NeuroVirology, 2018)

Anisotropic larval connectivity and metapopulation structure driven by directional oceanic currents in a marine fish targeted by small-scale fisheries - Adrian Munguia-Vega; S. Guido Marinone; David A. Paz-Garcia; Alfredo Giron-Nava; Tomas Plomozo-Lugo; Ollin Gonzalez-Cuellar; Amy Hudson Weaver; Francisco J. García-Rodriguez; Hector Reyes-Bonilla (Marine Biology, 2018)

Volume electron microscopy of the distribution of synapses in the neuropil of the juvenile rat somatosensory cortex - A. Santuy; J. R. Rodriguez; J. DeFelipe; A. Merchan-Perez (Brain Structure and Function, 2018)

Impact of rapid diagnosis of Staphylococcus aureus bacteremia from positive blood cultures on patient management - M. P. Romero-Gómez; E. Cendejas-Bueno; J. García Rodriguez; J. Mingorance (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Ocular flutter following Zika virus infection - Emely Karam; Jose Giraldo; Flor Rodriguez; Carlos E. Hernandez-Pereira; Alfonso J. Rodriguez-Morales; Gabriela M. Blohm; Alberto E. Paniz-Mondolfi (Journal of NeuroVirology, 2017)

Models for estimation of the presence of non-regulated disinfection by-products in small drinking water systems - Stéphanie Guilherme; Manuel J. Rodriguez (Environmental Monitoring and Assessment, 2017)

Autonomous Coral Reef Survey in Support of Remote Sensing - Steven G. Ackleson; Joseph P. Smith; Luis M. Rodriguez; Wesley J. Moses; Brandon J. Russell (Frontiers in Marine Science, 2017)

Wnts Are Expressed in the Ependymal Region of the Adult Spinal Cord - Carlos Gonzalez-Fernandez; Angel Arevalo-Martin; Beatriz Paniagua-Torija; Isidro Ferrer; Francisco J. Rodriguez; Daniel Garcia-Ovejero (Molecular Neurobiology, 2017)

Photosynthetic performance and pigment composition of Macrocystis pyrifera (Laminariales, Phaeophyceae) along a gradient of depth and seasonality in the ecoregion of Magellan, Chile - J. Marambio; J. P. Rodriguez; F. Mendez; P. Ocaranza; S. Rosenfeld; J. Ojeda; R. Rautenberger; K. Bischof; J. Terrados; A. Mansilla (Journal of Applied Phycology, 2017)

Nutritional properties of dishes prepared with sub-Antarctic macroalgae—an opportunity for healthy eating - Ma. S. Astorga-España; A. Mansilla; J. Ojeda; J. Marambio; S. Rosenfeld; F. Mendez; J. P. Rodriguez; P. Ocaranza (Journal of Applied Phycology, 2017)

Aerobic interval training reduces vascular resistances during submaximal exercise in obese metabolic syndrome individuals - Ricardo Mora-Rodriguez; V. E. Fernandez-Elias; F. Morales-Palomo; J. G. Pallares; M. Ramirez-Jimenez; J. F. Ortega (European Journal of Applied Physiology, 2017)

CO 2 exchange and evapotranspiration across dryland ecosystems of southwestern North America - Joel A. Biederman; Russell L. Scott; Tom W. Bell; David R. Bowling; Sabina Dore; Jaime Garatuza‐Payan; Thomas E. Kolb; Praveena Krishnan; Dan J. Krofcheck; Marcy E. Litvak; Gregory E. Maurer; Tilden P. Meyers; et al. (Global Change Biology, 2017)
Global‐scale studies suggest that dryland ecosystems dominate an increasing trend in the magnitude and interannual variability of the land CO 2 sink. However, such analyses are poorly constrained by measured CO 2 exchange in drylands. Here we address this observation gap with eddy covariance data from 25 sites in the water‐limited Southwest region of North America with observed ranges in annual precipitation of 100–1000 mm, annual temperatures of 2–25°C, and records of 3–10 years (150 site‐years in total). Annual fluxes were integrated using site‐specific ecohydrologic years to group precipitation with resulting ecosystem exchanges. We found a wide range of carbon sink/source function, with mean annual net ecosystem production ( NEP ) varying from ‐350 to +330 gC m −2 across sites with diverse vegetation types, contrasting with the more constant sink typically measured in mesic ecosystems. In this region, only forest‐dominated sites were consistent carbon sinks. Interannual variability of NEP , gross ecosystem production ( GEP ), and ecosystem respiration (R eco ) was larger than for mesic regions, and half the sites switched between functioning as C sinks/C sources in wet/dry years. The sites demonstrated coherent responses of GEP and NEP to anomalies in annual evapotranspiration ( ET ), used here as a proxy for annually available water after hydrologic losses. Notably, GEP and R eco were negatively related to temperature, both interannually within site and spatially across sites, in contrast to positive temperature effects commonly reported for mesic ecosystems. Models based on MODIS satellite observations matched the cross‐site spatial pattern in mean annual GEP but consistently underestimated mean annual ET by ~50%. Importantly, the MODIS ‐based models captured only 20–30% of interannual variation magnitude. These results suggest the contribution of this dryland region to variability of regional to global CO 2 exchange may be up to 3–5 times larger than current estimates.

Minimizing the impacts of contaminant intrusion in small water distribution networks through booster chlorination optimization - Nilufar Islam; Manuel J. Rodriguez; Ashraf Farahat; Rehan Sadiq (Stochastic Environmental Research and Risk Assessment, 2017)

Imaging Markers of Post-Stroke Depression and Apathy: a Systematic Review and Meta-Analysis - Elles Douven; Sebastian Köhler; Maria M. F. Rodriguez; Julie Staals; Frans R. J. Verhey; Pauline Aalten (Neuropsychology Review, 2017)

Ventilator-associated pneumonia by methicillin-susceptible Staphylococcus aureus: do minimum inhibitory concentrations to vancomycin and daptomycin matter? - J. Ruiz-Ramos; P. Vidal-Cortés; A. Díaz-Lamas; R. Reig-Valero; F. Roche-Campo; M. Del Valle-Ortiz; X. Nuvials-Casals; M. Ortiz-Piquer; D. Andaluz-Ojeda; L. Tamayo-Lomas; M. A. Blasco-Navalpotro; M. Rodriguez-Aguirregabiria; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Small drinking water systems under spatiotemporal water quality variability: a risk-based performance benchmarking framework - Ty Bereskie; Husnain Haider; Manuel J. Rodriguez; Rehan Sadiq (Environmental Monitoring and Assessment, 2017)

An integrated shear-wave velocity model for the Groningen gas field, The Netherlands - Pauline P. Kruiver; Ewoud van Dedem; Remco Romijn; Ger de Lange; Mandy Korff; Jan Stafleu; Jan L. Gunnink; Adrian Rodriguez-Marek; Julian J. Bommer; Jan van Elk; Dirk Doornhof (Bulletin of Earthquake Engineering, 2017)

An overview on the application of advanced oxidation processes for the removal of naphthenic acids from water - Xiyan Xu; Gema Pliego; Juan A. Zazo; Shibo Sun; Patricia García-Muñoz; Li He; Jose A. Casas; Juan J. Rodriguez (Critical Reviews in Environmental Science and Technology, 2017)

Advantage of multispectral imaging with sub-centimeter resolution in precision agriculture: generalization of training for supervised classification - F. Rodriguez-Moreno; J. Kren; F. Zemek; J. Novak; V. Lukas; M. Pikl (Precision Agriculture, 2017)

Satellite Remote Sensing for Coastal Management: A Review of Successful Applications - Matthew J. McCarthy; Kaitlyn E. Colna; Mahmoud M. El-Mezayen; Abdiel E. Laureano-Rosario; Pablo Méndez-Lázaro; Daniel B. Otis; Gerardo Toro-Farmer; Maria Vega-Rodriguez; Frank E. Muller-Karger (Environmental Management, 2017)

Drinking Water Management and Governance in Canada: An Innovative Plan-Do-Check-Act (PDCA) Framework for a Safe Drinking Water Supply - Ty Bereskie; Manuel J. Rodriguez; Rehan Sadiq (Environmental Management, 2017)

Effects of diurnal temperature range and drought on wheat yield in Spain - S. Hernandez-Barrera; C. Rodriguez-Puebla; A. J. Challinor (Theoretical and Applied Climatology, 2017)

Progressive Neuronal Pathology and Synaptic Loss Induced by Prediabetes and Type 2 Diabetes in a Mouse Model of Alzheimer’s Disease - Juan Jose Ramos-Rodriguez; Tara Spires-Jones; Amy M. Pooler; Alfonso Maria Lechuga-Sancho; Brian J. Bacskai; Monica Garcia-Alloza (Molecular Neurobiology, 2017)

Ambulatory blood pressure response to a bout of HIIT in metabolic syndrome patients - M. Ramirez-Jimenez; F. Morales-Palomo; J. G. Pallares; Ricardo Mora-Rodriguez; J. F. Ortega (European Journal of Applied Physiology, 2017)

Risk-based framework for optimizing residual chlorine in large water distribution systems - Muhammad Nadeem Sharif; Ashraf Farahat; Husnain Haider; Muhammad A. Al-Zahrani; Manuel J. Rodriguez; Rehan Sadiq (Environmental Monitoring and Assessment, 2017)

Behaviour of two typical stents towards a new stent evolution - M. Simão; J. M. Ferreira; J. Mora-Rodriguez; J. Fragata; H. M. Ramos (Medical & Biological Engineering & Computing, 2017)

Adaptation of Shigella flexneri to starvation: morphology, outer membrane proteins and lipopolysaccharide changes - K. Chourabi; F. Torrella; S. Kloula; J. A. Rodriguez; I. Trabelsi; S. Campoy; A. Landoulsi; A. Chatti (Arabian Journal of Geosciences, 2017)

A comparison of psychotic symptoms in subjects with methamphetamine versus cocaine dependence - Peter D Alexander; Kristina M Gicas; Taylor S Willi; Clara N Kim; Veronika Boyeva; Ric M Procyshyn; Geoff N. Smith; Allen E Thornton; William J Panenka; Andrea A. Jones; Fidel Vila-Rodriguez; Donna J. Lang; et al. (Psychopharmacology, 2017)

Does education influence wildlife friendly landscaping preferences? - Shari L. Rodriguez; M. Nils Peterson; Christopher J. Moorman (Urban Ecosystems, 2017)

Occurrence of Photobacterium damselae Subsp. Piscicida in Sea-Cage Farmed Meagre (Argyrosomus regius) in Tenerife, Canary Islands, Spain - J. Z. Costa; Ú. McCarthy; O. Perez; E. Ramos; M. Rodriguez; O. Monterroso; R. Riera (Thalassas: An International Journal of Marine Sciences, 2017)

Seasonal variations of the photosynthetic activity and pigment concentrations in different reproductive phases of Gigartina skottsbergii (Rhodophyta, Gigartinales) in the Magellan region, sub-Antarctic Chile - J. Marambio; F. Mendez; P. Ocaranza; J. P. Rodriguez; S. Rosenfeld; J. Ojeda; S. Murcia; J. Terrados; K. Bischof; A . Mansilla (Journal of Applied Phycology, 2017)

Spatio-temporal monitoring by ground-based and air- and space-borne lidars of a moderate Saharan dust event affecting southern Europe in June 2013 in the framework of the ADRIMED/ChArMEx campaign - R. Barragan; M. Sicard; J. Totems; J. F. Léon; F. Dulac; M. Mallet; J. Pelon; L. Alados-Arboledas; A. Amodeo; P. Augustin; A. Boselli; J. A. Bravo-Aranda; et al. (Air Quality, Atmosphere & Health, 2017)

Expression and biochemical characteristics of two different aldosterone receptors in both healthy and dilated cardiomyopathy dog heart tissue - Alejandro R. Reynoso Palomar; Moncerrat Rodriguez Bravo; Abel E. Villa Mancera; Carlos J. Mucha (Veterinary Research Communications, 2017)

Lizards fail to plastically adjust nesting behavior or thermal tolerance as needed to buffer populations from climate warming - Rory S. Telemeco; Brooke Fletcher; Ofir Levy; Angela Riley; Yesenia Rodriguez‐Sanchez; Colton Smith; Collin Teague; Amanda Waters; Michael J. Angilletta; Lauren B. Buckley (Global Change Biology, 2017)
Although observations suggest the potential for phenotypic plasticity to allow adaptive responses to climate change, few experiments have assessed that potential. Modeling suggests that Sceloporus tristichus lizards will need increased nest depth, shade cover, or embryonic thermal tolerance to avoid reproductive failure resulting from climate change. To test for such plasticity, we experimentally examined how maternal temperatures affect nesting behavior and embryonic thermal sensitivity. The temperature regime that females experienced while gravid did not affect nesting behavior, but warmer temperatures at the time of nesting reduced nest depth. Additionally, embryos from heat‐stressed mothers displayed increased sensitivity to high‐temperature exposure. Simulations suggest that critically low temperatures, rather than high temperatures, historically limit development of our study population. Thus, the plasticity needed to buffer this population has not been under selection. Plasticity will likely fail to compensate for ongoing climate change when such change results in novel stressors.

Consensus Paper: Towards a Systems-Level View of Cerebellar Function: the Interplay Between Cerebellum, Basal Ganglia, and Cortex - Daniele Caligiore; Giovanni Pezzulo; Gianluca Baldassarre; Andreea C. Bostan; Peter L. Strick; Kenji Doya; Rick C. Helmich; Michiel Dirkx; James Houk; Henrik Jörntell; Angel Lago-Rodriguez; Joseph M. Galea; et al. (The Cerebellum, 2017)

Gastrointestinal nematode infection does not affect selection of tropical foliage by goats in a cafeteria trial - J. Ventura-Cordero; P. G. González-Pech; P. R. Jaimez-Rodriguez; G. I. Ortíz-Ocampo; C. A. Sandoval-Castro; J. F. J. Torres-Acosta (Tropical Animal Health and Production, 2017)

Differential Response of a Local Population of Entomopathogenic Nematodes to Non-Native Herbivore Induced Plant Volatiles (HIPV) in the Laboratory and Field - Monique J. Rivera; Cesar Rodriguez-Saona; Hans T. Alborn; Albrecht M. Koppenhöfer (Journal of Chemical Ecology, 2016)

Erratum to: Soft Tissue Phantoms for Realistic Needle Insertion: A Comparative Study - Alexander Leibinger; Antonio E. Forte; Zhengchu Tan; Matthew J. Oldfield; Frank Beyrau; Daniele Dini; Ferdinando Rodriguez y Baena (Annals of Biomedical Engineering, 2016)

A Catalogue of Marine Biodiversity Indicators - Heliana Teixeira; Torsten Berg; Laura Uusitalo; Karin Fürhaupter; Anna-Stiina Heiskanen; Krysia Mazik; Christopher P. Lynam; Suzanna Neville; J. German Rodriguez; Nadia Papadopoulou; Snejana Moncheva; Tanya Churilova; et al. (Frontiers in Marine Science, 2016)

IFITM3 and severe influenza virus infection. No evidence of genetic association - M. López-Rodríguez; E. Herrera-Ramos; J. Solé-Violán; J. J. Ruíz-Hernández; L. Borderías; J. P. Horcajada; E. Lerma-Chippirraz; O. Rajas; M. Briones; M. C. Pérez-González; M. A. García-Bello; E. López-Granados; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Blade life span, structural investment, and nutrient allocation in giant kelp - Gabriel E. Rodriguez; Daniel C. Reed; Sally J. Holbrook (Oecologia, 2016)

Identification of DVT diseases using numerical simulations - M. Simão; J. M. Ferreira; J. Mora-Rodriguez; H. M. Ramos (Medical & Biological Engineering & Computing, 2016)

Free-living culturable bacteria and protozoa from the rhizoplanes of three floating aquatic plant species - E. Quisehuatl-Tepexicuapan; R. Ferrera-Cerrato; H. V. Silva-Rojas; S. Rodriguez-Zaragoza; A. Alarcón; J. J. Almaraz-Suárez (Plant Biosystems, 2016)

Genotype Number and Allelic Diversity Overview in the National Collection of Chilean Potatoes - M. Muñoz; C. Folch; F. Rodriguez; J. Kalazich; S. Orena; J. Santos; R. Vargas; A. Fahrenkrog; A. Puga (Potato Research, 2016)

Neisseria gonorrhoeae antimicrobial susceptibility in Barcelona: penA, ponA, mtrR, and porB mutations and NG-MAST sequence types associated with decreased susceptibility to cephalosporins - J. Serra-Pladevall; M. J. Barberá; S. Rodriguez; R. Bartolomé-Comas; G. Roig; R. Juvé; A. Andreu (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Erratum to: Optimal features for online seizure detection - Lojini Logesparan; Alexander J. Casson; Esther Rodriguez-Villegas (Medical & Biological Engineering & Computing, 2016)

Soil mercury levels in the area surrounding the Cerro Prieto geothermal complex, MEXICO - M. A. Pastrana-Corral; F. T. Wakida; E. García-Flores; D. D. Rodriguez-Mendivil; A. Quiñonez-Plaza; T. D. J. Piñon-Colin (Environmental Monitoring and Assessment, 2016)

Recurrence of progressive multifocal leukoencephalopathy despite immune recovery in two HIV seropositive individuals - Kate M. Crossley; Shruti Agnihotri; Joga Chaganti; Michael L. Rodriguez; Leon Patrick McNally; Nagagopal Venna; Sarah E. Turbett; Matthew Gutman; Adrienne Morey; Igor J. Koralnik; Bruce J. Brew (Journal of NeuroVirology, 2016)

Thalassospira australica sp. nov. isolated from sea water - Elena P. Ivanova; Mario López-Pérez; Hayden K. Webb; Hooi Jun Ng; Thi Hoang Yen Dang; Natalia V. Zhukova; Valery V. Mikhailov; Russell J. Crawford; Francisco Rodriguez-Valera (Antonie van Leeuwenhoek, 2016)

Soft Tissue Phantoms for Realistic Needle Insertion: A Comparative Study - Alexander Leibinger; Antonio E. Forte; Zhengchu Tan; Matthew J. Oldfield; Frank Beyrau; Daniele Dini; Ferdinando Rodriguez y Baena (Annals of Biomedical Engineering, 2016)

Assessing the potential of the European Atlantic sturgeon Acipenser sturio to control bivalve invasions in Europe - N. Ferreira‐Rodriguez; J. Gessner; I. Pardo (Journal of Fish Biology, 2016)
This pilot study explored the potential of juvenile European Atlantic sturgeon Acipenser sturio to feed on two invasive bivalve species, the Asian clam Corbicula fluminea and the Eurasian zebra mussel Dreissena polymorpha . Preliminary results indicate that native A. sturio were feeding on D. polymorpha at a very limited rate and their potential to prevent the establishment of invasive bivalve species, in new and previously invaded areas, is considered limited.

Oregano Essential Oil as an Antimicrobial and Antioxidant Additive in Food Products - I. Rodriguez-Garcia; B.A. Silva-Espinoza; L.A. Ortega-Ramirez; J.M. Leyva; M.W. Siddiqui; M.R. Cruz-Valenzuela; G.A. Gonzalez-Aguilar; J. F. Ayala-Zavala (Critical Reviews in Food Science and Nutrition, 2016)

Optimization of chlorination boosters in drinking water distribution network for Al-Khobar City in Saudi Arabia - Muhammad Nadeem Sharif; Ashraf Farahat; Muhammad A. Al-Zahrani; Nilufar Islam; Manuel J. Rodriguez; Rehan Sadiq (Arabian Journal of Geosciences, 2016)

Amphibian‐killing chytrid in B razil comprises both locally endemic and globally expanding populations - T. S. Jenkinson; C. M. Betancourt Román; C. Lambertini; A. Valencia‐Aguilar; D. Rodriguez; C. H. L. Nunes‐de‐Almeida; J. Ruggeri; A. M. Belasen; D. da Silva Leite; K. R. Zamudio; J. E. Longcore; L. F. Toledo; et al. (Molecular Ecology, 2016)
Chytridiomycosis, caused by the fungus Batrachochytrium dendrobatidis ( Bd ), is the emerging infectious disease implicated in recent population declines and extinctions of amphibian species worldwide. Bd strains from regions of disease‐associated amphibian decline to date have all belonged to a single, hypervirulent clonal genotype ( Bd ‐ GPL ). However, earlier studies in the Atlantic Forest of southeastern Brazil detected a novel, putatively enzootic lineage ( Bd ‐Brazil), and indicated hybridization between Bd ‐ GPL and Bd ‐Brazil. Here, we characterize the spatial distribution and population history of these sympatric lineages in the Brazilian Atlantic Forest. To investigate the genetic structure of Bd in this region, we collected and genotyped Bd strains along a 2400‐km transect of the Atlantic Forest. Bd ‐Brazil genotypes were restricted to a narrow geographic range in the southern Atlantic Forest, while Bd ‐ GPL strains were widespread and largely geographically unstructured. Bd population genetics in this region support the hypothesis that the recently discovered Brazilian lineage is enzootic in the Atlantic Forest of Brazil and that Bd ‐ GPL is a more recently expanded invasive. We collected additional hybrid isolates that demonstrate the recurrence of hybridization between panzootic and enzootic lineages, thereby confirming the existence of a hybrid zone in the Serra da Graciosa mountain range of Paraná State. Our field observations suggest that Bd ‐ GPL may be more infective towards native Brazilian amphibians, and potentially more effective at dispersing across a fragmented landscape. We also provide further evidence of pathogen translocations mediated by the Brazilian ranaculture industry with implications for regulations and policies on global amphibian trade.

Hydrological cycle effects on the aquatic community in a Neotropical stream of the Andean piedmont during the 2007–2010 ENSO events - M. I. Ríos‐Pulgarín; M. Barletta; N. J. Mancera‐Rodriguez (Journal of Fish Biology, 2016)
The seasonal and interannual changes in the fish, macroinvertebrates and phycoperiphyton assemblages of the Guarinó River were examined in relation to the physical and chemical environmental changes associated with the hydrological cycle and the El Niño‐Niña/Southern Oscillation (ENSO) between 2007 and 2010. Four samplings (in dry and rainy seasons) were performed per year. Environmental variables (temperature, pH, conductivity, turbidity, oxygen, total nitrogen, orthophosphate, depth and flow rate) were measured. The temporal patterns of the taxonomic compositions for the three assemblages and the functional composition of fish and macroinvertebrate assemblages with respect to environmental variables were examined through canonical discriminant analysis, multidimensional scaling and multiple correlations. The presence and abundance of fishes, macroinvertebrates and algae species were regulated by environmental variables associated with extreme hydrological events, which derived from the natural torrential regimen of the basin and larger‐scale phenomena, such as El Niño and La Niña. Fish abundance and richness were significantly correlated with algal density and pH, the macroinvertebrate density was negatively related to the flow rate and the richness was positively correlated with algal density. The algae richness was positively correlated with pH and negatively correlated with the flow rate and nitrogen. The algal density was positively correlated with pH and temperature and negatively correlated with river flow. The phycoperiphyton assemblage exhibited more direct responses in its density and richness to the hydrological changes ( r 2 = 0·743 and 0·800, respectively). In functional terms, the El Niño phenomenon was defined by a greater abundance of omnivorous and insectivorous fishes, as well as filter feeders, scrapers and macroinvertebrate predators. During La Niña, a greater abundance of benthic fishes (both detritivorous and insectivorous) and shredder and collector‐gatherer macroinvertebrates was observed. Differentiated responses recorded in the community were based on adaptive strategies for the local hydrological regime that enable fast recovery under conditions such as ENSO phenomena. Composition changes according to adaptations to different hydrological scenarios and the predominance of generalists' trophic guilds and species with plasticity in their habits and their ranges of environmental tolerance were found, supporting the habitat templet model.

Integrated Decision Support System for Prognostic and Diagnostic Analyses of Water Distribution System Failures - M. Shafiqul Islam; Rehan Sadiq; Manuel J. Rodriguez; Homayoun Najjaran; Mina Hoorfar (Water Resources Management, 2016)

Impact of Raw Water Quality and Climate Factors on the Variability of Drinking Water Quality in Small Systems - A. Scheili; I. Delpla; R. Sadiq; M. J. Rodriguez (Water Resources Management, 2016)

From chemosynthesis-based communities to cold-water corals: Vulnerable deep-sea habitats of the Gulf of Cádiz - José L. Rueda; Emilio González-García; Cinja Krutzky; Francisco J. López-Rodriguez; Gerardo Bruque; Nieves López-González; Desiree Palomino; Ricardo F. Sánchez; Juan Tomás Vázquez; Luis M. Fernández-Salas; Victor Díaz-del-Río (Marine Biodiversity, 2016)

Sulfide-oxidizing bacteria establishment in an innovative microaerobic reactor with an internal silicone membrane for sulfur recovery from wastewater - F. Valdés; P. R. Camiloti; R. P. Rodriguez; T. P. Delforno; J. Carrillo-Reyes; M. Zaiat; D. Jeison (Biodegradation, 2016)

Assessing regulatory violations of disinfection by-products in water distribution networks using a non-compliance potential index - Nilufar Islam; Rehan Sadiq; Manuel J. Rodriguez; Christelle Legay (Environmental Monitoring and Assessment, 2016)

The identification of additional zebrafish DICP genes reveals haplotype variation and linkage to MHC class I genes - Ivan Rodriguez-Nunez; Dustin J. Wcisel; Ronda T. Litman; Gary W. Litman; Jeffrey A. Yoder (Immunogenetics, 2016)

Cryopreserved amniotic membrane as transplant allograft: viability and post-transplant outcome - Natasha M. J. Perepelkin; Kirsten Hayward; Tumelo Mokoena; Michael J. Bentley; Lisa U. Ross-Rodriguez; Leah Marquez-Curtis; Locksley E. McGann; Jelena L. Holovati; Janet A. W. Elliott (Cell and Tissue Banking, 2016)

Cobia ( Rachycentron canadum ): A Selected Annotated Bibliography on Aquaculture, General Biology and Fisheries 1967–2015 - Uriel Rodriguez Estrada; Fanny Ayumi Yasumaru; Albert G. J. Tacon; Daniel Lemos (Reviews in Fisheries Science & Aquaculture, 2016)

Assessing stakeholder impacts and adaptation to low water-levels: the Trent-Severn waterway - J. M. A. Coleman; F. S. Sosa-Rodriguez; L. D. Mortsch; P. J. Deadman (Climatic Change, 2016)

Trends in the Intensification of the Fenton Process for Wastewater Treatment: An Overview - Gema Pliego; Juan A. Zazo; Patricia Garcia-Muñoz; Macarena Munoz; Jose A. Casas; Juan J. Rodriguez (Critical Reviews in Environmental Science and Technology, 2015)

Modelling the regional variability of the probability of high trihalomethane occurrence in municipal drinking water - Geneviève Cool; Alexandre Lebel; Rehan Sadiq; Manuel J. Rodriguez (Environmental Monitoring and Assessment, 2015)

New records of Antarctic lichens - A Passo; JM Rodriguez; J Chiapella (New Zealand Journal of Botany, 2015)
Recent collections from King George Island, Deception Island and the Antarctic Peninsula provide evidence of the presence of previously unrecorded lichen taxa in the Antarctic flora. Parmelia sulcata , previously cited for South Georgia, and Usnea neuropogonoides are recorded for the first time from maritime Antarctica. The distributions of Psoroma buchananii and U. acromelana are extended to the Antarctic Peninsula and to Deception Island, respectively. The taxonomic position of an abnormal form of U. aurantiaco‐atra is discussed.

Development, application, and sensitivity analysis of a water quality index for drinking water management in small systems - A. Scheili; Manuel J. Rodriguez; R. Sadiq (Environmental Monitoring and Assessment, 2015)

Differential gene transcription, biochemical responses, and cytotoxicity assessment in Pacific oyster Crassostrea gigas exposed to ibuprofen - Miguel A. S. Serrano; Maria Gonzalez-Rey; Jacó J. Mattos; Fabrício Flores-Nunes; Álvaro C. P. Mello; Flávia L. Zacchi; Clei E. Piazza; Marília N. Siebert; Rômi S. Piazza; Diana Alvarez-Muñoz; Sara Rodriguez-Mozaz; Damià Barceló; et al. (Environmental Science and Pollution Research, 2015)

Method to Reduce Target Motion Through Needle–Tissue Interactions - Matthew J. Oldfield; Alexander Leibinger; Tian En Timothy Seah; Ferdinando Rodriguez y Baena (Annals of Biomedical Engineering, 2015)

Nutrient enrichment intensifies hurricane impact in scrub mangrove ecosystems in the Indian River Lagoon, Florida, USA - Ilka C. Feller; Emily M. Dangremond; Donna J. Devlin; Catherine E. Lovelock; C. Edward Proffitt; Wilfrid Rodriguez (Ecology, 2015)
Mangroves are an ecological assemblage of trees and shrubs adapted to grow in intertidal environments along tropical, subtropical, and warm temperate coasts. Despite repeated demonstrations of their ecologic and economic value, multiple stressors including nutrient over‐enrichment threaten these and other coastal wetlands globally. These ecosystems will be further stressed if tropical storm intensity and frequency increase in response to global climate changes. These stressors will likely interact, but the outcome of that interaction is uncertain. Here, we examined potential interaction between nutrient over‐enrichment and the September 2004 hurricanes. Hurricanes Frances and Jeanne made landfall along Florida's Indian River Lagoon and caused extensive damage to a long‐term fertilization experiment in a mangrove forest, which previously revealed that productivity was nitrogen (N) limited across the forest and, in particular, that N enrichment dramatically increased growth rates and aboveground biomass of stunted Avicennia germinans trees in the interior scrub zone. During the hurricanes, these trees experienced significant defoliation with three to four times greater reduction in leaf area index (LAI) than control trees. Over the long term, the +N scrub trees took four years to recover compared to two years for controls. In the adjacent fringe and transition zones, LAI was reduced by >70%, but with no differences based on zone or fertilization treatment. Despite continued delayed mortality for at least five years after the storms, LAI in the fringe and transition returned to pre‐hurricane conditions in two years. Thus, nutrient over‐enrichment of the coastal zone will increase the productivity of scrub mangroves, which dominate much of the mangrove landscape in Florida and the Caribbean; however, that benefit is offset by a decrease in their resistance and resilience to hurricane damage that has the potential to destabilize the system.

Microsphere-Based Rapamycin Delivery, Systemic Versus Local Administration in a Rat Model of Renal Ischemia/Reperfusion Injury - Jurjen Zandstra; Marike M. van Beuge; Johan Zuidema; Arjen H. Petersen; Mark Staal; Luisa F. Duque; Sergio Rodriguez; Audrey A. R. Lathuile; Gert J. Veldhuis; Rob Steendam; Ruud A. Bank; Eliane R. Popa (Pharmaceutical Research, 2015)

The impact of signal normalization on seizure detection using line length features - Lojini Logesparan; Esther Rodriguez-Villegas; Alexander J. Casson (Medical & Biological Engineering & Computing, 2015)

Common polygenic variation contributes to risk of migraine in the Norfolk Island population - A. J. Rodriguez-Acevedo; M. A. Ferreira; Miles C. Benton; Melanie A. Carless; Harald H. Goring; Joanne E. Curran; John Blangero; R. A. Lea; L. R. Griffiths (Human Genetics, 2015)

Cellular metabolism of unnatural sialic acid precursors - Nam D. Pham; Charles S. Fermaintt; Andrea C. Rodriguez; Janet E. McCombs; Nicole Nischan; Jennifer J. Kohler (Glycoconjugate Journal, 2015)

Scenario-targeted toxicity assessment through multiple endpoint bioassays in a soil posing unacceptable environmental risk according to regulatory screening values - A. Rodriguez-Ruiz; J. Etxebarria; L. Boatti; I. Marigómez (Environmental Science and Pollution Research, 2015)

Micro-scale procedure for enzyme immobilization screening and operational stability assays - Lucia Fernandez-Arrojo; Paloma Santos-Moriano; Barbara Rodriguez-Colinas; Antonio O. Ballesteros; Francisco J. Plou (Biotechnology Letters, 2015)

Linking coastal aquaculture of meagre Argyrosomus regius and Western Mediterranean coastal fisheries through escapes incidents - P. Arechavala‐Lopez; J. M. Valero‐Rodriguez; J. Peñalver‐García; D. Izquierdo‐Gomez; P. Sanchez‐Jerez (Fisheries Management and Ecology, 2015)
Escape incidents in coastal aquaculture lead to economic losses for farmers and may have indirect socio‐economic effects on local fisheries. In this study, the relationship of meagre, Argyrosomus regius (Asso), production in open‐sea cages and coastal small‐scale fisheries was analysed through captures of escapes, which are easily detected because this species is considered locally absent in native communities in Western Mediterranean regions. Scale reading showed that 100% of captured meagre were escapees. The existence of a direct relationship, in terms of biomass, between the development of meagre coastal aquaculture and the increase of captures of this species by local fisheries was demonstrated. The spatial distribution of meagre captures suggested that there is a local environmental and economic interaction between meagre aquaculture and fisheries through escapees. Monitoring the presence of locally absent species such as meagre within landings might help to assess the magnitude of escapes, the potential economic effects on local aquaculture and fishery industries, and the potential adverse ecological impacts on local ecosystems.

Modeling the Phenanthrene Decomposition Adsorbed in Soil by Ozone: Model Characterization and Experimental Validation - J. Rodriguez-Aguilar; A. Garcia-Gonzalez; T. Poznyak; I. Chairez; A. Poznyak (Water, Air, & Soil Pollution, 2015)

Displacement of Br− and P22 in a Wetland Environment - Juan A. Vidales-Contreras; Humberto Rodriguez-Fuentes; Alejandro I. Luna-Maldonado; Jesus J. Hernandez-Escareño (Water, Air, & Soil Pollution, 2015)

Estimation of urban water supply issues at the local scale: a participatory approach - Christelle Legay; Geneviève Cloutier; Salem Chakhar; Florent Joerin; Manuel J. Rodriguez (Climatic Change, 2015)

Maintaining Antioxidant Potential of Fresh Fruits and Vegetables After Harvest - Jose A. Villa-Rodriguez; H. Palafox-Carlos; Elhadi M. Yahia; J. Fernando Ayala-Zavala; Gustavo A. Gonzalez-Aguilar (Critical Reviews in Food Science and Nutrition, 2015)

Elimination of Selected Emerging Contaminants by the Combination of Membrane Filtration and Chemical Oxidation Processes - Juan L. Acero; F. Javier Benitez; Francisco J. Real; Elena Rodriguez (Water, Air, & Soil Pollution, 2015)

Analysis of viscoelastic behaviour of rock salt using hydraulic cylinder test - F. Lopez-Gayarre; R. Fernandez-Rodriguez; C. Gonzalez-Nicieza; J. R. Garcia-Menendez (Bulletin of Engineering Geology and the Environment, 2015)

Vertical distribution and migration of fish larvae in the NW Iberian upwelling system during the winter mixing period: implications for cross‐shelf distribution - J.M. Rodriguez; A. Cabrero; J. Gago; C. Guevara‐Fletcher; M. Herrero; A. Hernandez de Rojas; A. Garcia; R. Laiz‐Carrion; A.R. Vergara; P. Alvarez; C. Piñeiro; F. Saborido‐Rey (Fisheries Oceanography, 2015)
The vertical distribution and vertical migrations of fish larvae and implications for their cross‐shelf distribution were investigated in the northern limit of the NE Atlantic upwelling region during the late winter mixing period of 2012. The average positive values of the upwelling index for February and March of this year were far from normal, although the average hydrographic conditions during the period of study were of downwelling and the water column was completely mixed. Fish larvae, most in the preflexion stage, were concentrated in the upper layers of the water column and their distribution was depth stratified, both day and night. However, the larval fish community was not structured in the vertical plane and fish larvae did not show significant diel vertical migration ( DVM ), although five species showed ontogenetic vertical migration. In regions of coastal upwelling and in the absence of DVM , the location of fish larvae in the water column is crucial for their cross‐shelf distribution. Thus, the cross‐shelf distribution of the six most abundant species collected in this study can be explained by the surface onshore flow associated with coastal downwelling, retaining larvae of the coastal spawning species with a relatively shallow distribution in the shelf region and transporting larvae of slope spawning species onto the shelf. The wide vertical distribution shown by larvae of the offshore spawning species could be an adaptation of these species to ensure that some larvae reach the inshore nursery areas.

Is Streptococcus bovis a urinary pathogen? - M. Matesanz; D. Rubal; I. Iñiguez; R. Rabuñal; F. García-Garrote; A. Coira; M. J. García-País; J. Pita; A. Rodriguez-Macias; M. J. López-Álvarez; M. P. Alonso; J. Corredoira (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

CXCL10/XCL1 fusokine elicits in vitro and in vivo chemotaxis - Yessica E. Sanchez-Lugo; Jose J. Perez-Trujillo; Yolanda Gutierrez-Puente; Aracely Garcia-Garcia; Humberto Rodriguez-Rocha; Oralia Barboza-Quintana; Gerardo E. Muñoz-Maldonado; Odila Saucedo-Cardenas; Roberto Montes de Oca-Luna; Maria J. Loera-Arias (Biotechnology Letters, 2015)

Impacts of future climatic and land cover changes on the hydrological regime of the Madeira River basin - J. L. Siqueira Júnior; J. Tomasella; D. A. Rodriguez (Climatic Change, 2015)

Interfacial pH during mussel adhesive plaque formation - Nadine R. Martinez Rodriguez; Saurabh Das; Yair Kaufman; Jacob N. Israelachvili; J. Herbert Waite (Biofouling, 2015)

Thermal Impact from a Thermoelectric Power Plant on a Tropical Coastal Lagoon - J. G. Cardoso-Mohedano; R. Bernardello; J. A. Sanchez-Cabeza; A. C. Ruiz-Fernández; R. Alonso-Rodriguez; A. Cruzado (Water, Air, & Soil Pollution, 2015)

Higher sensitivity to the conditioned rewarding effects of cocaine and MDMA in High-Novelty-Seekers mice exposed to a cocaine binge during adolescence - A. Mateos-García; C. Roger-Sánchez; M. Rodriguez-Arias; J. Miñarro; M. A. Aguilar; C. Manzanedo; M. C. Arenas (Psychopharmacology, 2015)

Detection of hotspots and rapid determination of methane emissions from landfills via a ground-surface method - R. Gonzalez-Valencia; F. Magana-Rodriguez; E. Maldonado; J. Salinas; F. Thalasso (Environmental Monitoring and Assessment, 2015)

Ecophysiological diversity of a novel member of the genus Alteromonas, and description of Alteromonas mediterranea sp. nov. - Elena P. Ivanova; Mario López-Pérez; Mila Zabalos; Song Ha Nguyen; Hayden K. Webb; Jason Ryan; Kiril Lagutin; Mikhail Vyssotski; Russell J. Crawford; Francisco Rodriguez-Valera (Antonie van Leeuwenhoek, 2015)

Triple-layered mixed co-culture model of RPE cells with neuroretina for evaluating the neuroprotective effects of adipose-MSCs - David Rodriguez-Crespo; Salvatore Di Lauro; Amar K. Singh; Maria T. Garcia-Gutierrez; Manuel Garrosa; J. Carlos Pastor; Ivan Fernandez-Bueno; Girish K. Srivastava (Cell and Tissue Research, 2014)

Testing a ‘genes‐to‐ecosystems’ approach to understanding aquatic–terrestrial linkages - Gregory M. Crutsinger; Seth M. Rudman; Mariano A. Rodriguez‐Cabal; Athena D. McKown; Takuya Sato; Andrew M. MacDonald; Julian Heavyside; Armando Geraldes; Edmund M. Hart; Carri J. LeRoy; Rana W. El‐Sabaawi (Molecular Ecology, 2014)
A ‘genes‐to‐ecosystems’ approach has been proposed as a novel avenue for integrating the consequences of intraspecific genetic variation with the underlying genetic architecture of a species to shed light on the relationships among hierarchies of ecological organization (genes → individuals → communities → ecosystems). However, attempts to identify genes with major effect on the structure of communities and/or ecosystem processes have been limited and a comprehensive test of this approach has yet to emerge. Here, we present an interdisciplinary field study that integrated a common garden containing different genotypes of a dominant, riparian tree, Populus trichocarpa , and aquatic mesocosms to determine how intraspecific variation in leaf litter alters both terrestrial and aquatic communities and ecosystem functioning. Moreover, we incorporate data from extensive trait screening and genome‐wide association studies estimating the heritability and genes associated with litter characteristics. We found that tree genotypes varied considerably in the quality and production of leaf litter, which contributed to variation in phytoplankton abundances, as well as nutrient dynamics and light availability in aquatic mesocosms. These ‘after‐life’ effects of litter from different genotypes were comparable to the responses of terrestrial communities associated with the living foliage. We found that multiple litter traits corresponding with aquatic community and ecosystem responses differed in their heritability. Moreover, the underlying genetic architecture of these traits was complex, and many genes contributed only a small proportion to phenotypic variation. Our results provide further evidence that genetic variation is a key component of aquatic–terrestrial linkages, but challenge the ability to predict community or ecosystem responses based on the actions of one or a few genes.

Treatment of cosmetic wastewater by a full-scale membrane bioreactor (MBR) - Victor M. Monsalvo; Jesus Lopez; Angel F. Mohedano; Juan J. Rodriguez (Environmental Science and Pollution Research, 2014)

Geomechanical modelling to assess fault integrity at the CO2CRC Otway Project, Australia - C. M. Aruffo; A. Rodriguez-herrera; E. Tenthorey; F. Krzikalla; J. Minton; A. Henk (Australian Journal of Earth Sciences, 2014)

Identifying the pollen of an extinct spruce species in the Late Quaternary sediments of the Tunica Hills region, south‐eastern United States - L. MANDER; J. RODRIGUEZ; P. G. MUELLER; S. T. JACKSON; S. W. PUNYASENA (Journal of Quaternary Science, 2014)
Late Quaternary fluvial deposits in the Tunica Hills region of Louisiana and Mississippi are rich in spruce macrofossils of the extinct species Picea critchfieldii , the one recognized plant extinction of the Late Quaternary. However, the morphology of P. critchfieldii pollen is unknown, presenting a barrier to the interpretation of pollen spectra from the last glacial of North America. To address this issue, we undertook a morphometric study of Picea pollen from Tunica Hills. Morphometric data, together with qualitative observations of pollen morphology using Apotome fluorescence microscopy, indicate that Picea pollen from Tunica Hills is morphologically distinct from the pollen of P. glauca , P. mariana and P. rubens . Measurements of grain length, corpus width and corpus height indicate that Picea pollen from Tunica Hills is larger than the pollen of P. mariana and P. rubens , and is slightly larger than P. glauca pollen. We argue that the morphologically distinctive Tunica Hills Picea pollen was probably produced by the extinct spruce species P. critchfieldii . These morphological differences could be used to identify P. critchfieldii in existing and newly collected pollen records, which would refine its paleoecologic and biogeographic history and clarify the nature and timing of its extinction in the Late Quaternary.

Long‐term hurricane damage effects on tropical forest tree growth and mortality - Edmund V. J. Tanner; Francisco Rodriguez-Sanchez; John R. Healey; Robert J. Holdaway; Peter J. Bellingham (Ecology, 2014)
Hurricane winds can have large impacts on forest structure and dynamics. To date, most evaluations of hurricane impacts have focused on short‐term responses after a hurricane, often lacked pre‐hurricane measurements, and missed responses occurring over longer time scales. Here, we use a long‐term data set (1974–2009, 35 years) of tree stems (>3 cm in diameter at 1.3 m aboveground) in four sites (0.35 ha in total) in montane rain forest (∼1600 m elevation) in Jamaica to investigate the patterns of crown damage in individual stems by Hurricane Gilbert in 1988, and how subsequent growth and mortality were affected by hurricane damage, sprouting, and the incidence of multiple stems. Topographical position on a mountain ridge was the best predictor of crown damage, followed by crown size and species identity. The average diameter growth rate of stems that survived the hurricane was greater than that pre‐hurricane for the whole 21‐yr post‐hurricane period. Growth rates of stems with damaged crowns increased less than those with undamaged crowns; differences in growth rate between damaged and undamaged trees disappeared after 11 years. Hurricane‐damaged stems had two to eight times higher mortality than undamaged stems for 19 years post hurricane. Many stems sprouted shortly after the hurricane, but few sprouts managed to establish (grow to >3 cm diameter at breast height). However, sprouting and multi‐stemming were associated with reduced mortality rate, particularly in damaged trees. From an initial population of 1670 stems in 1974, 54% were still alive in 2009 (21 years after the hurricane). We conclude that despite the high frequency of hurricane damage to tree crowns and the subsequent increased mortality rate in this hurricane‐prone tropical montane forest, many stems will be hit and recover from several hurricanes in their lifetime.

Record of an established population of Palaemon macrodactylus Rathbun, 1902 (Decapoda, Palaemonidae) in the Mediterranean Sea: confirming a prediction - J. A. CUESTA; N. BETTOSO; G. COMISSO; C. FROGLIA; G. MAZZA; A. RINALDI; A. RODRIGUEZ; T. SCOVACRICCHI (Mediterranean Marine Science, 2014)
The capture of larvae of Palaemon macrodactylus off Mallorca (Balearic Islands) has been recently reported as evidence of a potential presence of a population of this species in the Mediterranean Sea. Photos of this species, taken during dives in the Sacca di Goro (northern Adriatic) were published in the same year, but no specimen could be collected at that time. Herein we report the capture in 2013 of numerous individuals of the oriental shrimp, including ovigerous females, both in the Sacca di Goro and in the Lagoon of Marano and Grado (northern Adriatic Sea, Italy), confirming the existence of a well-established population of this species in the Mediterranean Sea.

Do Cloud Properties in a Puerto Rican Tropical Montane Cloud Forest Depend on Occurrence of Long-Range Transported African Dust? - Johanna K. Spiegel; Nina Buchmann; Olga L. Mayol-Bracero; Luis A. Cuadra-Rodriguez; Carlos J. Valle Díaz; Kimberly A. Prather; Stephan Mertes; Werner Eugster (Pure and Applied Geophysics, 2014)

Fear extinction and acute stress reactivity reveal a role of LPA1 receptor in regulating emotional-like behaviors - C. Pedraza; J. Sánchez-López; E. Castilla-Ortega; C. Rosell-Valle; E. Zambrana-Infantes; M. García-Fernández; F. Rodriguez de Fonseca; J. Chun; L. J. Santín; G. Estivill-Torrús (Brain Structure and Function, 2014)

Strategies to evaluate biodegradability: application to chlorinated herbicides - S. Sanchis; A. M. Polo; M. Tobajas; J. J. Rodriguez; A. F. Mohedano (Environmental Science and Pollution Research, 2014)

Hybridization rate and climate change: are endangered species at risk? - R. A. Sánchez-Guillén; J. Muñoz; J. Hafernik; M. Tierney; G. Rodriguez-Tapia; A. Córdoba-Aguilar (Journal of Insect Conservation, 2014)

Reducing the draconitic errors in GNSS geodetic products - C. J. Rodriguez-Solano; U. Hugentobler; P. Steigenberger; M. Bloßfeld; M. Fritsche (Journal of Geodesy, 2014)

New subgroup 16SrIII-Y phytoplasmas associated with false-blossom diseased cranberry (Vaccinium macrocarpon) plants and with known and potential insect vectors in New Jersey - I.-M. Lee; J. Polashock; K. D. Bottner-Parker; P. G. Bagadia; C. Rodriguez-Saona; Y. Zhao; R. E. Davis (European Journal of Plant Pathology, 2014)

A set of microsatellite markers for the threatened Murray hardyhead, Craterocephalus fluviatilis (Pisces: Atherinidae) from the southern Murray–Darling Basin - Clara J. Rodriguez-Zarate; Daniel C. Carvalho; Michael P. Hammer; Luciano B. Beheregaray (Conservation Genetics Resources, 2014)

Trophic ecology of Lampanyctus crocodilus on north‐west Mediterranean Sea slopes in relation to reproductive cycle and environmental variables - E. Fanelli; V. Papiol; J. E. Cartes; O. Rodriguez‐Romeu (Journal of Fish Biology, 2014)
This study examined the population structure, reproductive cycle and feeding pattern of the lanternfish Lampanyctus crocodilus in the Balearic Basin (north‐west Mediterranean Sea) from a depth of 450 to 1800 m and at a seasonal scale. Juveniles were mainly located at shallower depths, but also at deepest stations in autumn, while adults mostly inhabited intermediate depths with their centre of population density (CPD) located at 800–1000 m of depth. The migration of adults to deeper depths was detected in late summer to autumn, probably linked to the occurrence of nepheloid layers at c. 1200 m, which in turn enhances the biomass of the zooplankton prey. The diet was mainly based on euphausiids and mysids, with marked seasonal variations both on the upper (450–800 m) and lower (1000–1800 m), where suprabenthic gammariids and pelagic decapods were also dominant. Stomach fullness increased from winter to autumn on the US , while it had a maximum in spring on the LS , in parallel with high consumption of gelatinous zooplankton, which is probably more available after the phytoplankton bloom in late winter. Reproduction occurred in winter, confirmed by the higher percentage of mature females and high gonadosomatic indices ( I G ) at both depth ranges. Hepatosomatic indices ( I H ) showed an inverse trend to I G on the US, except in autumn, and was almost parallel on the LS, probably attributable to the migration of adults, which determined different temporal schemes in energy use and storage for reproduction on the US v . LS. Consistent with the different patterns observed at the two depth ranges, environmental drivers of fullness ( i.e. feeding intensity) and I G (as a proxy of reproductive cycle) differed on the US and LS. The biomass of mysids and euphausiids was the greatest explanatory variables of fullness on the US and LS, pointing to the increasing feeding intensity when a resource was more available. I H also explained fullness, suggesting that greater feeding intensity in pre‐reproductive periods enabled energy storage in the liver. I G was linked directly ( i.e. mysids) or indirectly ( i.e. surface primary production recorded 2 months before sampling) to food availability, implying a rapid response to vertical food inputs by deep‐sea predators. Also, I G in L. crocodilus was related to population density, which suggests aggregations for reproduction. Estimates of L. crocodilus trophic levels, and of other accompanying mesopelagic fishes, indicated that the species feed through a continuum spanning the third trophic level, confirming the key role of mesopelagic fishes in transferring organic carbon between trophic levels. Trophic niche segregation among mesopelagic species was pronounced and non‐overlapping groups could be distinguished because of the different vertical distribution and migratory behaviour. The study highlights the important role of the benthic boundary layer in sustaining benthopelagic communities in the deep Mediterranean Sea and the need to study the biology of a species throughout its whole depth range and not just at exploited depths ( i.e . fishing grounds).

Direct ageing of Thunnus thynnus from the eastern Atlantic Ocean and western Mediterranean Sea using dorsal fin spines - P. L. Luque; E. Rodriguez‐Marin; J. Landa; M. Ruiz; P. Quelle; D. Macias; J. M. Ortiz De Urbina (Journal of Fish Biology, 2014)
This study deals with important methodology issues that affect age estimates of eastern Atlantic bluefin tuna Thunnus thynnus using dorsal fin spines. Nearly 3800 spine sections were used from fish caught in the north‐east Atlantic Ocean and western Mediterranean Sea over a 21 year period. Edge type and marginal increment analyses indicated a yearly periodicity of annulus formation with the translucent bands (50% of occurrence) appearing from October to May. Nucleus vascularization seriously affected specimens older than 6 years, with the disappearance of 40–50% of the presumed annuli by that age. An alternate sectioning location was a clear improvement and this finding is an important contribution to the methodology of using this structure for ageing the full‐length range of eastern T. thynnus . Finally, there were no significant differences between the coefficients of von Bertalanffy growth model estimated from mean length at age data ( L ∞ = 327·4; k = 0·097; t 0 = −0·838) and those estimated from the growth curves accepted for the eastern and western T. thynnus management units.

Discrepant results from sampling different lumens of multilumen catheters: the case for sampling all lumens - J. Cuellar-Rodriguez; D. Connor; P. Murray; J. Gea-Banacloche (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Comparative study of fuzzy evidential reasoning and fuzzy rule-based approaches: an illustration for water quality assessment in distribution networks - E. Aghaarabi; F. Aminravan; R. Sadiq; M. Hoorfar; M. J. Rodriguez; H. Najjaran (Stochastic Environmental Research and Risk Assessment, 2014)

Ruminal epithelium transcriptome dynamics in response to plane of nutrition and age in young Holstein calves - Aisha Naeem; James K. Drackley; Jennifer Stamey Lanier; Robin E. Everts; Sandra L. Rodriguez-Zas; Juan J. Loor (Functional & Integrative Genomics, 2014)

Water distribution system failure: a framework for forensic analysis - M. Shafiqul Islam; Rehan Sadiq; Manuel J. Rodriguez; Homayoun Najjaran; Alex Francisque; Mina Hoorfar (Environment Systems and Decisions, 2014)

High-quality conforming hexahedral meshes of patient-specific abdominal aortic aneurysms including their intraluminal thrombi - J. Tarjuelo-Gutierrez; B. Rodriguez-Vila; D. M. Pierce; T. E. Fastl; P. Verbrugghe; I. Fourneau; G. Maleux; P. Herijgers; G. A. Holzapfel; E. J. Gomez (Medical & Biological Engineering & Computing, 2014)

Multiple spine boutons are formed after long-lasting LTP in the awake rat - N. I. Medvedev; G. Dallérac; V. I. Popov; J. J. Rodriguez Arellano; H. A. Davies; I. V. Kraev; V. Doyère; M. G. Stewart (Brain Structure and Function, 2014)

Diffusional conductances to CO2 as a target for increasing photosynthesis and photosynthetic water-use efficiency - Jaume Flexas; Ülo Niinemets; Alexander Gallé; Margaret M. Barbour; Mauro Centritto; Antonio Diaz-Espejo; Cyril Douthe; Jeroni Galmés; Miquel Ribas-Carbo; Pedro L. Rodriguez; Francesc Rosselló; Raju Soolanayakanahally; et al. (Photosynthesis Research, 2013)

Optimization of a Trap for Tuta absoluta Meyrick (Lepidoptera: Gelechiidae) and Trials to Determine the Effectiveness of Mass Trapping - E Lobos; M Occhionero; D Werenitzky; J Fernandez; L M Gonzalez; C Rodriguez; C Calvo; G Lopez; A C Oehlschlager (Neotropical Entomology, 2013)

Optimizing booster chlorination in water distribution networks: a water quality index approach - Nilufar Islam; Rehan Sadiq; Manuel J. Rodriguez (Environmental Monitoring and Assessment, 2013)

Fungal endophytes of invasive Phagramites australis populations vary in species composition and fungicide susceptibility - Monika S. Fischer; Rusty J. Rodriguez (Symbiosis, 2013)

The Immune System in Stroke: Clinical Challenges and Their Translation to Experimental Research - Craig J. Smith; Catherine B. Lawrence; Beatriz Rodriguez-Grande; Krisztina J. Kovacs; Jesus M. Pradillo; Adam Denes (Journal of Neuroimmune Pharmacology, 2013)

Spatial and temporal occurrence of N-nitrosamines in seven drinking water supply systems - Isabelle J. Brisson; Patrick Levallois; Hélène Tremblay; Jean Sérodes; Christian Deblois; Jeffrey Charrois; Vincent Taguchi; Jessica Boyd; XingFang Li; Manuel J. Rodriguez (Environmental Monitoring and Assessment, 2013)

A Novel Human Glycoprotein ACA is an Upstream Regulator of Human Hematopoiesis - Z. A. Becker-Kojić; J. R. Ureña-Peralta; R. Saffrich; F. J. Rodriguez-Jiménez; M. P. Rubio; P. Rios; A. Romero; A. D. Ho; M. Stojković (Bulletin of Experimental Biology and Medicine, 2013)

Activation by ACA Induces Pluripotency in Human Blood Progenitor Cells - Z. A. Becker-Kojić; J. R. Ureña-Peralta; I. Zipančić; F. J. Rodriguez-Jiménez; M. P. Rubio; P. Stojković; M. G. Roselló; M. Stojković (Bulletin of Experimental Biology and Medicine, 2013)

Quantifying fine-scale resource selection by introduced European hedgehogs (Erinaceus europaeus) in ecologically sensitive areas - Mariano Rodriguez Recio; Renaud Mathieu; M. Cecilia Latham; A. David M. Latham; Philip J. Seddon (Biological Invasions, 2013)

Ecological Inferences from a deep screening of the C omplex B acterial C onsortia associated with the coral, P orites astreoides - Mauricio Rodriguez‐Lanetty; Camila Granados‐Cifuentes; Albert Barberan; Anthony J. Bellantuono; Carolina Bastidas (Molecular Ecology, 2013)
The functional role of the bacterial organisms in the reef ecosystem and their contribution to the coral well‐being remain largely unclear. The first step in addressing this gap of knowledge relies on in‐depth characterization of the coral microbial community and its changes in diversity across coral species, space and time. In this study, we focused on the exploration of microbial community assemblages associated with an ecologically important C aribbean scleractinian coral, P orites astreoides , using I llumina high‐throughput sequencing of the V 5 fragment of 16 S r RNA gene. We collected data from a large set of biological replicates, allowing us to detect patterns of geographical structure and resolve co‐occurrence patterns using network analyses. The taxonomic analysis of the resolved diversity showed consistent and dominant presence of two OTU s affiliated with the order O ceanospirillales , which corroborates a specific pattern of bacterial association emerging for this coral species and for many other corals within the genus P orites . We argue that this specific association might indicate a symbiotic association with the adult coral partner. Furthermore, we identified a highly diverse rare bacterial ‘biosphere’ (725 OTU s) also living along with the dominant bacterial symbionts, but the assemblage of this biosphere is significantly structured along the geographical scale. We further discuss that some of these rare bacterial members show significant association with other members of the community reflecting the complexity of the networked consortia within the coral holobiont.

The importance of progressive senescence in the biomass dynamics of giant kelp ( Macrocystis pyrifera ) - Gabriel E. Rodriguez; Andrew Rassweiler; Daniel C. Reed; Sally J. Holbrook (Ecology, 2013)
Temporal variation in primary producer biomass has profound effects on the structure and function of the surrounding ecological community. The giant kelp ( Macrocystis pyrifera ) exhibits strong intra‐annual variation in biomass density, which is better explained by the demographic rates of fronds than by those of whole plants. To better understand the processes controlling the dynamics of giant kelp fronds we collected monthly time‐series data of frond initiation and survival. These data were used to determine how frond loss and frond initiation rates were predicted by factors thought to affect the growth and survival of Macrocystis , including external environmental factors (i.e., wave height, day length, temperature, nutrient concentration, and neighborhood density) and intrinsic biological characteristics (i.e., frond age, plant size, and nutritional status). Our results revealed that frond dynamics were better explained by intrinsic biological processes rather than external environmental factors. A metric of frond age structure that incorporated progressive senescence was the best predictor of frond loss rate, accounting for 58% of the explained variation in frond loss. A similar analysis revealed that frond age structure was also the single best predictor of frond initiation rate, accounting for 46% of the explained variation. To further examine the importance of senescence in biomass dynamics, we used frond age‐dependent mortality and frond initiation rates to predict biomass in subsequent months and found that the model explained 73% of the observed variation in biomass at our sites. Vegetation dynamics of many species including giant kelp are often considered largely in the context of external controls on resource availability and physical disturbance. Our results indicate that investigations of the processes controlling vegetation dynamics may benefit greatly from the inclusion of intrinsic biological factors such as age‐dependent mortality and growth, which can outweigh the effects of external forcing in accounting for fluctuations in vegetation biomass.

Geographic variation in allele frequency of the gamete recognition protein M7 lysin throughout a mosaic blue mussel hybrid zone - Matthew R. Gilg; M. Camila Restrepo; Ronald Walton; Pamela M. Brannock; Thomas J. Hilbish; Emmanuel Rodriguez (Marine Biology, 2013)

CHACO outreach project: the development of a primary health care-based medical genetic service in an Argentinean province - C. Z. Barreiro; M. P. Bidondo; J. A. Garrido; J. Deurloo; E. Acevedo; A. Luna; E. Gutiérrez; C. A. Dellamea; C. Picón; K. Torres; M. F. De Castro; M. V. Torrado; et al. (Journal of Community Genetics, 2013)

Assessing water stress in a hedgerow olive orchard from sap flow and trunk diameter measurements - M. V. Cuevas; M. J. Martín-Palomo; A. Diaz-Espejo; J. M. Torres-Ruiz; C. M. Rodriguez-Dominguez; A. Perez-Martin; R. Pino-Mejías; J. E. Fernández (Irrigation Science, 2013)

Hevea brasiliensis and Urtica dioica impact the in vitro mycorrhization of neighbouring Medicago truncatula seedlings - Tiffany Sosa-Rodriguez; Stéphane Declerck; Francoise Granet; Sylvie Gaurel; Els J. M. Van Damme; Hervé Dupré de Boulois (Symbiosis, 2013)

Relationship between hydraulic conductance and citrus dwarfing by the Flying Dragon rootstock (Poncirus trifoliata L. Raft var. monstruosa) - B. Martínez-Alcántara; J. Rodriguez-Gamir; M. R. Martínez-Cuenca; D. J. Iglesias; E. Primo-Millo; M. A. Forner-Giner (Trees, 2013)

Evaluating Water Quality Failure Potential in Water Distribution Systems: A Fuzzy-TOPSIS-OWA-based Methodology - M. Shafiqul Islam; Rehan Sadiq; Manuel J. Rodriguez; Homayoun Najjaran; Alex Francisque; Mina Hoorfar (Water Resources Management, 2013)

Acclimation to Elevated CO2 Increases Constitutive Glucosinolate Levels of Brassica Plants and Affects the Performance of Specialized Herbivores from Contrasting Feeding Guilds - J. Klaiber; S. Dorn; A. J. Najar-Rodriguez (Journal of Chemical Ecology, 2013)

Tradeoffs, competition, and coexistence in eastern deciduous forest ant communities - Katharine L. Stuble; Mariano A. Rodriguez-Cabal; Gail L. McCormick; Ivan Jurić; Robert R. Dunn; Nathan J. Sanders (Oecologia, 2013)

Virtual Treatment of Basilar Aneurysms Using Shape Memory Polymer Foam - J. M. Ortega; J. Hartman; J. N. Rodriguez; D. J. Maitland (Annals of Biomedical Engineering, 2013)

Performance evaluation of a new fourth-generation HIV combination antigen–antibody assay - A. Mühlbacher; H. Schennach; J. van Helden; T. Hebell; G. Pantaleo; P. Bürgisser; C. Cellerai; P. Permpikul; M. I. Rodriguez; A. Eiras; F. Alborino; P. Cunningham; et al. (Medical Microbiology and Immunology, 2013)

Cr(VI) Adsorption and Desorption on Soils and Biosorbents - M. T. Fernández-Pazos; B. Garrido-Rodriguez; J. C. Nóvoa-Muñoz; M. Arias-Estévez; M. J. Fernández-Sanjurjo; A. Núñez-Delgado; E. Álvarez (Water, Air, & Soil Pollution, 2013)

Plant acclimation to elevated CO2 affects important plant functional traits, and concomitantly reduces plant colonization rates by an herbivorous insect - Jeannine Klaiber; Adriana J. Najar-Rodriguez; Rafal Piskorski; Silvia Dorn (Planta, 2013)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Modelling geosmin concentrations in three sources of raw water in Quebec, Canada - Julien Parinet; Manuel J. Rodriguez; Jean-Baptiste Sérodes (Environmental Monitoring and Assessment, 2013)

Comparison of single-dose and extended methamphetamine administration on reversal learning in rats - Alisa R. Kosheleff; Danilo Rodriguez; Steve J. O’Dell; John F. Marshall; Alicia Izquierdo (Psychopharmacology, 2012)

Testing for hybridization and assessing genetic diversity in Morelet’s crocodile (Crocodylus moreletii) populations from central Veracruz - Ricardo González-Trujillo; David Rodriguez; Alberto González-Romero; Michael R. J. Forstner; Llewellyn D. Densmore III; Víctor Hugo Reynoso (Conservation Genetics, 2012)

Compressive sensing scalp EEG signals: implementations and practical performance - Amir M. Abdulghani; Alexander J. Casson; Esther Rodriguez-Villegas (Medical & Biological Engineering & Computing, 2012)

Full-length genome analysis of vesicular stomatitis New Jersey virus strains representing the phylogenetic and geographic diversity of the virus - Steven J. Pauszek; Luis L. Rodriguez (Archives of Virology, 2012)

Kinetics of biodegradation of diesel fuel by enriched microbial consortia from polluted soils - E. Moliterni; R. G. Jiménez-Tusset; M. Villar Rayo; L. Rodriguez; F. J. Fernández; J. Villaseñor (International Journal of Environmental Science and Technology, 2012)

Effect of stock type characteristics and time of planting on field performance of aspen (Populus tremuloides Michx.) seedlings on boreal reclamation sites - Simon M. Landhäusser; Javier Rodriguez-Alvarez; Eckehart H. Marenholtz; Victor J. Lieffers (New Forests, 2012)

Prevention of group B streptococcal neonatal disease revisited. The DEVANI European project - J. Rodriguez-Granger; J. C. Alvargonzalez; A. Berardi; R. Berner; M. Kunze; M. Hufnagel; P. Melin; A. Decheva; G. Orefici; C. Poyart; J. Telford; A. Efstratiou; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

A Common View of the Opportunities, Challenges, and Research Actions for Pongamia in Australia - Helen T. Murphy; Deborah A. O’Connell; Gary Seaton; R. John Raison; Luis C. Rodriguez; Andrew L. Braid; Darren J. Kriticos; Tom Jovanovic; Amir Abadi; Michael Betar; Heather Brodie; Malcolm Lamont; et al. (BioEnergy Research, 2012)

Zygomycosis Caused by Rhizopus microsporus and Rhizopus oryzae in Madhya Pradesh (M.P.) Central India: A Report of Two Cases - Shesh R. Nawange; S. M. Singh; J. Naidu; S. Jain; T. Nagpal; D. S. Behrani; E. Mellado; J. L. Rodriguez Tudela (Mycopathologia, 2012)

Low genetic diversity and evidence of population structure among subspecies of Nerodia harteri, a threatened water snake endemic to Texas - David Rodriguez; Michael R. J. Forstner; Dustin L. McBride; Llewellyn D. Densmore III; James R. Dixon (Conservation Genetics, 2012)

Optimal features for online seizure detection - Lojini Logesparan; Alexander J. Casson; Esther Rodriguez-Villegas (Medical & Biological Engineering & Computing, 2012)

BK virus infection in human immunodeficiency virus-infected patients - J. Ledesma; P. Muñoz; D. Garcia de Viedma; I. Cabrero; B. Loeches; P. Montilla; P. Gijon; B. Rodriguez-Sanchez; E. Bouza (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Towards the standardisation of the neuroblastoma (neuro-2a) cell-based assay for ciguatoxin-like toxicity detection in fish: application to fish caught in the Canary Islands - A. Caillaud; H. Eixarch; P. de la Iglesia; M. Rodriguez; L. Dominguez; K.B. Andree; J. Diogène (Food Additives & Contaminants: Part A, 2012)

Feasibility of Different Bioremediation Strategies for Treatment of Clayey and Silty Soils Recently Polluted with Diesel Hydrocarbons - E. Moliterni; L. Rodriguez; F. J. Fernández; J. Villaseñor (Water, Air, & Soil Pollution, 2012)

Modified Natural Clinoptilolite Detoxifies Small Mammal’s Organism Loaded with Lead II: Genetic, Cell, and Physiological Effects - Margarita Topashka-Ancheva; Michaela Beltcheva; Roumiana Metcheva; J. Antonio Heredia Rojas; Abraham O. Rodriguez-De la Fuente; Tsvetelina Gerasimova; Laura E. Rodríguez-Flores; Svetla E. Teodorova (Biological Trace Element Research, 2012)

Impact of Earth radiation pressure on GPS position estimates - C. J. Rodriguez-Solano; U. Hugentobler; P. Steigenberger; S. Lutz (Journal of Geodesy, 2012)

Molecular characterization of Staphylococcus aureus from outpatients in the Caribbean reveals the presence of pandemic clones - A.-C. Uhlemann; C. Dumortier; C. Hafer; B. S. Taylor; J. Sánchez E.; C. Rodriguez-Taveras; P. Leon; R. Rojas; C. Olive; F. D. Lowy (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Opacification of Shape Memory Polymer Foam Designed for Treatment of Intracranial Aneurysms - Jennifer N. Rodriguez; Ya-Jen Yu; Matthew W. Miller; Thomas S. Wilson; Jonathan Hartman; Fred J. Clubb; Brandon Gentry; Duncan J. Maitland (Annals of Biomedical Engineering, 2012)

The activity of leech motoneurons during motor patterns is regulated by intrinsic properties and synaptic inputs - C. Bernardo Perez-Etchegoyen; Rodrigo J. Alvarez; Mariano J. Rodriguez; Lidia Szczupak (Journal of Comparative Physiology A, 2012)

Disruption of ant-seed dispersal mutualisms by the invasive Asian needle ant (Pachycondyla chinensis) - Mariano A. Rodriguez-Cabal; Katharine L. Stuble; Benoit Guénard; Robert R. Dunn; Nathan J. Sanders (Biological Invasions, 2012)

Emission of volatile compounds by Erwinia amylovora: biological activity in vitro and possible exploitation for bacterial identification - Francesco Spinelli; Antonio Cellini; Joel L. Vanneste; Maria T. Rodriguez-Estrada; Guglielmo Costa; Stefano Savioli; Frans J. M. Harren; Simona M. Cristescu (Trees, 2012)

Jatropha adoption: a statistical observational study of factors influencing Malian farmers’ decision to grow Jatropha - M. Basinger; J. Chen; F. Jeffrey-Coker; F. S. Rodriguez-Sanchez; T. Singer; V. Modi (Agroforestry Systems, 2012)

Genetic and antigenic relationships of vesicular stomatitis viruses from South America - Steven J. Pauszek; Jose del C. Barrera; Tony Goldberg; Rossana Allende; Luis L. Rodriguez (Archives of Virology, 2011)

CIGB-300, a synthetic peptide-based drug that targets the CK2 phosphoaceptor domain. Translational and clinical research - Silvio E. Perea; Idania Baladron; Yanelda Garcia; Yasser Perera; Adlin Lopez; Jorge L. Soriano; Noyde Batista; Aley Palau; Ignacio Hernández; Hernán Farina; Idrian Garcia; Lidia Gonzalez; et al. (Molecular and Cellular Biochemistry, 2011)

Progressive Myoclonic Epilepsy-Associated Gene KCTD7 is a Regulator of Potassium Conductance in Neurons - Régis Azizieh; David Orduz; Patrick Van Bogaert; Tristan Bouschet; Wendy Rodriguez; Serge N. Schiffmann; Isabelle Pirson; Marc J. Abramowicz (Molecular Neurobiology, 2011)

Phenotype changes inherited by crossing pyrethroid susceptible and resistant genotypes from the cattle tick Riphicephalus (Boophilus) microplus - G. Aguilar-Tipacamú; R. Rosario-Cruz; Robert J. Miller; Felix D. Guerrero; R. I. Rodriguez-Vivas; Z. García-Vázquez (Experimental and Applied Acarology, 2011)

Multi-level modelling of chlorination by-product presence in drinking water distribution systems for human exposure assessment purposes - Christelle Legay; Manuel J. Rodriguez; Luis Miranda-Moreno; Jean-Baptiste Sérodes; Patrick Levallois (Environmental Monitoring and Assessment, 2011)

Shotgun Proteomic Analysis of Emiliania huxleyi, a Marine Phytoplankton Species of Major Biogeochemical Importance - Bethan M. Jones; Richard J. Edwards; Paul J. Skipp; C. David O’Connor; M. Debora Iglesias-Rodriguez (Marine Biotechnology, 2011)

Impact of administration of vancomycin or linezolid to critically ill patients with impaired renal function - O. Rodriguez Colomo; F. Álvarez Lerma; M.I. González Pérez; J-M. Sirvent; M. García Simón (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Effect of human-mediated migration and hybridization on the recovery of the American crocodile in Florida (USA) - David Rodriguez; Michael R. J. Forstner; Paul E. Moler; Joseph A. Wasilewski; Michael S. Cherkiss; Llewellyn D. Densmore III (Conservation Genetics, 2011)

Predisposition of cows to mastitis in non-infected mammary glands: effects of dietary-induced negative energy balance during mid-lactation on immune-related genes - Kasey M. Moyes; James K. Drackley; Dawn E. Morin; Sandra L. Rodriguez-Zas; Robin E. Everts; Harris A. Lewin; Juan J. Loor (Functional & Integrative Genomics, 2011)

Rapid identification of yeasts from positive blood culture bottles by pyrosequencing - I. Quiles-Melero; J. García-Rodriguez; M. P. Romero-Gómez; P. Gómez-Sánchez; J. Mingorance (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Communicating with Cancer Patients: What Areas do Physician Assistants Find Most Challenging? - Patricia A. Parker; Alicia C. Ross; Maura N. Polansky; J. Lynn Palmer; M. Alma Rodriguez; Walter F. Baile (Journal of Cancer Education, 2010)

Multifunctional Tumor-Targeted Polymer-Peptide-Drug Delivery System for Treatment of Primary and Metastatic Cancers - Pooja Chandna; Jayant J. Khandare; Elizabeth Ber; Lorna Rodriguez-Rodriguez; Tamara Minko (Pharmaceutical Research, 2010)

Sex-specific genetic architecture of human fatness in Chinese: the SAPPHIRe Study - Y.-F. Chiu; L.-M. Chuang; H.-Y. Kao; K.-C. Shih; M.-W. Lin; W.-J. Lee; T. Quertermous; J. D. Curb; I. Chen; B. L. Rodriguez; C. A. Hsiung (Human Genetics, 2010)

Cost-efficient management of coastal aquifers via recharge with treated wastewater and desalination of brackish groundwater: application to the Akrotiri basin and aquifer, Cyprus - A. D. Koussis; E. Georgopoulou; A. Kotronarou; K. Mazi; P. Restrepo; G. Destouni; C. Prieto; J. J. Rodriguez; J. Rodriguez-Mirasol; T. Cordero; C. Ioannou; A. Georgiou; et al. (Hydrological Sciences Journal, 2010)

Cost-efficient management of coastal aquifers via recharge with treated wastewater and desalination of brackish groundwater: general framework - A. D. Koussis; E. Georgopoulou; A. Kotronarou; D. P. Lalas; P. Restrepo; G. Destouni; C. Prieto; J. J. Rodriguez; J. Rodriguez-Mirasol; T. Cordero; A. Gomez-Gotor (Hydrological Sciences Journal, 2010)

Effects of density, climate, and supplementary forage on body mass and pregnancy rates of female red deer in Spain - P. Rodriguez-Hidalgo; C. Gortazar; F. S. Tortosa; C. Rodriguez-Vigal; Y. Fierro; J. Vicente (Oecologia, 2010)

Coordinated and sequential activation of neutral and acidic DNases during interdigital cell death in the embryonic limb - J. A. Montero; C. I. Lorda-Diez; A. C. Certal; N. Moreno; J. Rodriguez-Leon; A. Torriglia; J. M. Hurle (Apoptosis, 2010)

The possible origin of Zostera noltii in the Canary Islands and guidelines for restoration - O. E. Diekmann; L. Gouveia; J. A. Perez; C. Gil-Rodriguez; E. A. Serrão (Marine Biology, 2010)

Hepatitis A Virus: State of the Art - Rosa M. Pintó; M. Isabel Costafreda; Francisco J. Pérez-Rodriguez; Lucía D’Andrea; Albert Bosch (Food and Environmental Virology, 2010)

Association of physical activity with muscular strength and fat-free mass in adolescents: the HELENA study - Diego Moliner-Urdiales; Francisco B. Ortega; Germán Vicente-Rodriguez; Juan P. Rey-Lopez; Luis Gracia-Marco; Kurt Widhalm; Michael Sjöström; Luis A. Moreno; Manuel J. Castillo; Jonatan R. Ruiz (European Journal of Applied Physiology, 2010)

Using multi-criteria decision analysis to assess the vulnerability of drinking water utilities - Florent Joerin; Geneviève Cool; Manuel J. Rodriguez; Marc Gignac; Christian Bouchard (Environmental Monitoring and Assessment, 2010)

500-year temperature reconstruction in the Mediterranean Basin by means of documentary data and instrumental observations - Dario Camuffo; C. Bertolin; M. Barriendos; F. Dominguez-Castro; C. Cocheo; S. Enzi; M. Sghedoni; A. della Valle; E. Garnier; M.-J. Alcoforado; E. Xoplaki; J. Luterbacher; et al. (Climatic Change, 2010)

Characterization of three sect. Caulopterae species (Baccharis-Asteraceae) inferred from morphoanatomy, polypeptide profiles and spectrophotometry data - M. V. Rodriguez; M. L. Martínez; A. A. Cortadi; A. Bandoni; D. A. Giuliano; S. J. Gattuso; M. A. Gattuso (Plant Systematics and Evolution, 2010)

Nitrogen-Use Efficiency in Relation to Different Forms and Application Rates of Se in Lettuce Plants - Juan J. Ríos; Begoña Blasco; Luis M. Cervilla; Maria M. Rubio-Wilhelmi; Miguel A. Rosales; Eva Sanchez-Rodriguez; Luis Romero; Juan M. Ruiz (Journal of Plant Growth Regulation, 2010)

Metal–bipyridine complexes in DNA backbones and effects on thermal stability - Mildred M. Rodriguez-Ramos; Jonathan J. Wilker (JBIC Journal of Biological Inorganic Chemistry, 2010)

‘Alternate-goal bias’ in antisaccades and the influence of expectation - Mathias Abegg; Amadeo R. Rodriguez; Hyung Lee; Jason J. S. Barton (Experimental Brain Research, 2010)

Geomorphological reconstruction and morphometric modelling applied to past volcanism - A. Rodriguez-Gonzalez; J. L. Fernandez-Turiel; F. J. Perez-Torrado; D. Gimeno; M. Aulinas (International Journal of Earth Sciences, 2010)

Quantifying the limits of HANPP and carbon emissions which prolong total species well-being - Justin D. K. Bishop; Gehan A. J. Amaratunga; Cuauhtemoc Rodriguez (Environment, Development and Sustainability, 2010)

Greenhouse gas, upwelling‐favorable winds, and the future of coastal ocean upwelling ecosystems - ANDREW BAKUN; DAVID B. FIELD; ANA REDONDO‐RODRIGUEZ; SCARLA J. WEEKS (Global Change Biology, 2010)
Coastal ocean upwelling ecosystems generally represent the most productive large marine ecosystems of the world's oceans, in terms of both primary production rates and tonnages of exploitable fish produced. The Peruvian upwelling system, in particular, stands out as a major factor in world fish production. The Pacific trade winds have traditionally been considered to be the primary driving force for the upwelling system off Peru, but are projected to weaken as climate change proceeds. This leads to concern that the upwelling process in the Peru system, to which its productivity is linked, may likewise weaken. However, other mechanisms involving greenhouse‐associated intensification of thermal low‐pressure cells over the coastal landmasses of upwelling regions suggest general intensification of wind‐driven ocean upwelling in coastal upwelling regions of the world's oceans. But although certain empirical results have supported this expectation, it has not been consistently corroborated in climate model simulations, possibly because the scale of the coastal intensification may be small relative to the scales that are appropriately reflected in the standard models. Here we summarize available evidence for the intensification mechanism and present a proxy test that uses variations in water vapor, the dominant natural greenhouse gas, to offer multiple‐realization empirical evidence for action of the proposed mechanism in the real world situation. While many potential consequences to the future of marine ecosystems would codepend on climate change‐related changes in the thermocline and nutricline structures, an important subset, involving potential increased propensities for hypoxia, noxious gas eruptions, toxic red tide blooms, and/or jellyfish outbreaks, may depend more directly on changes in the upwelling‐favorable wind itself. A prospective role of fisheries in either mitigating or reinforcing this particular class of effects is suggested.

Ploidy levels of Dioscorea alata L. germplasm determined by flow cytometry - J. Obidiegwu; E. Rodriguez; E. Ene-Obong; J. Loureiro; C. Muoneke; C. Santos; M. Kolesnikova-Allen; R. Asiedu (Genetic Resources and Crop Evolution, 2010)

Seed treatments enhance photosynthesis in maize seedlings by reducing infection with Fusarium spp. and consequent disease development in maize - C. Rodriguez-Brljevich; C. Kanobe; J. F. Shanahan; A. E. Robertson (European Journal of Plant Pathology, 2010)

Why do humans make antisaccade errors? - Hyung Lee; Mathias Abegg; Amadeo Rodriguez; John Koehn; Jason J. S. Barton (Experimental Brain Research, 2010)

Potentiation of Local Anesthetic Activity of Neosaxitoxin with Bupivacaine or Epinephrine: Development of a Long-Acting Pain Blocker - Alberto J. Rodriguez-Navarro; Marcelo Lagos; Cristian Figueroa; Carlos Garcia; Pedro Recabal; Pamela Silva; Veronica Iglesias; Nestor Lagos (Neurotoxicity Research, 2009)

Ploidy level studies on the Dioscorea cayenensis/Dioscorea rotundata complex core set - J. Obidiegwu; J. Loureiro; E. Ene-Obong; E. Rodriguez; M. Kolesnikova-Allen; C. Santos; C. Muoneke; R. Asiedu (Euphytica, 2009)

Family history of various cancers and pancreatic cancer mortality in a large cohort - Eric J. Jacobs; Carmen Rodriguez; Christina C. Newton; Elizabeth B. Bain; Alpa V. Patel; Heather Spencer Feigelson; Michael J. Thun; Eugenia E. Calle (Cancer Causes & Control, 2009)

The Holocene volcanic history of Gran Canaria island: implications for volcanic hazards - Alejandro Rodriguez‐Gonzalez; Jose L. Fernandez‐Turiel; Francisco J. Perez‐Torrado; Alex Hansen; Meritxell Aulinas; Juan C. Carracedo; Domingo Gimeno; Hervé Guillou; Raphaël Paris; Martine Paterne (Journal of Quaternary Science, 2009)
Previous published data, combined with our results of 13 new radiocarbon ages and extensive geological fieldwork, indicate that during the past 11 ka 24 monogenetic basaltic eruptions occurred in the north sector of Gran Canaria. These eruptions can be grouped into three periods of eruptive activity: 1900–3200 14 C a BP; 5700–6000 14 C a BP; and an older period represented by only one eruption, El Draguillo, dated at 10 610 ± 190 14 C a BP. Archaeological studies have shown that the more recent eruptions affected prehistoric human settlements on the island. Field studies demonstrate that the eruptions typically built strombolian cones (30–250 m in height) and associated relatively long lava flows (100–10 350 m in length); a few eruptions also produced tephra fall deposits. The total erupted volume of these eruptions is about 0.388 km 3 (46.1% as tephra fall, 41.8% as cinder cone deposits and 12.1% as lava flows). The relatively low eruption rate (∼0.04 km 3 ka −1 ) during the past 11 ka is consistent with Gran Canaria's stage of evolution in the regional volcano‐tectonic setting of the Canary Archipelago. The results of our study were used to construct a volcanic hazards map that clearly delimits two sectors in the NE sector of Gran Canaria, where potential future eruptions would pose a substantial risk for densely populated areas. Copyright © 2009 John Wiley & Sons, Ltd.

Enhancement of the antioxidants ergothioneine and selenium in Pleurotus eryngii var. eryngii basidiomata through cultural practices - Alma E. Rodriguez Estrada; Hyun-Ju Lee; Robert B. Beelman; Maria del Mar Jimenez-Gasco; Daniel J. Royse (World Journal of Microbiology and Biotechnology, 2009)

Long‐term transpiration change with rainfall decline in a Mediterranean Quercus ilex forest - J. M. LIMOUSIN; S. RAMBAL; J. M. OURCIVAL; A. ROCHETEAU; R. JOFFRE; R. RODRIGUEZ‐CORTINA (Global Change Biology, 2009)
In the Mediterranean basin, precipitation is expected to decline as a consequence of climate change. The response of a Quercus ilex forest in southern France to such a decline in water availability was studied using a 4‐year throughfall exclusion experiment. Seasonal courses of sap flow and leaf water potential were obtained from 2004 to 2007 and used to characterize tree water relations in a control and a dry treatment. The experiment reduced the average precipitation input to the soil by 29%, and resulted in a 23% reduction in annual transpiration. Soil water potential was significantly lower in the dry treatment only during summer drought, but transpiration was reduced all year round even during well‐watered periods. Despite a tight stomatal control over transpiration, whole‐tree hydraulic conductance was found to be lower in the trees growing in the driest conditions. This reduction in water transport capacity was observed jointly with a reduction in leaf transpiring area. Canopy leaf area decreased by 18% in the dry treatment as a consequence of the throughfall exclusion, which was found to validate the ecohydrological equilibrium theory.

Association of matrix metalloproteinase-2 gene promoter polymorphism with myocardial infarction susceptibility in a Mexican population - Ivan Delgado-Enciso; Nelida A. Gonzalez-Hernandez; Luz M. Baltazar-Rodriguez; Rebeca O. Millan-Guerrero; Oscar Newton-Sanchez; Alfonso Bayardo-Noriega; Alfonso Aleman-Mireles; Irma G. Enriquez-Maldonado; Ma J. Anaya-Carrillo; Augusto Rojas-Martinez; Rocio Ortiz-Lopez (Journal of Genetics, 2009)

Oriented Immobilization of Anti-Pneumolysin Tagged Recombinant Antibody Fragments - Maria del Mar Garcia-Suarez; Roberto Villaverde; Irene Gonzalez-Rodriguez; Fernando Vazquez; Francisco J. Mendez (Current Microbiology, 2009)

Use of blood-pressure-lowering medication and risk of prostate cancer in the Cancer Prevention Study II Nutrition Cohort - Carmen Rodriguez; Eric J. Jacobs; Anusila Deka; Alpa V. Patel; Elizabeth B. Bain; Michael J. Thun; Eugenia E. Calle (Cancer Causes & Control, 2009)

Melatonin concentrations during larval and postlarval development of gilthead sea bream Sparus auratus : more than a time‐keeping molecule? - H. Kalamarz; M. Nietrzeba; J. Fuentes; G. Martinez‐Rodriguez; J.M. Mancera; E. Kulczykowska (Journal of Fish Biology, 2009)
In this study, melatonin (MEL) and thyroxine (T 4 ) concentrations were measured during larval and postlarval development of gilthead sea bream Sparus auratus Hormones were measured in whole bodies of larvae or the head and trunk of postlarvae after 67 days of exposure to constant light, 24L:0D, constant darkness, 0L:24D or 12L:12D and in the plasma of 6 month juveniles kept under the 12L:12D, 0L:24D and 24L:0D regimes. High MEL concentrations in larvae suggested a distinct role of MEL in early organogenesis and development of S. auratus . In larvae, the gastro‐intestinal tract seemed to be an important extrapineal and extraretinal source of MEL. No endogenous rhythm of MEL synthesis was demonstrated in 67 day larvae; however, in 6 month juveniles, it was evident. At early ontogenesis of S. auratus , the role of MEL is probably related mostly to the control of development and protection against free radicals, whereas its action as a time‐keeping molecule develops later. The increase in T 4 concentration during the S. auratus larva–juvenile transition, i.e . between 50 and 70 days post‐hatch, which was observed concurrently with the decrease of MEL concentration, may suggest an inverse relationship between T 4 and MEL.

One Hundred Questions of Importance to the Conservation of Global Biological Diversity - W. J. SUTHERLAND; W. M. ADAMS; R. B. ARONSON; R. AVELING; T. M. BLACKBURN; S. BROAD; G. CEBALLOS; I. M. CÔTÉ; R. M. COWLING; G. A. B. DA FONSECA; E. DINERSTEIN; P. J. FERRARO; et al. (Conservation Biology, 2009)
We identified 100 scientific questions that, if answered, would have the greatest impact on conservation practice and policy. Representatives from 21 international organizations, regional sections and working groups of the Society for Conservation Biology, and 12 academics, from all continents except Antarctica, compiled 2291 questions of relevance to conservation of biological diversity worldwide. The questions were gathered from 761 individuals through workshops, email requests, and discussions. Voting by email to short‐list questions, followed by a 2‐day workshop, was used to derive the final list of 100 questions. Most of the final questions were derived through a process of modification and combination as the workshop progressed. The questions are divided into 12 sections: ecosystem functions and services, climate change, technological change, protected areas, ecosystem management and restoration, terrestrial ecosystems, marine ecosystems, freshwater ecosystems, species management, organizational systems and processes, societal context and change, and impacts of conservation interventions. We anticipate that these questions will help identify new directions for researchers and assist funders in directing funds.

Molecular characterization of a foot-and-mouth disease virus containing a 57-nucleotide insertion in the 3′untranslated region - M. E. Piccone; S. Pauszek; J. Pacheco; E. Rieder; E. Kramer; L. L. Rodriguez (Archives of Virology, 2009)

Sex Pheromone of the Scarab Beetle Phyllophaga (Phytalus) georgiana (Horn) - Paul S. Robbins; Satoshi Nojima; Sridhar Polavarapu; Albrecht M. Koppenhöfer; Cesar Rodriguez-Saona; Robert J. Holdcraft; Nancy H. Consolie; Daniel C. Peck; Wendell L. Roelofs (Journal of Chemical Ecology, 2009)

Scintillometer Intercomparison Study—Continued - J. Kleissl; C. J. Watts; J. C. Rodriguez; S. Naif; E. R. Vivoni (Boundary-Layer Meteorology, 2009)

Herbivore-Induced Volatiles in the Perennial Shrub, Vaccinium corymbosum, and Their Role in Inter-branch Signaling - Cesar R. Rodriguez-Saona; Luis E. Rodriguez-Saona; Christopher J. Frost (Journal of Chemical Ecology, 2009)

Morphological and genetic variation in Aegilops geniculata from Algeria - H. Bandou; M. Rodriguez-Quijano; J. M. Carrillo; G. Branlard; M. Zaharieva; P. Monneveux (Plant Systematics and Evolution, 2009)

The Mitochondrial ATP-Sensitive Potassium Channel Blocker 5-Hydroxydecanoate Inhibits Toxicity of 6-Hydroxydopamine on Dopaminergic Neurons - J. Rodriguez-Pallares; J. A. Parga; B. Joglar; M. J. Guerra; J. L. Labandeira-Garcia (Neurotoxicity Research, 2009)

Proteomic analyses of monocyte-derived macrophages infected with human immunodeficiency virus type 1 primary isolates from Hispanic women with and without cognitive impairment - Dm Toro-Nieves; Y Rodriguez; M Plaud; P Ciborowski; F Duan; J Pérez Laspiur; V Wojna; LM Meléndez (Journal of NeuroVirology, 2009)

Lessons from comparative physiology: could uric acid represent a physiologic alarm signal gone awry in western society? - Richard J. Johnson; Yuri Y. Sautin; William J. Oliver; Carlos Roncal; Wei Mu; L. Gabriela Sanchez-Lozada; Bernardo Rodriguez-Iturbe; Takahiko Nakagawa; Steven A. Benner (Journal of Comparative Physiology B, 2009)

Dehydrin gene expression provides an indicator of low temperature and drought stress: transcriptome-based analysis of Barley (Hordeum vulgare L.) - Livia Tommasini; Jan T. Svensson; Edmundo M. Rodriguez; Abdul Wahid; Marina Malatrasi; Kenji Kato; Steve Wanamaker; Josh Resnik; Timothy J. Close (Functional & Integrative Genomics, 2008)

Phytolacca americana from Contaminated and Noncontaminated Soils of South Korea: Effects of Elevated Temperature, CO2 and Simulated Acid Rain on Plant Growth Response - Yong Ok Kim; Rusty J. Rodriguez; Eun Ju Lee; Regina S. Redman (Journal of Chemical Ecology, 2008)

Results of a short study of interactions of cetaceans and longline fisheries in Atlantic waters: environmental correlates of catches and depredation events - Gema Hernandez-Milian; Sabine Goetz; Catuxa Varela-Dopico; José Rodriguez-Gutierrez; Jorge Romón-Olea; José R. Fuertes-Gamundi; Edelmiro Ulloa-Alonso; Nick J. C. Tregenza; Andy Smerdon; Monserrat G. Otero; Vicente Tato; Jianjun Wang; et al. (Hydrobiologia, 2008)

Water-soluble organic and nitrogen levels in cloud and rainwater in a background marine environment under influence of different air masses - Adriana Gioda; Olga L. Mayol-Bracero; Gabriel J. Reyes-Rodriguez; Gilmarie Santos-Figueroa; Jeffrey L. Collett (Journal of Atmospheric Chemistry, 2008)

Transcriptional activity and distribution of splicing machinery elements during Hyacinthus orientalis pollen tube growth - K. Zienkiewicz; A. Zienkiewicz; M. I. Rodriguez-Garcia; D. J. Smoliński; M. Świdziński; E. Bednarska (Protoplasma, 2008)

CIGB-300, a novel proapoptotic peptide that impairs the CK2 phosphorylation and exhibits anticancer properties both in vitro and in vivo - Silvio E. Perea; Osvaldo Reyes; Idania Baladron; Yasser Perera; Hernán Farina; Jeovanis Gil; Arielis Rodriguez; Dania Bacardi; Jose L. Marcelo; Karelia Cosme; Marisol Cruz; Carmen Valenzuela; et al. (Molecular and Cellular Biochemistry, 2008)

Effect of growth temperature and pH on the aminopeptidase activity of Pseudomonas putida, P. fluorescens and Flavobacterium odoratum; the 4-nitroaniline test is reliable - L. A. Lopez-Tomas; J. A. Ordoñez; C. Mediavilla; J. L. Rodriguez-Marin; P. Sarmiento; A. Zamora; G. Garcia de Fernando (Folia Microbiologica, 2008)

Prevalence of BRCA1 and BRCA2 mutations in breast cancer patients from Cuba - Rolando Comacho Rodriguez; Antonio Alejandro Esperon; Ramon Ropero; Maria Caridad Rubio; Ronald Rodriguez; Rosa M. Ortiz; Juan J. Lence Anta; Mario de los Rios; Deyanira Carnesolta; Maria C. del Olivera; Somalia Stiu Vansam; Robert Royer; et al. (Familial Cancer, 2008)

Post-Treatment Hemodynamics of a Basilar Aneurysm and Bifurcation - J. Ortega; J. Hartman; J. Rodriguez; D. Maitland (Annals of Biomedical Engineering, 2008)

A potential function of endocannabinoids in the selection of a navigation strategy by rats - Pavel E. Rueda-Orozco; Edgar Soria-Gomez; Corinne J. Montes-Rodriguez; Marina Martínez-Vargas; Oscar Galicia; Luz Navarro; Oscar Prospero-García (Psychopharmacology, 2008)

Characterization of the full-length genomic sequences of vesicular stomatitis Cocal and Alagoas viruses - Steven J. Pauszek; Rossana Allende; Luis L. Rodriguez (Archives of Virology, 2008)

Developing UK farmers' institutional capacity to defend their water rights and effectively manage limited water resources - W. Leathes; J. W. Knox; M. G. Kay; P. Trawick; J. A. Rodriguez‐Diaz (Irrigation and Drainage, 2008)
Developing farmers' institutional capacity to defend their water rights is central to sustaining irrigation farming in the UK. Increasing demand and competition for water and the introduction of new water regulations have led many farmers to re‐evaluate the security of their water rights. As a consequence, some have formed water abstractors groups, a trend which is strongest in eastern England, where irrigation is most concentrated and water resources are most stressed. “Collective choice” theory attempts to explain how institutions evolve to share common resources and what key elements are needed for them to endure over the long term. This paper compares the characteristics of four existing water abstractors groups against those of “collective choice” theory. It concludes that it is applicable in the UK context and relevant when addressing a range of emerging water management challenges. The approach taken offers a means of analysing capacity at an institutional level and suggests a way of supporting the development of existing water abstractors groups as well as developing new ones. It is argued that this approach to developing institutional capacity could be used elsewhere where problems between resource availability, environmental protection and the sustainability of agricultural production are evident. Copyright © 2008 John Wiley & Sons, Ltd.

Genome-wide screen for asthma in Puerto Ricans: evidence for association with 5q23 region - Shweta Choudhry; Margaret Taub; Rui Mei; José Rodriguez-Santana; William Rodriguez-Cintron; Mark D. Shriver; Elad Ziv; Neil J. Risch; Esteban González Burchard (Human Genetics, 2008)

Paleoenvironmental evolution of the Pliocene Villarroya Lake, northern Spain, from stable isotopes and trace-element geochemistry of ostracods and molluscs - P. Anadón; R. Utrilla; A. Vázquez; M. Martín-Rubio; J. Rodriguez-Lázaro; F. Robles (Journal of Paleolimnology, 2008)

Characteristics of Streptococcus bovis endocarditis and its differences with Streptococcus viridans endocarditis - J. Corredoira; M. P. Alonso; A. Coira; E. Casariego; C. Arias; D. Alonso; J. Pita; A. Rodriguez; M. J. López; J. Varela (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Characterization of typo-, regio-, and stereo-selectivities of babaco latex lipase in aqueous and organic media - E. Cambon; J. A. Rodriguez; M. Pina; V. Arondel; F. Carriere; F. Turon; J. Ruales; P. Villeneuve (Biotechnology Letters, 2008)

Genetic characterization and molecular epidemiology of foot-and-mouth disease viruses isolated from Afghanistan in 2003–2005 - Kate R. Schumann; Nick J. Knowles; Paul R. Davies; Rebecca J. Midgley; Jean-Francois Valarcher; Abdul Quader Raoufi; Thomas S. McKenna; William Hurtle; James P. Burans; Barbara M. Martin; Luis L. Rodriguez; Tammy R. Beckham (Virus Genes, 2008)

Competing demands for irrigation water: golf and agriculture in Spain - J. A. Rodriguez Diaz; J. W. Knox; E. K. Weatherhead (Irrigation and Drainage, 2007)
In many countries where water resources are under stress, there is a perception that irrigating golf courses causes significant additional abstraction, and that this has major impacts on the environment and other abstractors, including irrigated agriculture. This paper provides a quantitative assessment of water use within the golf sector in Spain, and compares it with irrigated agriculture. It is based on literature review, a national survey of golf course irrigation practices, and a correlation of reported irrigation consumption against agroclimate. Using a geographical information system (GIS), the water consumption for all golf courses in Spain was modelled and mapped, and the total water consumption estimated. The results show that the volume of water used for golf irrigation is extremely small compared to agricultural irrigation. Furthermore, a significant portion comes from wastewater reuse (41%) and desalination (7%), rather than direct abstraction, which competes with agriculture. However, it is concentrated in particular tourist areas and could cause local problems. The average economic productivity of the water used for golf, estimated at around 9 € m −3 in direct benefits (course fees) and 28 € m −3 if including the benefits to the tourist industry, is very much higher than for even high‐value agricultural crops. These results suggest that irrigating golf courses for tourism purposes is an economically rational water use in Spain, even though the transfer of resources from agriculture is controversial. Copyright © 2007 John Wiley & Sons, Ltd.

Nickel Exposure Enhances the Susceptibility of Lichens Usnea amblyoclada and Ramalina celastri to Urban Atmospheric Pollutants - J. H. Rodriguez; H. A. Carreras; M. L. Pignata; C. M. González (Archives of Environmental Contamination and Toxicology, 2007)

In vitro activity of temocillin against prevalent extended-spectrum beta-lactamases producing Enterobacteriaceae from Belgian intensive care units - Y. Glupczynski; T.-D. Huang; C. Berhin; G. Claeys; M. Delmée; L. Ide; G. Ieven; D. Pierard; H. Rodriguez-Villalobos; M. Struelens; J. Vaneldere (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

A marker-assisted backcross approach for developing submergence-tolerant rice cultivars - C. N. Neeraja; R. Maghirang-Rodriguez; A. Pamplona; S. Heuer; B. C. Y. Collard; E. M. Septiningsih; G. Vergara; D. Sanchez; K. Xu; A. M. Ismail; D. J. Mackill (Theoretical and Applied Genetics, 2007)

Economic and management characterization of dehesa farms: implications for their sustainability - P. Gaspar; F. J. Mesías; M. Escribano; A. Rodriguez de Ledesma; F. Pulido (Agroforestry Systems, 2007)

Aquifer Vulnerability Zoning, an Indicator of Atmospheric Pollutants Input? Vanadium in the Salamanca Aquifer, Mexico - J. A. Mejia; R. Rodriguez; A. Armienta; E. Mata; A. Fiorucci (Water, Air, & Soil Pollution, 2007)

Evaluation of the Effects of a Single Exposure to Ethidium Bromide in Drosophila melanogaster (Diptera-Drosophilidae) - R. Y. Ouchi; A. J. Manzato; C. R. Ceron; G. O. Bonilla-Rodriguez (Bulletin of Environmental Contamination and Toxicology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Lack of evidence for effect modification by estrogen of association between body mass index and colorectal cancer risk among postmenopausal women - Yiting Wang; Eric J. Jacobs; Lauren R. Teras; Alexandre L. Pavluck; Carmen Rodriguez; Michael J. Thun; Eugenia E. Calle (Cancer Causes & Control, 2007)

Identification of two meridianins from the crude extract of the tunicate Aplidium meridianum by tandem mass spectrometry - A. M. Seldes; M. F. Rodriguez Brasco; L. Hernandez Franco; J. A. Palermo (Natural Product Research, 2007)

Implications of rainfall temporal resolution for soil-moisture and transpiration modeling - Michael J. Puma; Ignacio Rodriguez-Iturbe; Michael A. Celia; Andrew J. Guswa (Transport in Porous Media, 2007)

Communicating human health risks associated with disinfection by-products in drinking water supplies: a fuzzy-based approach - Rehan Sadiq; Manuel J. Rodriguez; Syed A. Imran; Homayoun Najjaran (Stochastic Environmental Research and Risk Assessment, 2007)

The use of transgenic canola (Brassica napus) and plant growth-promoting bacteria to enhance plant biomass at a nickel-contaminated field site - Andrea J. Farwell; Susanne Vesely; Vincent Nero; Hilda Rodriguez; Saleh Shah; D. George Dixon; Bernard R. Glick (Plant and Soil, 2006)

Spectral and thermal sensing for nitrogen and water status in rainfed and irrigated wheat environments - G. J. Fitzgerald; D. Rodriguez; L. K. Christensen; R. Belford; V. O. Sadras; T. R. Clarke (Precision Agriculture, 2006)

Nuclear DNA content of Vitis vinifera cultivars and ploidy level analyses of somatic embryo-derived plants obtained from anther culture - F. Leal; J. Loureiro; E. Rodriguez; M. S. Pais; C. Santos; O. Pinto-Carnide (Plant Cell Reports, 2006)

Changing trends in etiology of bacteremia in patients with cancer - A. Safdar; G. H. Rodriguez; M. Balakrishnan; J. J. Tarrand; K. V. I. Rolston (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Air Mercury Levels in a Pharmaceutical and Chemical Sciences School Building - J. Olivero-Verbel; J. Ropero-Vega; W. Ortiz-Rivera; P. Vera-Ospina; N. Torres-Fuentes; N. Montoya-Rodriguez (Bulletin of Environmental Contamination and Toxicology, 2006)

Toxicity of Santander Bay Sediments to the Euryhaline Freshwater Oligochaete Limnodrilus hoffmeisteri - P. Rodriguez; J. Arrate; M. Martinez-Madrid; T. B. Reynoldson; V. Schumacher; J. Viguri (Hydrobiologia, 2006)

Air Mercury Levels in a Pharmaceutical and Chemical Sciences School Building - J. Olivero-Verbel; J. Ropero-Vega; W. Ortiz-Rivera; P. Vera-Ospina; N. Torres-Fuentes; N. Montoya-Rodriguez (Bulletin of Environmental Contamination and Toxicology, 2006)

Successful treatment of septic shock due to pan-resistant Acinetobacter baumannii using combined antimicrobial therapy including tigecycline - F. S. Taccone; H. Rodriguez-Villalobos; D. De Backer; V. De Moor; J. Deviere; J.-L. Vincent; F. Jacobs (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

A Pooled Analysis of 12 Cohort Studies of Dietary Fat, Cholesterol and Egg Intake and Ovarian Cancer - Jeanine M. Genkinger; David J. Hunter; Donna Spiegelman; Kristin E. Anderson; W. Lawrence Beeson; Julie E. Buring; Graham A. Colditz; Gary E. Fraser; Jo L. Freudenheim; R. Alexandra Goldbohm; Susan E. Hankinson; Karen L. Koenig; et al. (Cancer Causes & Control, 2006)

Propensity for paternal inheritance of de novo mutations in Alexander disease - Rong Li; Anne B. Johnson; Gajja S. Salomons; Marjo S. van der Knaap; Diana Rodriguez; Odile Boespflug-Tanguy; J. Rafael Gorospe; James E. Goldman; Albee Messing; Michael Brenner (Human Genetics, 2006)

The effect of headspace renewal in a Temporary Immersion Bioreactor on plantain (Musa AAB) shoot proliferation and quality - S. Roels; C. Noceda; M. Escalona; J. Sandoval; M.J. Canal; R. Rodriguez; P. Debergh (Plant Cell, Tissue and Organ Culture (PCTOC), 2006)

Two new behavioral QTLs, Emo4 and Reb1, map to mouse Chromosome 1: Congenic strains and candidate gene identification studies - Ana Maria Rodriguez de Ledesma; Aarti N. Desai; Valerie J. Bolivar; Derek J. Symula; Lorraine Flaherty (Mammalian Genome, 2006)

The impacts of climate change in coastal marine systems - Christopher D. G. Harley; A. Randall Hughes; Kristin M. Hultgren; Benjamin G. Miner; Cascade J. B. Sorte; Carol S. Thornber; Laura F. Rodriguez; Lars Tomanek; Susan L. Williams (Ecology Letters, 2006)
Anthropogenically induced global climate change has profound implications for marine ecosystems and the economic and social systems that depend upon them. The relationship between temperature and individual performance is reasonably well understood, and much climate‐related research has focused on potential shifts in distribution and abundance driven directly by temperature. However, recent work has revealed that both abiotic changes and biological responses in the ocean will be substantially more complex. For example, changes in ocean chemistry may be more important than changes in temperature for the performance and survival of many organisms. Ocean circulation, which drives larval transport, will also change, with important consequences for population dynamics. Furthermore, climatic impacts on one or a few ‘leverage species’ may result in sweeping community‐level changes. Finally, synergistic effects between climate and other anthropogenic variables, particularly fishing pressure, will likely exacerbate climate‐induced changes. Efforts to manage and conserve living marine systems in the face of climate change will require improvements to the existing predictive framework. Key directions for future research include identifying key demographic transitions that influence population dynamics, predicting changes in the community‐level impacts of ecologically dominant species, incorporating populations’ ability to evolve (adapt), and understanding the scales over which climate will change and living systems will respond.

New Cyclodextrin Hydrogels Cross-Linked with Diglycidylethers with a High Drug Loading and Controlled Release Ability - Carmen Rodriguez-Tenreiro; Carmen Alvarez-Lorenzo; Ana Rodriguez-Perez; Angel Concheiro; Juan J. Torres-Labandeira (Pharmaceutical Research, 2006)

Field Performance of Pinus radiata D. Don Produced in Nursery with Different Types of Containers - U. Ortega; J. Majada; A. Mena-Petite; J. Sanchez-Zabala; N. Rodriguez-Iturrizar; K. Txarterina; J. Azpitarte; M. Duñabeitia (New Forests, 2006)

Population stratification confounds genetic association studies among Latinos - Shweta Choudhry; Natasha E. Coyle; Hua Tang; Keyan Salari; Denise Lind; Suzanne L. Clark; Hui-Ju Tsai; Mariam Naqvi; Angie Phong; Ngim Ung; Henry Matallana; Pedro C. Avila; et al. (Human Genetics, 2006)

Surfactant-Enhanced Desorption of Atrazine and Linuron Residues as Affected by Aging of Herbicides in Soil - M. S. Rodriguez-Cruz; M. J. Sanchez-Martin; M. Sanchez-Camazano (Archives of Environmental Contamination and Toxicology, 2006)

Genome-wide SNP discovery and linkage analysis in barley based on genes responsive to abiotic stress - Nils Rostoks; Sharon Mudie; Linda Cardle; Joanne Russell; Luke Ramsay; Allan Booth; Jan T. Svensson; Steve I. Wanamaker; Harkamal Walia; Edmundo M. Rodriguez; Peter E. Hedley; Hui Liu; et al. (Molecular Genetics and Genomics, 2005)

Targeted disruption of mouse Coch provides functional evidence that DFNA9 hearing loss is not a COCH haploinsufficiency disorder - Tomoko Makishima; Clara I. Rodriguez; Nahid G. Robertson; Cynthia C. Morton; Colin L. Stewart; Andrew J. Griffith (Human Genetics, 2005)

Laboratory-scale chlorination to estimate the levels of halogenated DBPs in full-scale distribution systems - Manuel J. Rodriguez; Jean Sérodes (Environmental Monitoring and Assessment, 2005)

The Effects of Spatial Scale on Trophic Interactions - Johan Van de Koppel; Richard D. Bardgett; Janne Bengtsson; Claudino Rodriguez-Barrueco; Max Rietkerk; Martin J. Wassen; Volkmar Wolters (Ecosystems, 2005)

Parity, Other Reproductive Factors, and Risk of Pancreatic Cancer Mortality in a Large Cohort of U.S. Women (United States) - Lauren R. Teras; Alpa V. Patel; Carmen Rodriguez; Michael J. Thun; Eugenia E. Calle (Cancer Causes & Control, 2005)

Melatonin increases the survival time of animals with untreated mammary tumours: Neuroendocrine stabilization - M. C. Saez; C. Barriga; J. J. Garcia; A. B. Rodriguez; J. Masot; E. Duran; E. Ortega (Molecular and Cellular Biochemistry, 2005)

Environmental Correlates of Tree and Seedling–Sapling Distributions in a Mexican Tropical Dry Forest - Yalma Luisa Vargas-Rodriguez; J. Antonio Vázquez-García; G. Bruce Williamson (Plant Ecology, 2005)

Behavioral alterations in lewis rats following two-day continuous 3-nitropropionic acid administration - J. D. Newcomb; W. D. Brown; A. I. Rodriguez; S. Garbuzova-Davis; S. Saporta; P. R. Sanberg; A. E. Willing (Neurotoxicity Research, 2005)

ATM Polymorphism and hereditary nonpolyposis colorectal cancer (HNPCC) ageof onset (United States) - J. Shawn Jones; Xiangjun Gu; Patrick M. Lynch; Miguel Rodriguez-Bigas; Christopher I. Amos; Marsha L. Frazier (Cancer Causes & Control, 2005)

Use of multivitamins and prostate cancer mortality in a large cohort of US men - Victoria L. Stevens; Marjorie L. McCullough; W. Ryan. Diver; Carmen Rodriguez; Eric J. Jacobs; Michael J. Thun; Eugenia E. Calle (Cancer Causes & Control, 2005)

Optimization of plantain (Musa AAB) micropropagation by temporary immersion system - S. Roels; M. Escalona; I. Cejas; C. Noceda; R. Rodriguez; M. J. Canal; J. Sandoval; P. Debergh (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Clinical characteristics and significance of Streptococcus salivarius bacteremia and Streptococcus bovis bacteremia: a prospective 16-year study - J. C. Corredoira; M. P. Alonso; J. F. García; E. Casariego; A. Coira; A. Rodriguez; J. Pita; C. Louzao; B. Pombo; M. J. López; J. Varela (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Secondary metabolites from endophytic fungi isolated from the Chilean gymnosperm Prumnopitys andina (Lleuque) - G. Schmeda-Hirschmann; E. Hormazabal; L. Astudillo; J. Rodriguez; C. Theoduloz (World Journal of Microbiology and Biotechnology, 2005)

Effects of Tropospheric Ozone on Potato Plants Protected by the Antioxidant Diphenylamine (DPA) - J. L. Carrasco-Rodriguez; A. Asensi-Fabado; S. Del Valle-Tascon (Water, Air, & Soil Pollution, 2005)

Development of a citrus genome-wide EST collection and cDNA microarray as resources for genomic studies - J. Forment; J. Gadea; L. Huerta; L. Abizanda; J. Agusti; S. Alamar; E. Alos; F. Andres; R. Arribas; J. P. Beltran; A. Berbel; M. A. Blazquez; et al. (Plant Molecular Biology, 2005)

Environmental Education as a Component of Multidisciplinary Conservation Programs: Lessons from Conservation Initiatives for Critically Endangered Fruit Bats in the Western Indian Ocean - W. J. TREWHELLA; K. M. RODRIGUEZ‐CLARK; N. CORP; A. ENTWISTLE; S. R. T. GARRETT; E. GRANEK; K. L. LENGEL; M. J. RABOUDE; P. F. REASON; B. J. SEWALL (Conservation Biology, 2005)
Pteropus livingstonii , P. voeltzkowi , and P. rodricensis are three critically endangered fruit bats from western Indian Ocean islands for which multidisciplinary conservation programs have been established that include environmental education programs (EEPs). We describe these EEPs in terms of the strategies used to achieve them and evaluate the educational and conservation outcomes and impacts of the programs. Educational outputs (including posters, stickers, videos, lesson plans, and workshops), primarily linking human needs to the ecosystem services provided by bats, were delivered to schools and community groups, and local environmental educators were trained to further develop the EEPs. Outcomes included increased local awareness about the bats and their conservation, training of environmental educators, inclusion of bat conservation and environmental issues in the school curricula, and establishment of community‐based environmental nongovernmental organizations (NGOs). Extensive prior planning, presentations in local languages, distribution of outputs through existing networks of educators, training of local educators, establishment of local environmental NGOs, and local capacity‐building were all associated with these EEPs achieving their goals in the under‐resourced island locations where these bats are found. The EEPs were also important in the development of other components of their respective conservation programs, such as population monitoring programs. Although long‐term conservation impacts, particularly tackling habitat loss, are slow to materialize and social and economic issues need to be addressed, these EEPs have already had important outcomes and have established the foundation for future conservation actions.

Nutrient study for the transition from earthen sedimentation ponds to ones lined with pvc in integrated mariculture systems, what needs to be done? - John J. Lee; Damaris Rodriguez; Amir Neori; Oded Zmora; Andrew Symons; Muki Shpigel (Journal of Applied Phycology, 2004)

Spatial partitioning and asymmetric hybridization among sympatric coastal steelhead trout ( Oncorhynchus mykiss irideus ), coastal cutthroat trout ( O. clarki clarki ) and interspecific hybrids - CARL O. OSTBERG; STACEY L. SLATTON; RUSSELL J. RODRIGUEZ (Molecular Ecology, 2004)
Hybridization between sympatric species provides unique opportunities to examine the contrast between mechanisms that promote hybridization and maintain species integrity. We surveyed hybridization between sympatric coastal steelhead ( Oncorhynchus mykiss irideus ) and coastal cutthroat trout ( O. clarki clarki ) from two streams in Washington State, Olsen Creek (256 individuals sampled) and Jansen Creek (431 individuals sampled), over a 3‐year period. We applied 11 O. mykiss ‐specific nuclear markers, 11 O. c. clarki ‐specific nuclear markers and a mitochondrial DNA marker to assess spatial partitioning among species and hybrids and determine the directionality of hybridization. F 1 and post‐F 1 hybrids, respectively, composed an average of 1.2% and 33.6% of the population sampled in Jansen Creek, and 5.9% and 30.4% of the population sampled in Olsen Creek. A modest level of habitat partitioning among species and hybrids was detected. Mitochondrial DNA analysis indicated that all F 1 hybrids (15 from Olsen Creek and five from Jansen Creek) arose from matings between steelhead females and cutthroat males implicating a sneak spawning behaviour by cutthroat males. First‐generation cutthroat backcrosses contained O. c. clarki mtDNA more often than expected suggesting natural selection against F 1 hybrids. More hybrids were backcrossed toward cutthroat than steelhead and our results indicate recurrent hybridization within these creeks. Age analysis demonstrated that hybrids were between 1 and 4 years old. These results suggest that within sympatric salmonid hybrid zones, exogenous processes (environmentally dependent factors) help to maintain the distinction between parental types through reduced fitness of hybrids within parental environments while divergent natural selection promotes parental types through distinct adaptive advantages of parental phenotypes.

Behavioral Response of Lygus hesperus to Conspecifics and Headspace Volatiles of Alfalfa in a Y-Tube Olfactometer - J. L. Blackmer; C. Rodriguez-Saona; J. A. Byers; K. L. Shope; J. P. Smith (Journal of Chemical Ecology, 2004)

The Role of Fungal Symbioses in the Adaptation of Plants to High Stress Environments - Russell J. Rodriguez; Regina S. Redman; Joan M. Henson (Mitigation and Adaptation Strategies for Global Change, 2004)

Transgenic Rice as a Vehicle for the Production of the Industrial Enzyme Transglutaminase - M.I. Claparols; L. Bassie; B. Miro; S. Del Duca; J. Rodriguez-Montesinos; P. Christou; D. Serafini-Fracassini; T. Capell (Transgenic Research, 2004)

Effects of lindane on the photosynthetic apparatus of the cyanobacteriumanabaena - Marta Bueno; Maria F. Fillat; Reto J. Strasser; Ronald Maldonado-Rodriguez; Nerea Marina; Henry Smienk; Carlos Gómez-Moreno; Francisco Barja (Environmental Science and Pollution Research, 2004)

Haemophilus parainfluenzae : an Underdiagnosed Pathogen of Biliary Tract Infections? - J. Frankard; H. Rodriguez-Villalobos; M. J. Struelens; F. Jacobs (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Experimental Study of the Formation of Chlorination By-Products in Potable Water of Quebec City, Canada - M. J. Rodriguez; M. Huard; J.-B. Srodes (Bulletin of Environmental Contamination and Toxicology, 2004)

Trihalomethanes in Drinking Water of Greater Québec Region (Canada): Occurrence, Variations and Modelling - Manuel J. Rodriguez; Yannick Vinette; Jean-B. Sérodes; Christian Bouchard (Environmental Monitoring and Assessment, 2003)

Can machines recognise stress in plants? - Ronald Maldonado-Rodriguez; Stancho Pavlov; Alberto Gonzalez; Abdallah Oukarroum; Reto J. Strasser (Environmental Chemistry Letters, 2003)

Volatile Emissions Triggered by Multiple Herbivore Damage: Beet Armyworm and Whitefly Feeding on Cotton Plants - Cesar Rodriguez-Saona; Steven J. Crafts-Brandner; Luis A. Cañas (Journal of Chemical Ecology, 2003)

A comparative study of the expression of monoamine oxidase-A and -B mRNA and protein in non-CNS human tissues - S. D. Sivasubramaniam; C. C. Finch; M. J. Rodriguez; N. Mahy; E. E. Billett (Cell and Tissue Research, 2003)

Integration of soil solarization with chemical, biological and cultural control for the management of soilborne diseases of vegetables - C. Stevens; V. A. Khan; R. Rodriguez-Kabana; L. D. Ploper; P. A. Backman; D. J. Collins; J. E. Brown; M. A. Wilson; E. C. K. Igwegbe (Plant and Soil, 2003)

Comparative analysis of superfamilies of NBS-encoding disease resistance gene analogs in cultivated and wild apple species - S.-Y. Lee; J.-S. Seo; M. Rodriguez-Lanetty; D.-H. Lee (Molecular Genetics and Genomics, 2003)

Characterization of the RNA-binding activity of VP3, a major structural protein of Infectious bursal disease virus - G. Kochan; D. Gonzalez; J. F. Rodriguez (Archives of Virology, 2003)

Calcium, vitamin D, dairy products, and risk of colorectal cancer in the Cancer Prevention Study II Nutrition Cohort (United States) - Marjorie L. McCullough; Andrea S. Robertson; Carmen Rodriguez; Eric J. Jacobs; Ann Chao; Carolyn Jonas; Eugenia E. Calle; Walter C. Willett; Michael J. Thun (Cancer Causes & Control, 2003)

Lygus hesperus Feeding and Salivary Gland Extracts Induce Volatile Emissions in Plants - Cesar Rodriguez-Saona; Steven J. Crafts-Brandner; Livy Williams; Paul W. Paré (Journal of Chemical Ecology, 2002)

Field evaluation of partially acidulated phosphate rocks in a Ferralsol from Cuba - R. Rodriguez; J. Herrera (Nutrient Cycling in Agroecosystems, 2002)

Late Holocene pollution in the Gernika estuary (southern Bay of Biscay) evidenced by the study of Foraminifera and Ostracoda - A. Pascual; J. Rodriguez-Lazaro; O. Weber; J.M. Jouanneau (Hydrobiologia, 2002)

Body mass index, height, and postmenopausal breast cancer mortality in a prospective cohort of US women - Jennifer M. Petrelli; Eugenia E. Calle; Carmen Rodriguez; Michael J. Thun (Cancer Causes & Control, 2002)

Jewish ethnicity and prostate cancer mortality in two large US cohorts - Carmen Rodriguez; Eric J. Jacobs; Alpa V. Patel; Eugenia E. Calle; Heather Spencer Feigelson; Dorna Fakhrabadi-Shokoohi; Michael J. Thun (Cancer Causes & Control, 2002)

The Bayesian approach applied to GPS ambiguity resolution. A mixture model for the discrete-real ambiguities alternative - M. C. de Lacy; F. Sansò; G. Rodriguez-Caderot; A. J. Gil (Journal of Geodesy, 2002)

Cross Reaction Between a Pan-Candida Genus Probe and Fusarium Spp. in a Fatal Case of Fusarium oxysporum Pneumonia - H. Rodriguez-Villalobos; M. Aoun; C. Heymans; J. De Bruyne; V. Duchateau; J. Verdebout; F. Crokaert (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

ICAM-1 is crucial for protection from TMEV-induced neuronal damage but not demyelination - Kristen M Drescher; Laurie J Zoecklein; Moses Rodriguez (Journal of NeuroVirology, 2002)

Multivitamin use and colon cancer mortality in the Cancer Prevention Study II cohort (United States) - Eric J. Jacobs; Cari J. Connell; Alpa V. Patel; Ann Chao; Carmen Rodriguez; Jennifer Seymour; Marjorie L. McCullough; Eugenia E. Calle; Michael J. Thun (Cancer Causes & Control, 2001)

Attempts at oral pharmacological treatment of Ichthyophthirius multifiliis in rainbow trout, Oncorhynchus mykiss (Walbaum) - J L Tojo Rodriguez; M T Santamarina Fernandez (Journal of Fish Diseases, 2001)

EXOGENOUS METHYL JASMONATE INDUCES VOLATILE EMISSIONS IN COTTON PLANTS - Cesar Rodriguez-Saona; Steven J. Crafts-Brandner; Paul W. ParÉ; Thomas J. Henneberry (Journal of Chemical Ecology, 2001)

The reliability of immunohistochemistry as a prescreening method for the diagnosis of hereditary nonpolyposis colorectal cancer (HNPCC) – Results of an international collaborative study - Wolfram Müller; Lawrence J. Burgart; Ruth Krause-Paulus; Stephen N. Thibodeau; M. Almeida; T. Brocker Edmonston; C. R. Boland; C. Sutter; J. R. Jass; A. Lindblom; J. Lubinski; K. MacDermot; et al. (Familial Cancer, 2001)

Molecular linkage mapping in rye (Secale cereale L.) - X.-F. Ma; M. K. Wanous; K. Houchins; M. A. Rodriguez Milla; P. G. Goicoechea; Z. Wang; M. Xie; J. P. Gustafson (Theoretical and Applied Genetics, 2001)

Identification of genomic regions that affect grain-mould incidence and other traits of agronomic importance in sorghum - R. R. Klein; R. Rodriguez-Herrera; J. A. Schlueter; P. E. Klein; Z. H. Yu; W. L. Rooney (Theoretical and Applied Genetics, 2001)

Physical and chemical processes in the application of CA and/or fumigation - Cecilia V. De Dios; Maria Finesa A. Cosico; Ma. Elvira M. Martinez; D. D. Julian; I. V. Dator; R. L. Tiongson; J. van S. Graver; S. Pratt; C. Reed; Sylvia Allen; G. N. Mbata; T. W. Phillips; et al. (Phytoparasitica, 2001)

Tubal sterilization and risk of breast cancer mortality in US women - Eugenia E. Calle; Carmen Rodriguez; Kimberly A. Walker; Phyllis A. Wingo; Jennifer M. Petrelli; Michael J. Thun (Cancer Causes & Control, 2001)

Mitochondrial DNA control region diversity in the endangered blue chaffinch, Fringilla teydea - J. Pestano; R. P. Brown; F. Rodriguez; A. Moreno (Molecular Ecology, 2000)
The blue chaffinch ( Fringilla teydea ) is found only on the two central Canary Islands of Gran Canaria and Tenerife, where it is restricted to pine forest habitat. It is reasonably abundant on the latter island but endangered on the former. Here, sequence variation was studied in a fragment spanning domains I and II of the mitochondrial DNA (mtDNA) control region. Phylogenetic analysis of all haplotypes with a F. coelebs outgroup indicated the two island populations were reciprocally monophyletic, supporting their individual conservation. Unlike in other species, most within‐island haplotype diversity was due to mutations in the domain II region. Surprisingly, genetic diversity was greater in the smaller Gran Canarian population. We suggest that this is unlikely to be maintained under current population sizes although it may be mitigated by incorporating genetic information into the captive breeding programme.

Ecotoxicological Assessment of Two Pulp Mill Effluent, Biobio River Basin, Chile - H. Gaete; A. Larrain; E. Bay-Schmith; J. Baeza; J. Rodriguez (Bulletin of Environmental Contamination and Toxicology, 2000)

Ecotoxicological Assessment of Two Pulp Mill Effluent, Biobio River Basin, Chile - H. Gaete; A. Larrain; E. Bay-Schmith; J. Baeza; J. Rodriguez (Bulletin of Environmental Contamination and Toxicology, 2000)

Plant species diversity as a driver of early succession in abandoned fields: a multi-site approach - W. H. Van der Putten; S. R. Mortimer; K. Hedlund; C. Van Dijk; V. K. Brown; J. Lepä; C. Rodriguez-Barrueco; J. Roy; T. A. Diaz Len; D. Gormsen; G. W. Korthals; S. Lavorel; et al. (Oecologia, 2000)

Linkage mapping and QTL analysis in coconut (Cocos nucifera L.) - A. Herrán; L. Estioko; D. Becker; M. J. B. Rodriguez; W. Rohde; E. Ritter (Theoretical and Applied Genetics, 2000)

Patterns of inpatient surgeries for the top four cancers in the United States, National Hospital Discharge Survey, 1988–95 - Phyllis A. Wingo; Jodie L. Guest; LaMar McGinnis; Daniel S. Miller; Carmen Rodriguez; Cheryll J. Cardinez; Brian Morrow; Michael J. Thun (Cancer Causes & Control, 2000)

Sequence and diversity of MHC DQA and DQB genes of the owl monkey Aotus nancymaae - Diana Diaz; Martin Naegeli; Raul Rodriguez; J. Javier Nino-Vasquez; Alberto Moreno; Manuel Elkin Patarroyo; Gerd Pluschke; Claudia A. Daubenberger (Immunogenetics, 2000)

El Niño influence on streamflow forecasting - J. Kelman; A. de M. Vieira; J. E. Rodriguez-Amaya (Stochastic Environmental Research and Risk Assessment, 2000)

Behavior of Brick Samples in Aggressive Environments - G. Cultrone; M. J. De la Torre; E. M. Sebastian; O. Cazalla; C. Rodriguez-Navarro (Water, Air, & Soil Pollution, 2000)

Reaction of common bean callus to culture filtrate of Colletotrichum lindemuthianum: Differences in the composition and toxic activity of fungal culture filtrates - M . T. Fernández; M. Fernández; M. L. Centeno; M . J. Cañal; R. Rodriguez (Plant Cell, Tissue and Organ Culture (PCTOC), 2000)

Characterization of novel microsatellite loci isolated from the tropical dioecious tree Simarouba amara - H. Rodriguez; J. Geistlinger; G. Berlyn; G. Kahl; K. Weising (Molecular Ecology, 2000)

Sequence and diversity of DRB genes of Aotus nancymaae , a primate model for human malaria parasites - J. Javier Nino-Vasquez; Denise Vogel; Raul Rodriguez; Alberto Moreno; Manuel Elkin Patarroyo; Gerd Pluschke; Claudia A. Daubenberger (Immunogenetics, 2000)

The correlation of the gene csoS2 of the carboxysome operon with two polypeptides of the carboxysome in Thiobacillus neapolitanus - S. H. Baker; S. C. Lorbach; M. Rodriguez-Buey; Donna S. Williams; Henry C. Aldrich; J. M. Shively (Archives of Microbiology, 1999)

A statistical approach to study the dynamics of micropropagation rates, using banana ( Musa spp.) as an example - B. M. J. Mendes; S. B. Filippi; C. G. B. Demétrio; A. P. M. Rodriguez (Plant Cell Reports, 1999)

Synthesis and characterization of Sodium cis-dichlorochenodeoxycholylglycinato(O,N) platinum(II) – Cytostatic activity - Julio J. Criado; M.C. Garcia-Moreno; Rocio R. Macias; Jose J.G. Marin; Manuel Medarde; E. Rodriguez-Fernandez (BioMetals, 1999)

Variation among and within Capsicum species revealed by RAPD markers - J. M. Rodriguez; T. Berke; L. Engle; J. Nienhuis (Theoretical and Applied Genetics, 1999)

Structure and function of the stalk, a putative regulatory element of the yeast ribosome. Role of stalk protein phosphorylation - M. A. Rodriguez-Gabriel; G. Bou; E. Briones; R. Zambrano; M. Remacha; J. P. G. Ballesta (Folia Microbiologica, 1999)

Sediment Toxicity Bioassays for Assessment of Contaminated Sites in the Nervion River (Northern Spain). 1. Three-Brood Sediment Chronic Bioassay of Daphnia Magna Straus - M. Martinez-Madrid; P. Rodriguez; J. I. Perez-Iglesias (Ecotoxicology, 1999)

Monthly mean pressure reconstructions for Europe for the 1780–1995 period - P.D. Jones; T.D. Davies; D.H. Lister; V. Slonosky; T. Jónsson; L. Bärring; P. Jönsson; P. Maheras; F. Kolyva‐Machera; M. Barriendos; J. Martin‐Vide; R. Rodriguez; et al. (International Journal of Climatology, 1999)

Regulation by members of the transforming growth factor beta superfamily of the digital and interdigital fates of the autopodial limb mesoderm - Domingo Macias; Yolanda Gañan; Joaquin Rodriguez-Leon; Ramon Merino; J. M. Hurle (Cell and Tissue Research, 1999)

Infertility and risk of fatal ovarian cancer in a prospective cohort of US women - Carmen Rodriguez; Lilith M. Tatham; Eugenia E. Calle; Michael J. Thun; Eric J. Jacobs; Clark W. Heath (Cancer Causes & Control, 1998)

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Diabetes mellitus and pancreaticcancer mortality in a prospectivecohort of United States adults - Eugenia E. Calle; Terrell K. Murphy; Carmen Rodriguez; Michael J. Thun; Clark W. Heath (Cancer Causes & Control, 1998)

Neurological and functional effects of short-term exposure to hand-arm vibration - J. Malchaire; L. S. Rodriguez Diaz; A. Piette; F. Gonçalves Amaral; D. de Schaetzen (International Archives of Occupational and Environmental Health, 1998)

The corticostriatal system mediates the "paradoxical" contraversive rotation but not the striatal hyperexpression of Fos induced by amphetamine early after 6-hydroxydopamine lesion of the nigrostriatal pathway - E. Lopez-Martin; G. Rozas; J. Rodriguez; M. J. Guerra; J. L. Labandeira-Garcia (Experimental Brain Research, 1998)

Spatial and temporal patterns of annual precipitation variability over the Iberian Peninsula - C. Rodriguez-Puebla; A. H. Encinas; S. Nieto; J. Garmendia (International Journal of Climatology, 1998)

The structure of carbonyl horseradish peroxidase: spectroscopic and kinetic characterization of the carbon monoxide complexes of His-42 → Leu and Arg-38 → Leu mutants - Jose Neptuno Rodriguez-Lopez; Simon J. George; R. N. F. Thorneley (JBIC Journal of Biological Inorganic Chemistry, 1998)

Seed germination in wild clovers ( Trifolium, Leguminosae ) from Southwestern Europe (Spain) - J. A. DEVESA; T. RUIZ; P. RODRIGUEZ (Plant Biosystems, 1998)

Biological Control of Maize and Sugarcane Stemborers in Mexico: A Review - L. A. Rodriguez-Del-Bosque; J. W. Smith (International Journal of Tropical Insect Science, 1997)

Embryogenesis induction in petals of Araujia sericifera - J. M. Torné; P. Rodriguez; A. Manich; I. Claparols; M. A. Santos (Plant Cell, Tissue and Organ Culture (PCTOC), 1997)

Metallothionein-like metalloproteins in the Baltic clam Macoma balthica : seasonal variations and induction upon metal exposure - G. Bordin; J. McCourt; F. Cordeiro Raposo; A. R. Rodriguez (Marine Biology, 1997)

Biodegradation of acidolysis lignins from Chilean hardwoods by the ascomycete Chrysonilia sitophila - H.D. Mansilla; J. Rodriguez; A. Ferraz; N. Duran (World Journal of Microbiology and Biotechnology, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Factors affecting mortality of crossbred and exotic chickens kept under backyard systems in Yucatan, Mexico - J. C. Rodriguez; J. C. Segura; A. Alzina; M. A. Gutierrez (Tropical Animal Health and Production, 1997)

A molecular genetic map of cassava (Manihot esculenta Crantz) - M. Fregene; F. Angel; R. Gomez; F. Rodriguez; P. Chavarriaga; W. Roca; J. Tohme; M. Bonierbale (Theoretical and Applied Genetics, 1997)

Prosthetic joint infection byPasteurella multocida - J. A. Maradona; V. Asensi; J. A. Carton; A. Rodriguez Guardado; J. Lizón Castellano (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Photosynthetic electron transport and carbon-reduction-cycle enzyme activities under long-term drought stress in Casuarina equisetifolia Forst. & Forst. - J. Sánchez-Rodriguez; R. Martínez-Carrasco; P. Pérez (Photosynthesis Research, 1997)

Reproductive Toxicology of 3,3',4,4'-Tetrachlorobiphenyl in Mice - J. Rodriguez; S. D. Kholkute; W. R. Dukelow (Bulletin of Environmental Contamination and Toxicology, 1997)

Body fluid homeostasis and cardiovascular adjustments during submaximal exercise: influence of chewing coca leaves - Hilde Spielvogel; Armando Rodriguez; Brigitte Sempore; Esperanza Caceres; J.-M. Cottet-Emard; Laurent Guillon; R. Favier (European Journal of Applied Physiology, 1997)

Differential effects of ventilatory stimulation by sex hormones and almitrine on hypoxic erythrocytosis - R. Favier; H. Spielvogel; E. Caceres; A. Rodriguez; B. Sempore; J. Pequignot; J. M. Pequignot (Pflügers Archiv - European Journal of Physiology, 1997)

Cocaine impairs acquisition of an autoshaped lever-touch response - P. H. Janak; Ward A. Rodriguez; J. L. Martinez Jr. (Psychopharmacology, 1997)

Influence of gender and endogenous sex steroids on catecholaminergic structures involved in physiological adaptation to hypoxia - J. M. Pequignot; H. Spielvogel; E. Caceres; A. Rodriguez; B. Semporé; J. Pequignot; R. Favier (Pflügers Archiv - European Journal of Physiology, 1997)

Oral immunization of rabbits with VP60 particles confers protection against rabbit hemorrhagic disease - J. Plana-Duran; M. Bastons; M. J. Rodriguez; I. Climent; E. Cortés; C. Vela; I. Casal (Archives of Virology, 1996)

The effects of polybrominated biphenyls and perchlorinated terphenyls on in vitro fertilization in the mouse - S.D. Kholkute; J. Rodriguez; W.R. Dukelow (Archives of Environmental Contamination and Toxicology, 1994)

Human acetylator genotype: Relationship to colorectal cancer incidence and arylamine N-acetyltransferase expression in colon cytosol - Jose W. Rodriguez; Ward G. Kirlin; Ronald J. Ferguson; Mark A. Doll; Kevin Gray; Timothy D. Rustan; Mark E. Lee; Katherine Kemp; Paul Urso; David W. Hein (Archives of Toxicology, 1993)

Book reviews - Jon F. Hunter; J. G. Llaurado; Jean O'Connor Dorsi; William M. Chilian; Harcharan Singh Ranu; David J. Pogue; Carlos A. Rodriguez-Garcia (Annals of Biomedical Engineering, 1990)

A malic acid dependent mutant of Schizosaccharomyces malidevorans - Susan B. Rodriguez; Roy J. Thornton (Archives of Microbiology, 1989)

Inhibition of the yeast-mycelial transition and the phorogenesis of Mucorales by diamino butanone - M. Martinez-Pacheco; G. Rodriguez; G. Reyna; C. Calvo-Mendez; J. Ruiz-Herrera (Archives of Microbiology, 1988)

Beta interferon production in primed and unprimed cells infected with human cytomegalovirus - J. E. Rodriguez; T. R. Loepfe; N. S. Swack (Archives of Virology, 1987)

Studies on the mechanism of entry of vaccinia virus in animal cells - R. A. Janeczko; J. F. Rodriguez; M. Esteban (Archives of Virology, 1987)

Insecticide effects onEntomophthora muscae [Zygomycetes: Entomophthorales] - B. A. Mullens; J. L. Rodriguez (BioControl, 1986)

Antibiotic susceptibility of clinical isolates of Pseudomonas aeruginosa - C. Cervantes-Vega; J. Chavez; M. G. Rodriguez (Antonie van Leeuwenhoek, 1986)

Human cytomegalovirus persists in cells treated with interferon - J. E. Rodriguez; T. R. Loepfe; M. F. Stinski (Archives of Virology, 1983)

Influenza A viruses: Combinations of hemagglutinin and neuraminidase subtypes isolated from animals and other sources - V. S. Hinshaw; R. G. Webster; R. J. Rodriguez (Archives of Virology, 1981)

Sensibilité des larves deSpodoptera littoralis [Lep.: Noctuidae] aux hyphomycètes entomopathogènesNomuraea rileyi etPaecilomyces fumoso-roseus - J. Fargues; Dora Rodriguez-Rueda (BioControl, 1980)

Influenza A viruses: Combinations of hemagglutinin and neuraminidase subtypes isolated from animals and other sources - V. S. Hinshaw; R. G. Webster; R. J. Rodriguez (Archives of Virology, 1979)

Fetal infection of the baboon(Papio cynocephalus) with lymphocytic choriomeningitis virus - R. Ackermann; S. S. Kalter; R. L. Heberling; B. McCullough; J. Eichberg; A. R. Rodriguez (Archives of Virology, 1979)

Clinical, virological, and pathological features of herpesvirus SA8 infection in conventional and gnotobiotic infant baboons(Papio cynocephalus) - J. W. Eichberg; B. McCullough; S. S. Kalter; D. E. Thor; A. R. Rodriguez (Archives of Virology, 1976)

s 60th annual PAA meeting (Part II) - J. Landeo; P. R. Rowe; M. Mayer de Scurrah; M. T. Jackson; P. R. Rowe; J. G. Hawkes; P. Jatala; H. A. Mendoza; F. L. Haynes; G. C. C. Tai; H. Dejong; N. S. Wright; et al. (American Journal of Potato Research, 1976)

Characterization of the lyticStreptomyces RA as a new strain ofStreptomyces venezuelae - Ma Dolores García López; Ma José Rodriguez Aguirre; Federico Uruburu; J. R. Villanueva (Antonie van Leeuwenhoek, 1967)

Formation of protoplasts ofFusarium culmorum by strepzyme - M. J. Rodriguez Aguirre; Isabel Garcia Acha; J. R. Villanueva (Antonie van Leeuwenhoek, 1964)